Bilateral Mechanoreception Discrimination based on Bihemispheric Somatosensory Response Patterns is Associated with Proprioception and Motor Function After Stroke. - Gupta, Disha; Farrens, Andria; Garcia-Fernandez, Luis; Rojas, Raymond Diaz; Chan, Vicky; Perry, Joel; Wolbrecht, Eric T; Reinkensmeyer, Dave (bioRxiv, 2026)
OBJECTIVES: Stroke commonly impairs proprioception and motor function, yet the cortical sensory processes underlying these impairments remain poorly understood. Prior electrophysiological studies have primarily focused on the average magnitude of unilateral cortical sensory responses to vibration, potentially overlooking distributed and trial-to-trial features of sensory processing that may be functionally relevant to proprioceptive processing and motor performance. We therefore aimed to characterize bilateral cortical sensory responses to determine their relationships with proprioceptive and motor function. METHODS: EEG was recorded from forty-six individuals with chronic stroke during a rapid, passive, vibrotactile stimulation paradigm applied to the left and right fingertips. Somatosensory evoked potentials (SEPs) and event-related desynchronization (ERD) were quantified. Finger proprioceptive performance was assessed using a passive, robotic, finger crossing identification task, while motor function was evaluated using the Box and Block Test, Fugl-Meyer Assessment, and Nine Hole Peg Test. Associations with function were assessed using (i) unilateral sensory response magnitude at the contralateral parietal cortex and (ii) somatosensory decoder performance, defined as the accuracy with which a decoder identified the location of the stimulated hand (i.e. paretic vs. non-paretic) from combined bihemispheric response patterns. The association between these responses and proprioceptive ability and motor function was assessed. These associations were further evaluated jointly across multiple motor function measures using an exploratory analysis leveraging nonlinear dimensionality reduction and clustering. RESULTS: Vibrotactile stimulation of the paretic hand elicited ipsilesional SEP and ERD that were reduced in magnitude compared to stimulation of the non-paretic hand. Both decreased SEP magnitude and reduced sensory decoder performance were associated with greater finger proprioceptive error. Unlike unilateral responses, the somatosensory decoder's performance was also strongly associated with motor function, explaining approximately 22.5% of the variance in motor performance. Dimensionality reduction and clustering across multiple motor assessment scores showed distinct subgroups, that showed significant differences in sensory decoding. CONCLUSIONS: The hemispheric distribution and discriminability of cortical sensory responses are functionally relevant markers of sensorimotor integrity after stroke. Assessing relative lateralization of somatosensory responses for each hand, rather than the magnitude of dominant contralateral responses alone, may better capture the reliability of sensory processing after stroke, as well as the distributed cortical reorganization supporting sensorimotor function. These findings support the potential value of a novel decoding-based neurophysiological measure for sensory-driven rehabilitation, biomarker development, and patient stratification.

Methodological optimization for eliciting robust median nerve somatosensory evoked potentials for realtime single trial applications. - Gupta, Disha; Brangaccio, Jodi; Hill, NJ (J Neural Eng, 2026)
Single-trial measurement of median nerve somatosensory evoked potentials (SEPs) with noninvasive electroencephalography (EEG) is challenging due to low signal-to-noise ratio (SNR), limiting its use in real-time neurorehabilitation applications. We describe and evaluate methodological optimizations for eliciting reliable median nerve SEPs measurable in real time, with reduced reliance on post-processing.In twelve healthy participants, two sessions each, SEPs were assessed at three pulse widths (0.1, 0.5, 1 ms), at a low-frequency stimulation (0.5 Hz ± 10%), and at an intensity sufficient to evoke consistent and robust sensory nerve action potentials and compound muscle action potentials. The evoked potential operant conditioning system platform was used to monitor responses in real time. Feasibility was also evaluated in a participant with incomplete spinal cord injury (iSCI).SEP P50 and N70 were reliably elicited in healthy participants, and in individual with iSCI, across all tested pulse widths with minimal discomfort. N70 amplitude increased significantly with pulse width (χ2= 17.64,= 0.0001,= 0.80), while P50 amplitude remained unchanged. SNR showed a significant pulse width-dependent increase (χ2= 7.82,= 0.02,= 0.35) with improvements of 40% and 52% at 0.5 and 1 ms, respectively. N70 single-trial separability significantly improved at 1 ms (AUC of 0.83,χ2= 8.17,= 0.017), including the iSCI participant (0.84-less impaired hand, 0.79-more impaired hand). Test-retest reliability (intraclass correlation coefficient = 0.70-0.84,< 0.05) was highest at 0.5 ms, indicating more consistent N70 and P50 measurements across sessions at a longer pulse width.Robust median nerve SEPs can be measured at single trials with methodological optimizations such as a longer pulse width (0.5-1 ms), low frequency (0.5 Hz), a consistent afferent excitation guided by nerve and muscle responses, and a robust EEG acquisition system. This setup can be useful for real time SEP-based brain computer interface applications for rehabilitation.
Keywords: Adult; Computer Systems; Electric Stimulation; Electroencephalography; Evoked Potentials, Somatosensory; Female; Humans; Male; Median Nerve; Middle Aged; Reproducibility of Results; Spinal Cord Injuries; Young Adult

Neurorehabilitation in the 21st Century: New Science, New Strategies, New Expectations. - Wolpaw, Jonathan R; Thompson, Aiko K; Perez, Monica A; Norman, Sumner L; Oudega, Martin; Winstein, Carolee J (Neurorehabil Neural Repair, 2026)
Background: Neurorehabilitation is among the most vibrant areas of biomedical research. Its main strategy has been skill-specific practice, which often fails to produce adequate recovery. Now, new recognition of central nervous system (CNS) plasticity, new understanding of skills, and new technologies provide new strategies that enhance the efficacy of practice. Objectives: The substrate of a skill is a network of neurons and synapses that extends from cortex to spinal cord and is now called a heksor. A heksor changes continually to maintain the key features of its skill, the attributes that make the skill satisfactory. Muscle activity and kinematics may change; key features are maintained. Heksors share neurons and synapses. Through their concurrent changes, they keep the CNS in a negotiated equilibrium that enables each to maintain its skill. When CNS damage occurs, the goal is to enable damaged heksors to repair themselves. Results: Two new strategies enhance the efficacy of skill-specific practice. One increases plasticity. A damaged heksor shapes the additional plasticity through practice. The other targets beneficial plasticity to a critical site in a damaged heksor. This improves practice, enabling the heksor to achieve wider beneficial plasticity. In animals and humans, protocols that combine these strategies with practice enhance lasting recovery. Conclusions: The challenge is to develop, optimize, and validate these combined protocols. Computational modeling can accelerate the process. Controlled trials and comprehensive outcome assessments are essential. Pre-morbid factors and physiological measures may identify biomarkers that can predict efficacy or guide patient-specific protocol design. Many combined protocols will be noninvasive and suitable for home use.

A portable closed-loop platform enabling cortical evoked potential operant conditioning: System development and validation of target intensity estimation - Gupta, Disha; Brangaccio, JA; Mojtabavi, Helia; Hill, NJ (Biomedical Physics & Engineering Express, 2026)

Bidirectional locomotion induces asymmetric limb adaptations - Hardesty, Russell L; Mojtabavi, Helia; Gemoets, Darren E; Wolpaw, Jonathan R (Journal of neurophysiology, 2025)
Humans can acquire and maintain motor skills throughout their lives through motor learning. Motor learning and skill acquisition are essential for rehabilitation after neurological disease or injury. Adaptation, the initial stage of motor learning, involves short-term changes in motor performance in response to a new demand in the person’s environment. Repeated adaptation can improve skill performance and result in long-term skill retention. Locomotor adaptation has been extensively studied with split-belt treadmill paradigms. In this study we explored whether bidirectional walking (BDW) on a split-belt treadmill can induce short-term gait adaptations. Twelve healthy volunteers participated in our single session, starting with 2 min of forward walking (FW), followed by four 5-min blocks of BDW with a 1-min passive rest in between blocks, and ending with another 2-min block of FW. We recorded body kinematics and ground reaction forces throughout the experiment. Participants modified both temporal (interlimb phasing, double stance duration) and spatial (step length) aspects of gait to meet the mechanical demands of backward dual walking (BDW). Adaptation occurred rapidly, with bilateral reductions in step length, adjustments in stance and swing phase timing, alterations in interlimb phasing, and decreased double stance duration in the limb walking backward. Notably, only the backward-walking limb (right) exhibited persistent aftereffects upon return to FW. These results demonstrate that BDW elicits adaptations in both spatial and temporal gait parameters, with transient aftereffects consistent with short-term motor learning. To our knowledge, this is the first report characterizing such spatiotemporal adaptations during BDW.

Brain-computer interface (BCI)-based identification of congenital red-green color vision deficiencies - Rueda-Parra, Sebastian; Caruso, Heather A; Norton, Penelope L; Gemoets, Darren E; Norton, James JS (Authorea Preprints, 2025)
We demonstrate brain-computer interface (BCI)- based color vision (CV) assessment for the identification of congenital red-green CV deficiencies. Experiments were based on the identification of metamers—light sources with different spectral distributions perceived to be the same color. Metamers elicit steady-state visual evoked potentials (SSVEPs) of minimal size and are different for people with versus without CV deficiencies. Methods: Thirty-one participants (20 control (CTR), 11 color vision deficient (CVdef)) completed behaviorand BCI-based CV assessments. Experiments used a visual stimulus that alternated between a monochromatic light source (yellow; fixed luminance) and a dichromatic light source (red and green; varying luminances) at a fixed frequency. During behavior-based CV assessment, participants identified metamers by manually adjusting the dichromatic source’s settings until its color matched that of the monochromatic source. During BCI-based CV assessment, participants attended a sequence of stimuli (each with a different dichromatic source setting) while electroencephalography was recorded; metamers were defined as the dichromatic source settings that minimized SSVEP size. Results: The behavior- and BCI-identified metamers were identical within each group, but different across groups (i.e., CTR and CVdef and for people with protan- versus deutan-type CV deficiencies). Automatic identification of CVdef individuals (and type of deficiency) was demonstrated using a classification analysis (93% accuracy). Conclusion: Experiments validated BCI-based CV assessment for the identification of congenital red-green CV deficiencies. Significance: BCI-based CV assessment does not require behavioral responses and can be automated, making it suitable for people with cognitive/motor deficits. With further development, BCI-based CV assessment may enable automatic identification of many types of congenital and acquired CV deficiencies.

Characterization of cutaneous reflexes elicited from saphenous nerve stimulation - Hardesty, Russell; Rueda-Parra, Sebastian; Wolpaw, Jonathan; Brangaccio, Jodi (bioRxiv, 2025)
Phantom limb pain (PLP) is a chronic neuropathic condition that affects amputees. Cutaneous reflexes (CRs), mediated by spinal interneuronal circuits, represent a potential pathway linking non-nociceptive input to nociceptive modulation that could be targeted with neuromodulatory techniques such as operant conditioning. The objective of this study was to develop and validate a novel method for eliciting CRs from proximal muscles via saphenous nerve stimulation to enable future applications in individuals with PLP. We recruited 14 healthy adults and elicited CRs in the rectus femoris muscle via transcutaneous stimulation of the saphenous nerve at multiple stimulation intensities below their pain thresholds. We evaluated the consistency and reliability of CR response latencies and magnitudes, comparing the symmetry between the bilaterally (e.g. right and left legs). We found that CRs could be reliably elicited 50-100ms post-stimulus using saphenous stimulation and that responses were reliable at stimulation intensities below pain thresholds. Furthermore, we found the CR responses were relatively symmetrical in our healthy adult population. This study is the first of its kind to show that proximal (vs distal) CRs could be consistently elicited through the saphenous nerve stimulation. These findings imply that proximal CRs may be a feasible target for neuromodulatory interventions such as operant conditioning paradigms in the future.

Circuit dynamics of approach-avoidance conflict in humans. - Staveland, Brooke R; Oberschulte, Julia; Kim-McManus, Olivia; Willie, Jon T; Brunner, Peter; Dastjerdi, Mohammad; Lin, Jack J; Hsu, Ming; Knight, Robert T (bioRxiv, 2025)
Debilitating anxiety is pervasive in the modern world. Choices to approach or avoid are common in everyday life and excessive avoidance is a cardinal feature of all anxiety disorders. Here, we used intracranial EEG to define a distributed prefrontal-limbic circuit dynamics supporting approach and avoidance. Presurgical epilepsy patients (n=20) performed an approach-avoidance conflict decision-making task inspired by the arcade game Pac-Man, where participants trade-off real-time harvesting rewards with potential losses from attack. As patients approached increasing rewards and threats, we found evidence of a limbic circuit mediated by increased theta power in the hippocampus, amygdala, orbitofrontal cortex (OFC) and anterior cingulate cortex (ACC), which then drops rapidly during avoidance. Theta band connectivity between these regions increases during approach and falls during avoidance, with OFC serving as a connector in this circuit with high theta coherence across limbic regions, but also with regions outside of the limbic system, including the lateral prefrontal cortex. Importantly, the degree of OFC-driven connectivity predicts how long participants approach, with enhanced network synchronicity extending approach times. Finally, under ghost attack, the system dynamically switches to a sustained increase in high-frequency activity (70-150Hz) in the middle frontal gyrus (MFG), marking the retreat from the ghost. The results provide evidence for a distributed prefrontal-limbic circuit, mediated by theta oscillations, underlying approach-avoidance conflict.

The effect of transcutaneous auricular vagus nerve stimulation on cardiovascular function in subarachnoid hemorrhage patients: A randomized trial. - Tan, Gansheng; Huguenard, Anna L; Donovan, Kara M; Demarest, Phillip; Liu, Xiaoxuan; Li, Ziwei; Adamek, Markus; Lavine, Kory; Vellimana, Ananthv K; Kummer, Terrance T; Osbun, Joshua W; Zipfel, Gregory J; et al. (Elife, 2025)
BACKGROUND: Subarachnoid hemorrhage (SAH) is characterized by intense central inflammation, leading to substantial post-hemorrhagic complications such as vasospasm and delayed cerebral ischemia. Given the anti-inflammatory effect of transcutaneous auricular vagus nerve stimulation (taVNS) and its ability to promote brain plasticity, taVNS has emerged as a promising therapeutic option for SAH patients. However, the effects of taVNS on cardiovascular dynamics in critically ill patients, like those with SAH, have not yet been investigated. Given the association between cardiac complications and elevated risk of poor clinical outcomes after SAH, it is essential to characterize the cardiovascular effects of taVNS to ensure this approach is safe in this fragile population. Therefore, this study assessed the impact of both acute and repetitive taVNS on cardiovascular function. METHODS: In this randomized clinical trial, 24 SAH patients were assigned to either a taVNS treatment or a sham treatment group. During their stay in the intensive care unit, we monitored patient electrocardiogram readings and vital signs. We compared long-term changes in heart rate, heart rate variability (HRV), QT interval, and blood pressure between the two groups. Additionally, we assessed the effects of acute taVNS by comparing cardiovascular metrics before, during, and after the intervention. We also explored acute cardiovascular biomarkers in patients exhibiting clinical improvement. RESULTS: We found that repetitive taVNS did not significantly alter heart rate, QT interval, blood pressure, or intracranial pressure (ICP). However, repetitive taVNS increased overall HRV and parasympathetic activity compared to the sham treatment. The increase in parasympathetic activity was most pronounced from 2 to 4 days after initial treatment (Cohen's = 0.50). Acutely, taVNS increased heart rate, blood pressure, and peripheral perfusion index without affecting the corrected QT interval, ICP, or HRV. The acute post-treatment elevation in heart rate was more pronounced in patients who experienced a decrease of more than one point in their modified Rankin Score at the time of discharge. CONCLUSIONS: Our study found that taVNS treatment did not induce adverse cardiovascular effects, such as bradycardia or QT prolongation, supporting its development as a safe immunomodulatory treatment approach for SAH patients. The observed acute increase in heart rate after taVNS treatment may serve as a biomarker for SAH patients who could derive greater benefit from this treatment. FUNDING: The American Association of Neurological Surgeons (ALH), The Aneurysm and AVM Foundation (ALH), The National Institutes of Health R01-EB026439, P41-EB018783, U24-NS109103, R21-NS128307 (ECL, PB), McDonnell Center for Systems Neuroscience (ECL, PB), and Fondazione Neurone (PB). CLINICAL TRIAL NUMBER: NCT04557618.
Keywords: Adult; Aged; Blood Pressure; Electrocardiography; Female; Heart Rate; Humans; Male; Middle Aged; Subarachnoid Hemorrhage; Transcutaneous Electric Nerve Stimulation; Vagus Nerve Stimulation

Extracting robust single-trial somatosensory evoked potentials for non-invasive brain computer interfaces - Gupta, Disha; Brangaccio, Jodi; Mojtabavi, Helia; Wolpaw, Jonathan; Hill, NJ (Journal of Neural Engineering, 2025)
Objective: Reliable extraction of single-trial somatosensory evoked potentials (SEPs) is essential for developing brain-computer interface (BCI) applications to support rehabilitation after brain injury. For real-time feedback, these responses must be extracted prospectively on every trial, with minimal post-processing and artifact correction. However, noninvasive SEPs elicited by electrical stimulation at recommended parameter settings (0.1–0.2 msec pulse width, stimulation at or below motor threshold, 2–5 Hz frequency) are typically small and variable, often requiring averaging across multiple trials or extensive processing. Here, we describe and evaluate ways to optimize the stimulation setup to enhance the signal-to-noise ratio (SNR) of noninvasive single-trial SEPs, enabling more reliable extraction. Approach: SEPs were recorded with scalp electroencephalography in tibial nerve stimulation in thirteen healthy people, and two people with CNS injuries. Three stimulation frequencies (lower than recommended: 0.2 Hz, 1 Hz, 2 Hz) with a pulse width longer than recommended (1 msec), at a stimulation intensity based on H-reflex and M-wave at Soleus muscle were evaluated. Detectability of single-trial SEPs relative to background noise was tested offline and in a pseudo-online analysis, followed by a real-time demonstration. Main results. SEP N70 was observed predominantly at the central scalp regions. Online decoding performance was significantly higher with Laplacian filter. Generalization performance showed an expected degradation, at all frequencies, with an average decrease of 5.9% (multivariate) and 6.5% (univariate), with an AUC score ranging from 0.78–0.90. The difference across stimulation frequencies was not significant. In individuals with injuries, AUC of 0.86 (incomplete spinal cord injury) and 0.81 (stroke) was feasible. Real-time demonstration showed SEP detection with AUC of 0.89. Significance This study describes and evaluates a system for extracting single-trial SEPs in real-time, suitable for a BCI-based operant conditioning. It enhances SNR of individual SEPs by alternate electrical stimulation parameters, dry headset, and optimized signal processing.

Frequency dependence of cortical somatosensory evoked response to peripheral nerve stimulation with controlled afferent excitation - Gupta, Disha; Brangaccio, Jodi; Mojtabavi, Helia; Carp, Jonathan S; Wolpaw, Jonathan R; Hill, N Jeremy (Journal of Neural Engineering, 2025)
Objective: H-reflex targeted neuroplasticity (HrTNP) protocols comprise a promising rehabilitation approach to improve motor function after brain or spinal injury. In this operant conditioning protocol, concurrent measurement of cortical responses, such as somatosensory evoked potentials (SEPs), would be useful for examining supraspinal involvement and neuroplasticity mechanisms. To date, this potential has not been exploited. However, the stimulation parameters used in the HrTNP protocol deviate from the classically recommended settings for SEP measurements. Most notably, it demands a much longer pulse width, higher stimulation intensity, and lower frequency than traditional SEP settings. In this paper, we report SEP measurements performed within the HrTNP stimulation parameter constraints, specifically characterizing the effect of stimulation frequency. Approach: SEPs were acquired for tibial nerve stimulation at three stimulation frequencies (0.2, 1, and 2 Hz) in 13 subjects while maintaining the afferent volley by controlling the direct soleus muscle response via the Evoked Potential Operant Conditioning System. The amplitude and latency of the short-latency P40 and mid-latency N70 SEP components were measured at the central scalp region using non-invasive electroencephalography. Main results: As frequency rose from 0.2 Hz, P40 amplitude and latency did not change. In contrast, N70 amplitude decreased significantly (39% decrease at 1 Hz, and 57% decrease at 2 Hz), presumably due to gating effects. N70 latency was not affected. Across all three frequencies, N70 amplitude increased significantly with stimulation intensity and correlated with M-wave amplitude. Significance: We assess SEPs within an HrTNP protocol, focusing on P40 and N70, elicited with controlled afferent excitation at three stimulation frequencies. HrTNP conditioning protocols show promise for enhancing motor function after brain and spinal injuries. While SEPs offer valuable insights into supraspinal involvement, the stimulation parameters in HrTNP often differ from standard SEP measurement protocols. We address these deviations and provide recommendations for effectively integrating SEP assessments into HrTNP studies.

A human single-neuron dataset for object recognition. - Cao, Runnan; Brunner, Peter; Brandmeir, Nicholas J; Willie, Jon T; Wang, Shuo (Sci Data, 2025)
Object recognition is fundamental to how we interact with and interpret the world around us. The human amygdala and hippocampus play a key role in object recognition, contributing to both the encoding and retrieval of visual information. Here, we recorded single-neuron activity from the human amygdala and hippocampus when neurosurgical epilepsy patients performed a one-back task using naturalistic object stimuli. We employed two sets of naturalistic object images from leading datasets extensively used in primate neural recordings and computer vision models: we recorded 1204 neurons using the ImageNet stimuli, which included broader object categories (10 different images per category for 50 categories), and we recorded 512 neurons using the Microsoft COCO stimuli, which featured a higher number of images per category (50 different images per category for 10 categories). Together, our extensive dataset, offering the highest spatial and temporal resolution currently available in humans, will not only facilitate a comprehensive analysis of the neural correlates of object recognition but also provide valuable opportunities for training and validating computational models.
Keywords: Amygdala; Epilepsy; Hippocampus; Humans; Neurons; Pattern Recognition, Visual; Recognition, Psychology

IpsiHand Brain-Computer Interface Therapy Induces Broad Upper Extremity Motor Rehabilitation in Chronic Stroke. - Rustamov, Nabi; Souders, Lauren; Sheehan, Lauren; Carter, Alexandre; Leuthardt, Eric C (Neurorehabil Neural Repair, 2025)
BACKGROUND: Chronic hemiparetic stroke patients have very limited benefits from current therapies. Brain-computer interface (BCI) engaging the unaffected hemisphere has emerged as a promising novel therapeutic approach for chronic stroke rehabilitation. OBJECTIVES: This study investigated the effectiveness of contralesionally-controlled BCI therapy in chronic stroke patients with impaired upper extremity motor function. We further explored neurophysiological features of motor recovery driven by BCI. We hypothesized that BCI therapy would induce a broad motor recovery in the upper extremity, and there would be corresponding changes in baseline theta and gamma oscillations, which have been shown to be associated with motor recovery. METHODS: Twenty-six prospectively enrolled chronic hemiparetic stroke patients performed a therapeutic BCI task for 12 weeks. Motor function assessment data and resting state electroencephalogram signals were acquired before initiating BCI therapy and across BCI therapy sessions. The Upper Extremity Fugl-Meyer assessment served as a primary motor outcome assessment tool. Theta-gamma cross-frequency coupling (CFC) was computed and correlated with motor recovery. RESULTS: Chronic stroke patients achieved significant motor improvement in both proximal and distal upper extremity with BCI therapy. Motor function improvement was independent of Botox application. Theta-gamma CFC enhanced bilaterally over the C3/C4 motor electrodes and positively correlated with motor recovery across BCI therapy sessions. CONCLUSIONS: BCI therapy resulted in significant motor function improvement across the proximal and distal upper extremities of patients, which significantly correlated with theta-gamma CFC increases in the motor regions. This may represent rhythm-specific cortical oscillatory mechanism for BCI-driven rehabilitation in chronic stroke patients. TRIAL REGISTRATION: Advarra Study: https://classic.clinicaltrials.gov/ct2/show/NCT04338971 and Washington University Study: https://classic.clinicaltrials.gov/ct2/show/NCT03611855.
Keywords: Adult; Aged; brain-computer interfaces; Chronic Disease; Electroencephalography; Female; Gamma Rhythm; Humans; Male; Middle Aged; Motor Activity; Paresis; Prospective Studies; Recovery of Function; Stroke; Stroke Rehabilitation; Theta Rhythm; Upper Extremity

Soleus H-reflex size versus stimulation rate in the presence of background muscle activity: a methodological study - Brangaccio, Jodi A; Gupta, Disha; Mojtabavi, Helia; Hardesty, Russell L; Hill, NJ; Carp, Jonathan S; Gemoets, Darren E; Vaughan, Theresa M; Norton, James JS; Perez, Monica A; others (Experimental brain research, 2025)
Hoffmann reflex (HR) operant conditioning (HROC) is an important intervention for neurorehabilitation. Current HROC paradigms elicit HRs at low rates (~ 0.2 Hz), minimizing rate-dependent depression (RDD). We investigated the impact of higher stimulation rates on HR size. Fifteen healthy participants maintained low background soleus electromyographic activity (EMG) while standing. Soleus HR and M-wave recruitment curves were obtained at rates of 0.2, 1, and 2 Hz twice, from which Mmax and Hmax were calculated. Seventy-five HRs were collected for each rate at a target M-wave size (~ 10 to 20% of Mmax). HR depression was minimal at higher stimulation rates. The mean HR amplitude was reliable across the two repetitions and three rates, with high intraclass correlation coefficient (ICC) values. HROC could be performed consistently at rates up to 2 Hz with minimal HR depression. Faster rates enable more conditioning trials per session, reducing session duration and/or number, thereby potentially accelerating conditioning and reducing participant burden.

Spinal reflexes: a potential target for treating hemiparetic gait. - Hardesty, Russell L; Mojtabavi, Helia; Wolpaw, Jonathan R (J Neurophysiol, 2025)

SyncGenie: A programmable event synchronization device for neuroscience research. - Alkhoury, Ludvik; Scanavini, Giacomo; Swissler, Petras; Shah, Sudhin A; Gupta, Disha; Jeremy Hill, N (HardwareX, 2025)
In neuroscience, accurately correlating brain activity with stimuli and other events requires precise synchronization between neural data and event timing. To achieve this, purpose-built synchronization devices are often used to detect events. This paper introduces SyncGenie, a programmable synchronization device designed for a range of uses in neuroscience research-primarily as a "trigger box" to align neurophysiological data with physical stimulus events, among other possibilities. It can support both hardware-triggered and software-triggered pulse synchronization and can even serve as a cost-effective digitizer for real-time analysis of analog signals. We provide the complete circuit-board designs, 3D models, and Arduino code necessary to build and use SyncGenie. The board is designed for easy manufacturing and assembly, with components that can be seamlessly soldered. It includes a range of connector types required for common applications, such as 3.5 mm TRS, D-sub25, BNC, and JST-XH. Additionally, SyncGenie features a user-friendly interface that allows for experiment-specific adjustments without requiring coding expertise. Its programmability, supported by our public-domain Arduino library, provides the flexibility to adapt SyncGenie to diverse experimental protocols. Overall, SyncGenie offers enhanced functionality at a lower cost relative to commercially available trigger boxes.

Tailored robotic training improves hand function and proprioceptive processing in stroke survivors with proprioceptive deficits: A randomized controlled trial - Farrens, Andria J; Garcia-Fernandez, Luis; Rojas, Raymond Diaz; Estrada, Jillian Obeso; Reinsdorf, Dylan; Chan, Vicky; Gupta, Disha; Perry, Joel; Wolbrecht, Eric; Do, An; others (arXiv preprint arXiv:2511.00259, 2025)
Precision rehabilitation aims to tailor movement training to improve outcomes. We tested whether proprioceptively-tailored robotic training improves hand function and neural processing in stroke survivors. Using a robotic finger exoskeleton, we tested two proprioceptively-tailored approaches: Propriopixel Training, which uses robot-facilitated, gamified movements to enhance proprioceptive processing, and Virtual Assistance Training, which reduces robotic aid to increase reliance on self-generated feedback. In a randomized controlled trial, forty-six chronic stroke survivors completed nine 2-hour sessions of Standard, Propriopixel or Virtual training. Among participants with proprioceptive deficits, Propriopixel ((Box and Block Test: 7 +/- 4.2, p=0.002) and Virtual Assistance (4.5 +/- 4.4 , p=0.068) yielded greater gains in hand function (Standard: 0.8 +/- 2.3 blocks). Proprioceptive gains correlated with improvements in hand function. Tailored training enhanced neural sensitivity to proprioceptive cues, evidenced by a novel EEG biomarker, the proprioceptive Contingent Negative Variation. These findings support proprioceptively-tailored training as a pathway to precision neurorehabilitation.

Test-retest reliability of kinematic and EEG low-beta spectral features in a robot-based arm movement task - Rueda-Parra, Sebastian; Hardesty, Russell; Gemoets, Darren E; Hill, N Jeremy; Gupta, Disha (Biomedical physics & engineering express, 2025)
Objective.Low-beta (Lβ, 13-20 Hz) power plays a key role in upper-limb motor control and afferent processing, making it a strong candidate for a neurophysiological biomarker. We investigate the test-retest reliability of Lβpower and kinematic features from a robotic task over extended intervals between sessions to assess its potential for tracking longitudinal changes in sensorimotor function.Approach.We designed and optimized a testing protocol to evaluate Lβpower and kinematic features (maximal and mean speed, reaction time, and movement duration) in ten right-handed healthy individuals that performed a planar center-out task using a robotic device and EEG for data collection. The task was performed with both hands, and the experiment was repeated approximately 40 days later under similar conditions, to resemble real-life intervention periods. We first characterized the selected features within the task context for each session, then assessed intersession agreement, the test-retest reliability (Intraclass Correlation Coefficient, ICC), and established threshold values for meaningful changes in Lβpower using Bland-Altman plots and repeatability coefficients.Main Results.Lβpower showed the expected contralateral reduction during movement preparation and onset. Both Lβpower and kinematic features exhibited good to excellent test-retest reliability (ICC > 0.8), displaying no significant intersession differences. Kinematic results align with prior literature, reinforcing the robustness of these measures in tracking motor performance over time. Changes in Lβpower between sessions exceeding 11.4% for right-arm and 16.5% for left-arm movements reflect meaningful intersession differences.Significance.This study provides evidence that Lβpower remains stable over extended intersession intervals comparable to rehabilitation timelines. The strong reliability of both Lβpower and kinematic features supports their use in monitoring upper-extremity sensorimotor function longitudinally, with Lβpower emerging as a promising biomarker for tracking therapeutic outcomes, postulating it as a reliable feature for long-term applications.

Anatomical registration of intracranial electrodes. Robust model-based localization and deformable smooth brain-shift compensation methods. - Blenkmann, Alejandro Omar; Leske, Sabine Liliana; Llorens, Anaïs; Lin, Jack J; Chang, Edward F; Brunner, Peter; Schalk, Gerwin; Ivanovic, Jugoslav; Larsson, Pål Gunnar; Knight, Robert Thomas; Endestad, Tor; Solbakk, Anne-Kristin (J Neurosci Methods, 2024)
BACKGROUND: Intracranial electrodes are typically localized from post-implantation CT artifacts. Automatic algorithms localizing low signal-to-noise ratio artifacts and high-density electrode arrays are missing. Additionally, implantation of grids/strips introduces brain deformations, resulting in registration errors when fusing post-implantation CT and pre-implantation MR images. Brain-shift compensation methods project electrode coordinates to cortex, but either fail to produce smooth solutions or do not account for brain deformations. NEW METHODS: We first introduce GridFit, a model-based fitting approach that simultaneously localizes all electrodes' CT artifacts in grids, strips, or depth arrays. Second, we present CEPA, a brain-shift compensation algorithm combining orthogonal-based projections, spring-mesh models, and spatial regularization constraints. RESULTS: We tested GridFit on ∼6000 simulated scenarios. The localization of CT artifacts showed robust performance under difficult scenarios, such as noise, overlaps, and high-density implants (<1 mm errors). Validation with data from 20 challenging patients showed 99% accurate localization of the electrodes (3160/3192). We tested CEPA brain-shift compensation with data from 15 patients. Projections accounted for simple mechanical deformation principles with < 0.4 mm errors. The inter-electrode distances smoothly changed across neighbor electrodes, while changes in inter-electrode distances linearly increased with projection distance. COMPARISON WITH EXISTING METHODS: GridFit succeeded in difficult scenarios that challenged available methods and outperformed visual localization by preserving the inter-electrode distance. CEPA registration errors were smaller than those obtained for well-established alternatives. Additionally, modeling resting-state high-frequency activity in five patients further supported CEPA. CONCLUSION: GridFit and CEPA are versatile tools for registering intracranial electrode coordinates, providing highly accurate results even in the most challenging implantation scenarios. The methods are implemented in the iElectrodes open-source toolbox.
Keywords: Brain; Cerebral Cortex; Electrodes; Electrodes, Implanted; Electroencephalography; Humans; Magnetic Resonance Imaging

Anatomical registration of intracranial electrodes. Robust model-based localization and deformable smooth brain-shift compensation methods - Blenkmann, Alejandro Omar; Leske, Sabine Liliana; Llorens, Anaïs; Lin, Jack J; Chang, Edward F; Brunner, Peter; Schalk, Gerwin; Ivanovic, Jugoslav; Larsson, Pål Gunnar; Knight, Robert Thomas; others (Journal of Neuroscience Methods, 2024)

Bidirectional locomotion induces unilateral limb adaptations. - Hardesty, Russell L; Motjabavi, Helia; Gemoets, Darren E; Wolpaw, Jonathan R (bioRxiv, 2024)
Humans can acquire and maintain motor skills throughout their lives through motor learning. Motor learning and skill acquisition are essential for rehabilitation following neurological disease or injury. Adaptation, the initial stage of motor learning, involves short-term changes in motor performance in response to a new demand in the person's environment. Repeated adaptation can improve skill performance and result in long-term skill retention. Locomotor adaptation is extensively studied using split-belt treadmill paradigms. In this study we explored whether bidirectional walking (BDW) on a split-belt treadmill can induce short-term gait adaptations. Twelve healthy volunteers participated in our single session, starting with 2 minutes of normal walking (NW), followed by four 5-minute blocks of BDW with a 1-minute passive rest in between blocks, and ending with another 2-minute of NW. We recorded body kinematics and ground reaction forces throughout the experiment. Participants quickly adapted to BDW with both legs showing decreased step lengths. However, only the backward-walking leg exhibited aftereffects upon returning to NW, indicating short-term adaptation. Notable kinematic changes were observed, particularly in hip extension and pelvis tilt, though these varied among participants. Our findings suggest that BDW induces unilateral adaptations despite bilateral changes in gait, offering new insights into locomotor control and spinal CPG organization.

Brain-Computer Interfaces for Communication in Patients with Disorders of Consciousness: A Gap Analysis and Scientific Roadmap. - Schiff, Nicholas D; Diringer, Michael; Diserens, Karin; Edlow, Brian L; Gosseries, Olivia; Hill, N Jeremy; Hochberg, Leigh R; Ismail, Fatima Y; Meyer, Ivo A; Mikell, Charles B; Mofakham, Sima; Molteni, Erika; et al. (Neurocrit Care, 2024)
BACKGROUND: We developed a gap analysis that examines the role of brain-computer interfaces (BCI) in patients with disorders of consciousness (DoC), focusing on their assessment, establishment of communication, and engagement with their environment. METHODS: The Curing Coma Campaign convened a Coma Science work group that included 16 clinicians and neuroscientists with expertise in DoC. The work group met online biweekly and performed a gap analysis of the primary question. RESULTS: We outline a roadmap for assessing BCI readiness in patients with DoC and for advancing the use of BCI devices in patients with DoC. Additionally, we discuss preliminary studies that inform development of BCI solutions for communication and assessment of readiness for use of BCIs in DoC study participants. Special emphasis is placed on the challenges posed by the complex pathophysiologies caused by heterogeneous brain injuries and their impact on neuronal signaling. The differences between one-way and two-way communication are specifically considered. Possible implanted and noninvasive BCI solutions for acute and chronic DoC in adult and pediatric populations are also addressed. CONCLUSIONS: We identify clinical and technical gaps hindering the use of BCI in patients with DoC in each of these contexts and provide a roadmap for research aimed at improving communication for adults and children with DoC, spanning the clinical spectrum from intensive care unit to chronic care.

Complexity organization of resting-state functional-MRI networks. - Trevino, Gabriel; Lee, John J; Shimony, Joshua S; Luckett, Patrick H; Leuthardt, Eric C (Hum Brain Mapp, 2024)
Entropy measures are increasingly being used to analyze the structure of neural activity observed by functional magnetic resonance imaging (fMRI), with resting-state networks (RSNs) being of interest for their reproducible descriptions of the brain's functional architecture. Temporal correlations have shown a dichotomy among these networks: those that engage with the environment, known as extrinsic, which include the visual and sensorimotor networks; and those associated with executive control and self-referencing, known as intrinsic, which include the default mode network and the frontoparietal control network. While these inter-voxel temporal correlations enable the assessment of synchrony among the components of individual networks, entropic measures introduce an intra-voxel assessment that quantifies signal features encoded within each blood oxygen level-dependent (BOLD) time series. As a result, this framework offers insights into comprehending the representation and processing of information within fMRI signals. Multiscale entropy (MSE) has been proposed as a useful measure for characterizing the entropy of neural activity across different temporal scales. This measure of temporal entropy in BOLD data is dependent on the length of the time series; thus, high-quality data with fine-grained temporal resolution and a sufficient number of time frames is needed to improve entropy precision. We apply MSE to the Midnight Scan Club, a highly sampled and well-characterized publicly available dataset, to analyze the entropy distribution of RSNs and evaluate its ability to distinguish between different functional networks. Entropy profiles are compared across temporal scales and RSNs. Our results have shown that the spatial distribution of entropy at infra-slow frequencies (0.005-0.1 Hz) reproduces known parcellations of RSNs. We found a complexity hierarchy between intrinsic and extrinsic RSNs, with intrinsic networks robustly exhibiting higher entropy than extrinsic networks. Finally, we found new evidence that the topography of entropy in the posterior cerebellum exhibits high levels of entropy comparable to that of intrinsic RSNs.
Keywords: Adult; Brain; Connectome; Default Mode Network; Entropy; Humans; Magnetic Resonance Imaging; Nerve Net; Rest

The development of aperiodic neural activity in the human brain. - Cross, Zachariah R; Gray, Samantha M; Dede, Adam J O; Rivera, Yessenia M; Yin, Qin; Vahidi, Parisa; Rau, Elias M B; Cyr, Christopher; Holubecki, Ania M; Asano, Eishi; Lin, Jack J; McManus, Olivia Kim; et al. (bioRxiv, 2024)
The neurophysiological mechanisms supporting brain maturation are fundamental to attention and memory capacity across the lifespan. Human brain regions develop at different rates, with many regions developing into the third and fourth decades of life. Here, in this preregistered study (https://osf.io/gsru7), we analyzed intracranial EEG (iEEG) recordings from widespread brain regions in a large developmental cohort. Using task-based (i.e., attention to-be-remembered visual stimuli) and task-free (resting-state) data from 101 children and adults (5.93 - 54.00 years, 63 males; electrodes = 5691), we mapped aperiodic (1/ƒ-like) activity, a proxy of excitation:inhibition (E:I) balance with steeper slopes indexing inhibition and flatter slopes indexing excitation. We reveal that aperiodic slopes flatten with age into young adulthood in both association and sensorimotor cortices, challenging models of early sensorimotor development based on brain structure. In prefrontal cortex (PFC), attentional state modulated age effects, revealing steeper task-based than task-free slopes in adults and the opposite in children, consistent with the development of cognitive control. Age-related differences in task-based slopes also explained age-related gains in memory performance, linking the development of PFC cognitive control to the development of memory. Last, with additional structural imaging measures, we reveal that age-related differences in gray matter volume are differentially associated with aperiodic slopes in association and sensorimotor cortices. Our findings establish developmental trajectories of aperiodic activity in localized brain regions and illuminate the development of PFC inhibitory control during adolescence in the development of attention and memory.

Does Vibrotactile Stimulation of the Auricular Vagus Nerve Enhance Working Memory? A Behavioral and Physiological Investigation. - Tan, Gansheng; Adams, Josh; Donovan, Kara; Demarest, Phillip; Willie, Jon T; Brunner, Peter; Gorlewicz, Jenna L; Leuthardt, Eric C (bioRxiv, 2024)
BACKGROUND: Working memory is essential to a wide range of cognitive functions and activities. Transcutaneous auricular VNS (taVNS) is a promising method to improve working memory performance. However, the feasibility and scalability of electrical stimulation are constrained by several limitations, such as auricular discomfort and inconsistent electrical contact. OBJECTIVE: We aimed to develop a novel and practical method, vibrotactile taVNS, to improve working memory. Further, we investigated its effects on arousal, measured by skin conductance and pupil diameter. METHOD: This study included 20 healthy participants. Behavioral response, skin conductance, and eye tracking data were concurrently recorded while the participants performed N-back tasks under three conditions: vibrotactile taVNS delivered to the cymba concha, earlobe (sham control), and no stimulation (baseline control). RESULTS: In 4-back tasks, which demand maximal working memory capacity, active vibrotactile taVNS significantly improved the performance metric ' compared to the baseline but not to the sham. Moreover, we found that the reduction rate of ' with increasing task difficulty was significantly smaller during vibrotactile taVNS sessions than in both baseline and sham conditions. Arousal, measured as skin conductance and pupil diameter, declined over the course of the tasks. Vibrotactile taVNS rescued this arousal decline, leading to arousal levels corresponding to optimal working memory levels. Moreover, pupil diameter and skin conductance level were higher during high-cognitive-load tasks when vibrotactile taVNS was delivered to the concha compared to baseline and sham. CONCLUSION: Our findings suggest that vibrotactile taVNS modulates the arousal pathway and could be a potential intervention for enhancing working memory. HIGHLIGHTS: Vibrotactile stimulation of the auricular vagus nerve increases general arousal.Vibrotactile stimulation of the auricular vagus nerve mitigates arousal decreases as subjects continuously perform working memory tasks.6 Hz Vibrotactile auricular vagus nerve stimulation is a potential intervention for enhancing working memory performance.

Does vibrotactile stimulation of the auricular vagus nerve enhance working memory? A behavioral and physiological investigation. - Tan, Gansheng; Adams, Josh; Donovan, Kara; Demarest, Phillip; Willie, Jon T; Brunner, Peter; Gorlewicz, Jenna L; Leuthardt, Eric C (Brain Stimul, 2024)
BACKGROUND: Working memory is essential to a wide range of cognitive functions and activities. Transcutaneous auricular vagus nerve stimulation (taVNS) is a promising method to improve working memory performance. However, the feasibility and scalability of electrical stimulation are constrained by several limitations, such as auricular discomfort and inconsistent electrical contact. OBJECTIVE: We aimed to develop a novel and practical method, vibrotactile taVNS, to improve working memory. Further, we investigated its effects on arousal, measured by skin conductance and pupil diameter. METHOD: This study included 20 healthy participants. Behavioral response, skin conductance, and eye tracking data were concurrently recorded while the participants performed N-back tasks under three conditions: vibrotactile taVNS delivered to the cymba concha, earlobe (sham control), and no stimulation (baseline control). RESULTS: In 4-back tasks, which demand maximal working memory capacity, active vibrotactile taVNS significantly improved the performance metric d compared to the baseline but not to the sham. Moreover, we found that the reduction rate of d with increasing task difficulty was significantly smaller during vibrotactile taVNS sessions than in both baseline and sham conditions. Arousal, measured as skin conductance and pupil diameter, declined over the course of the tasks. Vibrotactile taVNS rescued this arousal decline, leading to arousal levels corresponding to optimal working memory levels. Moreover, pupil diameter and skin conductance level were higher during high-cognitive-load tasks when vibrotactile taVNS was delivered to the concha compared to baseline and sham. CONCLUSION: Our findings suggest that vibrotactile taVNS modulates the arousal pathway and could be a potential intervention for enhancing working memory.
Keywords: Adult; Female; Galvanic Skin Response; Humans; Male; Memory, Short-Term; Pupil; Vagus Nerve; Vagus Nerve Stimulation; Vibration; Young Adult

Does vibrotactile stimulation of the auricular vagus nerve enhance working memory? A behavioral and physiological investigation - Tan, Gansheng; Adams, Josh; Donovan, Kara; Demarest, Phillip; Willie, Jon T; Brunner, Peter; Gorlewicz, Jenna L; Leuthardt, Eric C (Brain Stimulation, 2024)

The effect of transcutaneous auricular vagus nerve stimulation on cardiovascular function in subarachnoid hemorrhage patients: a safety study. - Tan, Gansheng; Huguenard, Anna L; Donovan, Kara M; Demarest, Phillip; Liu, Xiaoxuan; Li, Ziwei; Adamek, Markus; Lavine, Kory; Vellimana, Ananth K; Kummer, Terrance T; Osbun, Joshua W; Zipfel, Gregory J; et al. (medRxiv, 2024)
INTRODUCTION: Subarachnoid hemorrhage (SAH) is characterized by intense central inflammation, leading to substantial post-hemorrhagic complications such as vasospasm and delayed cerebral ischemia. Given the anti-inflammatory effect of transcutaneous auricular vagus nerve stimulation (taVNS) and its ability to promote brain plasticity, taVNS has emerged as a promising therapeutic option for SAH patients. However, the effects of taVNS on cardiovascular dynamics in critically ill patients, like those with SAH, have not yet been investigated. Given the association between cardiac complications and elevated risk of poor clinical outcomes after SAH, it is essential to characterize the cardiovascular effects of taVNS to ensure this approach is safe in this fragile population. Therefore, we assessed the impact of both acute taVNS and repetitive taVNS on cardiovascular function in this study. METHODS: In this randomized clinical trial, 24 SAH patients were assigned to either a taVNS treatment or a Sham treatment group. During their stay in the intensive care unit, we monitored patient electrocardiogram (ECG) readings and vital signs. We compared long-term changes in heart rate, heart rate variability, QT interval, and blood pressure between the two groups. Additionally, we assessed the effects of acute taVNS by comparing cardiovascular metrics before, during, and after the intervention. We also explored acute cardiovascular biomarkers in patients exhibiting clinical improvement. RESULTS: We found that repetitive taVNS did not significantly alter heart rate, QT interval, blood pressure, or intracranial pressure. However, taVNS increased overall heart rate variability and parasympathetic activity compared to the sham treatment. The increase in parasympathetic activity was most pronounced from 2-4 days after initial treatment (Cohen's d = 0.50). Acutely, taVNS increased heart rate, blood pressure, and peripheral perfusion index without affecting the corrected QT interval, intracranial pressure, or heart rate variability. The acute post-treatment elevation in heart rate was more pronounced in patients who experienced a decrease of more than one point in their Modified Rankin Score at the time of discharge. CONCLUSIONS: Our study found that taVNS treatment did not induce adverse cardiovascular effects, such as bradycardia or QT prolongation, supporting its development as a safe immunomodulatory treatment approach for SAH patients. The observed acute increase in heart rate after taVNS treatment may serve as a biomarker for SAH patients who could derive greater benefit from this treatment. TRIAL REGISTRATION: NCT04557618.

Graded decisions in the human brain. - Xie, Tao; Adamek, Markus; Cho, Hohyun; Adamo, Matthew A; Ritaccio, Anthony L; Willie, Jon T; Brunner, Peter; Kubanek, Jan (Nat Commun, 2024)
Decision-makers objectively commit to a definitive choice, yet at the subjective level, human decisions appear to be associated with a degree of uncertainty. Whether decisions are definitive (i.e., concluding in all-or-none choices), or whether the underlying representations are graded, remains unclear. To answer this question, we recorded intracranial neural signals directly from the brain while human subjects made perceptual decisions. The recordings revealed that broadband gamma activity reflecting each individual's decision-making process, ramped up gradually while being graded by the accumulated decision evidence. Crucially, this grading effect persisted throughout the decision process without ever reaching a definite bound at the time of choice. This effect was most prominent in the parietal cortex, a brain region traditionally implicated in decision-making. These results provide neural evidence for a graded decision process in humans and an analog framework for flexible choice behavior.
Keywords: Adult; Brain; Choice Behavior; Decision Making; Female; Humans; Male; Parietal Lobe; Uncertainty; Young Adult

Graded decisions in the human brain - Xie, Tao; Adamek, Markus; Cho, Hohyun; Adamo, Matthew A; Ritaccio, Anthony L; Willie, Jon T; Brunner, Peter; Kubanek, Jan (Nature communications, 2024)

The involvement of the piriform cortex in non-lesional temporal lobe epilepsy: an uncommon component of the epileptogenic network. - Pedersen, Nigel P; Raghu, Ashley; Shivamurthy, Veeresh Kumar N; Chern, Joshua J; Gross, Robert E; Willie, Jon T; Dingledine, Raymond J; Kheder, Ammar (Brain Commun, 2024)
The piriform cortex is recognized as highly epileptogenic in rodents, yet its electrophysiological role in human epilepsy remains understudied. Recent surgical outcomes have suggested potential benefits in resecting the piriform cortex for cases of medial temporal lobe epilepsy. However, little is known about its electrophysiological activity in human epilepsy. This case-series study aimed to explore the electrophysiological role of the piriform cortex within the epileptogenic network among patients with suspected temporal lobe epilepsy. Participants were recruited from Emory University Hospital or Children's Healthcare of Atlanta, with non-lesional frontotemporal or temporal lobe hypotheses, undergoing stereoelectroencephalographic studies. Specifically, focus was placed on patients with one or more electrode contacts in the piriform cortex. Primary objectives included determining piriform cortex involvement within the electrophysiologically defined epileptogenic network and assessing the effects of electrical stimulation. Twenty-two patients were included in the study. Notably, only one patient exhibited piriform cortex involvement at seizure onset, associated with an olfactory aura. Two patients showed early piriform cortex involvement, while others displayed late or no involvement. Electrical stimulation of the piriform cortex induced after-discharges in three patients and replicated a habitual seizure in one. These findings present a contrast to surgical outcome studies, suggesting that the piriform cortex may not typically play a significant role in the epileptogenic network among patients with non-lesional temporal lobe epilepsy.

Motor imagery ability scores are related to cortical activation during gait imagery. - Putzolu, Martina; Samogin, Jessica; Bonassi, Gaia; Cosentino, Carola; Mezzarobba, Susanna; Botta, Alessandro; Avanzino, Laura; Mantini, Dante; Vato, Alessandro; Pelosin, Elisa (Sci Rep, 2024)
Motor imagery (MI) is the mental execution of actions without overt movements that depends on the ability to imagine. We explored whether this ability could be related to the cortical activity of the brain areas involved in the MI network. To this goal, brain activity was recorded using high-density electroencephalography in nineteen healthy adults while visually imagining walking on a straight path. We extracted Event-Related Desynchronizations (ERDs) in the θ, α, and β band, and we measured MI ability via (i) the Kinesthetic and Visual Imagery Questionnaire (KVIQ), (ii) the Vividness of Movement Imagery Questionnaire-2 (VMIQ), and (iii) the Imagery Ability (IA) score. We then used Pearson's and Spearman's coefficients to correlate MI ability scores and average ERD power (avgERD). Positive correlations were identified between VMIQ and avgERD of the middle cingulum in the β band and with avgERD of the left insula, right precentral area, and right middle occipital region in the θ band. Stronger activation of the MI network was related to better scores of MI ability evaluations, supporting the importance of testing MI ability during MI protocols. This result will help to understand MI mechanisms and develop personalized MI treatments for patients with neurological dysfunctions.
Keywords: Adult; Animals; Brain; Cell Membrane; Electroencephalography; Gait; Gastropoda; Humans; Walking

Motor learning changes the axon initial segment of the spinal motoneuron. - Wang, Yu; Chen, Yi; Chen, Lu; Herron, Bruce J; Chen, Xiang Yang; Wolpaw, Jonathan R (J Physiol, 2024)
We are studying the mechanisms of H-reflex operant conditioning, a simple form of learning. Modelling studies in the literature and our previous data suggested that changes in the axon initial segment (AIS) might contribute. To explore this, we used blinded quantitative histological and immunohistochemical methods to study in adult rats the impact of H-reflex conditioning on the AIS of the spinal motoneuron that produces the reflex. Successful, but not unsuccessful, H-reflex up-conditioning was associated with greater AIS length and distance from soma; greater length correlated with greater H-reflex increase. Modelling studies in the literature suggest that these increases may increase motoneuron excitability, supporting the hypothesis that they may contribute to H-reflex increase. Up-conditioning did not affect AIS ankyrin G (AnkG) immunoreactivity (IR), p-p38 protein kinase IR, or GABAergic terminals. Successful, but not unsuccessful, H-reflex down-conditioning was associated with more GABAergic terminals on the AIS, weaker AnkG-IR, and stronger p-p38-IR. More GABAergic terminals and weaker AnkG-IR correlated with greater H-reflex decrease. These changes might potentially contribute to the positive shift in motoneuron firing threshold underlying H-reflex decrease; they are consistent with modelling suggesting that sodium channel change may be responsible. H-reflex down-conditioning did not affect AIS dimensions. This evidence that AIS plasticity is associated with and might contribute to H-reflex conditioning adds to evidence that motor learning involves both spinal and brain plasticity, and both neuronal and synaptic plasticity. AIS properties of spinal motoneurons are likely to reflect the combined influence of all the motor skills that share these motoneurons. KEY POINTS: Neuronal action potentials normally begin in the axon initial segment (AIS). AIS plasticity affects neuronal excitability in development and disease. Whether it does so in learning is unknown. Operant conditioning of a spinal reflex, a simple learning model, changes the rat spinal motoneuron AIS. Successful, but not unsuccessful, H-reflex up-conditioning is associated with greater AIS length and distance from soma. Successful, but not unsuccessful, down-conditioning is associated with more AIS GABAergic terminals, less ankyrin G, and more p-p38 protein kinase. The associations between AIS plasticity and successful H-reflex conditioning are consistent with those between AIS plasticity and functional changes in development and disease, and with those predicted by modelling studies in the literature. Motor learning changes neurons and synapses in spinal cord and brain. Because spinal motoneurons are the final common pathway for behaviour, their AIS properties probably reflect the combined impact of all the behaviours that use these motoneurons.
Keywords: Animals; Ankyrins; Axon Initial Segment; Axons; Conditioning, Operant; H-Reflex; Learning; Male; Motor Neurons; Neuronal Plasticity; Rats; Rats, Sprague-Dawley; Spinal Cord

Multidimensional feature analysis shows stratification in robotic-motor-training gains based on the level of pre-training motor impairment in stroke. - Rueda-Parra, Sebastian; Perry, Joel C; Wolbrecht, Eric T; Reinkensmeyer, David J; Gupta, Disha (Annu Int Conf IEEE Eng Med Biol Soc, 2024)
Stroke involves heterogeneity in injury and ongoing endogenous recovery, which are seldom stratified before testing post-stroke robot assisted motor training (RAMT). Pretraining variations, especially sensory-motor differences may also affect the gains achieved from the RAMT. Moreover, one assessment test may not effectively characterize the baseline sensory-motor status or the RAMT gains. Pre-therapy stratification may help personalize therapy and increase therapy gains. Towards this goal, we propose a data-driven approach to assess multiple functional scores with t-distributed stochastic neighbor embedding and affinity propagation clustering, both for pre-therapy and RAMT gains. Data included behavioral scores from 27 people with chronic stroke who underwent RAMT for finger movement. Three clusters were observed at start-of-therapy (SoT), concurrent with the overall impairment level. Four clusters were observed for the RAMT gains, indicating specific improvements. The SoT clusters showed agreement with the RAMT gain clusters, suggesting that the pre-therapy state, assessed across multiple domains, could be useful in guiding RAMT interventions to improve outcomes.
Keywords: Aged; Cluster Analysis; Female; Humans; Male; Middle Aged; Robotics; Stroke; Stroke Rehabilitation

Multisensory flicker modulates widespread brain networks and reduces interictal epileptiform discharges. - Blanpain, Lou T; Cole, Eric R; Chen, Emily; Park, James K; Walelign, Michael Y; Gross, Robert E; Cabaniss, Brian T; Willie, Jon T; Singer, Annabelle C (Nat Commun, 2024)
Modulating brain oscillations has strong therapeutic potential. Interventions that both non-invasively modulate deep brain structures and are practical for chronic daily home use are desirable for a variety of therapeutic applications. Repetitive audio-visual stimulation, or sensory flicker, is an accessible approach that modulates hippocampus in mice, but its effects in humans are poorly defined. We therefore quantified the neurophysiological effects of flicker with high spatiotemporal resolution in patients with focal epilepsy who underwent intracranial seizure monitoring. In this interventional trial (NCT04188834) with a cross-over design, subjects underwent different frequencies of flicker stimulation in the same recording session with the effect of sensory flicker exposure on local field potential (LFP) power and interictal epileptiform discharges (IEDs) as primary and secondary outcomes, respectively. Flicker focally modulated local field potentials in expected canonical sensory cortices but also in the medial temporal lobe and prefrontal cortex, likely via resonance of stimulated long-range circuits. Moreover, flicker decreased interictal epileptiform discharges, a pathological biomarker of epilepsy and degenerative diseases, most strongly in regions where potentials were flicker-modulated, especially the visual cortex and medial temporal lobe. This trial met the scientific goal and is now closed. Our findings reveal how multi-sensory stimulation may modulate cortical structures to mitigate pathological activity in humans.
Keywords: Brain; Cross-Over Studies; Electroencephalography; Epilepsies, Partial; Epilepsy; Humans; Temporal Lobe

Neural correlates of bilateral proprioception and adaptation with training - Rueda-Parra, Sebastian; Perry, Joel C.; Wolbrecht, Eric T.; Gupta, Disha (PLOS ONE, 2024)
Bilateral proprioception includes the ability to sense the position and motion of one hand relative to the other, without looking. This sensory ability allows us to perform daily activities seamlessly, and its impairment is observed in various neurological disorders such as cerebral palsy and stroke. It can undergo experience-dependent plasticity, as seen in trained piano players. If its neural correlates were better understood, it would provide a useful assay and target for neurorehabilitation for people with impaired proprioception. We designed a non-invasive electroencephalography-based paradigm to assess the neural features relevant to proprioception, especially focusing on bilateral proprioception, i.e., assessing the limb distance from the body with the other limb. We compared it with a movement-only task, with and without the visibility of the target hand. Additionally, we explored proprioceptive accuracy during the tasks. We tested eleven Controls and nine Skilled musicians to assess whether sensorimotor event-related spectral perturbations in μ (8-12Hz) and low-β (12-18Hz) rhythms differ in people with musical instrument training, which intrinsically involves a bilateral proprioceptive component, or when new sensor modalities are added to the task. The Skilled group showed significantly reduced μ and low-β suppression in bilateral tasks compared to movement-only, a significative difference relative to Controls. This may be explained by reduced top-down control due to intensive training, despite this, proprioceptive errors were not smaller for this group. Target visibility significantly reduced proprioceptive error in Controls, while no change was observed in the Skilled group. During visual tasks, Controls exhibited significant μ and low-β power reversals, with significant differences relative to proprioceptive-only tasks compared to the Skilled group—possibly due to reduced uncertainty and top-down control. These results provide support for sensorimotor μ and low-β suppression as potential neuromarkers for assessing proprioceptive ability. The identification of these features is significant as they could be used to quantify altered proprioceptive neural processing in skill and movement disorders. This in turn can be useful as an assay for pre and post sensory-motor intervention research.

Neural mechanisms of face familiarity and learning in the human amygdala and hippocampus. - Cao, Runnan; Wang, Jinge; Brunner, Peter; Willie, Jon T; Li, Xin; Rutishauser, Ueli; Brandmeir, Nicholas J; Wang, Shuo (Cell Rep, 2024)
Recognizing familiar faces and learning new faces play an important role in social cognition. However, the underlying neural computational mechanisms remain unclear. Here, we record from single neurons in the human amygdala and hippocampus and find a greater neuronal representational distance between pairs of familiar faces than unfamiliar faces, suggesting that neural representations for familiar faces are more distinct. Representational distance increases with exposures to the same identity, suggesting that neural face representations are sharpened with learning and familiarization. Furthermore, representational distance is positively correlated with visual dissimilarity between faces, and exposure to visually similar faces increases representational distance, thus sharpening neural representations. Finally, we construct a computational model that demonstrates an increase in the representational distance of artificial units with training. Together, our results suggest that the neuronal population geometry, quantified by the representational distance, encodes face familiarity, similarity, and learning, forming the basis of face recognition and memory.
Keywords: Amygdala; Facial Recognition; Hippocampus; Humans; Learning; Pattern Recognition, Visual; Recognition, Psychology

Neural mechanisms of face familiarity and learning in the human amygdala and hippocampus - Cao, Runnan; Wang, Jinge; Brunner, Peter; Willie, Jon T; Li, Xin; Rutishauser, Ueli; Brandmeir, Nicholas J; Wang, Shuo (Cell reports, 2024)

Neural populations in the language network differ in the size of their temporal receptive windows - Regev, Tamar I; Casto, Colton; Hosseini, Eghbal A; Adamek, Markus; Ritaccio, Anthony L; Willie, Jon T; Brunner, Peter; Fedorenko, Evelina (Nature Human Behaviour, 2024)

Non-invasive Auricular Vagus nerve stimulation for Subarachnoid Hemorrhage (NAVSaH): Protocol for a prospective, triple-blinded, randomized controlled trial. - Huguenard, Anna L; Tan, Gansheng; Johnson, Gabrielle W; Adamek, Markus; Coxon, Andrew T; Kummer, Terrance T; Osbun, Joshua W; Vellimana, Ananth K; Limbrick, David D; Zipfel, Gregory J; Brunner, Peter; Leuthardt, Eric C (medRxiv, 2024)
BACKGROUND: Inflammation has been implicated in driving the morbidity associated with subarachnoid hemorrhage (SAH). Despite understanding the important role of inflammation in morbidity following SAH, there is no current effective way to modulate this deleterious response. There is a critical need for a novel approach to immunomodulation that can be safely, rapidly, and effectively deployed in SAH patients. Vagus nerve stimulation (VNS) provides a non-pharmacologic approach to immunomodulation, with prior studies demonstrating VNS can reduce systemic inflammatory markers, and VNS has had early success treating inflammatory conditions such as arthritis, sepsis, and inflammatory bowel diseases. The aim of the Non-invasive Auricular Vagus nerve stimulation for Subarachnoid Hemorrhage (NAVSaH) trial is to translate the use of non-invasive transcutaneous auricular VNS (taVNS) to spontaneous SAH, with our central hypothesis being that implementing taVNS in the acute period following spontaneous SAH attenuates the expected inflammatory response to hemorrhage and curtails morbidity associated with inflammatory-mediated clinical endpoints. MATERIALS AND METHODS: The overall objectives for the NAHSaH trial are to 1) Define the impact that taVNS has on SAH-induced inflammatory markers in the plasma and cerebrospinal fluid (CSF), 2) Determine whether taVNS following SAH reduces radiographic vasospasm, and 3) Determine whether taVNS following SAH reduces chronic hydrocephalus. Following presentation to a single enrollment site, enrolled SAH patients are randomly assigned twice daily treatment with either taVNS or sham stimulation for the duration of their intensive care unit stay. Blood and CSF are drawn before initiation of treatment sessions, and then every three days during a patient's hospital stay. Primary endpoints include change in the inflammatory cytokine TNF-α in plasma and cerebrospinal fluid between day 1 and day 13, rate of radiographic vasospasm, and rate of requirement for long-term CSF diversion via a ventricular shunt. Secondary outcomes include exploratory analyses of a panel of additional cytokines, number and type of hospitalized acquired infections, duration of external ventricular drain in days, interventions required for vasospasm, continuous physiology data before, during, and after treatment sessions, hospital length of stay, intensive care unit length of stay, and modified Rankin Scale score (mRS) at admission, discharge, and each at follow-up appointment for up to two years following SAH. DISCUSSION: Inflammation plays a central role in morbidity following SAH. This NAVSaH trial is innovative because it diverges from the pharmacologic status quo by harnessing a novel non-invasive neuromodulatory approach and its known anti-inflammatory effects to alter the pathophysiology of SAH. The investigation of a new, effective, and rapidly deployable intervention in SAH offers a new route to improve outcomes following SAH. TRIAL REGISTRATION: Clinical Trials Registered, NCT04557618. Registered on September 21, 2020, and the first patient was enrolled on January 4, 2021.

Non-invasive Auricular Vagus nerve stimulation for Subarachnoid Hemorrhage (NAVSaH): Protocol for a prospective, triple-blinded, randomized controlled trial. - Huguenard, Anna; Tan, Gansheng; Johnson, Gabrielle; Adamek, Markus; Coxon, Andrew; Kummer, Terrance; Osbun, Joshua; Vellimana, Ananth; Limbrick, David; Zipfel, Gregory; Brunner, Peter; Leuthardt, Eric (PLoS One, 2024)
BACKGROUND: Inflammation has been implicated in driving the morbidity associated with subarachnoid hemorrhage (SAH). Despite understanding the important role of inflammation in morbidity following SAH, there is no current effective way to modulate this deleterious response. There is a critical need for a novel approach to immunomodulation that can be safely, rapidly, and effectively deployed in SAH patients. Vagus nerve stimulation (VNS) provides a non-pharmacologic approach to immunomodulation, with prior studies demonstrating VNS can reduce systemic inflammatory markers, and VNS has had early success treating inflammatory conditions such as arthritis, sepsis, and inflammatory bowel diseases. The aim of the Non-invasive Auricular Vagus nerve stimulation for Subarachnoid Hemorrhage (NAVSaH) trial is to translate the use of non-invasive transcutaneous auricular VNS (taVNS) to spontaneous SAH, with our central hypothesis being that implementing taVNS in the acute period following spontaneous SAH attenuates the expected inflammatory response to hemorrhage and curtails morbidity associated with inflammatory-mediated clinical endpoints. MATERIALS AND METHODS: The overall objectives for the NAHSaH trial are to 1) Define the impact that taVNS has on SAH-induced inflammatory markers in the plasma and cerebrospinal fluid (CSF), 2) Determine whether taVNS following SAH reduces radiographic vasospasm, and 3) Determine whether taVNS following SAH reduces chronic hydrocephalus. Following presentation to a single enrollment site, enrolled SAH patients are randomly assigned twice daily treatment with either taVNS or sham stimulation for the duration of their intensive care unit stay. Blood and CSF are drawn before initiation of treatment sessions, and then every three days during a patient's hospital stay. Primary endpoints include change in the inflammatory cytokine TNF-α in plasma and cerebrospinal fluid between day 1 and day 13, rate of radiographic vasospasm, and rate of requirement for long-term CSF diversion via a ventricular shunt. Secondary outcomes include exploratory analyses of a panel of additional cytokines, number and type of hospitalized acquired infections, duration of external ventricular drain in days, interventions required for vasospasm, continuous physiology data before, during, and after treatment sessions, hospital length of stay, intensive care unit length of stay, and modified Rankin Scale score (mRS) at admission, discharge, and each at follow-up appointment for up to two years following SAH. DISCUSSION: Inflammation plays a central role in morbidity following SAH. This NAVSaH trial is innovative because it diverges from the pharmacologic status quo by harnessing a novel non-invasive neuromodulatory approach and its known anti-inflammatory effects to alter the pathophysiology of SAH. The investigation of a new, effective, and rapidly deployable intervention in SAH offers a new route to improve outcomes following SAH. TRIAL REGISTRATION: Clinical Trials Registered, NCT04557618. Registered on September 21, 2020, and the first patient was enrolled on January 4, 2021.
Keywords: Adult; Female; Humans; Inflammation; Male; Middle Aged; Prospective Studies; Randomized Controlled Trials as Topic; Subarachnoid Hemorrhage; Treatment Outcome; Vagus Nerve Stimulation

Non-invasive Brain-Computer Interfaces: State of the Art and Trends - Edelman, Bradley J; Zhang, Shuailei; Schalk, Gerwin; Brunner, Peter; Müller-Putz, Gernot; Guan, Cuntai; He, Bin (IEEE Reviews in Biomedical Engineering, 2024)

Novel cyclic homogeneous oscillation detection method for high accuracy and specific characterization of neural dynamics - Cho, Hohyun; Adamek, Markus; Willie, Jon T; Brunner, Peter (Elife, 2024)

Novel Cyclic Homogeneous Oscillation Detection Method for High Accuracy and Specific Characterization of Neural Dynamics. - Cho, Hohyun; Adamek, Markus; Willie, Jon T; Brunner, Peter (bioRxiv, 2024)
Detecting temporal and spectral features of neural oscillations is essential to understanding dynamic brain function. Traditionally, the presence and frequency of neural oscillations are determined by identifying peaks over 1/f noise within the power spectrum. However, this approach solely operates within the frequency domain and thus cannot adequately distinguish between the fundamental frequency of a non-sinusoidal oscillation and its harmonics. Non-sinusoidal signals generate harmonics, significantly increasing the false-positive detection rate - a confounding factor in the analysis of neural oscillations. To overcome these limitations, we define the fundamental criteria that characterize a neural oscillation and introduce the Cyclic Homogeneous Oscillation (CHO) detection method that implements these criteria based on an auto-correlation approach that determines the oscillation's periodicity and fundamental frequency. We evaluated CHO by verifying its performance on simulated sinusoidal and non-sinusoidal oscillatory bursts convolved with 1/f noise. Our results demonstrate that CHO outperforms conventional techniques in accurately detecting oscillations. Specifically, we determined the sensitivity and specificity of CHO as a function of signal-to-noise ratio (SNR). We further assessed CHO by testing it on electrocorticographic (ECoG, 8 subjects) and electroencephalographic (EEG, 7 subjects) signals recorded during the pre-stimulus period of an auditory reaction time task and on electrocorticographic signals (6 SEEG subjects and 6 ECoG subjects) collected during resting state. In the reaction time task, the CHO method detected auditory alpha and pre-motor beta oscillations in ECoG signals and occipital alpha and pre-motor beta oscillations in EEG signals. Moreover, CHO determined the fundamental frequency of hippocampal oscillations in the human hippocampus during the resting state (6 SEEG subjects). In summary, CHO demonstrates high precision and specificity in detecting neural oscillations in time and frequency domains. The method's specificity enables the detailed study of non-sinusoidal characteristics of oscillations, such as the degree of asymmetry and waveform of an oscillation. Furthermore, CHO can be applied to identify how neural oscillations govern interactions throughout the brain and to determine oscillatory biomarkers that index abnormal brain function.

Novel cyclic homogeneous oscillation detection method for high accuracy and specific characterization of neural dynamics. - Cho, Hohyun; Adamek, Markus; Willie, Jon T; Brunner, Peter (Elife, 2024)
Determining the presence and frequency of neural oscillations is essential to understanding dynamic brain function. Traditional methods that detect peaks over 1/ noise within the power spectrum fail to distinguish between the fundamental frequency and harmonics of often highly non-sinusoidal neural oscillations. To overcome this limitation, we define fundamental criteria that characterize neural oscillations and introduce the cyclic homogeneous oscillation (CHO) detection method. We implemented these criteria based on an autocorrelation approach to determine an oscillation's fundamental frequency. We evaluated CHO by verifying its performance on simulated non-sinusoidal oscillatory bursts and validated its ability to determine the fundamental frequency of neural oscillations in electrocorticographic (ECoG), electroencephalographic (EEG), and stereoelectroencephalographic (SEEG) signals recorded from 27 human subjects. Our results demonstrate that CHO outperforms conventional techniques in accurately detecting oscillations. In summary, CHO demonstrates high precision and specificity in detecting neural oscillations in time and frequency domains. The method's specificity enables the detailed study of non-sinusoidal characteristics of oscillations, such as the degree of asymmetry and waveform of an oscillation. Furthermore, CHO can be applied to identify how neural oscillations govern interactions throughout the brain and to determine oscillatory biomarkers that index abnormal brain function.
Keywords: Brain; Electrocorticography; Electroencephalography; Humans; Signal Processing, Computer-Assisted

A novel theta-controlled vibrotactile brain-computer interface to treat chronic pain: a pilot study. - Demarest, Phillip; Rustamov, Nabi; Swift, James; Xie, Tao; Adamek, Markus; Cho, Hohyun; Wilson, Elizabeth; Han, Zhuangyu; Belsten, Alexander; Luczak, Nicholas; Brunner, Peter; Haroutounian, Simon; et al. (Sci Rep, 2024)
Limitations in chronic pain therapies necessitate novel interventions that are effective, accessible, and safe. Brain-computer interfaces (BCIs) provide a promising modality for targeting neuropathology underlying chronic pain by converting recorded neural activity into perceivable outputs. Recent evidence suggests that increased frontal theta power (4-7 Hz) reflects pain relief from chronic and acute pain. Further studies have suggested that vibrotactile stimulation decreases pain intensity in experimental and clinical models. This longitudinal, non-randomized, open-label pilot study's objective was to reinforce frontal theta activity in six patients with chronic upper extremity pain using a novel vibrotactile neurofeedback BCI system. Patients increased their BCI performance, reflecting thought-driven control of neurofeedback, and showed a significant decrease in pain severity (1.29 ± 0.25 MAD, p = 0.03, q = 0.05) and pain interference (1.79 ± 1.10 MAD p = 0.03, q = 0.05) scores without any adverse events. Pain relief significantly correlated with frontal theta modulation. These findings highlight the potential of BCI-mediated cortico-sensory coupling of frontal theta with vibrotactile stimulation for alleviating chronic pain.
Keywords: brain-computer interfaces; Chronic Pain; Electroencephalography; Humans; Longitudinal Studies; Neurofeedback; Non-Randomized Controlled Trials as Topic; Pilot Projects

A novel theta-controlled vibrotactile brain–computer interface to treat chronic pain: a pilot study - Demarest, Phillip; Rustamov, Nabi; Swift, James; Xie, Tao; Adamek, Markus; Cho, Hohyun; Wilson, Elizabeth; Han, Zhuangyu; Belsten, Alexander; Luczak, Nicholas; others (Scientific reports, 2024)

Operant up-conditioning of the soleus cutaneous reflex to non-noxious stimuli in a person with chronic incomplete spinal cord injury. - Phipps, Alan M; Thompson, Aiko K (Clin Neurophysiol, 2024)
Keywords: Conditioning, Operant; H-Reflex; Humans; Muscle, Skeletal; Reflex; Spinal Cord; Spinal Cord Injuries

Optimal approaches to analyzing functional MRI data in glioma patients. - Park, Ki Yun; Shimony, Joshua S; Chakrabarty, Satrajit; Tanenbaum, Aaron B; Hacker, Carl D; Donovan, Kara M; Luckett, Patrick H; Milchenko, Mikhail; Sotiras, Aristeidis; Marcus, Daniel S; Leuthardt, Eric C; Snyder, Abraham Z (J Neurosci Methods, 2024)
BACKGROUND: Resting-state fMRI is increasingly used to study the effects of gliomas on the functional organization of the brain. A variety of preprocessing techniques and functional connectivity analyses are represented in the literature. However, there so far has been no systematic comparison of how alternative methods impact observed results. NEW METHOD: We first surveyed current literature and identified alternative analytical approaches commonly used in the field. Following, we systematically compared alternative approaches to atlas registration, parcellation scheme, and choice of graph-theoretical measure as regards differentiating glioma patients (N = 59) from age-matched reference subjects (N = 163). RESULTS: Our results suggest that non-linear, as opposed to affine registration, improves structural match to an atlas, as well as measures of functional connectivity. Functionally- as opposed to anatomically-derived parcellation schemes maximized the contrast between glioma patients and reference subjects. We also demonstrate that graph-theoretic measures strongly depend on parcellation granularity, parcellation scheme, and graph density. COMPARISON WITH EXISTING METHODS AND CONCLUSIONS: Our current work primarily focuses on technical optimization of rs-fMRI analysis in glioma patients and, therefore, is fundamentally different from the bulk of papers discussing glioma-induced functional network changes. We report that the evaluation of glioma-induced alterations in the functional connectome strongly depends on analytical approaches including atlas registration, choice of parcellation scheme, and graph-theoretical measures.
Keywords: Brain; Connectome; Glioma; Humans; Magnetic Resonance Imaging

Predicting post-surgical functional status in high-grade glioma with resting state fMRI and machine learning. - Luckett, Patrick H; Olufawo, Michael O; Park, Ki Yun; Lamichhane, Bidhan; Dierker, Donna; Verastegui, Gabriel Trevino; Lee, John J; Yang, Peter; Kim, Albert; Butt, Omar H; Chheda, Milan G; Snyder, Abraham Z; et al. (J Neurooncol, 2024)
PURPOSE: High-grade glioma (HGG) is the most common and deadly malignant glioma of the central nervous system. The current standard of care includes surgical resection of the tumor, which can lead to functional and cognitive deficits. The aim of this study is to develop models capable of predicting functional outcomes in HGG patients before surgery, facilitating improved disease management and informed patient care. METHODS: Adult HGG patients (N = 102) from the neurosurgery brain tumor service at Washington University Medical Center were retrospectively recruited. All patients completed structural neuroimaging and resting state functional MRI prior to surgery. Demographics, measures of resting state network connectivity (FC), tumor location, and tumor volume were used to train a random forest classifier to predict functional outcomes based on Karnofsky Performance Status (KPS < 70, KPS ≥ 70). RESULTS: The models achieved a nested cross-validation accuracy of 94.1% and an AUC of 0.97 in classifying KPS. The strongest predictors identified by the model included FC between somatomotor, visual, auditory, and reward networks. Based on location, the relation of the tumor to dorsal attention, cingulo-opercular, and basal ganglia networks were strong predictors of KPS. Age was also a strong predictor. However, tumor volume was only a moderate predictor. CONCLUSION: The current work demonstrates the ability of machine learning to classify postoperative functional outcomes in HGG patients prior to surgery accurately. Our results suggest that both FC and the tumor's location in relation to specific networks can serve as reliable predictors of functional outcomes, leading to personalized therapeutic approaches tailored to individual patients.
Keywords: Adult; Aged; Brain; Brain Neoplasms; Female; Glioma; Humans; machine learning; Magnetic Resonance Imaging; Male; Middle Aged; Neoplasm Grading; Prognosis; Rest; Retrospective Studies

Variability of corticospinal and spinal reflex excitability for the ankle dorsiflexor tibialis anterior across repeated measurements in people with and without incomplete spinal cord injury. - Brangaccio, J A; Phipps, A M; Gemoets, D E; Sniffen, J M; Thompson, Aiko K (Exp Brain Res, 2024)
To adequately evaluate the corticospinal and spinal plasticity in health and disease, it is essential to understand whether and to what extent the corticospinal and spinal responses fluctuate systematically across multiple measurements. Thus, in this study, we examined the session-to-session variability of corticospinal excitability for the ankle dorsiflexor tibialis anterior (TA) in people with and without incomplete spinal cord injury (SCI). In neurologically normal participants, the following measures were obtained across 4 days at the same time of day (N = 13) or 4 sessions over a 12-h period (N = 9, at 8:00, 12:00, 16:00, and 20:00): maximum voluntary contraction (MVC), maximum M-wave and H-reflex (M and H), motor evoked potential (MEP) amplitude, and silent period (SP) after MEP. In participants with chronic incomplete SCI (N = 17), the same measures were obtained across 4 days. We found no clear diurnal variation in the spinal and corticospinal excitability of the TA in individuals with no known neurological conditions, and no systematic changes in any experimental measures of spinal and corticospinal excitability across four measurement days in individuals with or without SCI. Overall, mean deviations across four sessions remained in a range of 5-13% for all measures in participants with or without SCI. The study shows the limited extent of non-systematic session-to-session variability in the TA corticospinal excitability in individuals with and without chronic incomplete SCI, supporting the utility of corticospinal and spinal excitability measures in mechanistic investigation of neuromodulation interventions. The information provided through this study may serve as the reference in evaluating corticospinal plasticity across multiple experimental sessions.

Altered cutaneous reflexes to non-noxious stimuli in the triceps surae of people with chronic incomplete spinal cord injury. - Phipps, Alan M; Thompson, Aiko K (J Neurophysiol, 2023)
Following spinal cord injury (SCI) task-dependent modulation of spinal reflexes are often impaired. To gain insight into the state of the spinal interneuronal pathways following injury, we studied the amplitude modulation of triceps surae cutaneous reflexes to non-noxious stimuli during standing and early-to-mid stance phase of walking in participants with and without chronic incomplete SCI. Reflex eliciting nerve stimulation was delivered to the superficial peroneal, sural, and distal tibial nerves about the ankle. Reflexes were analyzed in the short (SLR, 50-80 ms post stimulation onset) and the medium (MLR, 80-120 ms) latency response windows. Further, the relation between cutaneous and H-reflexes was also examined during standing. In participants without injuries the soleus SLR was modulated task-dependently with nerve specificity, and the soleus and medial gastrocnemius MLRs were modulated task-dependently. In contrast, participants with SCI, no task-dependent or nerve-specific modulation of triceps cutaneous reflexes was observed. The triceps surae cutaneous and H-reflexes were not correlated in either group (r = 0.01-0.37). The presence of cutaneous reflexes but the absence of significant amplitude modulation may suggest impaired function of spinal interneuronal pathways in this population. The lack of correlation between the cutaneous and H-reflexes may suggest that interneurons that are involved in H-reflex modulation and cutaneous reflex modulation do not receive common input, or the impact of the common input is outweighed by other input. Present findings highlight the importance of examining multiple spinal reflexes to better understanding spinal interneuronal pathways that affect motor control in people after SCI.

Characterization of High-Gamma Activity in Electrocorticographic signals - Gruenwald, Johannes; Sieghartsleitner, Sebastian; Kapeller, Christoph; Scharinger, Josef; Kamada, Kyousuke; Brunner, Peter; Guger, Christoph (Frontiers in Neuroscience, 2023)
Introduction: Electrocorticographic (ECoG) high-gamma activity (HGA) is a widely recognized and robust neural correlate of cognition and behavior. However, fundamental signal properties of HGA, such as the high-gamma frequency band or temporal dynamics of HGA, have never been systematically characterized. As a result, HGA estimators are often poorly adjusted, such that they miss valuable physiological information. Methods: To address these issues, we conducted a thorough qualitative and quantitative characterization of HGA in ECoG signals. Our study is based on ECoG signals recorded from 18 epilepsy patients while performing motor control, listening, and visual perception tasks. In this study, we first categorize HGA into HGA types based on the cognitive/behavioral task. For each HGA type, we then systematically quantify three fundamental signal properties of HGA: the high-gamma frequency band, the HGA bandwidth, and the temporal dynamics of HGA. Results: The high-gamma frequency band strongly varies across subjects and across cognitive/behavioral tasks. In addition, HGA time courses have lowpass character, with transients limited to 10 Hz. The task-related rise time and duration of these HGA time courses depend on the individual subject and cognitive/behavioral task. Task-related HGA amplitudes are comparable across the investigated tasks. Discussion: This study is of high practical relevance because it provides a systematic basis for optimizing experiment design, ECoG acquisition and processing, and HGA estimation. Our results reveal previously unknown characteristics of HGA, the physiological principles of which need to be investigated in further studies.

Comparisons of electrophysiological markers of impaired executive attention after traumatic brain injury and in healthy aging. - Kim, Nayoung; Jamison, Keith; Jaywant, Abhishek; Garetti, Jacob; Blunt, Emily; RoyChoudhury, Arindam; Butler, Tracy; Dams-O'Connor, Kristen; Khedr, Shahenda; Chen, Chun-Cheng; Shetty, Teena; Winchell, Robert; et al. (Neuroimage, 2023)
Executive attention impairments are a persistent and debilitating consequence of traumatic brain injury (TBI). To make headway towards treating and predicting outcomes following heterogeneous TBI, cognitive impairment specific pathophysiology first needs to be characterized. In a prospective observational study, we measured EEG during the attention network test aimed at detecting alerting, orienting, executive attention and processing speed. The sample (N = 110) of subjects aged 18-86 included those with and without traumatic brain injury: n = 27, complicated mild TBI; n = 5, moderate TBI; n = 10, severe TBI; n = 63, non-brain-injured controls. Subjects with TBI had impairments in processing speed and executive attention. Electrophysiological markers of executive attention processing in the midline frontal regions reveal that, as a group, those with TBI and elderly non-brain-injured controls have reduced responses. We also note that those with TBI and elderly controls have responses that are similar for both low and high-demand trials. In subjects with moderate-severe TBI, reductions in frontal cortical activation and performance profiles are both similar to that of controls who are ∼4 to 7 years older. Our specific observations of frontal response reductions in subjects with TBI and in older adults is consistent with the suggested role of the anterior forebrain mesocircuit as underlying cognitive impairments. Our results provide novel correlative data linking specific pathophysiological mechanisms underlying domain-specific cognitive deficits following TBI and with normal aging. Collectively, our findings provide biomarkers that may serve to track therapeutic interventions and guide development of targeted therapeutics following brain injuries.
Keywords: Aged; Aging; Biomarkers; Brain Injuries; Brain Injuries, Traumatic; Executive Function; Healthy Aging; Humans; Neuropsychological Tests

Data-efficient resting-state functional magnetic resonance imaging brain mapping with deep learning. - Luckett, Patrick H; Park, Ki Yun; Lee, John J; Lenze, Eric J; Wetherell, Julie Loebach; Eyler, Lisa T; Snyder, Abraham Z; Ances, Beau M; Shimony, Joshua S; Leuthardt, Eric C (J Neurosurg, 2023)
OBJECTIVE: Resting-state functional MRI (RS-fMRI) enables the mapping of function within the brain and is emerging as an efficient tool for the presurgical evaluation of eloquent cortex. Models capable of reliable and precise mapping of resting-state networks (RSNs) with a reduced scanning time would lead to improved patient comfort while reducing the cost per scan. The aims of the present study were to develop a deep 3D convolutional neural network (3DCNN) capable of voxel-wise mapping of language (LAN) and motor (MOT) RSNs with minimal quantities of RS-fMRI data. METHODS: Imaging data were gathered from multiple ongoing studies at Washington University School of Medicine and other thoroughly characterized, publicly available data sets. All study participants (n = 2252 healthy adults) were cognitively screened and completed structural neuroimaging and RS-fMRI. Random permutations of RS-fMRI regions of interest were used to train a 3DCNN. After training, model inferences were compared using varying amounts of RS-fMRI data from the control data set as well as 5 patients with glioblastoma multiforme. RESULTS: The trained model achieved 96% out-of-sample validation accuracy on data encompassing a large age range collected on multiple scanner types and varying sequence parameters. Testing on out-of-sample control data showed 97.9% similarity between results generated using either 50 or 200 RS-fMRI time points, corresponding to approximately 2.5 and 10 minutes, respectively (96.9% LAN, 96.3% MOT true-positive rate). In evaluating data from patients with brain tumors, the 3DCNN was able to accurately map LAN and MOT networks despite structural and functional alterations. CONCLUSIONS: Functional maps produced by the 3DCNN can inform surgical planning in patients with brain tumors in a time-efficient manner. The authors present a highly efficient method for presurgical functional mapping and thus improved functional preservation in patients with brain tumors.

Effects of active and sham tDCS on the soleus H-reflex during standing. - McCane, Lynn M; Wolpaw, Jonathan R; Thompson, Aiko K (Exp Brain Res, 2023)
Weak transcranial direct current stimulation (tDCS) is known to affect corticospinal excitability and enhance motor skill acquisition, whereas its effects on spinal reflexes in actively contracting muscles are yet to be established. Thus, in this study, we examined the acute effects of Active and Sham tDCS on the soleus H-reflex during standing. In fourteen adults without known neurological conditions, the soleus H-reflex was repeatedly elicited at just above M-wave threshold throughout 30 min of Active (N = 7) or Sham (N = 7) 2-mA tDCS over the primary motor cortex in standing. The maximum H-reflex (H) and M-wave (M) were also measured before and immediately after 30 min of tDCS. The soleus H-reflex amplitudes became significantly larger (by 6%) ≈1 min into Active or Sham tDCS and gradually returned toward the pre-tDCS values, on average, within 15 min. With Active tDCS, the amplitude reduction from the initial increase appeared to occur more swiftly than with Sham tDCS. An acute temporary increase in the soleus H-reflex amplitude within the first minute of Active and Sham tDCS found in this study indicates a previously unreported effect of tDCS on the H-reflex excitability. The present study suggests that neurophysiological characterization of Sham tDCS effects is just as important as investigating Active tDCS effects in understanding and defining acute effects of tDCS on the excitability of spinal reflex pathways.
Keywords: Adult; Evoked Potentials, Motor; H-Reflex; Humans; Muscle, Skeletal; Standing Position; Transcranial Direct Current Stimulation

The human motor cortex contributes to gravity compensation to maintain posture and during reaching. - Hardesty, Russell L; Ellaway, Peter H; Gritsenko, Valeriya (J Neurophysiol, 2023)
The neural control of posture and movement is interdependent. During voluntary movement, the neural motor command is executed by the motor cortex through the corticospinal tract and its collaterals and subcortical targets. Here we address the question of whether the control mechanism for the postural adjustments at nonmoving joints is also involved in overcoming gravity at the moving joints. We used single-pulse transcranial magnetic stimulation to measure the corticospinal excitability in humans during postural and reaching tasks. We hypothesized that the corticospinal excitability is proportional to background muscle activity and the gravity-related joint moments during both static postures and reaching movements. To test this hypothesis, we used visual targets in virtual reality to instruct five postures and three movements with or against gravity. We then measured the amplitude and gain of motor evoked potentials in multiple arm and hand muscles at several phases of the reaching motion and during static postures. The stimulation caused motor evoked potentials in all muscles that were proportional to the muscle activity. During both static postures and reaching movements, the muscle activity and the corticospinal contribution to these muscles changed in proportion with the postural moments needed to support the arm against gravity, supporting the hypothesis. Notably, these changes happened not only in antigravity muscles. Altogether, these results provide evidence that the changes in corticospinal excitability cause muscle cocontraction that modulates limb stiffness. This suggests that the motor cortex is involved in producing postural adjustments that support the arm against gravity during posture maintenance and reaching. Animal studies suggest that the corticospinal tract and its collaterals are crucial for producing postural adjustments that accompany movement in limbs other than the moving limb. Here we provide evidence for a similar control schema for both arm posture maintenance and gravity compensation during movement of the same limb. The observed interplay between the postural and movement control signals within the corticospinal tract may help explain the underlying neural motor deficits after stroke.
Keywords: Electromyography; Evoked Potentials, Motor; Humans; Motor Cortex; Movement; Muscle, Skeletal; Posture; Pyramidal Tracts; Transcranial Magnetic Stimulation

Intracranial stimulation and EEG feature analysis reveal affective salience network specialization. - Metzger, Brian A; Kalva, Prathik; Mocchi, Madaline M; Cui, Brian; Adkinson, Joshua A; Wang, Zhengjia; Mathura, Raissa; Kanja, Kourtney; Gavvala, Jay; Krishnan, Vaishnav; Lin, Lu; Maheshwari, Atul; et al. (Brain, 2023)
Emotion is represented in limbic and prefrontal brain areas herein termed the Affective Salience Network (ASN). Within the ASN, there are substantial unknowns about how valence and emotional intensity are processed - specifically, which nodes are associated with affective bias (a phenomenon in which participants interpret emotions in a manner consistent with their own mood). A recently developed feature detection approach ("specparam") was used to select dominant spectral features from human intracranial electrophysiological data, revealing affective specialization within specific nodes of the ASN. Spectral analysis of dominant features at the channel level suggests that dorsal anterior cingulate (dACC), anterior insula (aINS) and ventral-medial prefrontal cortex (vmPFC) are sensitive to valence and intensity, while the amygdala is primarily sensitive to intensity. AIC model comparisons corroborated the spectral analysis findings, suggesting all four nodes are more sensitive to intensity compared to valence. The data also revealed that activity in dACC and vmPFC was predictive of the extent of affective bias in the ratings of facial expressions - a proxy measure of instantaneous mood. To examine causality of the dACC in affective experience, 130 Hz continuous stimulation was applied to dACC while patients viewed and rated emotional faces. Faces were rated significantly happier during stimulation, even after accounting for differences in baseline ratings. Together the data suggest a causal role for dACC during the processing of external affective stimuli.

Methods for automated delineation and assessment of EMG responses evoked by peripheral nerve stimulation in diagnostic and closed-loop therapeutic applications. - McKinnon, Michael L; Hill, N Jeremy; Carp, Jonathan S; Dellenbach, Blair; Thompson, Aiko K (J Neural Eng, 2023)
Surface electromyography measurements of the Hoffmann (H-) reflex are essential in a wide range of neuroscientific and clinical applications. One promising emerging therapeutic application is H-reflex operant conditioning, whereby a person is trained to modulate the H-reflex, with generalized beneficial effects on sensorimotor function in chronic neuromuscular disorders. Both traditional diagnostic and novel realtime therapeutic applications rely on accurate definitions of the H-reflex and M-wave temporal bounds, which currently depend on expert case-by-case judgment. The current study automates such judgments.Our novel wavelet-based algorithm automatically determines temporal extent and amplitude of the human soleus H-reflex and M-wave. In each of 20 participants, the algorithm was trained on data from a preliminary 3 or 4 min recruitment-curve measurement. Output was evaluated on parametric fits to subsequent sessions' recruitment curves (92 curves across all participants) and on the conditioning protocol's subsequent baseline trials (∼1200 per participant) performed near. Results were compared against the original temporal bounds estimated at the time, and against retrospective estimates made by an expert 6 years later.Automatic bounds agreed well with manual estimates: 95% lay within ±2.5 ms. The resulting H-reflex magnitude estimates showed excellent agreement (97.5% average across participants) between automatic and retrospective bounds regarding which trials would be considered successful for operant conditioning. Recruitment-curve parameters also agreed well between automatic and manual methods: 95% of the automatic estimates of the current required to elicitfell within±1.4%of the retrospective estimate; for the 'threshold' current that produced an M-wave 10% of maximum, this value was±3.5%.Such dependable automation of M-wave and H-reflex definition should make both established and emerging H-reflex protocols considerably less vulnerable to inter-personnel variability and human error, increasing translational potential.
Keywords: Electric Stimulation; Electromyography; H-Reflex; Humans; Muscle, Skeletal; Peripheral Nerves; Retrospective Studies

A motor association area in the depths of the central sulcus. - Jensen, Michael A; Huang, Harvey; Valencia, Gabriela Ojeda; Klassen, Bryan T; van den Boom, Max A; Kaufmann, Timothy J; Schalk, Gerwin; Brunner, Peter; Worrell, Gregory A; Hermes, Dora; Miller, Kai J (Nat Neurosci, 2023)
Cells in the precentral gyrus directly send signals to the periphery to generate movement and are principally organized as a topological map of the body. We find that movement-induced electrophysiological responses from depth electrodes extend this map three-dimensionally throughout the gyrus. Unexpectedly, this organization is interrupted by a previously undescribed motor association area in the depths of the midlateral aspect of the central sulcus. This 'Rolandic motor association' (RMA) area is active during movements of different body parts from both sides of the body and may be important for coordinating complex behaviors.
Keywords: Brain Mapping; Motor Cortex; Movement

Multisensory Flicker Modulates Widespread Brain Networks and Reduces Interictal Epileptiform Discharges in Humans. - Blanpain, Lou T; Chen, Emily; Park, James; Walelign, Michael Y; Gross, Robert E; Cabaniss, Brian T; Willie, Jon T; Singer, Annabelle C (medRxiv, 2023)
Modulating brain oscillations has strong therapeutic potential. However, commonly used non-invasive interventions such as transcranial magnetic or direct current stimulation have limited effects on deeper cortical structures like the medial temporal lobe. Repetitive audio- visual stimulation, or sensory flicker, modulates such structures in mice but little is known about its effects in humans. Using high spatiotemporal resolution, we mapped and quantified the neurophysiological effects of sensory flicker in human subjects undergoing presurgical intracranial seizure monitoring. We found that flicker modulates both local field potential and single neurons in higher cognitive regions, including the medial temporal lobe and prefrontal cortex, and that local field potential modulation is likely mediated via resonance of involved circuits. We then assessed how flicker affects pathological neural activity, specifically interictal epileptiform discharges, a biomarker of epilepsy also implicated in Alzheimer’s and other diseases. In our patient population with focal seizure onsets, sensory flicker decreased the rate interictal epileptiform discharges. Our findings support the use of sensory flicker to modulate deeper cortical structures and mitigate pathological activity in humans.

Passive functional mapping of receptive language cortex during general anesthesia using electrocorticography. - Nourmohammadi, Amin; Swift, James R; de Pesters, Adriana; Guay, Christian S; Adamo, Matthew A; Dalfino, John C; Ritaccio, Anthony L; Schalk, Gerwin; Brunner, Peter (Clin Neurophysiol, 2023)
OBJECTIVE: To investigate the feasibility of passive functional mapping in the receptive language cortex during general anesthesia using electrocorticographic (ECoG) signals. METHODS: We used subdurally placed ECoG grids to record cortical responses to speech stimuli during awake and anesthesia conditions. We identified the cortical areas with significant responses to the stimuli using the spectro-temporal consistency of the brain signal in the broadband gamma (BBG) frequency band (70-170 Hz). RESULTS: We found that ECoG BBG responses during general anesthesia effectively identify cortical regions associated with receptive language function. Our analyses demonstrated that the ability to identify receptive language cortex varies across different states and depths of anesthesia. We confirmed these results by comparing them to receptive language areas identified during the awake condition. Quantification of these results demonstrated an average sensitivity and specificity of passive language mapping during general anesthesia to be 49±7.7% and 100%, respectively. CONCLUSION: Our results demonstrate that mapping receptive language cortex in patients during general anesthesia is feasible. SIGNIFICANCE: Our proposed protocol could greatly expand the population of patients that can benefit from passive language mapping techniques, and could eliminate the risks associated with electrocortical stimulation during an awake craniotomy.
Keywords: Anesthesia, General; Brain; Brain Mapping; Cerebral Cortex; Electrocorticography; Humans; Language

Patients with Cognitive Impairment in Parkinson's Disease Benefit from Deep Brain Stimulation: A Case-Control Study. - Block, Cady K; Patel, Margi; Risk, Benjamin B; Staikova, Ekaterina; Loring, David; Esper, Christine D; Scorr, Laura; Higginbotham, Lenora; Aia, Pratibha; DeLong, Mahlon R; Wichmann, Thomas; Factor, Stewart A; et al. (Mov Disord Clin Pract, 2023)
BACKGROUND: Deep brain stimulation (DBS) for Parkinson's disease (PD) is generally contraindicated in persons with dementia but it is frequently performed in people with mild cognitive impairment or normal cognition, and current clinical guidelines are primarily based on these cohorts. OBJECTIVES: To determine if moderately cognitive impaired individuals including those with mild dementia could meaningfully benefit from DBS in terms of motor and non-motor outcomes. METHODS: In this retrospective case-control study, we identified a cohort of 40 patients with PD who exhibited moderate (two or more standard deviations below normative scores) cognitive impairment (CI) during presurgical workup and compared their 1-year clinical outcomes to a cohort of 40 matched patients with normal cognition (NC). The surgery targeted subthalamus, pallidus or motor thalamus, in a unilateral, bilateral or staged approach. RESULTS: At preoperative baseline, the CI cohort had higher Unified Parkinson's Disease Rating Scale (UPDRS) subscores, but similar levodopa responsiveness compared to the NC cohort. The NC and CI cohorts demonstrated comparable degrees of postoperative improvement in the OFF-medication motor scores, motor fluctuations, and medication reduction. There was no difference in adverse event rates between the two cohorts. Outcomes in the CI cohort did not depend on the target, surgical staging, or impaired cognitive domain. CONCLUSIONS: Moderately cognitively impaired patients with PD can experience meaningful motor benefit and medication reduction with DBS.

Resting state network mapping in individuals using deep learning. - Luckett, Patrick H; Lee, John J; Park, Ki Yun; Raut, Ryan V; Meeker, Karin L; Gordon, Evan M; Snyder, Abraham Z; Ances, Beau M; Leuthardt, Eric C; Shimony, Joshua S (Front Neurol, 2023)
INTRODUCTION: Resting state functional MRI (RS-fMRI) is currently used in numerous clinical and research settings. The localization of resting state networks (RSNs) has been utilized in applications ranging from group analysis of neurodegenerative diseases to individual network mapping for pre-surgical planning of tumor resections. Reproducibility of these results has been shown to require a substantial amount of high-quality data, which is not often available in clinical or research settings. METHODS: In this work, we report voxelwise mapping of a standard set of RSNs using a novel deep 3D convolutional neural network (3DCNN). The 3DCNN was trained on publicly available functional MRI data acquired in = 2010 healthy participants. After training, maps that represent the probability of a voxel belonging to a particular RSN were generated for each participant, and then used to calculate mean and standard deviation (STD) probability maps, which are made publicly available. Further, we compared our results to previously published resting state and task-based functional mappings. RESULTS: Our results indicate this method can be applied in individual subjects and is highly resistant to both noisy data and fewer RS-fMRI time points than are typically acquired. Further, our results show core regions within each network that exhibit high average probability and low STD. DISCUSSION: The 3DCNN algorithm can generate individual RSN localization maps, which are necessary for clinical applications. The similarity between 3DCNN mapping results and task-based fMRI responses supports the association of specific functional tasks with RSNs.

A somato-cognitive action network alternates with effector regions in motor cortex. - Gordon, Evan M; Chauvin, Roselyne J; Van, Andrew N; Rajesh, Aishwarya; Nielsen, Ashley; Newbold, Dillan J; Lynch, Charles J; Seider, Nicole A; Krimmel, Samuel R; Scheidter, Kristen M; Monk, Julia; Miller, Ryland L; et al. (Nature, 2023)
Motor cortex (M1) has been thought to form a continuous somatotopic homunculus extending down the precentral gyrus from foot to face representations, despite evidence for concentric functional zones and maps of complex actions. Here, using precision functional magnetic resonance imaging (fMRI) methods, we find that the classic homunculus is interrupted by regions with distinct connectivity, structure and function, alternating with effector-specific (foot, hand and mouth) areas. These inter-effector regions exhibit decreased cortical thickness and strong functional connectivity to each other, as well as to the cingulo-opercular network (CON), critical for action and physiological control, arousal, errors and pain. This interdigitation of action control-linked and motor effector regions was verified in the three largest fMRI datasets. Macaque and pediatric (newborn, infant and child) precision fMRI suggested cross-species homologues and developmental precursors of the inter-effector system. A battery of motor and action fMRI tasks documented concentric effector somatotopies, separated by the CON-linked inter-effector regions. The inter-effectors lacked movement specificity and co-activated during action planning (coordination of hands and feet) and axial body movement (such as of the abdomen or eyebrows). These results, together with previous studies demonstrating stimulation-evoked complex actions and connectivity to internal organs such as the adrenal medulla, suggest that M1 is punctuated by a system for whole-body action planning, the somato-cognitive action network (SCAN). In M1, two parallel systems intertwine, forming an integrate-isolate pattern: effector-specific regions (foot, hand and mouth) for isolating fine motor control and the SCAN for integrating goals, physiology and body movement.
Keywords: Animals; Brain Mapping; Child; Cognition; Datasets as Topic; Foot; Hand; Humans; Infant; Infant, Newborn; Macaca; Magnetic Resonance Imaging; Motor Cortex; Mouth

Subsets of cortico-cortical evoked potentials propagate as traveling waves. - Campbell, Justin M; Davis, Tyler S; Anderson, Daria Nesterovich; Arain, Amir; Inman, Cory S; Smith, Elliot H; Rolston, John D (bioRxiv, 2023)
Emerging evidence suggests that the temporal dynamics of cortico-cortical evoked potentials (CCEPs) may be used to characterize the patterns of information flow between and within brain networks. At present, however, the spatiotemporal dynamics of CCEP propagation cortically and subcortically are incompletely understood. We hypothesized that CCEPs propagate as an evoked traveling wave emanating from the site of stimulation. To elicit CCEPs, we applied single-pulse stimulation to stereoelectroencephalography (SEEG) electrodes implanted in 21 adult patients with intractable epilepsy. For each robust CCEP, we measured the timing of the maximal descent in evoked local field potentials and broadband high-gamma power (70-150 Hz) envelopes relative to the distance between the recording and stimulation contacts using three different metrics (i.e., Euclidean distance, path length, geodesic distance), representing direct, subcortical, and transcortical propagation, respectively. Many evoked responses to single-pulse electrical stimulation appear to propagate as traveling waves (âˆ½17-30%), even in the sparsely sampled, three-dimensional SEEG space. These results provide new insights into the spatiotemporal dynamics of CCEP propagation.

Towards clinical application of implantable brain-computer interfaces for people with late-stage ALS: medical and ethical considerations. - Vansteensel, Mariska J; Klein, Eran; van Thiel, Ghislaine; Gaytant, Michael; Simmons, Zachary; Wolpaw, Jonathan R; Vaughan, Theresa M (J Neurol, 2023)
Individuals with amyotrophic lateral sclerosis (ALS) frequently develop speech and communication problems in the course of their disease. Currently available augmentative and alternative communication technologies do not present a solution for many people with advanced ALS, because these devices depend on residual and reliable motor activity. Brain-computer interfaces (BCIs) use neural signals for computer control and may allow people with late-stage ALS to communicate even when conventional technology falls short. Recent years have witnessed fast progression in the development and validation of implanted BCIs, which place neural signal recording electrodes in or on the cortex. Eventual widespread clinical application of implanted BCIs as an assistive communication technology for people with ALS will have significant consequences for their daily life, as well as for the clinical management of the disease, among others because of the potential interaction between the BCI and other procedures people with ALS undergo, such as tracheostomy. This article aims to facilitate responsible real-world implementation of implanted BCIs. We review the state of the art of research on implanted BCIs for communication, as well as the medical and ethical implications of the clinical application of this technology. We conclude that the contribution of all BCI stakeholders, including clinicians of the various ALS-related disciplines, will be needed to develop procedures for, and shape the process of, the responsible clinical application of implanted BCIs.
Keywords: Amyotrophic Lateral Sclerosis; brain-computer interfaces; Electroencephalography; Humans; Self-Help Devices; Speech

Unexpected sound omissions are signaled in human posterior superior temporal gyrus: an intracranial study - Cho, H.; Fonken, Y. M.; Adamek, M.; Jimenez, R.; Lin, J. J.; Schalk, G.; Knight, R. T.; Brunner, P. (Cereb Cortex, 2023)
Context modulates sensory neural activations enhancing perceptual and behavioral performance and reducing prediction errors. However, the mechanism of when and where these high-level expectations act on sensory processing is unclear. Here, we isolate the effect of expectation absent of any auditory evoked activity by assessing the response to omitted expected sounds. Electrocorticographic signals were recorded directly from subdural electrode grids placed over the superior temporal gyrus (STG). Subjects listened to a predictable sequence of syllables, with some infrequently omitted. We found high-frequency band activity (HFA, 70-170 Hz) in response to omissions, which overlapped with a posterior subset of auditory-active electrodes in STG. Heard syllables could be distinguishable reliably from STG, but not the identity of the omitted stimulus. Both omission- and target-detection responses were also observed in the prefrontal cortex. We propose that the posterior STG is central for implementing predictions in the auditory environment. HFA omission responses in this region appear to index mismatch-signaling or salience detection processes.

Automated intraoperative central sulcus localization and somatotopic mapping using median nerve stimulation. - Xie, Tao; Wu, Zehan; Schalk, Gerwin; Tong, Yusheng; Vato, Alessandro; Raviv, Nataly; Guo, Qinglong; Ye, Huanpeng; Sheng, Xinjun; Zhu, Xiangyang; Peter Brunner; Chen, Liang (J Neural Eng, 2022)
OBJECTIVE: Accurate identiﬁcation of functional cortical regions is essential in neurological resection. The central sulcus (CS) is an important landmark that delineates functional cortical regions. Median nerve stimulation (MNS) is a standard procedure to identify the position of the CS intraoperatively. In this paper, we introduce an automated procedure that uses MNS to rapidly localize the CS and create functional somatotopic maps. APPROACH: We recorded electrocorticographic signals from 13 patients who underwent MNS in the course of an awake craniotomy. We analyzed these signals to develop an automated procedure that determines the location of the CS and that also produces functional somatotopic maps. MAIN RESULTS: The comparison between our automated method and visual inspection performed by the neurosurgeon shows that our procedure has a high sensitivity (89%) in identifying the CS. Further, we found substantial concordance between the functional somatotopic maps generated by our method and passive functional mapping (92% sensitivity). SIGNIFICANCE: Our automated MNS-based method can rapidly localize the CS and create functional somatotopic maps without imposing additional burden on the clinical procedure. With additional development and validation, our method may lead to a diagnostic tool that guides neurosurgeon and reduces postoperative morbidity in patients undergoing resective brain surgery.

Cognitive-Motor Dissociation Following Pediatric Brain Injury: What About the Children? - Kim, Nayoung; O'Sullivan, James; Olafson, Emily; Caliendo, Eric; Nowak, Sophie; Voss, Henning U; Lowder, Ryan; Watson, William D; Ivanidze, Jana; Fins, Joseph J; Schiff, Nicholas D; Hill, N Jeremy; et al. (Neurol Clin Pract, 2022)
BACKGROUND AND OBJECTIVES: Following severe brain injury, up to 16% of adults showing no clinical signs of cognitive function nonetheless have preserved cognitive capacities detectable via neuroimaging and neurophysiology; this has been designated cognitive-motor dissociation (CMD). Pediatric medicine lacks both practice guidelines for identifying covert cognition and epidemiologic data regarding CMD prevalence. METHODS: We applied a diverse battery of neuroimaging and neurophysiologic tests to evaluate 2 adolescents (aged 15 and 18 years) who had shown no clinical evidence of preserved cognitive function following brain injury at age 9 and 13 years, respectively. Clinical evaluations were consistent with minimally conscious state (minus) and vegetative state, respectively. RESULTS: Both participants' EEG, and 1 participant's fMRI, provided evidence that they could understand commands and make consistent voluntary decisions to follow them. Both participants' EEG demonstrated larger-than-expected responses to auditory stimuli and intact semantic processing of words in context. DISCUSSION: These converging lines of evidence lead us to conclude that both participants had preserved cognitive function dissociated from their motor output. Throughout the 5+ years since injury, communication attempts and therapy had remained uninformed by such objective evidence of their cognitive abilities. Proper diagnosis of CMD is an ethical imperative. Children with covert cognition reflect a vulnerable and isolated population; the methods outlined here provide a first step in identifying such persons to advance efforts to alleviate their condition.

Dynamics of Oddball Sound Processing: Trial-by-Trial Modeling of ECoG Signals. - Lecaignard, Françoise; Bertrand, Raphaëlle; Peter Brunner; Caclin, Anne; Schalk, Gerwin; Mattout, Jérémie (Front Hum Neurosci, 2022)
Recent computational models of perception conceptualize auditory oddball responses as signatures of a (Bayesian) learning process, in line with the influential view of the mismatch negativity (MMN) as a prediction error signal. Novel MMN experimental paradigms have put an emphasis on neurophysiological effects of manipulating regularity and predictability in sound sequences. This raises the question of the contextual adaptation of the learning process itself, which on the computational side speaks to the mechanisms of gain-modulated (or precision-weighted) prediction error. In this study using electrocorticographic (ECoG) signals, we manipulated the predictability of oddball sound sequences with two objectives: (i) Uncovering the computational process underlying trial-by-trial variations of the cortical responses. The fluctuations between trials, generally ignored by approaches based on averaged evoked responses, should reflect the learning involved. We used a general linear model (GLM) and Bayesian Model Reduction (BMR) to assess the respective contributions of experimental manipulations and learning mechanisms under probabilistic assumptions. (ii) To validate and expand on previous findings regarding the effect of changes in predictability using simultaneous EEG-MEG recordings. Our trial-by-trial analysis revealed only a few stimulus-responsive sensors but the measured effects appear to be consistent over subjects in both time and space. In time, they occur at the typical latency of the MMN (between 100 and 250 ms post-stimulus). In space, we found a dissociation between time-independent effects in more anterior temporal locations and time-dependent (learning) effects in more posterior locations. However, we could not observe any clear and reliable effect of our manipulation of predictability modulation onto the above learning process. Overall, these findings clearly demonstrate the potential of trial-to-trial modeling to unravel perceptual learning processes and their neurophysiological counterparts.

The Evoked Potential Operant Conditioning System (EPOCS): A Research Tool and an Emerging Therapy for Chronic Neuromuscular Disorders. - Hill, N Jeremy; Gupta, Disha; Eftekhar, Amir; Brangaccio, Jodi A; Norton, James J S; McLeod, Michelle; Fake, Tim; Wolpaw, Jonathan R; Thompson, Aiko K (J Vis Exp, 2022)
The Evoked Potential Operant Conditioning System (EPOCS) is a software tool that implements protocols for operantly conditioning stimulus-triggered muscle responses in people with neuromuscular disorders, which in turn can improve sensorimotor function when applied appropriately. EPOCS monitors the state of specific target muscles-e.g., from surface electromyography (EMG) while standing, or from gait cycle measurements while walking on a treadmill-and automatically triggers calibrated stimulation when pre-defined conditions are met. It provides two forms of feedback that enable a person to learn to modulate the targeted pathway's excitability. First, it continuously monitors ongoing EMG activity in the target muscle, guiding the person to produce a consistent level of activity suitable for conditioning. Second, it provides immediate feedback of the response size following each stimulation and indicates whether it has reached the target value. To illustrate its use, this article describes a protocol through which a person can learn to decrease the size of the Hoffmann reflex-the electrically-elicited analog of the spinal stretch reflex-in the soleus muscle. Down-conditioning this pathway's excitability can improve walking in people with spastic gait due to incomplete spinal cord injury. The article demonstrates how to set up the equipment; how to place stimulating and recording electrodes; and how to use the free software to optimize electrode placement, measure the recruitment curve of direct motor and reflex responses, measure the response without operant conditioning, condition the reflex, and analyze the resulting data. It illustrates how the reflex changes over multiple sessions and how walking improves. It also discusses how the system can be applied to other kinds of evoked responses and to other kinds of stimulation, e.g., motor evoked potentials to transcranial magnetic stimulation; how it can address various clinical problems; and how it can support research studies of sensorimotor function in health and disease.
Keywords: Chronic Disease; Conditioning, Operant; Electromyography; Evoked Potentials; H-Reflex; Humans; Neuromuscular Diseases; Spinal Cord Injuries

Heksor: the central nervous system substrate of an adaptive behaviour. - Wolpaw, Jonathan R; Kamesar, Adam (J Physiol, 2022)
Over the past half-century, the largely hardwired central nervous system (CNS) of 1970 has become the ubiquitously plastic CNS of today, in which change is the rule not the exception. This transformation complicates a central question in neuroscience: how are adaptive behaviours - behaviours that serve the needs of the individual - acquired and maintained through life? It poses a more basic question: how do many adaptive behaviours share the ubiquitously plastic CNS? This question compels neuroscience to adopt a new paradigm. The core of this paradigm is a CNS entity with unique properties, here given the name heksor from the Greek hexis. A heksor is a distributed network of neurons and synapses that changes itself as needed to maintain the key features of an adaptive behaviour, the features that make the behaviour satisfactory. Through their concurrent changes, the numerous heksors that share the CNS negotiate the properties of the neurons and synapses that they all use. Heksors keep the CNS in a state of negotiated equilibrium that enables each heksor to maintain the key features of its behaviour. The new paradigm based on heksors and the negotiated equilibrium they create is supported by animal and human studies of interactions among new and old adaptive behaviours, explains otherwise inexplicable results, and underlies promising new approaches to restoring behaviours impaired by injury or disease. Furthermore, the paradigm offers new and potentially important answers to extant questions, such as the generation and function of spontaneous neuronal activity, the aetiology of muscle synergies, and the control of homeostatic plasticity.
Keywords: Adaptation, Psychological; Animals; central nervous system; Humans; Neuronal Plasticity; Plastics; Synapses

Neural oscillations during motor imagery of complex gait: an HdEEG study. - Putzolu, Martina; Samogin, Jessica; Cosentino, Carola; Mezzarobba, Susanna; Bonassi, Gaia; Lagravinese, Giovanna; Vato, Alessandro; Mantini, Dante; Avanzino, Laura; Pelosin, Elisa (Sci Rep, 2022)
The aim of this study was to investigate differences between usual and complex gait motor imagery (MI) task in healthy subjects using high-density electroencephalography (hdEEG) with a MI protocol. We characterized the spatial distribution of α- and β-bands oscillations extracted from hdEEG signals recorded during MI of usual walking (UW) and walking by avoiding an obstacle (Dual-Task, DT). We applied a source localization algorithm to brain regions selected from a large cortical-subcortical network, and then we analyzed α and β bands Event-Related Desynchronizations (ERDs). Nineteen healthy subjects visually imagined walking on a path with (DT) and without (UW) obstacles. Results showed in both gait MI tasks, α- and β-band ERDs in a large cortical-subcortical network encompassing mostly frontal and parietal regions. In most of the regions, we found α- and β-band ERDs in the DT compared with the UW condition. Finally, in the β band, significant correlations emerged between ERDs and scores in imagery ability tests. Overall we detected MI gait-related α- and β-band oscillations in cortical and subcortical areas and significant differences between UW and DT MI conditions. A better understanding of gait neural correlates may lead to a better knowledge of pathophysiology of gait disturbances in neurological diseases.
Keywords: Brain; Electroencephalography; Gait; Humans; Imagery, Psychotherapy; Imagination; Walking

A neural population selective for song in human auditory cortex - Sam V. Norman-Haignere; Jenelle Feather; Dana Boebinger; Peter Brunner; Anthony Ritaccio; Josh H. McDermott; Gerwin Schalk; Nancy Kanwisher (Current Biology, 2022)
Summary How is music represented in the brain? While neuroimaging has revealed some spatial segregation between responses to music versus other sounds, little is known about the neural code for music itself. To address this question, we developed a method to infer canonical response components of human auditory cortex using intracranial responses to natural sounds, and further used the superior coverage of fMRI to map their spatial distribution. The inferred components replicated many prior findings, including distinct neural selectivity for speech and music, but also revealed a novel component that responded nearly exclusively to music with singing. Song selectivity was not explainable by standard acoustic features, was located near speech- and music-selective responses, and was also evident in individual electrodes. These results suggest that representations of music are fractionated into subpopulations selective for different types of music, one of which is specialized for the analysis of song.
Keywords: Auditory Cortex; component; ECoG; Electrocorticography; fMRI; music; natural sounds; song; Speech; voice

Objective Neurophysiologic Markers of Cognition After Pediatric Brain Injury. - Kim, Nayoung; Watson, William; Caliendo, Eric; Nowak, Sophie; Schiff, Nicholas D; Shah, Sudhin A; Hill, N Jeremy (Neurol Clin Pract, 2022)
BACKGROUND AND OBJECTIVES: Following brain injury, clinical assessments of residual and emerging cognitive function are difficult and fraught with errors. In adults, recent American Academy of Neurology (AAN) practice guidelines recommend objective neuroimaging and neurophysiologic measures to support diagnosis. Equivalent measures are lacking in pediatrics-an especially great challenge due to the combined heterogeneity of both brain injury and pediatric development. Therefore, we aim to establish quantitative, clinically practicable measures of cognitive function following pediatric brain injury. METHODS: Participants with and without brain injury were aged 8-18 years, clinically classified according to cognitive recovery state: N = 8 in disorders of consciousness (DoC), N = 7 in confusional state, N = 19 cognitively impaired, and N = 13 typically developing uninjured controls. We prospectively measured electroencephalographic markers of sensory processing and attention in an auditory oddball paradigm, and of covert movement attempts in a command-following paradigm. RESULTS: In 3 participants with DoC, EEG markers of active attempted command following revealed cognitive function that clinical assessment had failed to detect. These same 3 individuals could also be distinguished from the rest of their group by 2 event-related potentials that correlate with sensory processing and orienting attention in the oddball paradigm. Considered across the whole participant group, magnitudes of these 2 ERP markers significantly increased as cognitive recovery progressed (ANOVA: each < 0.001); viewed jointly, the 2 ERP markers cleanly delineated the 4 cognitive states. DISCUSSION: Despite heterogeneity of brain injuries and brain development, our objective EEG markers reflected cognitive recovery independent of motor function. Two of these markers required no active participation. Together, they allowed us to identify 3 individuals who meet the criteria for cognitive-motor dissociation. To diagnose, prognose, and track cognitive recovery accurately, such markers should be used in pediatrics.

Operant down-conditioning of the soleus H-reflex in people after stroke. - Thompson, Aiko K; Gill, Christina R; Feng, Wuwei; Segal, Richard L (Front Rehabil Sci, 2022)
Through operant conditioning, spinal reflex behaviors can be changed. Previous studies in rats indicate that the sensorimotor cortex and corticospinal tract are essential in inducing and maintaining reflex changes induced through conditioning. In people with incomplete spinal cord injury (SCI), an operant down-conditioning protocol decreased the soleus H-reflex size and improved walking speed and symmetry, suggesting that a partially preserved spinal cord can support conditioning-induced plasticity and benefit from it. This study examined whether down-conditioning can decrease the soleus H-reflex in people with supraspinal injury (i.e., cortical or subcortical stroke). Operant down-conditioning was applied to the soleus H-reflex in a cohort of 12 stroke people with chronic spastic hemiparesis (>12 months from stroke onset of symptoms). Each participant completed 6 baseline and 30 conditioning sessions over 12 weeks. In each baseline session, 225 control H-reflexes were elicited without any feedback on H-reflex size. In each conditioning session, 225 conditioned H-reflexes were elicited while the participant was asked to decrease H-reflex size and was given visual feedback as to whether the resulting H-reflex was smaller than a criterion value. In six of 12 participants, the conditioned H-reflex became significantly smaller by 30% on average, whereas in other 6 participants, it did not. The difference between the subgroups was largely attributable to the difference in across-session control reflex change. Ten-meter walking speed was increased by various extent (+0.04 to +0.35, +0.14 m/s on average) among the six participants whose H-reflex decreased, whereas the change was 0.00 m/s on average for the rest of participants. Although less than what was seen in participants with SCI, the fact that conditioning succeeded in 50% of stroke participants supports the feasibility of reflex down-conditioning in people after stroke. At the same time, the difference in across-session control reflex change and conditioning success rate may reflect a critical role of supraspinal activity in producing long-term plasticity in the spinal cord, as previous animal studies suggested.

Soleus H-reflex modulation during a double-legged drop landing task. - Lyle, Mark A; McLeod, Michelle M; Pouliot, Bridgette A; Thompson, Aiko K (Exp Brain Res, 2022)
Muscle spindle afferent feedback is modulated during different phases of locomotor tasks in a way that facilitates task goals. However, only a few studies have studied H-reflex modulation during landing. This study aimed to characterize soleus (SOL) H-reflex modulation during the flight and early landing period of drop landings. Since landing presumably involves a massive increase in spindle afferent firing due to rapid SOL muscle stretching, we hypothesized H-reflex size would decrease near landing reflecting neural modulation to prevent excessive motoneuron excitation. The soleus H-reflex was recorded during drop landings from a 30 cm height in nine healthy adults. Electromyography (SOL, tibialis anterior (TA), medial gastrocnemius, and vastus lateralis), ankle and knee joint motion and ground reaction force were recorded during landings. Tibial nerve stimulation was timed to elicit H-reflexes during the flight and early ground contact period (five 30 ms Bins from 90 ms before to 60 ms after landing). The H-reflexes recorded after landing (0-30 and 30-60 ms) were significantly smaller (21-36% less) than that recorded during the flight periods (90-0 ms before ground contact; P ≤ 0.004). The decrease in H-reflex size not occurring until after ground contact indicates a time-critical modulation of reflex gain during the last 30 ms of flight (i.e., time of tibial nerve stimulation). H-reflex size reduction after ground contact supports a probable neural strategy to prevent excessive reflex-mediated muscle activation and thereby facilitates appropriate musculotendon and joint stiffness.
Keywords: Adult; Ankle Joint; Electromyography; H-Reflex; Humans; Muscle Spindles; Muscle, Skeletal

Toward a fully implantable ecosystem for adaptive neuromodulation in humans: Preliminary experience with the CorTec BrainInterchange device in a canine model. - Schalk, Gerwin; Worrell, Samuel; Mivalt, Filip; Belsten, Alexander; Kim, Inyong; Morris, Jonathan M; Hermes, Dora; Klassen, Bryan T; Staff, Nathan P; Messina, Steven; Kaufmann, Timothy; Rickert, Jörn; et al. (Front Neurosci, 2022)
This article describes initial work toward an ecosystem for adaptive neuromodulation in humans by documenting the experience of implanting CorTec's BrainInterchange (BIC) device in a beagle canine and using the BCI2000 environment to interact with the BIC device. It begins with laying out the substantial opportunity presented by a useful, easy-to-use, and widely available hardware/software ecosystem in the current landscape of the field of adaptive neuromodulation, and then describes experience with implantation, software integration, and post-surgical validation of recording of brain signals and implant parameters. Initial experience suggests that the hardware capabilities of the BIC device are fully supported by BCI2000, and that the BIC/BCI2000 device can record and process brain signals during free behavior. With further development and validation, the BIC/BCI2000 ecosystem could become an important tool for research into new adaptive neuromodulation protocols in humans.

Workshops of the Eighth International Brain-Computer Interface Meeting: BCIs: The Next Frontier. - Huggins, Jane E; Krusienski, Dean; Vansteensel, Mariska J; Valeriani, Davide; Thelen, Antonia; Stavisky, Sergey; Norton, James J S; Nijholt, Anton; Müller-Putz, Gernot; Kosmyna, Nataliya; Korczowski, Louis; Kapeller, Christoph; et al. (Brain Comput Interfaces (Abingdon), 2022)
The Eighth International Brain-Computer Interface (BCI) Meeting was held June 7-9th, 2021 in a virtual format. The conference continued the BCI Meeting series' interactive nature with 21 workshops covering topics in BCI (also called brain-machine interface) research. As in the past, workshops covered the breadth of topics in BCI. Some workshops provided detailed examinations of specific methods, hardware, or processes. Others focused on specific BCI applications or user groups. Several workshops continued consensus building efforts designed to create BCI standards and increase the ease of comparisons between studies and the potential for meta-analysis and large multi-site clinical trials. Ethical and translational considerations were both the primary topic for some workshops or an important secondary consideration for others. The range of BCI applications continues to expand, with more workshops focusing on approaches that can extend beyond the needs of those with physical impairments. This paper summarizes each workshop, provides background information and references for further study, presents an overview of the discussion topics, and describes the conclusion, challenges, or initiatives that resulted from the interactions and discussion at the workshop.

audiomath: A neuroscientist's sound toolkit. - Hill, N Jeremy; Mooney, Scott W J; Prusky, Glen T (Heliyon, 2021)
In neuroscientific experiments and applications, working with auditory stimuli demands software tools for generation and acquisition of raw audio, for composition and tailoring of that material into finished stimuli, for precisely timed presentation of the stimuli, and for experimental session recording. Numerous programming tools exist to approach these tasks, but their differing specializations and conventions demand extra time and effort for integration. In particular, verifying stimulus timing requires extensive engineering effort when developing new applications. This paper has two purposes. The first is to present (https://pypi.org/project/audiomath), a sound software library for Python that prioritizes the needs of neuroscientists. It minimizes programming effort by providing a simple object-oriented interface that unifies functionality for audio generation, manipulation, visualization, decoding, encoding, recording, and playback. It also incorporates specialized tools for measuring and optimizing stimulus timing. The second purpose is to relay what we have learned, during development and application of the software, about the twin challenges of delivering stimuli precisely at a certain time, and of precisely measuring the time at which stimuli were delivered. We provide a primer on these problems and the possible approaches to them. We then report audio latency measurements across a range of hardware, operating systems and settings, to illustrate the ways in which hardware and software factors interact to affect stimulus presentation performance, and the resulting pitfalls for the programmer and experimenter. In particular, we highlight the potential conflict between demands for low latency, low variability in latency ("jitter"), cooperativeness, and robustness. We report the ways in which can help to map this territory and provide a simplified path toward each application's particular priority. By unifying audio-related functionality and providing specialized diagnostic tools, both simplifies and potentiates the development of neuroscientific applications in Python.

Brain-computer interface-based assessment of color vision. - Norton, James J S; DiRisio, Grace F; Carp, Jonathan S; Norton, Amanda E; Kochan, Nicholas S; Wolpaw, Jonathan R (J Neural Eng, 2021)
Present methods for assessing color vision require the person's active participation. Here we describe a brain-computer interface-based method for assessing color vision that does not require the person's participation.This method uses steady-state visual evoked potentials to identify metamers-two light sources that have different spectral distributions but appear to the person to be the same color.We demonstrate that: minimization of the visual evoked potential elicited by two flickering light sources identifies the metamer; this approach can distinguish people with color-vision deficits from those with normal color vision; and this metamer-identification process can be automated.This new method has numerous potential clinical, scientific, and industrial applications.
Keywords: brain-computer interfaces; Color Vision; Electroencephalography; Evoked Potentials, Visual; Humans; Light; Photic Stimulation; Research Design

Modulation in cortical excitability disrupts information transfer in perceptual-level stimulus processing. - Moheimanian, Ladan; Paraskevopoulou, Sivylla E; Adamek, Markus; Schalk, Gerwin; Peter Brunner (Neuroimage, 2021)
Despite significant interest in the neural underpinnings of behavioral variability, little light has been shed on the cortical mechanism underlying the failure to respond to perceptual-level stimuli. We hypothesized that cortical activity resulting from perceptual-level stimuli is sensitive to the moment-to-moment fluctuations in cortical excitability, and thus may not suffice to produce a behavioral response. We tested this hypothesis using electrocorticographic recordings to follow the propagation of cortical activity in six human subjects that responded to perceptual-level auditory stimuli. Here we show that for presentations that did not result in a behavioral response, the likelihood of cortical activity decreased from auditory cortex to motor cortex, and was related to reduced local cortical excitability. Cortical excitability was quantified using instantaneous voltage during a short window prior to cortical activity onset. Therefore, when humans are presented with an auditory stimulus close to perceptual-level threshold, moment-by-moment fluctuations in cortical excitability determine whether cortical responses to sensory stimulation successfully connect auditory input to a resultant behavioral response.
Keywords: Acoustic Stimulation; Adult; Aged; Alpha Rhythm; Auditory Cortex; Brain Mapping; Cortical Excitability; Electrocorticography; Female; Humans; Male; Middle Aged

Recommendations for Responsible Development and Application of Neurotechnologies. - Goering, Sara; Klein, Eran; Specker Sullivan, Laura; Wexler, Anna; Agüera Y Arcas, Blaise; Bi, Guoqiang; Carmena, Jose M; Fins, Joseph J; Friesen, Phoebe; Gallant, Jack; Huggins, Jane E; Kellmeyer, Philipp; et al. (Neuroethics, 2021)
Advancements in novel neurotechnologies, such as brain computer interfaces (BCI) and neuromodulatory devices such as deep brain stimulators (DBS), will have profound implications for society and human rights. While these technologies are improving the diagnosis and treatment of mental and neurological diseases, they can also alter individual agency and estrange those using neurotechnologies from their sense of self, challenging basic notions of what it means to be human. As an international coalition of interdisciplinary scholars and practitioners, we examine these challenges and make recommendations to mitigate negative consequences that could arise from the unregulated development or application of novel neurotechnologies. We explore potential ethical challenges in four key areas: identity and agency, privacy, bias, and enhancement. To address them, we propose (1) democratic and inclusive summits to establish globally-coordinated ethical and societal guidelines for neurotechnology development and application, (2) new measures, including "Neurorights," for data privacy, security, and consent to empower neurotechnology users' control over their data, (3) new methods of identifying and preventing bias, and (4) the adoption of public guidelines for safe and equitable distribution of neurotechnological devices.

A Voting-Enhanced Dynamic-Window-Length Classifier for SSVEP-Based BCIs. - Habibzadeh, Hadi; Norton, James J S; Vaughan, Theresa M; Soyata, Tolga; Zois, Daphney-Stavroula (IEEE Trans Neural Syst Rehabil Eng, 2021)
We present a dynamic window-length classifier for steady-state visual evoked potential (SSVEP)-based brain-computer interfaces (BCIs) that does not require the user to choose a feature extraction method or channel set. Instead, the classifier uses multiple feature extraction methods and channel selections to infer the SSVEP and relies on majority voting to pick the most likely target. The classifier extends the window length dynamically if no target obtains the majority of votes. Compared with existing solutions, our classifier: (i) does not assume that any single feature extraction method will consistently outperform the others; (ii) adapts the channel selection to individual users or tasks; (iii) uses dynamic window lengths; (iv) is unsupervised (i.e., does not need training). Collectively, these characteristics make the classifier easy-to-use, especially for caregivers and others with limited technical expertise. We evaluated the performance of our classifier on a publicly available benchmark dataset from 35 healthy participants. We compared the information transfer rate (ITR) of this new classifier to those of the minimum energy combination (MEC), maximum synchronization index (MSI), and filter bank canonical correlation analysis (FBCCA). The new classifier increases average ITR to 123.5 bits-per-minute (bpm), 47.5, 51.2, and 19.5 bpm greater than the MEC, MSI, and FBCCA classifiers, respectively.
Keywords: Algorithms; brain-computer interfaces; Electroencephalography; Evoked Potentials, Visual; Humans; Photic Stimulation

Within-subject reaction time variability: Role of cortical networks and underlying neurophysiological mechanisms. - Paraskevopoulou, Sivylla E; Coon, William G; Peter Brunner; Miller, Kai J; Schalk, Gerwin (Neuroimage, 2021)
Variations in reaction time are a ubiquitous characteristic of human behavior. Extensively documented, they have been successfully modeled using parameters of the subject or the task, but the neural basis of behavioral reaction time that varies within the same subject and the same task has been minimally studied. In this paper, we investigate behavioral reaction time variance using 28 datasets of direct cortical recordings in humans who engaged in four different types of simple sensory-motor reaction time tasks. Using a previously described technique that can identify the onset of population-level cortical activity and a novel functional connectivity algorithm described herein, we show that the cumulative latency difference of population-level neural activity across the task-related cortical network can explain up to 41% of the trial-by-trial variance in reaction time. Furthermore, we show that reaction time variance may primarily be due to the latencies in specific brain regions and demonstrate that behavioral latency variance is accumulated across the whole task-related cortical network. Our results suggest that population-level neural activity monotonically increases prior to movement execution, and that trial-by-trial changes in that increase are, in part, accounted for by inhibitory activity indexed by low-frequency oscillations. This pre-movement neural activity explains 19% of the measured variance in neural latencies in our data. Thus, our study provides a mechanistic explanation for a sizable fraction of behavioral reaction time when the subject's task is the same from trial to trial.
Keywords: Adult; Algorithms; Alpha Rhythm; Cerebral Cortex; Connectome; Electrocorticography; Female; Gamma Rhythm; Humans; Male; Middle Aged; Nerve Net; Psychomotor Performance; Reaction Time; Young Adult

BCI-based sensorimotor rhythm training can affect individuated finger movements - D.J. McFarland; S.L. Norman; W.A. Sarnacki; E.T. Wolbrecht; D.J. Reinkensmeyer; J.R. Wolpaw (Brain Computer Interface Society, 2020)
Brain-computer interface (BCI) technology can restore communication and control to people who are severely paralyzed. BCI technology might also be able to enhance rehabilitation of motor function. We have previously shown that pre-movement sensorimotor rhythm (SMR) amplitude affects reaction time and performance on a joystick-based cursor movement task. The present study explores in adults without motor impairment the possibility that pre-movement SMR amplitude affects performance of individuated finger movements. In Phase 1, 8 individuals performed a finger flexion task that was monitored by an exoskeleton. During a 1-sec preparatory period, two colored targets on a video monitor cued flexion of the index finger, middle finger, both fingers, or neither finger; sudden color change then triggered the movement (or non-movement). SMR features (i.e. EEG amplitudes in specific frequency bands at specific scalp locations) in the pre-movement EEG that correlated with movement versus no movement were identified. In Phase 2, the participants learned to increase or decrease these SMR features to control a two-target BCI task. Finally, in Phase 3, they were asked to increase or decrease the SMR features to initiate the finger flexion task of Phase 1 and the impact on finger flexion performance was assessed. After BCI training, pre-movement SMR feature amplitude affected performance in a subset of individuals: lower amplitude was associated with shorter movement onset. In a subset of individuals, the beneficial effect on performance of lower SMR amplitude was greater when both fingers were flexed than when one was flexed and the other remained extended; thus, the impact of SMR amplitude modulation depended on the specificity of the subsequent motor task. These results indicate that BCI-based training of SMR activity in the pre-movement preparatory period can affect finger movements in a subset of individuals. They encourage studies that integrate such training into rehabilitation protocols and examine its capacity to enhance restoration of useful hand function.
Keywords: BCI; movement preparation; Rehabilitation; Robotics; sensorimotor beta rhythms

Brain-computer interfaces: Definitions and principles - J.R. Wolpaw; José del R. Millán; N.F. Ramsey (Handbook of Clinical Neurology, 2020)
Throughout life, the central nervous system (CNS) interacts with the world and with the body by activating muscles and excreting hormones. In contrast, brain-computer interfaces (BCIs) quantify CNS activity and translate it into new artificial outputs that replace, restore, enhance, supplement, or improve the natural CNS outputs. BCIs thereby modify the interactions between the CNS and the environment. Unlike the natural CNS outputs that come from spinal and brainstem motoneurons, BCI outputs come from brain signals that represent activity in other CNS areas, such as the sensorimotor cortex. If BCIs are to be useful for important communication and control tasks in real life, the CNS must control these brain signals nearly as reliably and accurately as it controls spinal motoneurons. To do this, they might, for example, need to incorporate software that mimics the function of the subcortical and spinal mechanisms that participate in normal movement control. The realization of high reliability and accuracy is perhaps the most difficult and critical challenge now facing BCI research and development. The ongoing adaptive modifications that maintain effective natural CNS outputs take place primarily in the CNS. The adaptive modifications that maintain effective BCI outputs can also take place in the BCI. This means that the BCI operation depends on the effective collaboration of two adaptive controllers, the CNS and the BCI. Realization of this second adaptive controller, the BCI, and management of its interactions with concurrent adaptations in the CNS comprise another complex and critical challenge for BCI development. BCIs can use different kinds of brain signals recorded in different ways from different brain areas. Decisions about which signals recorded in which ways from which brain areas should be selected for which applications are empirical questions that can only be properly answered by experiments. BCIs, like other communication and control technologies, often face artifacts that contaminate or imitate their chosen signals. Noninvasive BCIs (e.g., EEG- or fNIRS-based) need to take special care to avoid interpreting nonbrain signals (e.g., cranial EMG) as brain signals. This typically requires comprehensive topographical and spectral evaluations. In theory, the outputs of BCIs can select a goal or control a process. In the future, the most effective BCIs will probably be those that combine goal selection and process control so as to distribute control between the BCI and the application in a fashion suited to the current action. Through such distribution, BCIs may most effectively imitate natural CNS operation. The primary measure of BCI development is the extent to which BCI systems benefit people with neuromuscular disorders. Thus, BCI clinical evaluation, validation, and dissemination is a key step. It is at the same time a complex and difficult process that depends on multidisciplinary collaboration and management of the demanding requirements of clinical studies. Twenty-five years ago, BCI research was an esoteric endeavor pursued in only a few isolated laboratories. It is now a steadily growing field that engages many hundreds of scientists, engineers, and clinicians throughout the world in an increasingly interconnected community that is addressing the key issues and pursuing the high potential of BCI technology.
Keywords: BCI; BMI; brain-computer interface; brain–machine interface

Brain-computer interfaces for people with amyotrophic lateral sclerosis - T. Vaughan (Handbook of Clinical Neurology, 2020)
A brain-computer interface (BCI) records and extracts features from brain signals, and translates these features into commands that can replace, restore, enhance, supplement, or improve natural CNS outputs. As demonstrated in the other chapters of this book, the focus of the work of the last three decades of BCI research has been the replacement, restoration, or improvement of diminished or lost function in people with CNS disease or injury including those with amyotrophic lateral sclerosis (ALS). Due in part to the desire to conduct controlled studies, and, in part, to the complexity of BCI technology, most of this work has been carried out in laboratories with healthy controls or with limited numbers of potential consumers with a variety of diagnoses under supervised conditions. The intention of this chapter is to describe the growing body of BCI research that has included people with amyotrophic lateral sclerosis (ALS). People in the late stages of ALS can lose all voluntary control, including the ability to communicate; and while recent research has provided new insights into underlying mechanisms, ALS remains a disease with no cure. As a result, people with ALS and their families, caregivers, and advocates have an active interest in both the current and potential capabilities of BCI technology. The focus of BCI research for people with ALS is on communication, and this topic is well covered elsewhere in this volume. This chapter focuses on the efforts dedicated to make BCI technology useful to people with ALS in their daily lives with a discussion of how researchers, clinicians, and patients must become partners in that process.
Keywords: Amyotrophic Lateral Sclerosis; Augmentative and alternative communication; Electroencephalography

Breathable, large-area epidermal electronic systems for recording electromyographic activity during operant conditioning of H-reflex. - Kwon, Young-Tae; Norton, James J S; Cutrone, Andrew; Lim, Hyo-Ryoung; Kwon, Shinjae; Choi, Jeongmoon J; Kim, Hee Seok; Jang, Young C; Wolpaw, Jonathan R; Yeo, Woon-Hong (Biosens Bioelectron, 2020)
Operant conditioning of Hoffmann's reflex (H-reflex) is a non-invasive and targeted therapeutic intervention for patients with movement disorders following spinal cord injury. The reflex-conditioning protocol uses electromyography (EMG) to measure reflexes from specific muscles elicited using transcutaneous electrical stimulation. Despite recent advances in wearable electronics, existing EMG systems that measure muscle activity for operant conditioning of spinal reflexes still use rigid metal electrodes with conductive gels and aggressive adhesives, while requiring precise positioning to ensure reliability of data across experimental sessions. Here, we present the first large-area epidermal electronic system (L-EES) and demonstrate its use in every step of the reflex-conditioning protocol. The L-EES is a stretchable and breathable composite of nanomembrane electrodes (16 electrodes in a four by four array), elastomer, and fabric. The nanomembrane electrode array enables EMG recording from a large surface area on the skin and the breathable elastomer with fabric is biocompatible and comfortable for patients. We show that L-EES can record direct muscle responses (M-waves) and H-reflexes, both of which are comparable to those recorded using conventional EMG recording systems. In addition, L-EES may improve the reflex-conditioning protocol; it has potential to automatically optimize EMG electrode positioning, which may reduce setup time and error across experimental sessions.
Keywords: Biosensing Techniques; Conditioning, Operant; Electronics; H-Reflex; Humans; Reproducibility of Results

Can Operant Conditioning of EMG-Evoked Responses Help to Target Corticospinal Plasticity for Improving Motor Function in People With Multiple Sclerosis? - Thompson, Aiko K; Sinkjær, Thomas (Front Neurol, 2020)
Corticospinal pathway and its function are essential in motor control and motor rehabilitation. Multiple sclerosis (MS) causes damage to the brain and descending connections, and often diminishes corticospinal function. In people with MS, neural plasticity is available, although it does not necessarily remain stable over the course of disease progress. Thus, inducing plasticity to the corticospinal pathway so as to improve its function may lead to motor control improvements, which impact one's mobility, health, and wellness. In order to harness plasticity in people with MS, over the past two decades, non-invasive brain stimulation techniques have been examined for addressing common symptoms, such as cognitive deficits, fatigue, and spasticity. While these methods appear promising, when it comes to motor rehabilitation, just inducing plasticity or having a capacity for it does not guarantee generation of better motor functions. Targeting plasticity to a key pathway, such as the corticospinal pathway, could change what limits one's motor control and improve function. One of such neural training methods is operant conditioning of the motor-evoked potential that aims to train the behavior of the corticospinal-motoneuron pathway. Through up-conditioning training, the person learns to produce the rewarded neuronal behavior/state of increased corticospinal excitability, and through iterative training, the rewarded behavior/state becomes one's habitual, daily motor behavior. This minireview introduces operant conditioning approach for people with MS. Guiding beneficial CNS plasticity on top of continuous disease progress may help to prolong the duration of maintained motor function and quality of life in people living with MS.

Enhancing Communication for People in Late-Stage ALS Using an fNIRS-Based BCI System. - Borgheai, Seyyed Bahram; McLinden, John; Zisk, Alyssa Hillary; Hosni, Sarah Ismail; Deligani, Roohollah Jafari; Abtahi, Mohammadreza; Mankodiya, Kunal; Shahriari, Yalda (IEEE Trans Neural Syst Rehabil Eng, 2020)
OBJECTIVE: Brain-computer interface (BCI) based communication remains a challenge for people with later-stage amyotrophic lateral sclerosis (ALS) who lose all voluntary muscle control. Although recent studies have demonstrated the feasibility of functional near-infrared spectroscopy (fNIRS) to successfully control BCIs primarily for healthy cohorts, these systems are yet inefficient for people with severe motor disabilities like ALS. In this study, we developed a new fNIRS-based BCI system in concert with a single-trial Visuo-Mental (VM) paradigm to investigate the feasibility of enhanced communication for ALS patients, particularly those in the later stages of the disease. METHODS: In the first part of the study, we recorded data from six ALS patients using our proposed protocol (fNIRS-VM) and compared the results with the conventional electroencephalography (EEG)-based multi-trial P3Speller (P3S). In the second part, we recorded longitudinal data from one patient in the late locked-in state (LIS) who had fully lost eye-gaze control. Using statistical parametric mapping (SPM) and correlation analysis, the optimal channels and hemodynamic features were selected and used in linear discriminant analysis (LDA). RESULTS: Over all the subjects, we obtained an average accuracy of 81.3%±5.7% within comparatively short times (< 4 sec) in the fNIRS-VM protocol relative to an average accuracy of 74.0%±8.9% in the P3S, though not competitive in patients with no substantial visual problems. Our longitudinal analysis showed substantially superior accuracy using the proposed fNIRS-VM protocol (73.2%±2.0%) over the P3S (61.8%±1.5%). SIGNIFICANCE: Our findings indicate the potential efficacy of our proposed system for communication and control for late-stage ALS patients.
Keywords: Amyotrophic Lateral Sclerosis; brain-computer interfaces; Communication; Electroencephalography; Humans; Spectroscopy, Near-Infrared

Operant Condition of the Flexor Carpi Radialis H-reflex - J Norton; T Vaughan; D Gemoets; S Heckman; S.D. Toliou; J Carp; J.R. Wolpaw (Archives of Physical Medicine and Rehabilitation, 2020)
Operant conditioning of the largely monosynaptic H-reflex is a targeted and non-invasive therapeutic intervention for people with motor dysfunction after spinal cord injury and possibly stroke.1,2,3 It can complement other therapies and has no known adverse side effects. To date, H-reflex operant conditioning has focused on the leg. Here, we extend it to the arm by asking participants to either increase or decrease the flexor carpi radialis (FCR) H-reflex. In addition, we examine concurrent changes in brain activity by recording electroencephalographic activity (EEG).
Keywords: BCI; FCR; H-Reflex; operant conditioning; Rehabilitation

Potential differences between monolingual and bilingual patients in approach and outcome after awake brain surgery. - ReFaey, Karim; Tripathi, Shashwat; Bhargav, Adip G; Grewal, Sanjeet S; Middlebrooks, Erik H; Sabsevitz, David S; Jentoft, Mark; Peter Brunner; Wu, Adela; Tatum, William O; Ritaccio, Anthony; Chaichana, Kaisorn L; et al. (J Neurooncol, 2020)
INTRODUCTION: 20.8% of the United States population and 67% of the European population speak two or more languages. Intraoperative different languages, mapping, and localization are crucial. This investigation aims to address three questions between BL and ML patients: (1) Are there differences in complications (i.e. seizures) and DECS techniques during intra-operative brain mapping? (2) Is EOR different? and (3) Are there differences in the recovery pattern post-surgery? METHODS: Data from 56 patients that underwent left-sided awake craniotomy for tumors infiltrating possible dominant hemisphere language areas from September 2016 to June 2019 were identified and analyzed in this study; 14 BL and 42 ML control patients. Patient demographics, education level, and the age of language acquisition were documented and evaluated. fMRI was performed on all participants. RESULTS: 0 (0%) BL and 3 (7%) ML experienced intraoperative seizures (P = 0.73). BL patients received a higher direct DECS current in comparison to the ML patients (average = 4.7, 3.8, respectively, P = 0.03). The extent of resection was higher in ML patients in comparison to the BL patients (80.9 vs. 64.8, respectively, P = 0.04). The post-operative KPS scores were higher in BL patients in comparison to ML patients (84.3, 77.4, respectively, P = 0.03). BL showed lower drop in post-operative KPS in comparison to ML patients (- 4.3, - 8.7, respectively, P = 0.03). CONCLUSION: We show that BL patients have a lower incidence of intra-operative seizures, lower EOR, higher post-operative KPS and tolerate higher DECS current, in comparison to ML patients.
Keywords: Brain Mapping; Brain Neoplasms; Craniotomy; Female; Follow-Up Studies; Glioma; Humans; Incidence; Language; Male; Middle Aged; Monitoring, Intraoperative; Prognosis; Retrospective Studies; Seizures; United States; Wakefulness

An exploration of BCI performance variations in people with amyotrophic lateral sclerosis using longitudinal EEG data - Shahriari, Yalda; Vaughan, Theresa; McCane, Lynn; Allison, Brendan; Wolpaw, Jonathan; Krusienski, Dean (Journal of Neural Engineering, 2019)
Objective. Brain-computer interface (BCI) technology enables people to use direct measures of brain activity for communication and control. The National Center for Adaptive Neurotechnologies (NCAN) and Helen Hayes Hospital are studying long-term independent home use of P300-based BCIs by people with amyotrophic lateral sclerosis (ALS). This BCI use takes place without technical oversight, and users can encounter substantial variation in their day-to-day BCI performance. The purpose of this study is to identify and evaluate features in the electroencephalogram (EEG) that correlate with successful BCI performance during home use with the goal of improving BCI for people with neuromuscular disorders. Approach. Nine people with ALS used a P300-based BCI at home over several months for communication and computer control. Sessions from a routine calibration task were categorized as successful (≥70%) or unsuccessful (<70%) BCI performance. The correlation of temporal and spectral EEG features with BCI performance was then evaluated. Main Results. BCI performance was positively correlated with an increase in alpha-band (8-14 Hz) activity at locations PO8, P3, Pz, and P4; and beta-band (15-30 Hz) activity at occipital locations. In addition, performance was significantly positively correlated with a positive deflection in EEG amplitude around 220 ms at frontal mid-line locations (i.e., Fz and Cz). BCI performance was negatively correlated with delta-band (1-3 Hz) activity recorded from occipital locations. Significance. These results highlight the variability found in the EEG and describe EEG features that correlate with successful BCI performance during day-to-day use of a P300-based BCI by people with ALS. These results should inform studies focused on improved BCI reliability for people with neuromuscular disorders.
Keywords: amyotrophic lateral sclerosis (ALS); Brain-computer interface (BCI); Longitudinal Electroencephalogram (EEG); P300 speller

iEEGview: an open-source multifunction GUI-based Matlab toolbox for localization and visualization of human intracranial electrodes. - Li, Guangye; Jiang, Shize; Chen, Chen; Peter Brunner; Wu, Zehan; Schalk, Gerwin; Chen, Liang; Zhang, Dingguo (J Neural Eng, 2019)
OBJECTIVE: The precise localization of intracranial electrodes is a fundamental step relevant to the analysis of intracranial electroencephalography (iEEG) recordings in various fields. With the increasing development of iEEG studies in human neuroscience, higher requirements have been posed on the localization process, resulting in urgent demand for more integrated, easy-operation and versatile tools for electrode localization and visualization. With the aim of addressing this need, we develop an easy-to-use and multifunction toolbox called iEEGview, which can be used for the localization and visualization of human intracranial electrodes. APPROACH: iEEGview is written in Matlab scripts and implemented with a GUI. From the GUI, by taking only pre-implant MRI and post-implant CT images as input, users can directly run the full localization pipeline including brain segmentation, image co-registration, electrode reconstruction, anatomical information identification, activation map generation and electrode projection from native brain space into common brain space for group analysis. Additionally, iEEGview implements methods for brain shift correction, visual location inspection on MRI slices and computation of certainty index in anatomical label assignment. MAIN RESULTS: All the introduced functions of iEEGview work reliably and successfully, and are tested by images from 28 human subjects implanted with depth and/or subdural electrodes. SIGNIFICANCE: iEEGview is the first public Matlab GUI-based software for intracranial electrode localization and visualization that holds integrated capabilities together within one pipeline. iEEGview promotes convenience and efficiency for the localization process, provides rich localization information for further analysis and offers solutions for addressing raised technical challenges. Therefore, it can serve as a useful tool in facilitating iEEG studies.
Keywords: Brain; Brain Mapping; Electrocorticography; Electrodes, Implanted; Electroencephalography; Humans; Magnetic Resonance Imaging

A quantitative method for evaluating cortical responses to electrical stimulation - Lawrence J. Crowther; Peter Brunner; Christoph Kapeller; Christoph Guger; Kyousuke Kamada; Marjorie E. Bunch; Bridget K. Frawley; Timothy M. Lynch; Anthony L. Ritaccio; Gerwin Schalk (Journal of Neuroscience Methods, 2019)
Background Electrical stimulation of the cortex using subdurally implanted electrodes can causally reveal structural connectivity by eliciting cortico-cortical evoked potentials (CCEPs). While many studies have demonstrated the potential value of CCEPs, the methods to evaluate them were often relatively subjective, did not consider potential artifacts, and did not lend themselves to systematic scientific investigations. New method We developed an automated and quantitative method called SIGNI (Stimulation-Induced Gamma-based Network Identification) to evaluate cortical population-level responses to electrical stimulation that minimizes the impact of electrical artifacts. We applied SIGNI to electrocorticographic (ECoG) data from eight human subjects who were implanted with a total of 978 subdural electrodes. Across the eight subjects, we delivered 92 trains of approximately 200 discrete electrical stimuli each (amplitude 4–15 mA) to a total of 64 electrode pairs. Results We verified SIGNI's efficacy by demonstrating a relationship between the magnitude of evoked cortical activity and stimulation amplitude, as well as between the latency of evoked cortical activity and the distance from the stimulated locations. Conclusions SIGNI reveals the timing and amplitude of cortical responses to electrical stimulation as well as the structural connectivity supporting these responses. With these properties, it enables exploration of new and important questions about the neurophysiology of cortical communication and may also be useful for pre-surgical planning.
Keywords: Connectivity; Cortico-cortical evoked potentials; Electrical stimulation; Electrocorticography

7th Operant Conditioning Meeting, Charleston, SC - Jonathan Wolpaw (2018)

Acquisition, maintenance, and therapeutic use of a simple motor skill - James JS Norton; Jonathan Wolpaw (Current Opinion in Behavioral Sciences, 2018)
Operant conditioning of the spinal stretch reflex (SSR) or its electrical analog, the H-reflex, is a valuable experimental paradigm for studying the acquisition and maintenance of a simple motor skill. The central nervous system (CNS) substrate of this skill consists of brain and spinal cord plasticity that operates as a hierarchy—the learning experience induces plasticity in the brain that guides and maintains plasticity in the spinal cord. This is apparent in the two components of the skill acquisition: task-dependent adaptation, reflecting brain plasticity; and long-term change, reflecting gradual development of spinal plasticity. The inferior olive, cerebellum, sensorimotor cortex, and corticospinal tract (CST) are essential components of this hierarchy. The neuronal and synaptic mechanisms of the spinal plasticity are under study. Because acquisition of this skill changes the spinal cord, it can affect other skills, such as locomotion. Thus, it enables investigation of how the highly plastic spinal cord supports the acquisition and maintenance of a broad repertoire of motor skills throughout life. These studies have resulted in the negotiated equilibrium model of spinal cord function, which reconciles the spinal cord's long-recognized reliability as the final common pathway for behaviors with its recently recognized ongoing plasticity. In accord with this model, appropriate H-reflex conditioning in a person with spasticity due to an incomplete spinal cord injury can trigger wider beneficial plasticity that markedly improves walking. H-reflex operant conditioning appears to provide a valuable new method for enhancing functional recovery in people with spinal cord injury and possibly other disorders as well.

BCI Software - Peter Brunner; Schalk, Gerwin (Brain–Computer Interfaces Handbook: Technological and Theoretical Advances, 2018)

Brain-Computer Interfaces For Communication And Control - Jonathan Wolpaw (2018)
NANS Summer Series, New York City, NY

Combining H-reflex conditioning and locomotor training appears to enhance locomotor recovery in rats with incomplete spinal cord injury: Initial results - X. Y. Chen; L. Chen; X. Yang; Y. Wang; Y. Chen; Jonathan Wolpaw (Program No. 387.12. 2018 Neuroscience Meeting Planner. San Diego, CA: Society for Neuroscience. Online., 2018)

Controlling pre-movement sensorimotor rhythm can improve finger extension after stroke - Norman, SL; McFarland, DJ; Miner, A; Cramer, SC; Wolbrecht, ET; Jonathan Wolpaw; Reinkensmeyer, DJ (Journal of Neural Engineering, 2018)
Objective. Brain–computer interface (BCI) technology is attracting increasing interest as a tool for enhancing recovery of motor function after stroke, yet the optimal way to apply this technology is unknown. Here, we studied the immediate and therapeutic effects of BCI-based training to control pre-movement sensorimotor rhythm (SMR) amplitude on robot-assisted finger extension in people with stroke. Approach. Eight people with moderate to severe hand impairment due to chronic stroke completed a four-week three-phase protocol during which they practiced finger extension with assistance from the FINGER robotic exoskeleton. In Phase 1, we identified spatiospectral SMR features for each person that correlated with the intent to extend the index and/or middle finger(s). In Phase 2, the participants learned to increase or decrease SMR features given visual feedback, without movement. In Phase 3, the participants were cued to increase or decrease their SMR features, and when successful, were then cued to immediately attempt to extend the finger(s) with robot assistance. Main results. Of the four participants that achieved SMR control in Phase 2, three initiated finger extensions with a reduced reaction time after decreasing (versus increasing) pre-movement SMR amplitude during Phase 3. Two also extended at least one of their fingers more forcefully after decreasing pre-movement SMR amplitude. Hand function, measured by the box and block test (BBT), improved by 7.3  ±  7.5 blocks versus 3.5  ±  3.1 blocks in those with and without SMR control, respectively. Higher BBT scores at baseline correlated with a larger change in BBT score. Significance. These results suggest that learning to control person-specific pre-movement SMR features associated with finger extension can improve finger extension ability after stroke for some individuals. These results merit further investigation in a rehabilitation context.
Keywords: BCI; Motor control; Rehabilitation; robot; sensorimotor rhythm; Stroke

Creating an eyes-closed binary SSVEP-based brain-computer interface (BCI) for the bedside: A comparison of foveal centered and off-centered stimulus presentation - T. M. Vaughan; M. Aslam; B. Zoltan; Peter Brunner; J. J. Norton; C. S. Carmack; D. J. Zeitlin; Jonathan Wolpaw (2018)

Creating an eyes-closed binary SSVEP-based brain-computer interface (BCI) for the bedside: A comparison of foveal centered and off-centered stimulus presentation - T.M. Vaughan; M. Aslam; B. Zoltan; Peter Brunner; J. J. Norton; C. S. Carmack; D. J. Zeitlin; Jonathan Wolpaw (Program No. 225.17. 2018 Neuroscience Meeting Planner. San Diego, CA: Society for Neuroscience. Online., 2018)

Department of Kinesiology, Penn State University, State College, PA. - Jonathan Wolpaw (2018)

ECoG-Based BCIs - Gunduz, Aysegul; Schalk, Gerwin (Brain–Computer Interfaces Handbook: Technological and Theoretical Advances, 2018)

Effects of Sensorimotor Rhythm Modulation on the Human Flexor Carpi Radialis H-Reflex - Thompson, AK; Carruth, H; Haywood, R; Hill, NJ; Sarnacki, WA; McCane, LM; Jonathan Wolpaw; McFarland, DJ (Frontiers in Neuroscience, 2018)
People can learn over training sessions to increase or decrease sensorimotor rhythms (SMRs) in the electroencephalogram (EEG). Activity-dependent brain plasticity is thought to guide spinal plasticity during motor skill learning; thus, SMR training may affect spinal reflexes and thereby influence motor control. To test this hypothesis, we investigated the effects of learned mu (8–13 Hz) SMR modulation on the flexor carpi radialis (FCR) H-reflex in 6 subjects with no known neurological conditions and 2 subjects with chronic incomplete spinal cord injury (SCI). All subjects had learned and practiced over more than 10 < 30-min training sessions to increase (SMR-up trials) and decrease (SMR-down trials) mu-rhythm amplitude over the hand/arm area of left sensorimotor cortex with ≥80% accuracy. Right FCR H-reflexes were elicited at random times during SMR-up and SMR-down trials, and in between trials. SMR modulation affected H-reflex size. In all the neurologically normal subjects, the H-reflex was significantly larger [116% ± 6 (mean ± SE)] during SMR-up trials than between trials, and significantly smaller (92% ± 1) during SMR-down trials than between trials (p < 0.05 for both, paired t-test). One subject with SCI showed similar H-reflex size dependence (high for SMR-up trials, low for SMR-down trials): the other subject with SCI showed no dependence. These results support the hypothesis that SMR modulation has predictable effects on spinal reflex excitability in people who are neurologically normal; they also suggest that it might be used to enhance therapies that seek to improve functional recovery in some individuals with SCI or other CNS disorders.
Keywords: brain-computer interface (BC); EEG mu-rhythm; H-Reflex; Spinal Cord Injuries; task-dependent adaptation

Electrical Stimulation Mapping of the Brain: Basic Principles and Emerging Alternatives - Ritaccio, A; Peter Brunner; Schalk, G (Journal of Clinical Neurophysiology, 2018)
The application of electrical stimulation mapping (ESM) of the brain for clinical use is approximating a century. Despite this long-standing history, the value of ESM for guiding surgical resections and sparing eloquent cortex is documented largely by small retrospective studies, and ESM protocols are largely inherited and lack standardization. Although models are imperfect and mechanisms are complex, the probabilistic causality of ESM has guaranteed its perpetuation into the 21st century. At present, electrical stimulation of cortical tissue is being revisited for network connectivity. In addition, noninvasive and passive mapping techniques are rapidly evolving to complement and potentially replace ESM in specific clinical situations. Lesional and epilepsy neurosurgery cases now offer different opportunities for multimodal functional assessments.
Keywords: Brain Mapping; Corticocortical-evoked potentials; electrical stimulation mapping; Electrocorticography; Functional localization; Passive gamma mapping

Encoding of Multiple Reward-Related Computations in Transient and Sustained High-Frequency Activity in Human OFC - Ignacio Saez; Jack Lin; Arjen Stolk; Edward Chang; Josef Parvizi; Gerwin Schalk; Robert T. Knight; Ming Hsu (Current Biology, 2018)
Summary Human orbitofrontal cortex (OFC) has long been implicated in value-based decision making. In recent years, convergent evidence from human and model organisms has further elucidated its role in representing reward-related computations underlying decision making. However, a detailed description of these processes remains elusive due in part to (1) limitations in our ability to observe human OFC neural dynamics at the timescale of decision processes and (2) methodological and interspecies differences that make it challenging to connect human and animal findings or to resolve discrepancies when they arise. Here, we sought to address these challenges by conducting multi-electrode electrocorticography (ECoG) recordings in neurosurgical patients during economic decision making to elucidate the electrophysiological signature, sub-second temporal profile, and anatomical distribution of reward-related computations within human OFC. We found that high-frequency activity (HFA) (70–200 Hz) reflected multiple valuation components grouped in two classes of valuation signals that were dissociable in temporal profile and information content: (1) fast, transient responses reflecting signals associated with choice and outcome processing, including anticipated risk and outcome regret, and (2) sustained responses explicitly encoding what happened in the immediately preceding trial. Anatomically, these responses were widely distributed in partially overlapping networks, including regions in the central OFC (Brodmann areas 11 and 13), which have been consistently implicated in reward processing in animal single-unit studies. Together, these results integrate insights drawn from human and animal studies and provide evidence for a role of human OFC in representing multiple reward computations.
Keywords: ECoC; Electrocorticography; ERP; event-related potential; field potential; FP; HFA; high-frequency activity; OFC; orbitofrontal cortex; reward-prediction error; RPE

H-reflex conditioning of the flexor carpi radialis: Updated data analysis methods and preliminary data - Norton, James J. S. (2018)
Society for Neuroscience Satellite Symposium on Spinal Cord Plasticity in Motor Control. San Diego, CA

Independent home use of a brain-computer interface by people with amyotrophic lateral sclerosis - Jonathan Wolpaw; Bedlack, RS; Reda, DJ; Ringer, RJ; Banks, PG; Vaughan, TM; Heckman, SM; McCrane, LM; Carmack, CS; Winden, S; McFarland, DJ; Sellers, EW; et al. (Neurology, 2018)
Objective: To assess the reliability and usefulness of an EEG-based brain-computer interface (BCI) for patients with advanced amyotrophic lateral sclerosis (ALS) who used it independently at home for up to 18 months. Methods: Of 42 patients consented, 39 (93%) met the study criteria, and 37 (88%) were assessed for use of the Wadsworth BCI. Nine (21%) could not use the BCI. Of the other 28, 27 (men, age 28–79 years) (64%) had the BCI placed in their homes, and they and their caregivers were trained to use it. Use data were collected by Internet. Periodic visits evaluated BCI benefit and burden and quality of life. Results: Over subsequent months, 12 (29% of the original 42) left the study because of death or rapid disease progression and 6 (14%) left because of decreased interest. Fourteen (33%) completed training and used the BCI independently, mainly for communication. Technical problems were rare. Patient and caregiver ratings indicated that BCI benefit exceeded burden. Quality of life remained stable. Of those not lost to the disease, half completed the study; all but 1 patient kept the BCI for further use. Conclusion: The Wadsworth BCI home system can function reliably and usefully when operated by patients in their homes. BCIs that support communication are at present most suitable for people who are severely disabled but are otherwise in stable health. Improvements in BCI convenience and performance, including some now underway, should increase the number of people who find them useful and the extent to which they are used.
Keywords: All clinical neurophysiology; All Neuromuscular Disease; Evoked Potentials; visual

Instantaneous voltage of electroencephalographic oscillatory activity: An alternative to power and phase measurements - M. Adamek; Peter Brunner; L. Moheimanian; R. Scherer; G. Schalk (Program No. 125.17. 2018 Neuroscience Meeting Planner. San Diego, CA: Society for Neuroscience. Online., 2018)

Instantaneous voltage of electroencephalographic oscillatory activity: An alternative to power and phase measurements - M. Adamek; Peter Brunner; L. Moheimanian; R. Scherer; G. Schalk (Program No. 125.17. 2018 Neuroscience Meeting Planner. San Diego, CA: Society for Neuroscience. Online., 2018)

McDowell Award Lecture - Jonathan Wolpaw (2018)
Burke Neurological Research Inst, Weill-Cornell Sch Med, White Plains, NY

National Center for Neuromodulation for Rehabilitation Workshop, Medical University of South Carolina, Charleston, SC. - Jonathan Wolpaw (2018)

Neuromodulation for Rehabilitation after Spinal Cord Injury - Jonathan Wolpaw (2018)
NANS Summer Series, New York City, NY, August, 2018

NeuroRehabilitation CME Course, Harvard Medical School, Waltham, MA - Jonathan Wolpaw (2018)

New York State Spinal Cord Injury Research Board Symposium, New York, NY. - Jonathan Wolpaw (2018)

Optimal referencing for stereo-electroencephalographic (SEEG) recordings - Li, G; Jiang, S; Paraskevopoulou, S; Wang, M; Xu, Y; Wu, Z; Chen, L; Zhang, D; Schalk, Gerwin (NeuroImage, 2018)
Stereo-electroencephalography (SEEG) is an intracranial recording technique in which depth electrodes are inserted in the brain as part of presurgical assessments for invasive brain surgery. SEEG recordings can tap into neural signals across the entire brain and thereby sample both cortical and subcortical sites. However, even though signal referencing is important for proper assessment of SEEG signals, no previous study has comprehensively evaluated the optimal referencing method for SEEG. In our study, we recorded SEEG data from 15 human subjects during a motor task, referencing them against the average of two white matter contacts (monopolar reference). We then subjected these signals to 5 different re-referencing approaches: common average reference (CAR), gray-white matter reference (GWR), electrode shaft reference (ESR), bipolar reference, and Laplacian reference. The results from three different signal quality metrics suggest the use of the Laplacian re-reference for study of local population-level activity and low-frequency oscillatory activity.
Keywords: Noise subtraction; Referencing method; SEEG; Signal quality; Stereo-electroencephalography

Organizer and Speaker - Jonathan Wolpaw (2018)
Neuroethics Symposium, Seventh International Brain-Computer Interface Meeting, Asilomar, CA

Passive functional mapping of receptive language areas using electrocorticographic signals - J.R. Swift; W.G. Coon; C. Guger; Peter Brunner; M. Bunch; T. Lynch; B. Frawley; A.L. Ritaccio; G. Schalk (Clinical Neurophysiology, 2018)
Keywords: ECoG; Electrocorticography; functional mapping; Intracranial; Receptive language

The performance of 9–11-year-old children using an SSVEP-based BCI for target selection - James J S Norton; Jessica Mullins; Birgit E Alitz; Timothy Bretl (Journal of Neural Engineering, 2018)
Objective . In this paper, we report the performance of 9–11-year-old children using a steady-state visual evoked potential (SSVEP)-based brain–computer interface (BCI) and provide control data collected from adults for comparison. Children in our study achieved a much higher performance (79% accuracy; average age 9.64 years old) than the only previous investigation of children using an SSVEP-based BCI (∼50% accuracy; average age 9.86 years old). Approach . Experiments were conducted in two phases, a short calibration phase and a longer experimental phase. An offline analysis of the data collected during the calibration phase was used to set two parameters for a classifier and to screen participants who did not achieve a minimum accuracy of 85%. Main results . Eleven of the 14 children and all 11 of the adults who completed the calibration phase met the minimum accuracy requirement. During the experimental phase, children selected targets with a similar accuracy (79% for children versus 78% for adults), latency (2.1 s for children versus 1.9 s for adults), and bitrate (0.50 bits s −1 for children and 0.56 bits s −1 for adults) as adults. Significance . This study shows that children can use an SSVEP-based BCI with higher performance than previously believed and is the first to report the performance of children using an SSVEP-based BCI in terms of latency and bitrate. The results of this study imply that children with severe motor disabilities (such as locked-in syndrome) may use an SSVEP-based BCI to restore/replace the ability to communicate.

Perspectives on Brain–Computer Interfaces - Schalk, Gerwin (Brain–Computer Interfaces Handbook, 2018)

Progress in Clinical Motor Control Symposium, Penn State Univ, State College, PA - Jonathan Wolpaw (2018)

Rapid Identification of Cortical Connectivity During Functional Mapping - Lawrence J. Crowther; Peter Brunner; Anthony L. Ritaccio; Gerwin Schalk (American Epilepsy Society 72nd Annual Meeting, 2018)

Real-time detection and discrimination of visual perception using electrocorticographic signals - Kapeller, C; Ogawa, H; Schalk, G; Kunii, N; Coon, WG; Scharinger, J; Guger, C; Kamada, K (Journal of Neural Engineering, 2018)
Several neuroimaging studies have demonstrated that the ventral temporal cortex contains specialized regions that process visual stimuli. This study investigated the spatial and temporal dynamics of electrocorticographic (ECoG) responses to different types and colors of visual stimulation that were presented to four human participants, and demonstrated a real-time decoder that detects and discriminates responses to untrained natural images. Approach. ECoG signals from the participants were recorded while they were shown colored and greyscale versions of seven types of visual stimuli (images of faces, objects, bodies, line drawings, digits, and kanji and hiragana characters), resulting in 14 classes for discrimination (experiment I). Additionally, a real-time system asynchronously classified ECoG responses to faces, kanji and black screens presented via a monitor (experiment II), or to natural scenes (i.e. the face of an experimenter, natural images of faces and kanji, and a mirror) (experiment III). Outcome measures in all experiments included the discrimination performance across types based on broadband γ activity. Main results. Experiment I demonstrated an offline classification accuracy of 72.9% when discriminating among the seven types (without color separation). Further discrimination of grey versus colored images reached an accuracy of 67.1%. Discriminating all colors and types (14 classes) yielded an accuracy of 52.1%. In experiment II and III, the real-time decoder correctly detected 73.7% responses to face, kanji and black computer stimuli and 74.8% responses to presented natural scenes. Significance. Seven different types and their color information (either grey or color) could be detected and discriminated using broadband γ activity. Discrimination performance maximized for combined spatial-temporal information. The discrimination of stimulus color information provided the first ECoG-based evidence for color-related population-level cortical broadband γ responses in humans. Stimulus categories can be detected by their ECoG responses in real time within 500 ms with respect to stimulus onset.
Keywords: BCI; Brain–computer interface; ECoG; gamma; high gamma mapping; real-time; visual

Retraining Reflexes: Clinical Translation of Spinal Reflex Operant Conditioning - Eftekhar, A; Norton, JJS; McDonough, CM; Jonathan Wolpaw (Neurotherapeutics, 2018)
Neurological disorders, such as spinal cord injury, stroke, traumatic brain injury, cerebral palsy, and multiple sclerosis cause motor impairments that are a huge burden at the individual, family, and societal levels. Spinal reflex abnormalities contribute to these impairments. Spinal reflex measurements play important roles in characterizing and monitoring neurological disorders and their associated motor impairments, such as spasticity, which affects nearly half of those with neurological disorders. Spinal reflexes can also serve as therapeutic targets themselves. Operant conditioning protocols can target beneficial plasticity to key reflex pathways; they can thereby trigger wider plasticity that improves impaired motor skills, such as locomotion. These protocols may complement standard therapies such as locomotor training and enhance functional recovery. This paper reviews the value of spinal reflexes and the therapeutic promise of spinal reflex operant conditioning protocols; it also considers the complex process of translating this promise into clinical reality.
Keywords: clinical translation; H-Reflex; neurological disorders; operant conditioning; plasticity; Rehabilitation; spinal reflex

Spinal Cord Plasticity in Motor Control Symposium, San Diego, CA. - Jonathan Wolpaw (2018)

Studies of urinary dysfunction after spinal cord injury in vivo and in vitro - Jonathan Carp (2018)
School of Behavioral and Brain Sciences, University of Texas at Dallas, Richardson, TX

Towards operant conditioning of the flexor carpi radialis: Methods and initial results - J. Norton; A. Eftekhar; S. Heckman; J. H. Barnes; L. McCane; Jonathan Wolpaw (Program No. 387.08. 2018 Neuroscience Meeting Planner. San Diego, CA: Society for Neuroscience. Online., 2018)

Activity-Dependent Plasticity in the CNS - Jonathan Wolpaw (2017)
NIH Short Course in Adaptive Neurotechnologies, Wadsworth Center, Albany, NY

Center for Brain Plasticity and Recovery, Georgetown Univ. Med. Ctr., Washington, DC - Jonathan Wolpaw (2017)

Contralesional Brain-Computer Interface Control of a Powered Exoskeleton for Motor Recovery in Chronic Stroke Survivors. - Bundy, David T.; Souders, Lauren; Baranyai, Kelly; Leonard, Laura; Gerwin Schalk; Coker, Robert; Moran, Daniel W.; Huskey, Thy; Leuthardt, Eric C. (Stroke, 2017)
There are few effective therapies to achieve functional recovery from motor-related disabilities affecting the upper limb after stroke. This feasibility study tested whether a powered exoskeleton driven by a brain-computer interface (BCI), using neural activity from the unaffected cortical hemisphere, could affect motor recovery in chronic hemiparetic stroke survivors. This novel system was designed and configured for a home-based setting to test the feasibility of BCI-driven neurorehabilitation in outpatient environments.

Demystifying Medicine Lecture - Jonathan Wolpaw (2017)
National Institutes of Health, Bethesda, MD

Distinguished Scholar Lecture Series, University of Delaware, Newark, DE - Jonathan Wolpaw (2017)

EEG based zero-phase phase-locking value (PLV) and effects of spatial filtering during actual movement. - Jian, Wenjuan; Chen, Minyou; Dennis J. McFarland (Brain research bulletin, 2017)
Phase-locking value (PLV) is a well-known feature in sensorimotor rhythm (SMR) based BCI. Zero-phase PLV has not been explored because it is generally regarded as the result of volume conduction. Because spatial filters are often used to enhance the amplitude (square root of band power (BP)) feature and attenuate volume conduction, they are frequently applied as pre-processing methods when computing PLV. However, the effects of spatial filtering on PLV are ambiguous. Therefore, this article aims to explore whether zero-phase PLV is meaningful and how this is influenced by spatial filtering. Based on archival EEG data of left and right hand movement tasks for 32 subjects, we compared BP and PLV feature using data with and without pre-processing by a large Laplacian. Results showed that using ear-referenced data, zero-phase PLV provided unique information independent of BP for task prediction which was not explained by volume conduction and was significantly decreased when a large Laplacian was applied. In other words, the large Laplacian eliminated the useful information in zero-phase PLV for task prediction suggesting that it contains effects of both amplitude and phase. Therefore, zero-phase PLV may have functional significance beyond volume conduction. The interpretation of spatial filtering may be complicated by effects of phase.

EEG Error Prediction as a Solution for Combining the Advantages of Retrieval Practice and Errorless Learning. - Riley, Ellyn A.; Dennis J. McFarland (Frontiers in human neuroscience, 2017)
Given the frequency of naming errors in aphasia, a common aim of speech and language rehabilitation is the improvement of naming. Based on evidence of significant word recall improvements in patients with memory impairments, errorless learning methods have been successfully applied to naming therapy in aphasia; however, other evidence suggests that although errorless learning can lead to better performance during treatment sessions, retrieval practice may be the key to lasting improvements. Task performance may vary with brain state (e.g., level of arousal, degree of task focus), and changes in brain state can be detected using EEG. With the ultimate goal of designing a system that monitors patient brain state in real time during therapy, we sought to determine whether errors could be predicted using spectral features obtained from an analysis of EEG. Thus, this study aimed to investigate the use of individual EEG responses to predict error production in aphasia. Eight participants with aphasia each completed 900 object-naming trials across three sessions while EEG was recorded and response accuracy scored for each trial. Analysis of the EEG response for seven of the eight participants showed significant correlations between EEG features and response accuracy (correct vs. incorrect) and error correction (correct, self-corrected, incorrect). Furthermore, upon combining the training data for the first two sessions, the model generalized to predict accuracy for performance in the third session for seven participants when accuracy was used as a predictor, and for five participants when error correction category was used as a predictor. With such ability to predict errors during therapy, it may be possible to use this information to intervene with errorless learning strategies only when necessary, thereby allowing patients to benefit from both the high within-session success of errorless learning as well as the longer-term improvements associated with retrieval practice.

EEG-based brain-computer interfaces - McFarland, D. J.; Jonathan Wolpaw (Current Opinion in Biomedical Engineering, 2017)
Brain–Computer Interfaces (BCIs) are real-time computer-based systems that translate brain signals into useful commands. To date most applications have been demonstrations of proof-of-principle; widespread use by people who could benefit from this technology requires further development. Improvements in current EEG recording technology are needed. Better sensors would be easier to apply, more comfortable for the user, and produce higher quality and more stable signals. Although considerable effort has been devoted to evaluating classifiers using public datasets, more attention to real-time signal processing issues and to optimizing the mutually adaptive interaction between the brain and the BCI are essential for improving BCI performance. Further development of applications is also needed, particularly applications of BCI technology to rehabilitation. The design of rehabilitation applications hinges on the nature of BCI control and how it might be used to induce and guide beneficial plasticity in the brain.
Keywords: brain-computer interface; neurotechnology; Rehabilitation

Evaluation of multidimensional models of WAIS-IV subtest performance. - Dennis J. McFarland (The Clinical neuropsychologist, 2017)
The present study examined the extent to which the covariance structure of the WAIS-IV is best accounted for by models that assume that test performance is the result of group-level factors and multiple independent general factors.

Facephenes and rainbows: Causal evidence for functional and anatomical specificity of face and color processing in the human brain - Gerwin Schalk; Kapeller, C.; Guger, C.; Ogawa, H.; Hiroshima, S.; Lafer-Sousa, R.; Saygin, Z. M.; Kamada, K.; Kanwisher, N. (Proc. Natl. Acad. Sci. U.S.A., 2017)
Neuroscientists have long debated whether some regions of the human brain are exclusively engaged in a single specific mental process. Consistent with this view, fMRI has revealed cortical regions that respond selectively to certain stimulus classes such as faces. However, results from multivoxel pattern analyses (MVPA) challenge this view by demonstrating that category-selective regions often contain information about "nonpreferred" stimulus dimensions. But is this nonpreferred information causally relevant to behavior? Here we report a rare opportunity to test this question in a neurosurgical patient implanted for clinical reasons with strips of electrodes along his fusiform gyri. Broadband gamma electrocorticographic responses in multiple adjacent electrodes showed strong selectivity for faces in a region corresponding to the fusiform face area (FFA), and preferential responses to color in a nearby site, replicating earlier reports. To test the causal role of these regions in the perception of nonpreferred dimensions, we then electrically stimulated individual sites while the patient viewed various objects. When stimulated in the FFA, the patient reported seeing an illusory face (or "facephene"), independent of the object viewed. Similarly, stimulation of color-preferring sites produced illusory "rainbows." Crucially, the patient reported no change in the object viewed, apart from the facephenes and rainbows apparently superimposed on them. The functional and anatomical specificity of these effects indicate that some cortical regions are exclusively causally engaged in a single specific mental process, and prompt caution about the widespread assumption that any information scientists can decode from the brain is causally relevant to behavior.
Keywords: cortical specificity; electrical stimulation; fusiform face area

How neuroscience can inform the study of individual differences in cognitive abilities. - Dennis J. McFarland (Reviews in the neurosciences, 2017)
Theories of human mental abilities should be consistent with what is known in neuroscience. Currently, tests of human mental abilities are modeled by cognitive constructs such as attention, working memory, and speed of information processing. These constructs are in turn related to a single general ability. However, brains are very complex systems and whether most of the variability between the operations of different brains can be ascribed to a single factor is questionable. Research in neuroscience suggests that psychological processes such as perception, attention, decision, and executive control are emergent properties of interacting distributed networks. The modules that make up these networks use similar computational processes that involve multiple forms of neural plasticity, each having different time constants. Accordingly, these networks might best be characterized in terms of the information they process rather than in terms of abstract psychological processes such as working memory and executive control.

Invited Speaker - Jonathan Wolpaw (2017)
Department of Rehabilitation Medicine, Emory University School of Medicine, Atlanta, GA

National Center of Neuromodulation for Rehabilitation (NM4R) Workshop, Charleston, SC - Jonathan Wolpaw (2017)

NeuroRehabilitation CME Course, Harvard Medical School, Waltham, MA - Jonathan Wolpaw (2017)

Nothing either good or bad but action makes it so. - Jonathan Wolpaw; Thompson, Aiko K. (The Journal of physiology, 2017)

Plenary Lecture, Summer School on Neurorehabilitation, Baiona, Spain - Jonathan Wolpaw (2017)

Prediction of subjective ratings of emotional pictures by EEG features. - Dennis J. McFarland; Parvaz, Muhammad A.; Sarnacki, William A.; Goldstein, Rita Z.; Jonathan Wolpaw (Journal of neural engineering, 2017)
Emotion dysregulation is an important aspect of many psychiatric disorders. Brain-computer interface (BCI) technology could be a powerful new approach to facilitating therapeutic self-regulation of emotions. One possible BCI method would be to provide stimulus-specific feedback based on subject-specific electroencephalographic (EEG) responses to emotion-eliciting stimuli.

Progress in Motor Control IX, University of Miami, Miami, FL - Jonathan Wolpaw (2017)

A reference free olfactory-ERP measurement to detect Parkinson’s disease - Emilia Iannilli (2017)
National Center for Adaptive Neurotechnologies, Wadsworth Center, Albany, NY

Spatiotemporal dynamics of word retrieval in speech production revealed by cortical high-frequency band activity. - Riès, Stephanie K.; Dhillon, Rummit K.; Clarke, Alex; King-Stephens, David; Laxer, Kenneth D.; Weber, Peter B.; Kuperman, Rachel A.; Auguste, Kurtis I.; Peter Brunner; Gerwin Schalk; Lin, Jack J.; Parvizi, Josef; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Word retrieval is core to language production and relies on complementary processes: the rapid activation of lexical and conceptual representations and word selection, which chooses the correct word among semantically related competitors. Lexical and conceptual activation is measured by semantic priming. In contrast, word selection is indexed by semantic interference and is hampered in semantically homogeneous (HOM) contexts. We examined the spatiotemporal dynamics of these complementary processes in a picture naming task with blocks of semantically heterogeneous (HET) or HOM stimuli. We used electrocorticography data obtained from frontal and temporal cortices, permitting detailed spatiotemporal analysis of word retrieval processes. A semantic interference effect was observed with naming latencies longer in HOM versus HET blocks. Cortical response strength as indexed by high-frequency band (HFB) activity (70-150 Hz) amplitude revealed effects linked to lexical-semantic activation and word selection observed in widespread regions of the cortical mantle. Depending on the subsecond timing and cortical region, HFB indexed semantic interference (i.e., more activity in HOM than HET blocks) or semantic priming effects (i.e., more activity in HET than HOM blocks). These effects overlapped in time and space in the left posterior inferior temporal gyrus and the left prefrontal cortex. The data do not support a modular view of word retrieval in speech production but rather support substantial overlap of lexical-semantic activation and word selection mechanisms in the brain.

Spinal transection alters external urethral sphincter activity during spontaneous voiding in freely-moving rats. - LaPallo, Brandon K.; Jonathan Wolpaw; Xiang Yang Chen; Jonathan S. Carp (Journal of neurotrauma, 2017)
The rat is a commonly used model for the study of lower urinary tract function before and after spinal cord injury. We have previously reported that in unanesthetized, freely-moving rats, although phasic external urethral sphincter (EUS) activity (bursting) is most common during micturition, productive voiding can occur in the absence of bursting, which differs from results seen in anesthetized or unanesthetized restrained animals. The purpose of the present study was to characterize EUS behavior in unanesthetized, freely-moving rats before and after mid-thoracic (T8) or thoraco-lumbar (T13-L1) spinal transection to determine how EUS behavior after spinal cord injury differs from that seen in anesthetized or unanesthetized restrained rats. Several abnormalities became evident that were comparable after transection at either level including: repetitive non-voiding EUS contractions; increased prevalence, intensity and duration of EUS bursting; decreased rate of urine evacuation during bursting; increased void size and decreased number of daily voids; shorter inter-burst silent period and increased frequency of bursting; and loss of the direct linear relationships that are evident in intact animals between void size and bursting silent period. These data suggest that transection-induced delayed initiation of EUS bursting allows co-contraction of the bladder and the EUS that prevents or limits urine evacuation, resulting in a detrusor-sphincter dyssynergia-like phenomenon. In addition, the higher-than-normal frequency at which EUS bursting occurs after transection is associated with shorter silent periods during which urine typically flows, which interferes with voiding by slowing the rate of urine evacuation. That results were comparable after either transection suggests that the central pattern generator responsible for EUS bursting is located caudal to the L1 spinal segment.

Therapeutic Applications of BCI Technologies - McFarland, Dennis J; Daly, Janis; Boulay, Chadwick; Parvaz, Muhammad (Brain computer interfaces (Abingdon, England), 2017)

Use of phase-locking value in sensorimotor rhythm-based brain-computer interface: zero-phase coupling and effects of spatial filters. - Jian, Wenjuan; Chen, Minyou; Dennis J. McFarland (Medical & biological engineering & computing, 2017)
Phase-locking value (PLV) is a potentially useful feature in sensorimotor rhythm-based brain-computer interface (BCI). However, volume conduction may cause spurious zero-phase coupling between two EEG signals and it is not clear whether PLV effects are independent of spectral amplitude. Volume conduction might be reduced by spatial filtering, but it is uncertain what impact this might have on PLV. Therefore, the goal of this study was to explore whether zero-phase PLV is meaningful and how it is affected by spatial filtering. Both amplitude and PLV feature were extracted in the frequency band of 10-15?Hz by classical methods using archival EEG data of 18 subjects trained on a two-target BCI task. The results show that with right ear-referenced data, there is meaningful long-range zero-phase synchronization likely involving the primary motor area and the supplementary motor area that cannot be explained by volume conduction. Another novel finding is that the large Laplacian spatial filter enhances the amplitude feature but eliminates most of the phase information seen in ear-referenced data. A bipolar channel using phase-coupled areas also includes both phase and amplitude information and has a significant practical advantage since fewer channels required.

Why New Spinal Cord Plasticity Does Not Disrupt Old Motor Behaviors - Chen, Yi; Chen, Lu; Wang, Yu; Chen, Xiang Yang; Jonathan Wolpaw (The Journal of Neuroscience, 2017)
When new motor learning changes the spinal cord, old behaviors are not impaired; their key features are preserved by additional compensatory plasticity. To explore the mechanisms responsible for this compensatory plasticity, we transected the spinal dorsal ascending tract before or after female rats acquired a new behavior—operantly conditioned increase or decrease in the right soleus H-reflex—and examined an old behavior—locomotion. Neither spinal dorsal ascending tract transection nor H-reflex conditioning alone impaired locomotion. Nevertheless, when spinal dorsal ascending tract transection and H-reflex conditioning were combined, the rats developed a limp and a tilted posture that correlated in direction and magnitude with the H-reflex change. When the right H-reflex was increased by conditioning, the right step lasted longer than the left and the right hip was higher than the left; when the right H-reflex was decreased by conditioning, the opposite occurred. These results indicate that ascending sensory input guides the compensatory plasticity that normally prevents the plasticity underlying H-reflex change from impairing locomotion. They support the concept of the state of the spinal cord as a negotiated equilibrium that reflects the concurrent influences of all the behaviors in an individual's repertoire; and they support the new therapeutic strategies this concept introduces.
Keywords: H-Reflex; motor learning; operant conditioning; plasticity; Rehabilitation; Spinal Cord

50th Anniversary Symposium, Spinal Cord Injury Center, Heidelberg University Hospital, Heidelberg, Germany - Jonathan Wolpaw (2016)

Ablation of the inferior olive prevents H-reflex down-conditioning in rats. - Xiang Yang Chen; Wang, Yu; Yi Chen; Chen, Lu; Jonathan Wolpaw (Journal of neurophysiology, 2016)
We evaluated the role of the inferior olive (IO) in acquisition of the spinal cord plasticity that underlies H-reflex down-conditioning, a simple motor skill. The IO was chemically ablated before a 50-day exposure to an operant conditioning protocol that rewarded a smaller soleus H-reflex. In normal rats, down-conditioning succeeds (i.e., H-reflex size decreases at least 20%) in 80% of animals. Down-conditioning failed in every IO-ablated rat (P< 0.001 vs. normal rats). IO ablation itself had no long-term effect on H-reflex size. These results indicate that the IO is essential for acquisition of a down-conditioned H-reflex. With previous data, they support the hypothesis that IO and cortical inputs to cerebellum enable the cerebellum to guide sensorimotor cortex plasticity that produces and maintains the spinal cord plasticity that underlies the down-conditioned H-reflex. They help to further define H-reflex conditioning as a model for understanding motor learning and as a new approach to enhancing functional recovery after trauma or disease.
Keywords: Spinal Cord

Activity-Dependent Plasticity in the CNS - Jonathan Wolpaw (2016)
NIH Short Course in Adaptive Neurotechnologies, Wadsworth Center, Albany, NY

Alpha power indexes task-related networks on large and small scales: A multimodal ECoG study in humans and a non-human primate. - de Pesters, A.; Coon, W. G.; Peter Brunner; Gunduz, A.; A L Ritaccio; Brunet, N. M.; de Weerd, P.; Roberts, M. J.; Oostenveld, R.; Fries, P.; Gerwin Schalk (NeuroImage, 2016)
Performing different tasks, such as generating motor movements or processing sensory input, requires the recruitment of specific networks of neuronal populations. Previous studies suggested that power variations in the alpha band (8-12Hz) may implement such recruitment of task-specific populations by increasing cortical excitability in task-related areas while inhibiting population-level cortical activity in task-unrelated areas (Klimesch et al., 2007; Jensen and Mazaheri, 2010). However, the precise temporal and spatial relationships between the modulatory function implemented by alpha oscillations and population-level cortical activity remained undefined. Furthermore, while several studies suggested that alpha power indexes task-related populations across large and spatially separated cortical areas, it was largely unclear whether alpha power also differentially indexes smaller networks of task-related neuronal populations. Here we addressed these questions by investigating the temporal and spatial relationships of electrocorticographic (ECoG) power modulations in the alpha band and in the broadband gamma range (70-170Hz, indexing population-level activity) during auditory and motor tasks in five human subjects and one macaque monkey. In line with previous research, our results confirm that broadband gamma power accurately tracks task-related behavior and that alpha power decreases in task-related areas. More importantly, they demonstrate that alpha power suppression lags population-level activity in auditory areas during the auditory task, but precedes it in motor areas during the motor task. This suppression of alpha power in task-related areas was accompanied by an increase in areas not related to the task. In addition, we show for the first time that these differential modulations of alpha power could be observed not only across widely distributed systems (e.g., motor vs. auditory system), but also within the auditory system. Specifically, alpha power was suppressed in the locations within the auditory system that most robustly responded to particular sound stimuli. Altogether, our results provide experimental evidence for a mechanism that preferentially recruits task-related neuronal populations by increasing cortical excitability in task-related cortical areas and decreasing cortical excitability in task-unrelated areas. This mechanism is implemented by variations in alpha power and is common to humans and the non-human primate under study. These results contribute to an increasingly refined understanding of the mechanisms underlying the selection of the specific neuronal populations required for task execution.

Atlantic Health Symposium, Atlantic Neuroscience Institute, Overlook Med Center, Summit, NJ - Jonathan Wolpaw (2016)

Chapter 13 - BCI in practice - D.J. McFarland; T.M. Vaughan (Brain-Computer Interfaces: Lab Experiments to Real-World Applications, 2016)
Brain–computer interfaces are systems that use signals recorded from the brain to enable communication and control applications for individuals who have impaired function. This technology has developed to the point that it is now being used by individuals who can actually benefit from it. However, there are several outstanding issues that prevent widespread use. These include the ease of obtaining high-quality recordings by home users, the speed, and accuracy of current devices and adapting applications to the needs of the user. In this chapter, we discuss some of these unsolved issues.
Keywords: Brain–computer interface; Home use; Neurotechnologies

Contribution of the external urethral sphincter to urinary void size in unanesthetized unrestrained rats. - LaPallo, Brandon K.; Jonathan Wolpaw; Xiang Yang Chen; Jonathan S. Carp (Neurourology and urodynamics, 2016)
In anesthetized rats, voiding is typically associated with phasic activation (bursting) of the external urethral sphincter (EUS). During spontaneous voiding in unanesthetized, unrestrained rats, EUS bursting is the most common form of EUS activity exhibited, but it is not necessary for productive voiding to occur. The aim of the present study was to determine which aspects of EUS activity contributed to void size during bursting and non-bursting voiding in conscious, freely moving rats.

Department of Cognitive Science, Rensselaer Polytechnic Institute, Troy, NY - Jonathan Wolpaw (2016)

Departments of Rehabilitation and Biomedical Engineering, Emory University and Georgia Institute of Technology, Atlanta, GA - Jonathan Wolpaw (2016)

Differential roles of high gamma and local motor potentials for movement preparation and execution - Gunduz, Aysegul; Peter Brunner; Sharma, Mohit; Leuthardt, Eric C.; Ritaccio, Anthony L.; Pesaran, Bijan; Schalk, Gerwin (Brain-Computer Interfaces, 2016)
Determining a person’s intent, such as the planned direction of their movement, directly from their cortical activity could support important applications such as brain-computer interfaces (BCIs). Continuing development of improved BCI systems requires a better understanding of how the brain prepares for and executes movements. To contribute to this understanding, we recorded surface cortical potentials (electrocorticographic signals; ECoG) in 11 human subjects performing a delayed center-out task to establish the differential role of high gamma activity (HGA) and the local motor potential (LMP) as a function of time and anatomical area during movement preparation and execution. High gamma modulations mostly confirm previous findings of sensorimotor cortex involvement, whereas modulations in LMPs are observed in prefrontal cortices. These modulations include directional information during movement planning as well as execution. Our results suggest that sampling signals from these widely distributed cortical areas improves decoding accuracy.
Keywords: BCI; brain-computer interfaces; ECoG; Electrocorticography; sensorimotor systems

Effective connectivity of the insular gustatory cortex - Emilia Iannilli (2016)
38th Annual Meeting of the Association for Chemoreception Sciences, April 20-23, 2016 Florida (USA)

Electrocorticographic mapping of expressive language function without requiring the patient to speak: A report of three cases. - de Pesters, Adriana; Taplin, AmiLyn M.; Adamo, Matthew A.; A L Ritaccio; Gerwin Schalk (Epilepsy & behavior case reports, 2016)
Patients requiring resective brain surgery often undergo functional brain mapping during perioperative planning to localize expressive language areas. Currently, all established protocols to perform such mapping require substantial time and patient participation during verb generation or similar tasks. These issues can make language mapping impractical in certain clinical circumstances (e.g., during awake craniotomies) or with certain populations (e.g., pediatric patients). Thus, it is important to develop new techniques that reduce mapping time and the requirement for active patient participation. Several neuroscientific studies reported that the mere auditory presentation of speech stimuli can engage not only receptive but also expressive language areas. Here, we tested the hypothesis that submission of electrocorticographic (ECoG) recordings during a short speech listening task to an appropriate analysis procedure can identify eloquent expressive language cortex without requiring the patient to speak.

The elicitation of steady-state visual evoked potentials during sleep - Norton, James J. S. (2016)
Northwestern University, Slutzky Neuroprosthetics Laboratory. Chicago, IL

Grand Rounds, Department of Neurology, Columbia University, New York, NY - Jonathan Wolpaw (2016)

The inferior olive is essential for long-term maintenance of a simple motor skill. - Xiang Yang Chen; Wang, Yu; Yi Chen; Chen, Lu; Jonathan Wolpaw (Journal of neurophysiology, 2016)
The inferior olive (IO) is essential for operant down-conditioning of the rat soleus H-reflex, a simple motor skill. To evaluate the role of the IO in long-term maintenance of this skill, the H-reflex was down-conditioned over 50 days, the IO was chemically ablated, and down-conditioning continued for up to 102 more days. H-reflex size just before IO ablation averaged 62(±2 SE)% of its initial value (P < 0.001 vs. initial). After IO ablation, H-reflex size rose to 75-80% over ?10 days, remained there for ?30 days, rose over 10 days to above its initial value, and averaged 140(±14)% for the final 10 days of study (P < 0.01 vs. initial). This two-stage loss of down-conditioning maintenance correlated with IO neuronal loss (r = 0.75, P < 0.01) and was similar to the loss of down-conditioning that follows ablation of the cerebellar output nuclei dentate and interpositus. In control (i.e., unconditioned) rats, IO ablation has no long-term effect on H-reflex size. These results indicate that the IO is essential for long-term maintenance of a down-conditioned H-reflex. With previous data, they support the hypothesis that IO and cortical inputs to cerebellum combine to produce cerebellar plasticity that produces sensorimotor cortex plasticity that produces spinal cord plasticity that produces the smaller H-reflex. H-reflex down-conditioning appears to depend on a hierarchy of plasticity that may be guided by the IO and begin in the cerebellum. Similar hierarchies may underlie other motor learning.

Intraoperative mapping of expressive language cortex using passive real-time electrocorticography. - Taplin, AmiLyn M.; de Pesters, Adriana; Peter Brunner; Hermes, Dora; Dalfino, John C.; Adamo, Matthew A.; A L Ritaccio; Gerwin Schalk (Epilepsy & behavior case reports, 2016)
In this case report, we investigated the utility and practicality of passive intraoperative functional mapping of expressive language cortex using high-resolution electrocorticography (ECoG). The patient presented here experienced new-onset seizures caused by a medium-grade tumor in very close proximity to expressive language regions. In preparation of tumor resection, the patient underwent multiple functional language mapping procedures. We examined the relationship of results obtained with intraoperative high-resolution ECoG, extraoperative ECoG utilizing a conventional subdural grid, extraoperative electrical cortical stimulation (ECS) mapping, and functional magnetic resonance imaging (fMRI). Our results demonstrate that intraoperative mapping using high-resolution ECoG is feasible and, within minutes, produces results that are qualitatively concordant to those achieved by extraoperative mapping modalities. They also suggest that functional language mapping of expressive language areas with ECoG may prove useful in many intraoperative conditions given its time efficiency and safety. Finally, they demonstrate that integration of results from multiple functional mapping techniques, both intraoperative and extraoperative, may serve to improve the confidence in or precision of functional localization when pathology encroaches upon eloquent language cortex.

Keynote Lecture, Neural Engineering Research Symposium, University of Miami, Miami, FL - Jonathan Wolpaw (2016)

Keynote Speaker, Neuromodulation for Rehabilitation Workshop, Medical University of South Carolina, Charleston, SC - Jonathan Wolpaw (2016)

A method to establish the spatiotemporal evolution of task-related cortical activity from electrocorticographic signals in single trials. - Coon, W. G.; Gerwin Schalk (Journal of neuroscience methods, 2016)
Progress in neuroscience depends substantially on the ability to establish the detailed spatial and temporal sequence of neuronal population-level activity across large areas of the brain. Because there is substantial inter-trial variability in neuronal activity, traditional techniques that rely on signal averaging obscure where and when neuronal activity occurs. Thus, up to the present, it has been difficult to examine the detailed progression of neuronal activity across large areas of the brain.

The Miami Project, University of Miami, Miami, FL - Jonathan Wolpaw (2016)

Modeling General and Specific Abilities: Evaluation of Bifactor Models for the WJ-III. - Dennis J. McFarland (Assessment, 2016)
The present study examined issues related to structural modeling of abilities by the use of simulated data as well as analysis of the standardization data from the Woodcock-Johnson-III. In both cases, results were evaluated with cross-validation. Simulation results showed that cross-validation with an independent data set was more successful in identifying the model that was used to generate test scores than were several fit indices. Analysis of the Woodcock-Johnson-III standardization data with cross-validation showed that bifactor models provided better fit than hierarchical or correlated factor models. This was true considering both fit indices and cross-validation. General and specific factors shared a considerable amount of variance as evaluated by using the bifactor models to partition variance. The results of the present study suggest that there is a certain degree of ambiguity in determining the exact amount of covariance in test performance accounted for by general and specific factors. This calls in to question the practice of adjusting or controlling for general abilities when evaluating measures of specific abilities. Evidence for the validity of a construct should not be limited to factor analysis of tests purported to measure that construct.

Neural correlate of the construction of sentence meaning. - Fedorenko, Evelina; Scott, Terri L.; Peter Brunner; Coon, William G.; Pritchett, Brianna; Gerwin Schalk; Kanwisher, Nancy (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The neural processes that underlie your ability to read and understand this sentence are unknown. Sentence comprehension occurs very rapidly, and can only be understood at a mechanistic level by discovering the precise sequence of underlying computational and neural events. However, we have no continuous and online neural measure of sentence processing with high spatial and temporal resolution. Here we report just such a measure: intracranial recordings from the surface of the human brain show that neural activity, indexed by $γ$-power, increases monotonically over the course of a sentence as people read it. This steady increase in activity is absent when people read and remember nonword-lists, despite the higher cognitive demand entailed, ruling out accounts in terms of generic attention, working memory, and cognitive load. Response increases are lower for sentence structure without meaning (``Jabberwocky'' sentences) and word meaning without sentence structure (word-lists), showing that this effect is not explained by responses to syntax or word meaning alone. Instead, the full effect is found only for sentences, implicating compositional processes of sentence understanding, a striking and unique feature of human language not shared with animal communication systems. This work opens up new avenues for investigating the sequence of neural events that underlie the construction of linguistic meaning.

Neuromodulation for Rehabilitation Workshop, Medical University of South Carolina, Charleston, SC - Jonathan Wolpaw (2016)

Oscillatory phase modulates the timing of neuronal activations and resulting behavior. - Coon, W. G.; Gunduz, A.; Peter Brunner; A L Ritaccio; Pesaran, B.; Gerwin Schalk (NeuroImage, 2016)
Human behavioral response timing is highly variable from trial to trial. While it is generally understood that behavioral variability must be due to trial-by-trial variations in brain function, it is still largely unknown which physiological mechanisms govern the timing of neural activity as it travels through networks of neuronal populations, and how variations in the timing of neural activity relate to variations in the timing of behavior. In our study, we submitted recordings from the cortical surface to novel analytic techniques to chart the trajectory of neuronal population activity across the human cortex in single trials, and found joint modulation of the timing of this activity and of consequent behavior by neuronal oscillations in the alpha band (8-12Hz). Specifically, we established that the onset of population activity tends to occur during the trough of oscillatory activity, and that deviations from this preferred relationship are related to changes in the timing of population activity and the speed of the resulting behavioral response. These results indicate that neuronal activity incurs variable delays as it propagates across neuronal populations, and that the duration of each delay is a function of the instantaneous phase of oscillatory activity. We conclude that the results presented in this paper are supportive of a general model for variability in the effective speed of information transmission in the human brain and for variability in the timing of human behavior.

Pioneer Award Lecture, SPIE Conference, Baltimore, MD - Jonathan Wolpaw (2016)

Plenary Lecture, International Conference on Neurorehabilitation, Segovia, Spain - Jonathan Wolpaw (2016)

Presidential Lecture, Sixth Annual International Brain-Computer Interface Meeting, Asilomar, CA - Jonathan Wolpaw (2016)

Proceedings of the Eighth International Workshop on Advances in Electrocorticography. - A L Ritaccio; Williams, Justin; Denison, Tim; Foster, Brett L.; Starr, Philip A.; Gunduz, Aysegul; Zijlmans, Maeike; Gerwin Schalk (Epilepsy & behavior : E&B, 2016)
Excerpted proceedings of the Eighth International Workshop on Advances in Electrocorticography (ECoG), which convened October 15-16, 2015 in Chicago, IL, are presented. The workshop series has become the foremost gathering to present current basic and clinical research in subdural brain signal recording and analysis.

Robust Signal Identification for Dynamic Pattern Classification - Zhao, Rui; Schalk, Gerwin; Ji, Qiang (2016 23rd International Conference on Pattern Recognition, 2016)
This paper addresses the problem of identifying signals of interest from discrete-time sequences contaminated by erroneous segments, which we define as the part of time series whose dynamic patterns are inconsistent with that of the signals. Assuming the signals of interest consist of consecutive samples with arbitrary starting point, duration and following a stationary dynamic pattern, we propose a robust algorithm combining Random Sample Consensus (RANSAC) and Hidden Markov Model (HMM) to automatically identify the start and end of signals of interest from time series. To evaluate the identification quality, we perform a classification task, where the identified signals are used to train a classifier. A majority vote strategy is adopted to handle error contaminated testing sequences. Compared with manual selection approach and other unsupervised learning methods, the proposed method shows improvement in classification accuracy on both synthetic and real Electrocorticographic (ECoG) data.
Keywords: computational modeling; data models; Hidden Markov models; motion segmentation; robustness; testing; Time series analysis

Session Chair, Neural Interfaces Conference, Baltimore, MD - Jonathan Wolpaw (2016)

Spatio-Temporal Progression of Cortical Activity Related to Continuous Overt and Covert Speech Production in a Reading Task. - Brumberg, Jonathan S.; Krusienski, Dean J.; Chakrabarti, Shreya; Gunduz, Aysegul; Peter Brunner; A L Ritaccio; Gerwin Schalk (PloS one, 2016)
How the human brain plans, executes, and monitors continuous and fluent speech has remained largely elusive. For example, previous research has defined the cortical locations most important for different aspects of speech function, but has not yet yielded a definition of the temporal progression of involvement of those locations as speech progresses either overtly or covertly. In this paper, we uncovered the spatio-temporal evolution of neuronal population-level activity related to continuous overt speech, and identified those locations that shared activity characteristics across overt and covert speech. Specifically, we asked subjects to repeat continuous sentences aloud or silently while we recorded electrical signals directly from the surface of the brain (electrocorticography (ECoG)). We then determined the relationship between cortical activity and speech output across different areas of cortex and at sub-second timescales. The results highlight a spatio-temporal progression of cortical involvement in the continuous speech process that initiates utterances in frontal-motor areas and ends with the monitoring of auditory feedback in superior temporal gyrus. Direct comparison of cortical activity related to overt versus covert conditions revealed a common network of brain regions involved in speech that may implement orthographic and phonological processing. Our results provide one of the first characterizations of the spatiotemporal electrophysiological representations of the continuous speech process, and also highlight the common neural substrate of overt and covert speech. These results thereby contribute to a refined understanding of speech functions in the human brain.

Spontaneous Decoding of the Timing and Content of Human Object Perception from Cortical Surface Recordings Reveals Complementary Information in the Event-Related Potential and Broadband Spectral Change. - Miller, Kai J.; Gerwin Schalk; Hermes, Dora; Ojemann, Jeffrey G.; Rao, Rajesh P. N. (PLoS computational biology, 2016)
The link between object perception and neural activity in visual cortical areas is a problem of fundamental importance in neuroscience. Here we show that electrical potentials from the ventral temporal cortical surface in humans contain sufficient information for spontaneous and near-instantaneous identification of a subject's perceptual state. Electrocorticographic (ECoG) arrays were placed on the subtemporal cortical surface of seven epilepsy patients. Grayscale images of faces and houses were displayed rapidly in random sequence. We developed a template projection approach to decode the continuous ECoG data stream spontaneously, predicting the occurrence, timing and type of visual stimulus. In this setting, we evaluated the independent and joint use of two well-studied features of brain signals, broadband changes in the frequency power spectrum of the potential and deflections in the raw potential trace (event-related potential; ERP). Our ability to predict both the timing of stimulus onset and the type of image was best when we used a combination of both the broadband response and ERP, suggesting that they capture different and complementary aspects of the subject's perceptual state. Specifically, we were able to predict the timing and type of 96% of all stimuli, with less than 5% false positive rate and a {~}20ms error in timing.
Keywords: Visual Perception

Symposium, International Conference on Neurorehabilitation, Segovia, Spain - Jonathan Wolpaw (2016)

Symposium, International Society of Electrophysiology and Kinesiology, Chicago, IL - Jonathan Wolpaw (2016)

Word pair classification during imagined speech using direct brain recordings. - Martin, Stéphanie; Peter Brunner; Iturrate, Iñaki; Millán, José Del R.; Gerwin Schalk; Robert T. Knight; Pasley, Brian N. (Scientific reports, 2016)
People that cannot communicate due to neurological disorders would benefit from an internal speech decoder. Here, we showed the ability to classify individual words during imagined speech from electrocorticographic signals. In a word imagery task, we used high gamma (70-150þinspaceHz) time features with a support vector machine model to classify individual words from a pair of words. To account for temporal irregularities during speech production, we introduced a non-linear time alignment into the SVM kernel. Classification accuracy reached 88% in a two-class classification framework (50% chance level), and average classification accuracy across fifteen word-pairs was significant across five subjects (meanþinspace=þinspace58%; pþinspace<þinspace0.05). We also compared classification accuracy between imagined speech, overt speech and listening. As predicted, higher classification accuracy was obtained in the listening and overt speech conditions (meanþinspace=þinspace89% and 86%, respectively; pþinspace<þinspace0.0001), where speech stimuli were directly presented. The results provide evidence for a neural representation for imagined words in the temporal lobe, frontal lobe and sensorimotor cortex, consistent with previous findings in speech perception and production. These data represent a proof of concept study for basic decoding of speech imagery, and delineate a number of key challenges to usage of speech imagery neural representations for clinical applications.

Biomedical Technology Research Centers Principal Investigator Annual Meeting, Rockville, MD - Jonathan Wolpaw (2015)

Brain-to-text: Decoding spoken sentences from phone representations in the brain. - Herff, C.; Heger, D.; Pesters, Adriana de; Telaar, D.; Peter Brunner; Gerwin Schalk; Schultz, T. (Journal of Neural Engineering, 2015)
It has long been speculated whether communication between humans and machines based on natural speech related cortical activity is possible. Over the past decade, studies have suggested that it is feasible to recognize isolated aspects of speech from neural signals, such as auditory features, phones or one of a few isolated words. However, until now it remained an unsolved challenge to decode continuously spoken speech from the neural substrate associated with speech and language processing. Here, we show for the first time that continuously spoken speech can be decoded into the expressed words from intracranial electrocorticographic (ECoG) recordings.Specifically, we implemented a system, which we call Brain-To-Text that models single phones, employs techniques from automatic speech recognition (ASR), and thereby transforms brain activity while speaking into the corresponding textual representation. Our results demonstrate that our system can achieve word error rates as low as 25% and phone error rates below 50%. Additionally, our approach contributes to the current understanding of the neural basis of continuous speech production by identifying those cortical regions that hold substantial information about individual phones. In conclusion, the Brain-To- Text system described in this paper represents an important step toward human-machine communication based on imagined speech.
Keywords: automatic speech recognition; brain-computer interface; broadband gamma; ECoG; Electrocorticography; pattern recognition; speech decoding; speech production

Cortical alpha activity predicts the confidence in an impending action. - Kubánek, J; Jeremy Jeremy Hill; Snyder, Lawrence H.; Gerwin Schalk (Front. Neurosci, 2015)
When we make a decision, we experience a degree of confidence that our choice may lead to a desirable outcome. Recent studies in animals have probed the subjective aspects of the choice confidence using confidence-reporting tasks. These studies showed that estimates of the choice confidence substantially modulate neural activity in multiple regions of the brain. Building on these findings, we investigated the neural representation of the confidence in a choice in humans who explicitly reported the confidence in their choice. Subjects performed a perceptual decision task in which they decided between choosing a button press or a saccade while we recorded EEG activity. Following each choice, subjects indicated whether they were sure or unsure about the choice. We found that alpha activity strongly encodes a subject's confidence level in a forthcoming button press choice. The neural effect of the subjects' confidence was independent of the reaction time and independent of the sensory input modeled as a decision variable. Furthermore, the effect is not due to a general cognitive state, such as reward expectation, because the effect was specifically observed during button press choices and not during saccade choices. The neural effect of the confidence in the ensuing button press choice was strong enough that we could predict, from independent single trial neural signals, whether a subject was going to be sure or unsure of an ensuing button press choice. In sum, alpha activity in human cortex provides a window into the commitment to make a hand movement.
Keywords: certainty; EEG; human; neural correlates; perceptual decision-making

The effects of spatial filtering and artifacts on electrocorticographic signals. - Liu, Y.; Coon, W. G.; de Pesters, A.; Peter Brunner; Gerwin Schalk (Journal of neural engineering, 2015)
Electrocorticographic (ECoG) signals contain noise that is common to all channels and noise that is specific to individual channels. Most published ECoG studies use common average reference (CAR) spatial filters to remove common noise, but CAR filters may introduce channel-specific noise into other channels. To address this concern, scientists often remove artifactual channels prior to data analysis. However, removing these channels depends on expert-based labeling and may also discard useful data. Thus, the effects of spatial filtering and artifacts on ECoG signals have been largely unknown. This study aims to quantify these effects and thereby address this gap in knowledge.
Keywords: Young Adult

Effects of training pre-movement sensorimotor rhythms on behavioral performance. - Dennis J. McFarland; Sarnacki, William A.; Jonathan Wolpaw (Journal of neural engineering, 2015)
Brain-computer interface (BCI) technology might contribute to rehabilitation of motor function. This speculation is based on the premise that modifying the electroencephalographic (EEG) activity will modify behavior, a proposition for which there is limited empirical data. The present study asked whether learned modulation of pre-movement sensorimotor rhythm (SMR) activity can affect motor performance in normal human subjects.
Keywords: sensorimotor cortex

Electrocorticographic activity over sensorimotor cortex and motor function in awake behaving rats. - Chadwick B. Boulay; Xiang Yang Chen; Jonathan Wolpaw (J Neurophysiol, 2015)
Sensorimotor cortex exerts both short-term and long-term control over the spinal reflex pathways that serve motor behaviors. Better understanding of this control could offer new possibilities for restoring function after central nervous system trauma or disease. We examined the impact of ongoing sensorimotor cortex (SMC) activity on the largely monosynaptic pathway of the H-reflex, the electrical analog of the spinal stretch reflex. In 41 awake adult rats, we measured soleus electromyographic (EMG) activity, the soleus H-reflex, and electrocorticographic activity over the contralateral SMC while rats were producing steady-state soleus EMG activity. Principal component analysis of electrocorticographic frequency spectra before H-reflex elicitation consistently revealed three frequency bands: μβ (5-30 Hz), low γ (γ1; 40-85 Hz), and high γ (γ2; 100-200 Hz). Ongoing (i.e., background) soleus EMG amplitude correlated negatively with μβ power and positively with γ1 power. In contrast, H-reflex size correlated positively with μβ power and negatively with γ1 power, but only when background soleus EMG amplitude was included in the linear model. These results support the hypothesis that increased SMC activation (indicated by decrease in μβ power and/or increase in γ1 power) simultaneously potentiates the H-reflex by exciting spinal motoneurons and suppresses it by decreasing the efficacy of the afferent input. They may help guide the development of new rehabilitation methods and of brain-computer interfaces that use SMC activity as a substitute for lost or impaired motor outputs.
Keywords: brain-computer interface; cortex; H-Reflex; Motor control; Spinal Cord

Electrocorticographic representations of segmental features in continuous speech. - Lotte, Fabien; Jonathan S Brumberg; Peter Brunner; Gunduz, Aysegul; A L Ritaccio; Guan, Cuntai; Gerwin Schalk (Front Hum Neurosci, 2015)
Acoustic speech output results from coordinated articulation of dozens of muscles, bones and cartilages of the vocal mechanism. While we commonly take the fluency and speed of our speech productions for granted, the neural mechanisms facilitating the requisite muscular control are not completely understood. Previous neuroimaging and electrophysiology studies of speech sensorimotor control has typically concentrated on speech sounds (i.e., phonemes, syllables and words) in isolation; sentence-length investigations have largely been used to inform coincident linguistic processing. In this study, we examined the neural representations of segmental features (place and manner of articulation, and voicing status) in the context of fluent, continuous speech production. We used recordings from the cortical surface [electrocorticography (ECoG)] to simultaneously evaluate the spatial topography and temporal dynamics of the neural correlates of speech articulation that may mediate the generation of hypothesized gestural or articulatory scores. We found that the representation of place of articulation involved broad networks of brain regions during all phases of speech production: preparation, execution and monitoring. In contrast, manner of articulation and voicing status were dominated by auditory cortical responses after speech had been initiated. These results provide a new insight into the articulatory and auditory processes underlying speech production in terms of their motor requirements and acoustic correlates.
Keywords: electrocorticography (ECoG); manner of articulation; place of articulation; speech processing; voicing

A general framework for dynamic cortical function: the function-through-biased-oscillations (FBO) hypothesis. - Gerwin Schalk (Front. Hum. Neurosci., 2015)
A central goal of neuroscience is to determine how the brain’s relatively static anatomy can support dynamic cortical function, i.e., cortical function that varies according to task demands. In pursuit of this goal, scientists have produced a large number of experimental results and established influential conceptual frameworks, in particular communication-through-coherence (CTC) and gating-by-inhibition (GBI), but these data and frameworks have not provided a parsimonious view of the principles that underlie cortical function. Here I synthesize these existing experimental results and the CTC and GBI frameworks, and propose the function-through-biased-oscillations (FBO) hypothesis as a model to understand dynamic cortical function. The FBO hypothesis suggests that oscillatory voltage amplitude is the principal measurement that directly reflects cortical excitability, that asymmetries in voltage amplitude explain a range of brain signal phenomena, and that predictive variations in such asymmetric oscillations provide a simple and general model for information routing that can help to explain dynamic cortical function.
Keywords: communication-through-coherence; gating-by-inhibition; information routing; oscillations; oscillatory modulation

How the CNS operates as a multi-user system - Jonathan Wolpaw (2015)
Panel (Chairman), Neural Control of Movement Meeting, Charleston, SC

Identifying the Attended Speaker Using Electrocorticographic (ECoG) Signals. - Dijkstra, K.; Peter Brunner; Gunduz, Aysegul; Coon, W.G.; A L Ritaccio; Farquhar, Jason; Gerwin Schalk (Journal of Neural Engineering, 2015)
People affected by severe neuro-degenerative diseases (e.g., late-stage amyotrophic lateral sclerosis (ALS) or locked-in syndrome) eventually lose all muscular control. Thus, they cannot use traditional assistive communication devices that depend on muscle control, or brain-computer interfaces (BCIs) that depend on the ability to control gaze. While auditory and tactile BCIs can provide communication to such individuals, their use typically entails an artificial mapping between the stimulus and the communication intent. This makes these BCIs difficult to learn and use. In this study, we investigated the use of selective auditory attention to natural speech as an avenue for BCI communication. In this approach, the user communicates by directing his/her attention to one of two simultaneously presented speakers. We used electrocorticographic (ECoG) signals in the gamma band (70–170 Hz) to infer the identity of attended speaker, thereby removing the need to learn such an artificial mapping. Our results from twelve human subjects show that a single cortical location over superior temporal gyrus or pre-motor cortex is typically sufficient to identify the attended speaker within 10 s and with 77% accuracy (50% accuracy due to chance). These results lay the groundwork for future studies that may determine the real-time performance of BCIs based on selective auditory attention to speech.
Keywords: auditory attention; Brain-computer interface (BCI); Cocktail Party; electrocorticography (ECoG)

Kavli Seminar, Center for Sensorimotor Neural Engineering, Seattle, WA - Jonathan Wolpaw (2015)

Keynote Address, College of Health Sciences Spring Research Symposium, University of Wisconsin, Milwaukee, WI - Jonathan Wolpaw (2015)

Near-Instantaneous Classification of Perceptual States from Cortical Surface Recordings - Miller, Kai J; Gerwin Schalk; Hermes, Dora; Ojemann, Jeffrey G; Rao, Rajesh P N (Brain-Computer Interface Research: A State-of-the-Art Summary, 2015)
Human visual processing is of such complexity that, despite decades of focused research, many basic questions remain unanswered. Although we know that the inferotemporal cortex is a key region in object recognition, we don’t fully understand its physiologic role in brain function, nor do we have the full set of tools to explore this question. Here we show that electrical potentials from the surface of the human brain contain enough information to decode a subject’s perceptual state accurately, and with fine temporal precision. Electrocorticographic (ECoG) arrays were placed over the inferotemporal cortical areas of seven subjects. Pictures of faces and houses were quickly presented while each subject performed a simple visual task. Results showed that two well-known types of brain signals—event-averaged broadband power and event-averaged raw potential—can independently or together be used to classify the presented image. When applied to continuously recorded brain activity, our decoding technique could accurately predict whether each stimulus was a face, house, or neither, with  20 ms timing error. These results provide a roadmap for improved brain-computer interfacing tools to help neurosurgeons, research scientists, engineers, and, ultimately, patients.
Keywords: broadband power; Electrocorticography; event-related potential; fusiform cortex; human vision

NeuralAct: A Tool to Visualize Electrocortical (ECoG) Activity on a Three-Dimensional Model of the Cortex. - Kubanek, Jan; Gerwin Schalk (Neuroinformatics, 2015)
Electrocorticography (ECoG) records neural signals directly from the surface of the cortex. Due to its high temporal and favorable spatial resolution, ECoG has emerged as a valuable new tool in acquiring cortical activity in cognitive and systems neuroscience. Many studies using ECoG visualized topographies of cortical activity or statistical tests on a three-dimensional model of the cortex, but a dedicated tool for this function has not yet been described. In this paper, we describe the NeuralAct package that serves this purpose. This package takes as input the 3D coordinates of the recording sensors, a cortical model in the same coordinate system (e.g., Talairach), and the activation data to be visualized at each sensor. It then aligns the sensor coordinates with the cortical model, convolves the activation data with a spatial kernel, and renders the resulting activations in color on the cortical model. The NeuralAct package can plot cortical activations of an individual subject as well as activations averaged over subjects. It is capable to render single images as well as sequences of images. The software runs under Matlab and is stable and robust. We here provide the tool and describe its visualization capabilities and procedures. The provided package contains thoroughly documented code and includes a simple demo that guides the researcher through the functionality of the tool.
Keywords: Brain; DOT; ECoG; EEG; imaging; Matlab; MEG

P300-based brain-computer interface (BCI) event-related potentials (ERPs): People with amyotrophic lateral sclerosis (ALS) vs. age-matched controls. - McCane, Lynn M; Susan M Heckman; Dennis J. McFarland; Townsend, George; Mak, Joseph N; Sellers, Eric W; Zeitlin, Debra; Tenteromano, Laura M; Jonathan Wolpaw; Theresa M Vaughan (Clin Neurophysiol, 2015)
OBJECTIVE: Brain-computer interfaces (BCIs) aimed at restoring communication to people with severe neuromuscular disabilities often use event-related potentials (ERPs) in scalp-recorded EEG activity. Up to the present, most research and development in this area has been done in the laboratory with young healthy control subjects. In order to facilitate the development of BCI most useful to people with disabilities, the present study set out to: (1) determine whether people with amyotrophic lateral sclerosis (ALS) and healthy, age-matched volunteers (HVs) differ in the speed and accuracy of their ERP-based BCI use; (2) compare the ERP characteristics of these two groups; and (3) identify ERP-related factors that might enable improvement in BCI performance for people with disabilities. METHODS: Sixteen EEG channels were recorded while people with ALS or healthy age-matched volunteers (HVs) used a P300-based BCI. The subjects with ALS had little or no remaining useful motor control (mean ALS Functional Rating Scale-Revised 9.4 (±9.5SD) (range 0-25)). Each subject attended to a target item as the items in a 6×6 visual matrix flashed. The BCI used a stepwise linear discriminant function (SWLDA) to determine the item the user wished to select (i.e., the target item). Offline analyses assessed the latencies, amplitudes, and locations of ERPs to the target and non-target items for people with ALS and age-matched control subjects. RESULTS: BCI accuracy and communication rate did not differ significantly between ALS users and HVs. Although ERP morphology was similar for the two groups, their target ERPs differed significantly in the location and amplitude of the late positivity (P300), the amplitude of the early negativity (N200), and the latency of the late negativity (LN). CONCLUSIONS: The differences in target ERP components between people with ALS and age-matched HVs are consistent with the growing recognition that ALS may affect cortical function. The development of BCIs for use by this population may begin with studies in HVs but also needs to include studies in people with ALS. Their differences in ERP components may affect the selection of electrode montages, and might also affect the selection of presentation parameters (e.g., matrix design, stimulation rate). SIGNIFICANCE: P300-based BCI performance in people severely disabled by ALS is similar to that of age-matched control subjects. At the same time, their ERP components differ to some degree from those of controls. Attention to these differences could contribute to the development of BCIs useful to those with ALS and possibly to others with severe neuromuscular disabilities.
Keywords: alternative and augmentative communication (AAC); amyotrophic lateral sclerosis (ALS); Brain-computer interface (BCI); brain-machine interface (BMI); electroencephalography (EEG); event-related potentials (ERP)

The Plurality of Human Brain-Computer Interfacing. - Mueller-Putz, G.; Millán, José del R; Gerwin Schalk; Mueller, K.R. (Proceedings of the IEEE, 2015)
The articles in this special issue focus on brain-computer interfacing. The papers are dedicated to this growing and diversifying research enterprise, and features important review articles as well as some important current examples of research in this area. The field of brain-computer interface (BCI) research began to develop about 25 years ago and transformed from initially isolated demonstrations by a few groups into a large scientific enterprise that is currently producing hundreds of peer-reviewed articles and several dedicated conferences and workshops each year. This level of productivity is reflective of the large and continually growing enthusiasm by the scientific community, funding agencies, and the public.
Keywords: Brain-computer interface (BCI)

Proceedings of the Seventh International Workshop on Advances in Electrocorticography. - A L Ritaccio; Matsumoto, Riki; Morrell, Martha; Kamada, Kyousuke; Koubeissi, Mohamad; Poeppel, David; Lachaux, Jean-Philippe; Yanagisawa, Yakufumi; Hirata, Masayuki; Guger, Christoph; Gerwin Schalk (Epilepsy & behavior : E&B, 2015)
The Seventh International Workshop on Advances in Electrocorticography (ECoG) convened in Washington, DC, on November 13-14, 2014. Electrocorticography-based research continues to proliferate widely across basic science and clinical disciplines. The 2014 workshop highlighted advances in neurolinguistics, brain-computer interface, functional mapping, and seizure termination facilitated by advances in the recording and analysis of the ECoG signal. The following proceedings document summarizes the content of this successful multidisciplinary gathering.
Keywords: Humans

Restoring walking after spinal cord injury: operant conditioning of spinal reflexes can help. - Thompson, Aiko K; Jonathan Wolpaw (Neuroscientist, 2015)
People with incomplete spinal cord injury (SCI) frequently suffer motor disabilities due to spasticity and poor muscle control, even after conventional therapy. Abnormal spinal reflex activity often contributes to these problems. Operant conditioning of spinal reflexes, which can target plasticity to specific reflex pathways, can enhance recovery. In rats in which a right lateral column lesion had weakened right stance and produced an asymmetrical gait, up-conditioning of the right soleus H-reflex, which increased muscle spindle afferent excitation of soleus, strengthened right stance and eliminated the asymmetry. In people with hyperreflexia due to incomplete SCI, down-conditioning of the soleus H-reflex improved walking speed and symmetry. Furthermore, modulation of electromyographic activity during walking improved bilaterally, indicating that a protocol that targets plasticity to a specific pathway can trigger widespread plasticity that improves recovery far beyond that attributable to the change in the targeted pathway. These improvements were apparent to people in their daily lives. They reported walking faster and farther, and noted less spasticity and better balance. Operant conditioning protocols could be developed to modify other spinal reflexes or corticospinal connections; and could be combined with other therapies to enhance recovery in people with SCI or other neuromuscular disorders.
Keywords: Learning; Locomotion; spinal cord injury; spinal cord plasticity; spinal reflexes

Retraction Note: Comparison of the sagittal profiles among thoracic idiopathic scoliosis patients with different Cobb angles and growth potentials. - Ran, Bo; Zhang, Guo-You; Shen, Feng; Chen, Jia-Yu; Wu, Ji-Bin; Zhao, Feng-Chao; Guo, Kai-Jin; Qi, Dun-Yi; Zhou, Bing; Xiang Yang Chen; Zhang, Xin-Zhu; Qiao, Yue-Hua; et al. (J Orthop Surg Res, 2015)

Spinal Cord Injury Grand Rounds, Medical University of South Carolina, Charleston, SC - Jonathan Wolpaw (2015)

Summer School on Neurorehabilitation, Valencia, Spain - Jonathan Wolpaw (2015)

Symposium, American Congress of Rehabilitation Medicine, Dallas, TX - Jonathan Wolpaw (2015)

Symposium, Annual Meeting of the Society for Neuroscience, Chicago, IL - Jonathan Wolpaw (2015)

Targeted neuroplasticity for rehabilitation. - Thompson, Aiko K; Jonathan Wolpaw (Progress in Brain Research, 2015)
An operant-conditioning protocol that bases reward on the electromyographic response produced by a specific CNS pathway can change that pathway. For example, in both animals and people, an operant-conditioning protocol can increase or decrease the spinal stretch reflex or its electrical analog, the H-reflex. Reflex change is associated with plasticity in the pathway of the reflex as well as elsewhere in the spinal cord and brain. Because these pathways serve many different behaviors, the plasticity produced by this conditioning can change other behaviors. Thus, in animals or people with partial spinal cord injuries, appropriate reflex conditioning can improve locomotion. Furthermore, in people with spinal cord injuries, appropriate reflex conditioning can trigger widespread beneficial plasticity. This wider plasticity appears to reflect an iterative process through which the multiple behaviors in the individual's repertoire negotiate the properties of the spinal neurons and synapses that they all use. Operant-conditioning protocols are a promising new therapeutic method that could complement other rehabilitation methods and enhance functional recovery. Their successful use requires strict adherence to appropriately designed procedures, as well as close attention to accommodating and engaging the individual subject in the conditioning process.
Keywords: activity-dependent plasticity; H-Reflex; operant conditioning; Rehabilitation; spinal cord injury; spinal reflex

Toward independent home use of brain-computer interfaces: a decision algorithm for selection of potential end-users. - Kübler, Andrea; Holz, Elisa Mira; Sellers, Eric W; Theresa M Vaughan (Arch Phys Med Rehabil, 2015)
Noninvasive brain-computer interfaces (BCIs) use scalp-recorded electrical activity from the brain to control an application. Over the past 20 years, research demonstrating that BCIs can provide communication and control to individuals with severe motor impairment has increased almost exponentially. Although considerable effort has been dedicated to offline analysis for improving signal detection and translation, far less effort has been made to conduct online studies with target populations. Thus, there remains a great need for both long-term and translational BCI studies that include individuals with disabilities in their own homes. Completing these studies is the only sure means to answer questions about BCI utility and reliability. Here we suggest an algorithm for candidate selection for electroencephalographic (EEG)-based BCI home studies. This algorithm takes into account BCI end-users and their environment and should assist in study design and substantially improve subject retention rates, thereby improving the overall efficacy of BCI home studies. It is the result of a workshop at the Fifth International BCI Meeting that allowed us to leverage the expertise of multiple research laboratories and people from multiple backgrounds in BCI research.
Keywords: Algorithms; brain-computer interfaces; Cognition; Disabled Persons; Electroencephalography; Environment; Humans; Patient Selection; Physical Therapy Modalities

Towards an Auditory Attention BCI - Peter Brunner; Dijkstra, K.; Coon, W.G.; Mellinger, Jürgen; A L Ritaccio; Gerwin Schalk (Brain-Computer Interface Research: A State-of-the-Art Summary, 2015)
People affected by severe neuro-degenerative diseases (e.g., late-stage amyotrophic lateral sclerosis (ALS) or locked-in syndrome) eventually lose all muscular control and are no longer able to gesture or speak. For this population, an auditory BCI is one of only a few remaining means of communication. All currently used auditory BCIs require a relatively artificial mapping between a stimulus and a communication output. This mapping is cumbersome to learn and use. Recent studies suggest that electrocorticographic (ECoG) signals in the gamma band (i.e., 70–170 Hz) can be used to infer the identity of auditory speech stimuli, effectively removing the need to learn such an artificial mapping. However, BCI systems that use this physiological mechanism for communication purposes have not yet been described. In this study, we explore this possibility by implementing a BCI2000-based real-time system that uses ECoG signals to identify the attended speaker.

An update on oligosaccharides and their esters from traditional chinese medicines: chemical structures and biological activities. - Xiang Yang Chen; Wang, Ru-Feng; Liu, Bin (Evid Based Complement Alternat Med, 2015)
A great number of naturally occurring oligosaccharides and oligosaccharide esters have been isolated from traditional Chinese medicinal plants, which are used widely in Asia and show prominent curative effects in the prevention and treatment of kinds of diseases. Numerous in vitro and in vivo experiments have revealed that oligosaccharides and their esters exhibited various activities, including antioxidant, antidepressant, cytotoxic, antineoplastic, anti-inflammatory, neuroprotective, cerebral protective, antidiabetic, plant growth-regulatory, and immunopotentiating activities. This review summarizes the investigations on the distribution, chemical structures, and bioactivities of natural oligosaccharides and their esters from traditional Chinese medicines between 2003 and 2013.

Word-level language modeling for P300 spellers based on discriminative graphical models. - Saa, Jaime F Delgado; Pesters, Adriana de; Dennis J. McFarland; Çetin, Müjdat (J Neural Eng, 2015)
OBJECTIVE: In this work we propose a probabilistic graphical model framework that uses language priors at the level of words as a mechanism to increase the performance of P300-based spellers. APPROACH: This paper is concerned with brain-computer interfaces based on P300 spellers. Motivated by P300 spelling scenarios involving communication based on a limited vocabulary, we propose a probabilistic graphical model framework and an associated classification algorithm that uses learned statistical models of language at the level of words. Exploiting such high-level contextual information helps reduce the error rate of the speller. MAIN RESULTS: Our experimental results demonstrate that the proposed approach offers several advantages over existing methods. Most importantly, it increases the classification accuracy while reducing the number of times the letters need to be flashed, increasing the communication rate of the system. SIGNIFICANCE: The proposed approach models all the variables in the P300 speller in a unified framework and has the capability to correct errors in previous letters in a word, given the data for the current one. The structure of the model we propose allows the use of efficient inference algorithms, which in turn makes it possible to use this approach in real-time applications.
Keywords: Brain Computer Interfaces; inference algorithms; language models; P300 speller; probabilistic graphical models

Adaptive spatio-temporal filtering for movement related potentials in EEG-based brain-computer interfaces. - Lu, Jun; Xie, Kan; Dennis J. McFarland (IEEE Trans Neural Syst Rehabil Eng, 2014)
Movement related potentials (MRPs) are used as features in many brain-computer interfaces (BCIs) based on electroencephalogram (EEG). MRP feature extraction is challenging since EEG is noisy and varies between subjects. Previous studies used spatial and spatio-temporal filtering methods to deal with these problems. However, they did not optimize temporal information or may have been susceptible to overfitting when training data are limited and the feature space is of high dimension. Furthermore, most of these studies manually select data windows and low-pass frequencies. We propose an adaptive spatio-temporal (AST) filtering method to model MRPs more accurately in lower dimensional space. AST automatically optimizes all parameters by employing a Gaussian kernel to construct a low-pass time-frequency filter and a linear ridge regression (LRR) algorithm to compute a spatial filter. Optimal parameters are simultaneously sought by minimizing leave-one-out cross-validation error through gradient descent. Using four BCI datasets from 12 individuals, we compare the performances of AST filter to two popular methods: the discriminant spatial pattern filter and regularized spatio-temporal filter. The results demonstrate that our AST filter can make more accurate predictions and is computationally feasible.
Keywords: Algorithms; Artificial Intelligence; brain-computer interfaces; Data Interpretation, Statistical; Electroencephalography; Evoked Potentials, Motor; Humans; Imagination; Motor Cortex; Movement; Pattern Recognition, Automated; Reproducibility of Results; Sensitivity and Specificity; Signal Processing, Computer-Assisted; Spatio-Temporal Analysis

The advantages of the surface Laplacian in brain-computer interface research. - Dennis J. McFarland (Int J Psychophysiol, 2014)
Brain-computer interface (BCI) systems frequently use signal processing methods, such as spatial filtering, to enhance performance. The surface Laplacian can reduce spatial noise and aid in identification of sources. In BCI research, these two functions of the surface Laplacian correspond to prediction accuracy and signal orthogonality. In the present study, an off-line analysis of data from a sensorimotor rhythm-based BCI task dissociated these functions of the surface Laplacian by comparing nearest-neighbor and next-nearest neighbor Laplacian algorithms. The nearest-neighbor Laplacian produced signals that were more orthogonal while the next-nearest Laplacian produced signals that resulted in better accuracy. Both prediction and signal identification are important for BCI research. Better prediction of user's intent produces increased speed and accuracy of communication and control. Signal identification is important for ruling out the possibility of control by artifacts. Identifying the nature of the control signal is relevant both to understanding exactly what is being studied and in terms of usability for individuals with limited motor control.
Keywords: brain-computer interface; sensorimotor rhythms; surface laplacian

American Psychological Association Ann Mtg, Washington, DC - Jonathan Wolpaw (2014)

Assessing dynamics, spatial scale, and uncertainty in task-related brain network analyses. - Stephen, Emily P; Lepage, Kyle Q; Eden, Uri T; Peter Brunner; Gerwin Schalk; Jonathan S Brumberg; Guenther, Frank H; Kramer, Mark A (Frontiers in Computational Neuroscience, 2014)
The brain is a complex network of interconnected elements, whose interactions evolve dynamically in time to cooperatively perform specific functions. A common technique to probe these interactions involves multi-sensor recordings of brain activity during a repeated task. Many techniques exist to characterize the resulting task-related activity, including establishing functional networks, which represent the statistical associations between brain areas. Although functional network inference is commonly employed to analyze neural time series data, techniques to assess the uncertainty—both in the functional network edges and the corresponding aggregate measures of network topology—are lacking. To address this, we describe a statistically principled approach for computing uncertainty in functional networks and aggregate network measures in task-related data. The approach is based on a resampling procedure that utilizes the trial structure common in experimental recordings. We show in simulations that this approach successfully identifies functional networks and associated measures of confidence emergent during a task in a variety of scenarios, including dynamically evolving networks. In addition, we describe a principled technique for establishing functional networks based on predetermined regions of interest using canonical correlation. Doing so provides additional robustness to the functional network inference. Finally, we illustrate the use of these methods on example invasive brain voltage recordings collected during an overt speech task. The general strategy described here—appropriate for static and dynamic network inference and different statistical measures of coupling—permits the evaluation of confidence in network measures in a variety of settings common to neuroscience.
Keywords: canonical correlation; coherence; ECoG; EEG; functional connectivity; MEG

Brain-computer interface (BCI) evaluation in people with amyotrophic lateral sclerosis. - McCane, Lynn M; Sellers, Eric W; Dennis J. McFarland; Mak, Joseph N; Carmack, C Steve; Zeitlin, Debra; Jonathan Wolpaw; Theresa M Vaughan (Amyotroph Lateral Scler Frontotemporal Degener, 2014)
Brain-computer interfaces (BCIs) might restore communication to people severely disabled by amyotrophic lateral sclerosis (ALS) or other disorders. We sought to: 1) define a protocol for determining whether a person with ALS can use a visual P300-based BCI; 2) determine what proportion of this population can use the BCI; and 3) identify factors affecting BCI performance. Twenty-five individuals with ALS completed an evaluation protocol using a standard 6 × 6 matrix and parameters selected by stepwise linear discrimination. With an 8-channel EEG montage, the subjects fell into two groups in BCI accuracy (chance accuracy 3%). Seventeen averaged 92 (± 3)% (range 71-100%), which is adequate for communication (G70 group). Eight averaged 12 (± 6)% (range 0-36%), inadequate for communication (L40 subject group). Performance did not correlate with disability: 11/17 (65%) of G70 subjects were severely disabled (i.e. ALSFRS-R < 5). All L40 subjects had visual impairments (e.g. nystagmus, diplopia, ptosis). P300 was larger and more anterior in G70 subjects. A 16-channel montage did not significantly improve accuracy. In conclusion, most people severely disabled by ALS could use a visual P300-based BCI for communication. In those who could not, visual impairment was the principal obstacle. For these individuals, auditory P300-based BCIs might be effective.
Keywords: Adult; Aged; Amyotrophic Lateral Sclerosis; Biofeedback, Psychology; brain-computer interfaces; Communication Disorders; Electroencephalography; Event-Related Potentials, P300; Female; Humans; Male; Middle Aged; Online Systems; Photic Stimulation; Psychomotor Performance; Reaction Time

C. Warren Olanow Lecture - Jonathan Wolpaw (2014)
Mt. Sinai School of Medicine, New York, NY

Decoding spectrotemporal features of overt and covert speech from the human cortex. - Martin, Stéphanie; Peter Brunner; Holdgraf, Chris; Heinze, Hans-Jochen; Nathan E. Crone; Rieger, Jochem; Gerwin Schalk; Robert T. Knight; Pasley, Brian N. (Frontiers in Neuroengineering, 2014)
Auditory perception and auditory imagery have been shown to activate overlapping brain regions. We hypothesized that these phenomena also share a common underlying neural representation. To assess this, we used electrocorticography intracranial recordings from epileptic patients performing an out loud or a silent reading task. In these tasks, short stories scrolled across a video screen in two conditions: subjects read the same stories both aloud (overt) and silently (covert). In a control condition the subject remained in a resting state. We first built a high gamma (70–150 Hz) neural decoding model to reconstruct spectrotemporal auditory features of self-generated overt speech. We then evaluated whether this same model could reconstruct auditory speech features in the covert speech condition. Two speech models were tested: a spectrogram and a modulation-based feature space. For the overt condition, reconstruction accuracy was evaluated as the correlation between original and predicted speech features, and was significant in each subject (p < 0.00001; paired two-sample t-test). For the covert speech condition, dynamic time warping was first used to realign the covert speech reconstruction with the corresponding original speech from the overt condition. Reconstruction accuracy was then evaluated as the correlation between original and reconstructed speech features. Covert reconstruction accuracy was compared to the accuracy obtained from reconstructions in the baseline control condition. Reconstruction accuracy for the covert condition was significantly better than for the control condition (p < 0.005; paired two-sample t-test). The superior temporal gyrus, pre- and post-central gyrus provided the highest reconstruction information. The relationship between overt and covert speech reconstruction depended on anatomy. These results provide evidence that auditory representations of covert speech can be reconstructed from models that are built from an overt speech data set, supporting a partially shared neural substrate.
Keywords: covert speech; decoding model; Electrocorticography; pattern recognition; speech production

Distinguished Lectures in Biological Engineering - Jonathan Wolpaw (2014)
EPFL, Lausanne, Switzerland

ECoG high gamma activity reveals distinct cortical representations of lyrics passages, harmonic and timbre-related changes in a rock song. - Sturm, Irene; Benjamin Blankertz; Potes, Cristhian; Gerwin Schalk; Curio, Gabriel (Front Hum Neurosci, 2014)
Listening to music moves our minds and moods, stirring interest in its neural underpinnings. A multitude of compositional features drives the appeal of natural music. How such original music, where a composer's opus is not manipulated for experimental purposes, engages a listener's brain has not been studied until recently. Here, we report an in-depth analysis of two electrocorticographic (ECoG) data sets obtained over the left hemisphere in ten patients during presentation of either a rock song or a read-out narrative. First, the time courses of five acoustic features (intensity, presence/absence of vocals with lyrics, spectral centroid, harmonic change, and pulse clarity) were extracted from the audio tracks and found to be correlated with each other to varying degrees. In a second step, we uncovered the specific impact of each musical feature on ECoG high-gamma power (70-170 Hz) by calculating partial correlations to remove the influence of the other four features. In the music condition, the onset and offset of vocal lyrics in ongoing instrumental music was consistently identified within the group as the dominant driver for ECoG high-gamma power changes over temporal auditory areas, while concurrently subject-individual activation spots were identified for sound intensity, timbral, and harmonic features. The distinct cortical activations to vocal speech-related content embedded in instrumental music directly demonstrate that song integrated in instrumental music represents a distinct dimension in complex music. In contrast, in the speech condition, the full sound envelope was reflected in the high gamma response rather than the onset or offset of the vocal lyrics. This demonstrates how the contributions of stimulus features that modulate the brain response differ across the two examples of a full-length natural stimulus, which suggests a context-dependent feature selection in the processing of complex auditory stimuli.
Keywords: acoustic features; electrocorticography (ECoG); high gamma; music processing; natural music

Effects of pamidronate disodium on the loss of osteoarthritic subchondral bone and the expression of cartilaginous and subchondral osteoprotegerin and RANKL in rabbits. - Lv, You; Xia, Jie-yun; Xiang Yang Chen; Zhao, Hui; Yan, Hai-cui; Yang, Han-shi; Li, Qiang; Fan, Yu-xin; Guo, Kai-Jin; Xiang Yang Chen (BMC Musculoskelet Disord, 2014)
BACKGROUND: Osteoarthritis (OA) is a major health problem in the increasingly elderly population. Therefore, it is crucial to prevent and treat OA at an early stage. The present study investigated whether pamidronate disodium (PAM), a bone-loss inhibitor, can significantly prevent or reverse the progression of early anterior cruciate ligament transection (ACLT)-induced OA. Whether therapeutic intervention is associated with regulation of the expression of osteoprotegerin (OPG), receptor activator of nuclear factor-κB ligand (RANKL), metalloproteinase-9 (MMP-9) or Toll-like receptor-4 (TLR-4) in cartilage and/or subchondral bone was also investigated. METHODS: 60 New Zealand rabbits were randomized into four groups: Sham-operated (n = 20); ACLT (n = 20); short-term treatment with PAM (PAM-S, n = 10) and long-term treatment with PAM (PAM-L, n = 10). For cartilage and subchondral bone testing, rabbits from Sham and ACLT groups were harvested at 2, 4, 6, and 14 weeks. Rabbits were given PAM from the 4th week after ACLT operation in PAM-S and PAM-L group, and were harvested at 6 and 14 weeks, respectively. Trabecular characteristics and cartilage changes were detected using Micro-CT, safranin O and rapid green staining, respectively. Immunohistochemical staining for OPG and RANKL were also performed. OPG, RANKL, MMP-9 and TLR-4 expression was evaluated by western blot analysis. RESULTS: Micro-CT and histology analyses indicated that PAM treatment for 2 or 10 weeks could completely prevent or reverse osteoarthritic subchondral bone loss and cartilage surface erosion. Immunohistochemistry and western blot analysis indicated that expression of OPG and RANKL increased, although RANKL expression increased more significantly than that of OPG. Therefore the ratio of OPG to RANKL was lower in the ACLT group. However, the ratio of OPG to RANKL in the PAM group was significantly higher than that in the ACLT group. Additionally, expression of MMP-9 and TLR-4 were upregulated in the ACLT group and downregulated in the PAM treated groups. CONCLUSIONS: PAM can significantly inhibit and even reverse early osteoarthritic subchondral bone loss, thus alleviating the process of cartilaginous degeneration. The mechanisms involved may be associated with the upregulation of OPG expression, and downregulation of RANKL, MMP-9 and TLR-4 expression.
Keywords: cartilage; osteoarthritis; osteoprotegerin (OPG); pamidronate disodium; Receptor activator of nuclear factor-κ B ligand (RANKL); subchondral bone

Erratum: comparison of the sagittal profiles among thoracic idiopathic scoliosis patients with different Cobb angles and growth potentials. - Ran, Bo; Xiang Yang Chen; Zhang, Guo-You; Shen, Feng; Chen, Jia-Yu; Wu, Ji-Bin; Zhao, Feng-Chao; Qiao, Dun-Yi; Zhou, Bing; Zhang, Xin-Zhu; Qiao, Yue-Hua; Guan, Jun-Hui; et al. (J Orthop Surg Res, 2014)

A general method for assessing brain–computer interface performance and its limitations. - Jeremy Jeremy Hill; Häuser, Ann-Katrin; Gerwin Schalk (Journal of Neural Engineering, 2014)
Objective. When researchers evaluate brain–computer interface (BCI) systems, we want quantitative answers to questions such as: How good is the system's performance? How good does it need to be? and: Is it capable of reaching the desired level in future? In response to the current lack of objective, quantitative, study-independent approaches, we introduce methods that help to address such questions. We identified three challenges: (I) the need for efficient measurement techniques that adapt rapidly and reliably to capture a wide range of performance levels; (II) the need to express results in a way that allows comparison between similar but non-identical tasks; (III) the need to measure the extent to which certain components of a BCI system (e.g. the signal processing pipeline) not only support BCI performance, but also potentially restrict the maximum level it can reach. Approach. For challenge (I), we developed an automatic staircase method that adjusted task difficulty adaptively along a single abstract axis. For challenge (II), we used the rate of information gain between two Bernoulli distributions: one reflecting the observed success rate, the other reflecting chance performance estimated by a matched random-walk method. This measure includes Wolpaw's information transfer rate as a special case, but addresses the latter's limitations including its restriction to item-selection tasks. To validate our approach and address challenge (III), we compared four healthy subjects' performance using an EEG-based BCI, a 'Direct Controller' (a high-performance hardware input device), and a 'Pseudo-BCI Controller' (the same input device, but with control signals processed by the BCI signal processing pipeline). Main results. Our results confirm the repeatability and validity of our measures, and indicate that our BCI signal processing pipeline reduced attainable performance by about 33% (21 bits/min). Significance. Our approach provides a flexible basis for evaluating BCI performance and its limitations, across a wide range of tasks and task difficulties.
Keywords: brain-computer interface; information gain; information transfer rate; Neuroprosthetics; performance evaluation

Invited Speaker - Jonathan Wolpaw (2014)
Brain Research Institute, ETH, Zurich, Switzerland

Invited Speaker - Jonathan Wolpaw (2014)
International Collaboration on Repair Discoveries (ICORD), Vancouver, BC

Keynote Speaker - Jonathan Wolpaw (2014)
UNYTE Translational Research Network, Univ of Rochester, NY

Localizing ECoG electrodes on the cortical anatomy without post-implantation imaging. - Disha Gupta; Jeremy Jeremy Hill; Adamo, Matthew A; A L Ritaccio; Gerwin Schalk (Neuroimage Clin, 2014)
INTRODUCTION: Electrocorticographic (ECoG) grids are placed subdurally on the cortex in people undergoing cortical resection to delineate eloquent cortex. ECoG signals have high spatial and temporal resolution and thus can be valuable for neuroscientific research. The value of these data is highest when they can be related to the cortical anatomy. Existing methods that establish this relationship rely either on post-implantation imaging using computed tomography (CT), magnetic resonance imaging (MRI) or X-Rays, or on intra-operative photographs. For research purposes, it is desirable to localize ECoG electrodes on the brain anatomy even when post-operative imaging is not available or when intra-operative photographs do not readily identify anatomical landmarks. METHODS: We developed a method to co-register ECoG electrodes to the underlying cortical anatomy using only a pre-operative MRI, a clinical neuronavigation device (such as BrainLab VectorVision), and fiducial markers. To validate our technique, we compared our results to data collected from six subjects who also had post-grid implantation imaging available. We compared the electrode coordinates obtained by our fiducial-based method to those obtained using existing methods, which are based on co-registering pre- and post-grid implantation images. RESULTS: Our fiducial-based method agreed with the MRI-CT method to within an average of 8.24 mm (mean, median = 7.10 mm) across 6 subjects in 3 dimensions. It showed an average discrepancy of 2.7 mm when compared to the results of the intra-operative photograph method in a 2D coordinate system. As this method does not require post-operative imaging such as CTs, our technique should prove useful for research in intra-operative single-stage surgery scenarios. To demonstrate the use of our method, we applied our method during real-time mapping of eloquent cortex during a single-stage surgery. The results demonstrated that our method can be applied intra-operatively in the absence of post-operative imaging to acquire ECoG signals that can be valuable for neuroscientific investigations.
Keywords: auditory processing; electrocorticography (ECoG); electrode localization; fiducials; interaoperative localization

Locomotor impact of beneficial or nonbeneficial H-reflex conditioning after spinal cord injury. - Yi Chen; Lu Chen; Liu, Rongliang; Wang, Yu; Xiang Yang Chen; Jonathan Wolpaw (J Neurophysiol, 2014)
When new motor learning changes neurons and synapses in the spinal cord, it may affect previously learned behaviors that depend on the same spinal neurons and synapses. To explore these effects, we used operant conditioning to strengthen or weaken the right soleus H-reflex pathway in rats in which a right spinal cord contusion had impaired locomotion. When up-conditioning increased the H-reflex, locomotion improved. Steps became longer, and step-cycle asymmetry (i.e., limping) disappeared. In contrast, when down-conditioning decreased the H-reflex, locomotion did not worsen. Steps did not become shorter, and asymmetry did not increase. Electromyographic and kinematic analyses explained how H-reflex increase improved locomotion and why H-reflex decrease did not further impair it. Although the impact of up-conditioning or down-conditioning on the H-reflex pathway was still present during locomotion, only up-conditioning affected the soleus locomotor burst. Additionally, compensatory plasticity apparently prevented the weaker H-reflex pathway caused by down-conditioning from weakening the locomotor burst and further impairing locomotion. The results support the hypothesis that the state of the spinal cord is a "negotiated equilibrium" that serves all the behaviors that depend on it. When new learning changes the spinal cord, old behaviors undergo concurrent relearning that preserves or improves their key features. Thus, if an old behavior has been impaired by trauma or disease, spinal reflex conditioning, by changing a specific pathway and triggering a new negotiation, may enable recovery beyond that achieved simply by practicing the old behavior. Spinal reflex conditioning protocols might complement other neurorehabilitation methods and enhance recovery.
Keywords: Animals; Conditioning, Operant; Female; H-Reflex; Learning; Locomotion; Male; Rats; Rats, Sprague-Dawley; Spinal Cord Injuries

Long-term recording of external urethral sphincter EMG activity in unanesthetized, unrestrained rats. - LaPallo, Brandon K; Jonathan Wolpaw; Xiang Yang Chen; Jonathan S. Carp (Am J Physiol Renal Physiol, 2014)
The external urethral sphincter muscle (EUS) plays an important role in urinary function and often contributes to urinary dysfunction. EUS study would benefit from methodology for longitudinal recording of electromyographic activity (EMG) in unanesthetized animals, but this muscle is a poor substrate for chronic intramuscular electrodes, and thus the required methodology has not been available. We describe a method for long-term recording of EUS EMG by implantation of fine wires adjacent to the EUS that are secured to the pubic bone. Wires pass subcutaneously to a skull-mounted plug and connect to the recording apparatus by a flexible cable attached to a commutator. A force transducer-mounted cup under a metabolic cage collected urine, allowing recording of EUS EMG and voided urine weight without anesthesia or restraint. Implant durability permitted EUS EMG recording during repeated (up to 3 times weekly) 24-h sessions for more than 8 wk. EMG and voiding properties were stable over weeks 2-8. The degree of EUS phasic activity (bursting) during voiding was highly variable, with an average of 25% of voids not exhibiting bursting. Electrode implantation adjacent to the EUS yielded stable EMG recordings over extended periods and eliminated the confounding effects of anesthesia, physical restraint, and the potential for dislodgment of the chronically implanted intramuscular electrodes. These results show that micturition in unanesthetized, unrestrained rats is usually, but not always, associated with EUS bursting. This methodology is applicable to studying EUS behavior during progression of gradually evolving disease and injury models and in response to therapeutic interventions.
Keywords: Animals; Electrodes, Implanted; Electromyography; Female; Pubic Bone; Rats; Rats, Sprague-Dawley; Urethra; Urination; Urodynamics

Modality specificity is the preferred method for diagnosing the auditory processing disorder (APD): response to Moore and Ferguson. - Dennis J. McFarland; Cacace, Anthony T (J Am Acad Audiol, 2014)
Keywords: Auditory Perception; Auditory Perceptual Disorders; Evoked Potentials, Auditory, Brain Stem; Humans; Neuropsychological Tests; Psychoacoustics

Modality Specificity trumps other methods for diagnosing the auditory processing disorder (APD): response to Dillon et al. - Cacace, Anthony T; Dennis J. McFarland (J Am Acad Audiol, 2014)
Keywords: Auditory Perception; Auditory Perceptual Disorders; Evoked Potentials, Auditory, Brain Stem; Humans; Neuropsychological Tests; Psychoacoustics

Neurology Grand Rounds - Jonathan Wolpaw (2014)
Penn State University, Hershey, PA

Operant conditioning of spinal reflexes: from basic science to clinical therapy. - Thompson, Aiko K; Jonathan Wolpaw (Front Integr Neurosci, 2014)
New appreciation of the adaptive capabilities of the nervous system, recent recognition that most spinal cord injuries are incomplete, and progress in enabling regeneration are generating growing interest in novel rehabilitation therapies. Here we review the 35-year evolution of one promising new approach, operant conditioning of spinal reflexes. This work began in the late 1970's as basic science; its purpose was to develop and exploit a uniquely accessible model for studying the acquisition and maintenance of a simple behavior in the mammalian central nervous system (CNS). The model was developed first in monkeys and then in rats, mice, and humans. Studies with it showed that the ostensibly simple behavior (i.e., a larger or smaller reflex) rests on a complex hierarchy of brain and spinal cord plasticity; and current investigations are delineating this plasticity and its interactions with the plasticity that supports other behaviors. In the last decade, the possible therapeutic uses of reflex conditioning have come under study, first in rats and then in humans. The initial results are very exciting, and they are spurring further studies. At the same time, the original basic science purpose and the new clinical purpose are enabling and illuminating each other in unexpected ways. The long course and current state of this work illustrate the practical importance of basic research and the valuable synergy that can develop between basic science questions and clinical needs.
Keywords: H-Reflex; learning and memory; Locomotion; spinal cord injury; spinal cord plasticity

Operant conditioning of the soleus H-reflex does not induce long-term changes in the gastrocnemius H-reflexes and does not disturb normal locomotion in humans. - Makihara, Yukiko; Segal, Richard L; Jonathan Wolpaw; Thompson, Aiko K (J Neurophysiol, 2014)
In normal animals, operant conditioning of the spinal stretch reflex or the H-reflex has lesser effects on synergist muscle reflexes. In rats and people with incomplete spinal cord injury (SCI), soleus H-reflex operant conditioning can improve locomotion. We studied in normal humans the impact of soleus H-reflex down-conditioning on medial (MG) and lateral gastrocnemius (LG) H-reflexes and on locomotion. Subjects completed 6 baseline and 30 conditioning sessions. During conditioning trials, the subject was encouraged to decrease soleus H-reflex size with the aid of visual feedback. Every sixth session, MG and LG H-reflexes were measured. Locomotion was assessed before and after conditioning. In successfully conditioned subjects, the soleus H-reflex decreased 27.2%. This was the sum of within-session (task dependent) adaptation (13.2%) and across-session (long term) change (14%). The MG H-reflex decreased 14.5%, due mainly to task-dependent adaptation (13.4%). The LG H-reflex showed no task-dependent adaptation or long-term change. No consistent changes were detected across subjects in locomotor H-reflexes, EMG activity, joint angles, or step symmetry. Thus, in normal humans, soleus H-reflex down-conditioning does not induce long-term changes in MG/LG H-reflexes and does not change locomotion. In these subjects, task-dependent adaptation of the soleus H-reflex is greater than it is in people with SCI, whereas long-term change is less. This difference from results in people with SCI is consistent with the fact that long-term change is beneficial in people with SCI, since it improves locomotion. In contrast, in normal subjects, long-term change is not beneficial and may necessitate compensatory plasticity to preserve satisfactory locomotion.
Keywords: Learning; plasticity; Rehabilitation; Spinal Cord; synergists

Persistent beneficial impact of H-reflex conditioning in spinal cord-injured rats. - Yi Chen; Lu Chen; Wang, Yu; Jonathan Wolpaw; Xiang Yang Chen (J Neurophysiol, 2014)
Operant conditioning of a spinal cord reflex can improve locomotion in rats and humans with incomplete spinal cord injury. This study examined the persistence of its beneficial effects. In rats in which a right lateral column contusion injury had produced asymmetric locomotion, up-conditioning of the right soleus H-reflex eliminated the asymmetry while down-conditioning had no effect. After the 50-day conditioning period ended, the H-reflex was monitored for 100 [±9 (SD)] (range 79-108) more days and locomotion was then reevaluated. After conditioning ended in up-conditioned rats, the H-reflex continued to increase, and locomotion continued to improve. In down-conditioned rats, the H-reflex decrease gradually disappeared after conditioning ended, and locomotion at the end of data collection remained as impaired as it had been before and immediately after down-conditioning. The persistence (and further progression) of H-reflex increase but not H-reflex decrease in these spinal cord-injured rats is consistent with the fact that up-conditioning improved their locomotion while down-conditioning did not. That is, even after up-conditioning ended, the up-conditioned H-reflex pathway remained adaptive because it improved locomotion. The persistence and further enhancement of the locomotor improvement indicates that spinal reflex conditioning protocols might supplement current therapies and enhance neurorehabilitation. They may be especially useful when significant spinal cord regeneration becomes possible and precise methods for retraining the regenerated spinal cord are needed.
Keywords: H-reflex conditioning; Learning; Locomotion; Memory; Motor control; Rehabilitation; spinal cord injury; spinal cord plasticity

A practical, intuitive brain-computer interface for communicating 'yes' or 'no' by listening. - Jeremy Jeremy Hill; Ricci, Erin; Haider, Sameah; McCane, Lynn M; Susan M Heckman; Jonathan Wolpaw; Theresa M Vaughan (J Neural Eng, 2014)
OBJECTIVE: Previous work has shown that it is possible to build an EEG-based binary brain-computer interface system (BCI) driven purely by shifts of attention to auditory stimuli. However, previous studies used abrupt, abstract stimuli that are often perceived as harsh and unpleasant, and whose lack of inherent meaning may make the interface unintuitive and difficult for beginners. We aimed to establish whether we could transition to a system based on more natural, intuitive stimuli (spoken words 'yes' and 'no') without loss of performance, and whether the system could be used by people in the locked-in state. APPROACH: We performed a counterbalanced, interleaved within-subject comparison between an auditory streaming BCI that used beep stimuli, and one that used word stimuli. Fourteen healthy volunteers performed two sessions each, on separate days. We also collected preliminary data from two subjects with advanced amyotrophic lateral sclerosis (ALS), who used the word-based system to answer a set of simple yes-no questions. MAIN RESULTS: The N1, N2 and P3 event-related potentials elicited by words varied more between subjects than those elicited by beeps. However, the difference between responses to attended and unattended stimuli was more consistent with words than beeps. Healthy subjects' performance with word stimuli (mean 77% ± 3.3 s.e.) was slightly but not significantly better than their performance with beep stimuli (mean 73% ± 2.8 s.e.). The two subjects with ALS used the word-based BCI to answer questions with a level of accuracy similar to that of the healthy subjects. SIGNIFICANCE: Since performance using word stimuli was at least as good as performance using beeps, we recommend that auditory streaming BCI systems be built with word stimuli to make the system more pleasant and intuitive. Our preliminary data show that word-based streaming BCI is a promising tool for communication by people who are locked in.
Keywords: Adult; Aged; Algorithms; Auditory Perception; brain-computer interfaces; Communication Aids for Disabled; Electroencephalography; Equipment Design; Equipment Failure Analysis; Female; Humans; Male; Man-Machine Systems; Middle Aged; Quadriplegia; Treatment Outcome; User-Computer Interface

Proceedings of the Fifth International Workshop on Advances in Electrocorticography. - A L Ritaccio; Peter Brunner; Gunduz, Aysegul; Hermes, Dora; Hirsch, Lawrence J; Jacobs, Joshua; Kamada, Kyousuke; Kastner, Sabine; Robert T. Knight; Lesser, Ronald P; Miller, Kai; Sejnowski, Terrence; et al. (Epilepsy Behav, 2014)
The Fifth International Workshop on Advances in Electrocorticography convened in San Diego, CA, on November 7-8, 2013. Advancements in methodology, implementation, and commercialization across both research and in the interval year since the last workshop were the focus of the gathering. Electrocorticography (ECoG) is now firmly established as a preferred signal source for advanced research in functional, cognitive, and neuroprosthetic domains. Published output in ECoG fields has increased tenfold in the past decade. These proceedings attempt to summarize the state of the art.
Keywords: Brain Mapping; brain-computer interface; electrical stimulation mapping; Electrocorticography; functional mapping; Gamma-frequency electroencephalography; High-frequency oscillations; Neuroprosthetics; Seizure detection; Subdural grid

Real-time functional mapping: potential tool for improving language outcome in pediatric epilepsy surgery. - Korostenskaja, Milena; Chen, Po-Ching; Salinas, Christine M; Westerveld, Michael; Peter Brunner; Gerwin Schalk; Cook, Jane C; Baumgartner, James; Lee, Ki H (J Neurosurg Pediatr, 2014)
Accurate language localization expands surgical treatment options for epilepsy patients and reduces the risk of postsurgery language deficits. Electrical cortical stimulation mapping (ESM) is considered to be the clinical gold standard for language localization. While ESM affords clinically valuable results, it can be poorly tolerated by children, requires active participation and compliance, carries a risk of inducing seizures, is highly time consuming, and is labor intensive. Given these limitations, alternative and/or complementary functional localization methods such as analysis of electrocorticographic (ECoG) activity in high gamma frequency band in real time are needed to precisely identify eloquent cortex in children. In this case report, the authors examined 1) the use of real-time functional mapping (RTFM) for language localization in a high gamma frequency band derived from ECoG to guide surgery in an epileptic pediatric patient and 2) the relationship of RTFM mapping results to postsurgical language outcomes. The authors found that RTFM demonstrated relatively high sensitivity (75%) and high specificity (90%) when compared with ESM in a "next-neighbor" analysis. While overlapping with ESM in the superior temporal region, RTFM showed a few other areas of activation related to expressive language function, areas that were eventually resected during the surgery. The authors speculate that this resection may be associated with observed postsurgical expressive language deficits. With additional validation in more subjects, this finding would suggest that surgical planning and associated assessment of the risk/benefit ratio would benefit from information provided by RTFM mapping.
Keywords: Adolescent; Anticonvulsants; Brain Mapping; Cerebral Cortex; Electric Stimulation; Electroencephalography; Epilepsies, Partial; Female; Humans; Language; Neuropsychological Tests; Sensitivity and Specificity; Speech

Real-Time Functional Mapping with Electrocorticography in Pediatric Epilepsy: Comparison with fMRI and ESM Findings. - Korostenskaja, Milena; Adam J Wilson; Rose, Douglas F; Peter Brunner; Gerwin Schalk; Leach, James; Mangano, Francesco T; Fujiwara, Hisako; Rozhkov, Leonid; Harris, Elana; Chen, Po-Ching; Seo, Joo-Hee; et al. (Clinical EEG and neuroscience, 2014)
SIGFRIED (SIGnal modeling For Real-time Identification and Event Detection) software provides real-time functional mapping (RTFM) of eloquent cortex for epilepsy patients preparing to undergo resective surgery. This study presents the first application of paradigms used in functional magnetic resonance (fMRI) and electrical cortical stimulation mapping (ESM) studies for shared functional cortical mapping in the context of RTFM. Results from the 3 modalities are compared. A left-handed 13-year-old male with intractable epilepsy participated in functional mapping for localization of eloquent language cortex with fMRI, ESM, and RTFM. For RTFM, data were acquired over the frontal and temporal cortex. Several paradigms were sequentially presented: passive (listening to stories) and active (picture naming and verb generation). For verb generation and story processing, fMRI showed atypical right lateralizing language activation within temporal lobe regions of interest and bilateral frontal activation with slight right lateralization. Left hemisphere ESM demonstrated no eloquent language areas. RTFM procedures using story processing and picture naming elicited activity in the right lateral and basal temporal regions. Verb generation elicited strong right lateral temporal lobe activation, as well as left frontal lobe activation. RTFM results confirmed atypical language lateralization evident from fMRI and ESM. We demonstrated the feasibility and usefulness of a new RTFM stimulation paradigm during presurgical evaluation. Block design paradigms used in fMRI may be optimal for this purpose. Further development is needed to create age-appropriate RTFM test batteries.
Keywords: Brain-computer interface (BCI); cortical stimulation; electrocorticography (ECoG); epilepsy surgery; functional magnetic resonance imaging (fMRI); functional mapping; pediatrics; SIGFRIED

Satellite Symposium, Spinal Cord Plasticity in Motor Control, Washington, DC - Jonathan Wolpaw (2014)

The simplest motor skill: mechanisms and applications of reflex operant conditioning. - Thompson, Aiko K; Jonathan Wolpaw (Exerc Sport Sci Rev, 2014)
Operant conditioning protocols can change spinal reflexes gradually, which are the simplest behaviors. This article summarizes the evidence supporting two propositions: that these protocols provide excellent models for defining the substrates of learning and that they can induce and guide plasticity to help restore skills, such as locomotion, that have been impaired by spinal cord injury or other disorders.
Keywords: Animals; Conditioning, Operant; H-Reflex; Humans; Motor Skills; Muscle, Skeletal; Neuronal Plasticity; Reflex; Spinal Cord; Spinal Cord Injuries

Simulating the effects of common and specific abilities on test performance: an evaluation of factor analysis. - Dennis J. McFarland (J Speech Lang Hear Res, 2014)
PURPOSE: Factor analysis is a useful technique to aid in organizing multivariate data characterizing speech, language, and auditory abilities. However, knowledge of the limitations of factor analysis is essential for proper interpretation of results. The present study used simulated test scores to illustrate some characteristics of factor analysis. METHOD: Linear models were used to simulate test scores that were determined by multiple latent variables. These simulated test scores were evaluated with principal components analysis and, in certain cases, structural equation modeling. In addition, a subset of simulated individuals characterized by poor test performance was examined. RESULTS: The number of factors recovered and their identity do not necessarily correspond to the structure of the latent variables that generated the test scores. The first principal component may represent variance from multiple uncorrelated sources. Practices such as correction or control for general cognitive ability may produce misleading results. CONCLUSIONS: Inferences from the results of factor analysis should be primarily about the structure of test batteries rather than the structure of human mental abilities. Researchers and clinicians should consider multiple sources of evidence to evaluate hypotheses about the processes generating test results.

Simultaneous Real-Time Monitoring of Multiple Cortical Systems. - Disha Gupta; Jeremy Jeremy Hill; Peter Brunner; Gunduz, Aysegul; A L Ritaccio; Gerwin Schalk (Journal of Neural Engineering, 2014)
OBJECTIVE: Real-time monitoring of the brain is potentially valuable for performance monitoring, communication, training or rehabilitation. In natural situations, the brain performs a complex mix of various sensory, motor or cognitive functions. Thus, real-time brain monitoring would be most valuable if (a) it could decode information from multiple brain systems simultaneously, and (b) this decoding of each brain system were robust to variations in the activity of other (unrelated) brain systems. Previous studies showed that it is possible to decode some information from different brain systems in retrospect and/or in isolation. In our study, we set out to determine whether it is possible to simultaneously decode important information about a user from different brain systems in real time, and to evaluate the impact of concurrent activity in different brain systems on decoding performance. APPROACH: We study these questions using electrocorticographic signals recorded in humans. We first document procedures for generating stable decoding models given little training data, and then report their use for offline and for real-time decoding from 12 subjects (six for offline parameter optimization, six for online experimentation). The subjects engage in tasks that involve movement intention, movement execution and auditory functions, separately, and then simultaneously. Main Results: Our real-time results demonstrate that our system can identify intention and movement periods in single trials with an accuracy of 80.4% and 86.8%, respectively (where 50% would be expected by chance). Simultaneously, the decoding of the power envelope of an auditory stimulus resulted in an average correlation coefficient of 0.37 between the actual and decoded power envelopes. These decoders were trained separately and executed simultaneously in real time. SIGNIFICANCE: This study yielded the first demonstration that it is possible to decode simultaneously the functional activity of multiple independent brain systems. Our comparison of univariate and multivariate decoding strategies, and our analysis of the influence of their decoding parameters, provides benchmarks and guidelines for future research on this topic.
Keywords: auditory processing; Electrocorticography; movement intention; realtime decoding; simultaneous decoding

Spatial and temporal relationships of electrocorticographic alpha and gamma activity during auditory processing. - Potes, Cristhian; Peter Brunner; Gunduz, Aysegul; Robert T. Knight; Gerwin Schalk (NeuroImage, 2014)
Neuroimaging approaches have implicated multiple brain sites in musical perception, including the posterior part of the superior temporal gyrus and adjacent perisylvian areas. However, the detailed spatial and temporal relationship of neural signals that support auditory processing is largely unknown. In this study, we applied a novel inter-subject analysis approach to electrophysiological signals recorded from the surface of the brain (electrocorticography (ECoG)) in ten human subjects. This approach allowed us to reliably identify those ECoG features that were related to the processing of a complex auditory stimulus (i.e., continuous piece of music) and to investigate their spatial, temporal, and causal relationships. Our results identified stimulus-related modulations in the alpha (8-12 Hz) and high gamma (70-110 Hz) bands at neuroanatomical locations implicated in auditory processing. Specifically, we identified stimulus-related ECoG modulations in the alpha band in areas adjacent to primary auditory cortex, which are known to receive afferent auditory projections from the thalamus (80 of a total of 15,107 tested sites). In contrast, we identified stimulus-related ECoG modulations in the high gamma band not only in areas close to primary auditory cortex but also in other perisylvian areas known to be involved in higher-order auditory processing, and in superior premotor cortex (412/15,107 sites). Across all implicated areas, modulations in the high gamma band preceded those in the alpha band by 280 ms, and activity in the high gamma band causally predicted alpha activity, but not vice versa (Granger causality, p<1e(-8)). Additionally, detailed analyses using Granger causality identified causal relationships of high gamma activity between distinct locations in early auditory pathways within superior temporal gyrus (STG) and posterior STG, between posterior STG and inferior frontal cortex, and between STG and premotor cortex. Evidence suggests that these relationships reflect direct cortico-cortical connections rather than common driving input from subcortical structures such as the thalamus. In summary, our inter-subject analyses defined the spatial and temporal relationships between music-related brain activity in the alpha and high gamma bands. They provide experimental evidence supporting current theories about the putative mechanisms of alpha and gamma activity, i.e., reflections of thalamo-cortical interactions and local cortical neural activity, respectively, and the results are also in agreement with existing functional models of auditory processing.
Keywords: alpha and high gamma activity; auditory processing; electrocorticography (ECoG); functional connectivity; granger causality; thalamo-cortical interactions

Summer School on Neurorehabilitation, Baiona, Spain - Jonathan Wolpaw (2014)

Symposium, American Society of Neurorehabilitation, Washington, DC - Jonathan Wolpaw (2014)

Symposium Speaker - Jonathan Wolpaw (2014)
Sensorimotor Rehabilitation, University of Montreal, Canada

Symposium Speaker - Jonathan Wolpaw (2014)
International Conference on NeuroRehabilitation, Aalborg, Denmark

Adaptive Laplacian filtering for sensorimotor rhythm-based brain-computer interfaces. - Lu, Jun; Dennis J. McFarland; Jonathan Wolpaw (Journal of neural engineering, 2013)
OBJECTIVE: Sensorimotor rhythms (SMRs) are 8-30 Hz oscillations in the electroencephalogram (EEG) recorded from the scalp over sensorimotor cortex that change with movement and/or movement imagery. Many brain-computer interface (BCI) studies have shown that people can learn to control SMR amplitudes and can use that control to move cursors and other objects in one, two or three dimensions. At the same time, if SMR-based BCIs are to be useful for people with neuromuscular disabilities, their accuracy and reliability must be improved substantially. These BCIs often use spatial filtering methods such as common average reference (CAR), Laplacian (LAP) filter or common spatial pattern (CSP) filter to enhance the signal-to-noise ratio of EEG. Here, we test the hypothesis that a new filter design, called an 'adaptive Laplacian (ALAP) filter', can provide better performance for SMR-based BCIs. APPROACH: An ALAP filter employs a Gaussian kernel to construct a smooth spatial gradient of channel weights and then simultaneously seeks the optimal kernel radius of this spatial filter and the regularization parameter of linear ridge regression. This optimization is based on minimizing the leave-one-out cross-validation error through a gradient descent method and is computationally feasible. MAIN RESULTS: Using a variety of kinds of BCI data from a total of 22 individuals, we compare the performances of ALAP filter to CAR, small LAP, large LAP and CSP filters. With a large number of channels and limited data, ALAP performs significantly better than CSP, CAR, small LAP and large LAP both in classification accuracy and in mean-squared error. Using fewer channels restricted to motor areas, ALAP is still superior to CAR, small LAP and large LAP, but equally matched to CSP. SIGNIFICANCE: Thus, ALAP may help to improve the accuracy and robustness of SMR-based BCIs.
Keywords: assistive communication; brain computer interface (BCI); brain-machine interface (BMI); electroencephalogram (EEG); leave-one-out (LOO) cross-validation; spatial filter

BCI Software Platforms. - Brunner, Clemens; Andreoni, G; Bianchi, L; Benjamin Blankertz; Breitwieser, C.; Kanoh, S.; Kothe, C. A.; Lecuyer, A.; Makeig, S; Mellinger, J.; Perego, P.; Renard, Y.; et al. (Towards Practical Brain-Computer Interfaces, 2013)
In this chapter, we provide an overview of publicly available software platforms for brain–computer interfaces. We have identified seven major BCI platforms and one platform specifically targeted towards feedback and stimulus presentation. We describe the intended target user group (which includes researchers, programmers, and end users), the most important features of each platform such as availability on different operating systems, licences, programming languages involved, supported devices, and so on. These seven platforms are: (1) BCI2000, (2) OpenViBE, (3) TOBI Common Implementation Platform (CIP), (4) BCILAB, (5) BCI++, (6) xBCI, and (7) BF++. The feedback framework is called Pyff. Our conclusion discusses possible synergies and future developments, such as combining different components of different platforms. With this overview, we hope to identify the strengths and weaknesses of each available platform, which should help anyone in the BCI research field in their decision which platform to use for their specific purposes.

Brain Computer Interface Development Based on Recurrent Neural Networks and ANFIS Systems. - Emmanuel Morales-Flores; Ramirez-Cortes, J.; Gomez-Gil, P.; Alarcon-Aquino, V. (Soft Computing Applications in Optimization, Control and Recognition, 2013)

Brain-computer interfaces. - Jonathan Wolpaw (Handbook of clinical neurology, 2013)
Brain-computer interfaces (BCIs) are systems that give their users communication and control capabilities that do not depend on muscles. The user's intentions are determined from activity recorded by electrodes on the scalp, on the cortical surface, or within the brain. BCIs can enable people who are paralyzed by amyotrophic lateral sclerosis (ALS), brainstem stroke, or other disorders to convey their needs and wishes to others, to operate word-processing programs or other software, or possibly to control a wheelchair or a neuroprosthesis. BCI technology might also augment rehabilitation protocols aimed at restoring useful motor function. With continued development and clinical implementation, BCIs could substantially improve the lives of those with severe disabilities.
Keywords: Software

Brain-Computer Interfaces Yesterday, Today, and Tomorrow: A Status Report of Bioengineering Research Partnership EB0085 - Gerwin Schalk (2013)
National Institute of Biomedical Imaging and Bioengineering, National Institutes of Health, Bethesda, MD

Brain-Computer Interfacing Using P300 Evoked Potentials - Gerwin Schalk (2013)
Guest lecture in course Brain-Computer Interfaces, Departments of Neurosurgery/Bioengineering, University of Pennsylvania

Brain-Computer Interfacing Using P300 Evoked Potentials - Gerwin Schalk (2013)
Guest lecture in course Brain-Computer Interfaces, Electrical and Computer Engineering Department, NYU Poly

Characterizing multivariate decoding models based on correlated EEG spectral features. - Dennis J. McFarland (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2013)
OBJECTIVE: Multivariate decoding methods are popular techniques for analysis of neurophysiological data. The present study explored potential interpretative problems with these techniques when predictors are correlated. METHODS: Data from sensorimotor rhythm-based cursor control experiments was analyzed offline with linear univariate and multivariate models. Features were derived from autoregressive (AR) spectral analysis of varying model order which produced predictors that varied in their degree of correlation (i.e., multicollinearity). RESULTS: The use of multivariate regression models resulted in much better prediction of target position as compared to univariate regression models. However, with lower order AR features interpretation of the spectral patterns of the weights was difficult. This is likely to be due to the high degree of multicollinearity present with lower order AR features. CONCLUSIONS: Care should be exercised when interpreting the pattern of weights of multivariate models with correlated predictors. Comparison with univariate statistics is advisable. SIGNIFICANCE: While multivariate decoding algorithms are very useful for prediction their utility for interpretation may be limited when predictors are correlated.
Keywords: brain-computer interface; multicollinearity; multivariate decoding; sensorimotor rhythm

Communicating Directly With the Brain - Gerwin Schalk (2013)
Annual Gala of Fondazione Neurone, Rome, Italy

cortiQ – Clinical Software for Electrocorticographic Real-Time Functional Mapping of the Eloquent Cortex - Prueckl, R.; Kapeller, C; Potes, Cristhian; Korostenskaja, M; Gerwin Schalk; Lee, K.H.; Guger, C (35th Annual International IEEE EMBS Conference (EMBC), 2013)

CortiQ - clinical software for electrocorticographic real-time functional mapping of the eloquent cortex. - Prueckl, Robert; Kapeller, Christoph; Potes, Cristhian; Korostenskaja, Milena; Gerwin Schalk; Lee, Ki H; Guger, Christoph (Conf Proc IEEE Eng Med Biol Soc, 2013)
Planning for epilepsy surgery depends substantially on the localization of brain cortical areas responsible for sensory, motor, or cognitive functions, clinically also known as eloquent cortex. In this paper, we present the novel software package 'cortiQ' that allows clinicians to localize eloquent cortex, thus providing a safe margin for surgical resection with a low incidence of neurological deficits. This software can be easily used in addition to traditional mapping procedures such as the electrical cortical stimulation (ECS) mapping. The software analyses task-related changes in gamma activity recorded from implanted subdural electrocorticography electrodes using extensions to previously published methods. In this manuscript, we describe the system's architecture and workflow required to obtain a map of the eloquent cortex. We validate the system by comparing our mapping results with those acquired using ECS mapping in two subjects. Our results indicate that cortiQ reliably identifies eloquent cortex much faster (several minutes compared to an hour or more) than ECS mapping. Next-neighbour analyses show that there are no false positives and an average of 1.24% false negatives.

ECoG-Based Neuroscience and Neuroengineering - Gerwin Schalk (2013)
Center for Neuropharmacology and Neuroscience Seminar Series, Albany Medical College, Albany, NY

Exciting Opportunities for Neuroengineering - Gerwin Schalk (2013)
Hershey Medical Center, Penn State University

The Exciting World of Brain-Computer Interfaces - Gerwin Schalk (2013)
Society of Physics Students, State University of New York at Albany, Albany, NY

Factors Influencing Tests of Auditory Processing: A Perspective on Current Issues and Relevant Concerns. - Anthony T. Cacace; Dennis J. McFarland (Journal of the American Academy of Audiology, 2013)
Background: Tests of auditory perception, such as those used in the assessment of central auditory processing disorders ([C]APDs), represent a domain in audiological assessment where measurement of this theoretical construct is often confounded by nonauditory abilities due to methodological shortcomings. These confounds include the effects of cognitive variables such as memory and attention and suboptimal testing paradigms, including the use of verbal reproduction as a form of response selection. We argue that these factors need to be controlled more carefully and/or modified so that their impact on tests of auditory and visual perception is only minimal. Purpose: To advocate for a stronger theoretical framework than currently exists and to suggest better methodological strategies to improve assessment of auditory processing disorders (APDs). Emphasis is placed on adaptive forced-choice psychophysical methods and the use of matched tasks in multiple sensory modalities to achieve these goals. Together, this approach has potential to improve the construct validity of the diagnosis, enhance and develop theory, and evolve into a preferred method of testing. Research Design: Examination of methods commonly used in studies of APDs. Where possible, currently used methodology is compared to contemporary psychophysical methods that emphasize computer-controlled forced-choice paradigms. Results: In many cases, the procedures used in studies of APD introduce confounding factors that could be minimized if computer-controlled forced-choice psychophysical methods were utilized. Conclusions: Ambiguities of interpretation, indeterminate diagnoses, and unwanted confounds can be avoided by minimizing memory and attentional demands on the input end and precluding the use of response-selection strategies that use complex motor processes on the output end. Advocated are the use of computer-controlled forced-choice psychophysical paradigms in combination with matched tasks in multiple sensory modalities to enhance the prospect of obtaining a valid diagnosis.
Keywords: adaptive forced-choice psychophysical methods; auditory processing disorder; dissociation; double dissociation; forced-choice psychophysical methods; modality specificity; response selection

FPGA-based educational platform for real-time image processing experiments. - Ramirez-Cortes, J.; Martinez-Carballido; Alarcon-Aquino, V.; Gomez-Gil, P.; Emmanuel Morales-Flores (Computer Applications in Engineering Education, 2013)
In this paper, an implementation of an educational platform for real-time linear and morphological image filtering using a FPGA NexysII, Xilinx®, Spartan 3E, is described. The system is connected to a USB port of a personal computer, which in that way form a powerful and low-cost design station for educational purposes. The FPGA-based system is accessed through a MATLAB graphical user interface, which handles the communication setup and data transfer. The system allows the students to perform comparisons between results obtained from MATLAB simulations and FPGA-based real-time processing. Concluding remarks derived from course evaluations and lab reports are presented.
Keywords: education; filtering; hardware; image; processing

Interactions Between Pre-Processing and Classification Methods for Event-Related-Potential Classification : Best-Practice Guidelines for Brain-Computer Interfacing. - Farquhar, Jason; Jeremy Jeremy Hill (Neuroinformatics, 2013)
Detecting event related potentials (ERPs) from single trials is critical to the operation of many stimulus-driven brain computer interface (BCI) systems. The low strength of the ERP signal compared to the noise (due to artifacts and BCI irrelevant brain processes) makes this a challenging signal detection problem. Previous work has tended to focus on how best to detect a single ERP type (such as the visual oddball response). However, the underlying ERP detection problem is essentially the same regardless of stimulus modality (e.g. visual or tactile), ERP component (e.g. P300 oddball response, or the error-potential), measurement system or electrode layout. To investigate whether a single ERP detection method might work for a wider range of ERP BCIs we compare detection performance over a large corpus of more than 50 ERP BCI datasets whilst systematically varying the electrode montage, spectral filter, spatial filter and classifier training methods. We identify an interesting interaction between spatial whitening and regularised classification which made detection performance independent of the choice of spectral filter low-pass frequency. Our results show that pipeline consisting of spectral filtering, spatial whitening, and regularised classification gives near maximal performance in all cases. Importantly, this pipeline is simple to implement and completely automatic with no expert feature selection or parameter tuning required. Thus, we recommend this combination as a "best-practice" method for ERP detection problems.
Keywords: BCI; decoding; EEG; ERP; LDA; spatial filtering; spectral filtering

Long-term Cortical Neuroprostheses: Prospects and Challenges - Gerwin Schalk (2013)
1st Bernstein Sparks Workshop on Cortical Neurointerfaces, Delmenhorst, Germany

A low-frequency oscillatory neural signal in humans encodes a developing decision variable. - Kubanek, Jan; Snyder, Lawrence H.; Brunton, Bingni W.; Brody, Carlos D.; Gerwin Schalk (NeuroImage, 2013)
We often make decisions based on sensory evidence that is accumulated over a period of time. How the evidence for such decisions is represented in the brain and how such a neural representation is used to guide a subsequent action are questions of considerable interest to decision sciences. The neural correlates of developing perceptual decisions have been thoroughly investigated in the oculomotor system of macaques who communicated their decisions using an eye movement. It has been found that the evidence informing a decision to make an eye movement is in part accumulated within the same oculomotor circuits that signal the upcoming eye movement. Recent evidence suggests that the somatomotor system may exhibit an analogous property for choices made using a hand movement. To investigate this possibility, we engaged humans in a decision task in which they integrated discrete quanta of sensory information over a period of time and signaled their decision using a hand movement or an eye movement. The discrete form of the sensory evidence allowed us to infer the decision variable on which subjects base their decision on each trial and to assess the neural processes related to each quantum of the incoming decision evidence. We found that a low-frequency electrophysiological signal recorded over centroparietal regions strongly encodes the decision variable inferred in this task, and that it does so specifically for hand movement choices. The signal ramps up with a rate that is proportional to the decision variable, remains graded by the decision variable throughout the delay period, reaches a common peak shortly before a hand movement, and falls off shortly after the hand movement. Furthermore, the signal encodes the polarity of each evidence quantum, with a short latency, and retains the response level over time. Thus, this neural signal shows properties of evidence accumulation. These findings suggest that the decision-related effects observed in the oculomotor system of the monkey during eye movement choices may share the same basic properties with the decision-related effects in the somatomotor system of humans during hand movement choices.

Mental Tasks Temporal Classification Using an Architecture Based on ANFIS and Recurrent Neural Networks. - Emmanuel Morales-Flores; Ramirez-Cortes, J.; Gomez-Gil, P.; Alarcon-Aquino, V. (Recent Advances on Hybrid Intelligent Systems, 2013)
In this paper, an architecture based on adaptive neuro-fuzzy inference systems (ANFIS) assembled to recurrent neural networks, applied to the problem of mental tasks temporal classification, is proposed. The electroencephalographic signals (EEG) are pre-processed through band-pass filtering in order to separate the set of energy signals in alpha and beta bands. The energy in each band is represented by fuzzy sets obtained through an ANFIS system, and the temporal sequence corresponding to the combination to be detected, associated to the specific mental task, is entered into a recurrent neural networks. This experiment has been carried out in the context of brain-computer-interface (BCI) systems development. Experimentation using EEG signals corresponding to mental tasks exercises, obtained from a database available to the international community for research purposes, is reported. Two recurrent neural networks are used for comparison purposes: Elman network and a fully connected recurrent neural network (FCRNN) trained by RTRL-EKF (real time recurrent learning – extended Kalman filter). A classification rate of 88.12% in average was obtained through the FCRNN during the generalization stage.

Modeling Individual Subtests of the WAIS IV with Multiple Latent Factors. - Dennis J. McFarland (PloS one, 2013)
Performance on a cognitive test can be viewed either as measuring a unitary function or as reflecting the operation of multiple factors. Individual subtests in batteries designed to measure human abilities are commonly modeled as a single latent factor. Several latent factors are then used to model groups of subtests. However these latent factors are not independent as they are related through hierarchical or oblique structures. As a result, the simple structure of subtest performance results in complex latent factors. The present study used structural equation modeling to evaluate several multidimensional models of the Wechsler Adult Intelligence Scales- fourth edition (WAIS-IV) subtests. Multidimensional models of subtest performance provided better model fit as compared to several previously proposed one dimensional models. These multidimensional models also generalized well to new samples of populations differing in age from that used to estimate the model parameters. Overall these results show that models that describe subtests as multidimensional functions of uncorrelated factors provided a better fit to the WAIS-IV correlations than models that describe subtests as one dimensional functions of correlated factors. There appears to be a trade-off in modeling subtests as one dimensional and modeling with homogeneous latent traits. More consideration should be given to models that include multiple uncorrelated latent factors as determinants of the performance on a given subtest. These results support the view that performance on any given cognitive test is potentially the result of multiple factors. Simple structure may be too simple.

Novel inter-hemispheric white matter connectivity in the BTBR mouse model of autism. - Miller, V M; Disha Gupta; Neu, N; Cotroneo, A; Chadwick B. Boulay; Seegal, R F (Brain Res, 2013)
Alterations in the volume, density, connectivity and functional activation of white matter tracts are reported in some individuals with autism and may contribute to their abnormal behaviors. The BTBR (BTBR T+tf/J) inbred strain of mouse, is used to model facets of autism because they develop low social behaviors, stereotypical and immune changes similar to those found in people with autism. Previously, it was thought a total absence of corpus callosal interhemispheric connective tissues in the BTBR mice may underlie their abnormal behaviors. However, postnatal lesions of the corpus callosum do not precipitate social behavioral problems in other strains of mice suggesting a flaw in this theory. In this study we used digital pathological methods to compare subcortical white matter connective tracts in the BTBR strain of mice with those found in the C57Bl/6 mouse and those reported in a standardized mouse brain atlas. We report, for the first time, a novel connective subcortical interhemispheric bridge of tissue in the posterior, but not anterior, cerebrum of the BTBR mouse. These novel connective tissues are comprised of myelinated fibers, with reduced myelin basic protein levels (MBP) compared to levels in the C57Bl/6 mouse. We used electrophysiological analysis and found increased inter-hemispheric connectivity in the posterior hemispheres of the BTBR strain compared with the anterior hemispheres. The conduction velocity was slower than that reported in normal mice. This study shows there is novel abnormal interhemispheric connectivity in the BTBR strain of mice, which may contribute to their behavioral abnormalities.
Keywords: Analysis of Variance; Animals; Autistic Disorder; Brain; Corpus Callosum; Disease Models, Animal; Electroencephalography; Enzyme-Linked Immunosorbent Assay; Female; Functional Laterality; Image Processing, Computer-Assisted; Male; Mice; Mice, Inbred C57BL; Mice, Neurologic Mutants; Microtubule-Associated Proteins; Myelin Basic Protein; Nerve Fibers, Myelinated; Neuroimaging; Spectrum Analysis

Operant conditioning of a spinal reflex can improve locomotion after spinal cord injury in humans. - Thompson, Aiko K.; Pomerantz, Ferne R.; Jonathan Wolpaw (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2013)
Operant conditioning protocols can modify the activity of specific spinal cord pathways and can thereby affect behaviors that use these pathways. To explore the therapeutic application of these protocols, we studied the impact of down-conditioning the soleus H-reflex in people with impaired locomotion caused by chronic incomplete spinal cord injury. After a baseline period in which soleus H-reflex size was measured and locomotion was assessed, subjects completed either 30 H-reflex down-conditioning sessions (DC subjects) or 30 sessions in which the H-reflex was simply measured [unconditioned (UC) subjects], and locomotion was reassessed. Over the 30 sessions, the soleus H-reflex decreased in two-thirds of the DC subjects (a success rate similar to that in normal subjects) and remained smaller several months later. In these subjects, locomotion became faster and more symmetrical, and the modulation of EMG activity across the step cycle increased bilaterally. Furthermore, beginning about halfway through the conditioning sessions, all of these subjects commented spontaneously that they were walking faster and farther in their daily lives, and several noted less clonus, easier stepping, and/or other improvements. The H-reflex did not decrease in the other DC subjects or in any of the UC subjects; and their locomotion did not improve. These results suggest that reflex-conditioning protocols can enhance recovery of function after incomplete spinal cord injuries and possibly in other disorders as well. Because they are able to target specific spinal pathways, these protocols could be designed to address each individual's particular deficits, and might thereby complement other rehabilitation methods.
Keywords: Learning; Locomotion; operant conditioning; plasticity; Rehabilitation; spasticity

Opportunities in Computation Electrophysiological Imaging - Gerwin Schalk (2013)
Department of Psychology, NYU, New York, NY

Opportunities in Computation Electrophysiological Imaging - Gerwin Schalk (2013)
McGovern Institute for Brain Research, MIT

Proceedings of the Fourth International Workshop on Advances in Electrocorticography. - A L Ritaccio; Peter Brunner; Nathan E. Crone; Gunduz, Aysegul; Hirsch, Lawrence J.; Kanwisher, Nancy; Litt, Brian; Kai J. Miller; Morani, Daniel; Parvizi, Josef; Ramsey, Nick F; Richner, Thomas J.; et al. (Epilepsy & Behavior, 2013)
The Fourth International Workshop on Advances in Electrocorticography (ECoG) convened in New Orleans, LA, on October 11–12, 2012. The proceedings of the workshop serves as an accurate record of the most contemporary clinical and experimental work on brain surface recording and represents the insights of a unique multidisciplinary ensemble of expert clinicians and scientists. Presentations covered a broad range of topics, including innovations in passive functional mapping, increased understanding of pathologic high-frequency oscillations, evolving sensor technologies, a human trial of ECoG-driven brain–machine interface, as well as fresh insights into brain electrical stimulation.
Keywords: Brain Mapping; Brain–computer interface; Electrocorticography; Gamma-frequency electroencephalography; High-frequency oscillations; Neuroprosthetics; Seizure detection; Subdural grid

Reliability of broadband middle-ear power-reflectance in younger and older adults: Application of Generalizability Theory. - Mahoney, Marty J.; Dennis J. McFarland; Carpenter, Michelle S.; Rizvi, Sabahet; Anthony T. Cacace (American journal of audiology, 2013)
PURPOSE: To assess the reliability of broadband middle-ear power reflectance (BMEPR) and transmittance profiles for chirp and tonal stimuli using generalizability theory (GT). METHOD: In adults without a history of middle-ear disease, the authors assessed the reliability of BMEPR to chirp and tonal stimuli using a multivariate approach based on an analysis of variance model (GT). For comparisons with other published studies, Pearson's product-moment correlation coefficients (Pearson's r) also were used. RESULTS: Based on GT with chirp stimuli, overall BMEPR measures had good reliability; however, the reliability of individual profiles across frequencies and ears was less than optimal. Lower generalizability coefficients were found when transmittance was evaluated. Test-retest reliability using Pearson's r was better for right versus left ears, and mid-frequencies were generally more reliable than those at either extreme of the frequency range. In contrast, tonal stimuli had higher generalizability coefficients and Pearson's r values than chirps for all frequencies tested; Pearson's r values were also higher for right versus left ears. CONCLUSION: The authors extended the use of GT as a preferred way to evaluate reliability of BMEPR and transmittance profiles for chirps and tones because it allows for a more comprehensive evaluation compared with unidimensional pairwise correlations.

Soleus H-reflex operant conditioning changes the H-reflex recruitment curve. - Thompson, Aiko K.; Xiang Yang Chen; Jonathan Wolpaw (Muscle & nerve, 2013)
INTRODUCTION: Operant conditioning can gradually change the human soleus H-reflex. The protocol conditions the reflex near M-wave threshold. In this study we examine its impact on the reflexes at other stimulus strengths. METHODS: H-reflex recruitment curves were obtained before and after a 24-session exposure to an up-conditioning (HRup) or a down-conditioning (HRdown) protocol and were compared. RESULTS: In both HRup and HRdown subjects, conditioning affected the entire H-reflex recruitment curve. In 5 of 6 HRup and 3 of 6 HRdown subjects, conditioning elevated (HRup) or depressed (HRdown), respectively, the entire curve. In the other HRup subject or the other 3 HRdown subjects, the curve was shifted to the left or to the right, respectively. CONCLUSIONS: H-reflex conditioning does not simply change the H-reflex to a stimulus of particular strength; it also changes the H-reflexes to stimuli of different strengths. Thus, it is likely to affect many actions in which this pathway participates.
Keywords: motor learning; plasticity; Rehabilitation; Spinal Cord

Toward Gaze-Independent Brain-Computer Interfaces. - Peter Brunner; Gerwin Schalk (Clinical Neurophysiology, 2013)

The Tracking of Speech Envelope in the Human Cortex. - Kubanek, Jan; Peter Brunner; Gunduz, Aysegul; Poeppel, David; Gerwin Schalk (PLoS ONE, 2013)
Humans are highly adept at processing speech. Recently, it has been shown that slow temporal information in speech (i.e., the envelope of speech) is critical for speech comprehension. Furthermore, it has been found that evoked electric potentials in human cortex are correlated with the speech envelope. However, it has been unclear whether this essential linguistic feature is encoded differentially in specific regions, or whether it is represented throughout the auditory system. To answer this question, we recorded neural data with high temporal resolution directly from the cortex while human subjects listened to a spoken story. We found that the gamma activity in human auditory cortex robustly tracks the speech envelope. The effect is so marked that it is observed during a single presentation of the spoken story to each subject. The effect is stronger in regions situated relatively early in the auditory pathway (belt areas) compared to other regions involved in speech processing, including the superior temporal gyrus (STG) and the posterior inferior frontal gyrus (Broca's region). To further distinguish whether speech envelope is encoded in the auditory system as a phonological (speech-related), or instead as a more general acoustic feature, we also probed the auditory system with a melodic stimulus. We found that belt areas track melody envelope weakly, and as the only region considered. Together, our data provide the first direct electrophysiological evidence that the envelope of speech is robustly tracked in non-primary auditory cortex (belt areas in particular), and suggest that the considered higher-order regions (STG and Broca's region) partake in a more abstract linguistic analysis.

BCI2000: A General-Purpose BCI System and Its Application to ECoG Signals - Gerwin Schalk (2012)
g.tec Brain-Computer Interface Workshop, New Orleans, LA

BCI2000: A General-Purpose BCI System and its Application to ECoG Signals - Gerwin Schalk (2012)
g.tec Brain-Computer Interface Workshop, New Orleans, LA

BCIs That Use Electrocorticographic Activity. - Jonathan Wolpaw; E. Winter-Wolpaw; Gerwin Schalk (Brain-Computer Interfaces: Principles and Practice, 2012)
This chapter discusses the potential of electrocorticography (ECoG) as a clinically useful brain-computer interface signal modality. ECoG has greater amplitude, higher topographical resolution, and a much broader frequency range than scalp-recorded electroencephalography and is less susceptible to artifacts. With current and foreseeable recording methodologies, ECoG is likely to have greater long-term stability than intracortically recorded signals. Furthermore, it can more readily be recorded from larger cortical areas, and it requires much lower digitization rates, thus greatly reducing the power requirements of wholly implanted systems.
Keywords: brain signals; brain-computer interfaces; ECoG; intracortically recorded signals

Brain-computer interfaces in medicine. - Shih, Jerry J.; Krusienski, Dean J.; Jonathan Wolpaw (Mayo Clinic proceedings. Mayo Clinic, 2012)
Brain-computer interfaces (BCIs) acquire brain signals, analyze them, and translate them into commands that are relayed to output devices that carry out desired actions. BCIs do not use normal neuromuscular output pathways. The main goal of BCI is to replace or restore useful function to people disabled by neuromuscular disorders such as amyotrophic lateral sclerosis, cerebral palsy, stroke, or spinal cord injury. From initial demonstrations of electroencephalography-based spelling and single-neuron-based device control, researchers have gone on to use electroencephalographic, intracortical, electrocorticographic, and other brain signals for increasingly complex control of cursors, robotic arms, prostheses, wheelchairs, and other devices. Brain-computer interfaces may also prove useful for rehabilitation after stroke and for other disorders. In the future, they might augment the performance of surgeons or other medical professionals. Brain-computer interface technology is the focus of a rapidly growing research and development enterprise that is greatly exciting scientists, engineers, clinicians, and the public in general. Its future achievements will depend on advances in 3 crucial areas. Brain-computer interfaces need signal-acquisition hardware that is convenient, portable, safe, and able to function in all environments. Brain-computer interface systems need to be validated in long-term studies of real-world use by people with severe disabilities, and effective and viable models for their widespread dissemination must be implemented. Finally, the day-to-day and moment-to-moment reliability of BCI performance must be improved so that it approaches the reliability of natural muscle-based function.
Keywords: User-Computer Interface

Brain-Computer Interfacing Using P300 Evoked Potentials - Gerwin Schalk (2012)
Guest lecture in course Brain-Computer Interfaces, Electrical and Computer Engineering Department, NYU poly, New York, NY

Brain-Computer Interfacing Using P300 Evoked Potentials - Gerwin Schalk (2012)
Guest lecture in course Brain-Computer Interfaces, Departments of Neurosurgery/Bioengineering, University of Pennsylvania, Philadelphia, Pennsylvania

Communicating Directly With the Brain - Gerwin Schalk (2012)
Introductory lecture at the initial public presentation of the €20m Italian project "cyber brain." Chamber of Commerce, Avellino, Italy.

Communication and control by listening: towards optimal design of a two-class auditory streaming brain-computer interface. - Jeremy Jeremy Hill; Moinuddin, Aisha; Häuser, Ann-Katrin; Kienzle, Stephan; Gerwin Schalk (Frontiers in Neuroscience, 2012)
Most brain-computer interface (BCI) systems require users to modulate brain signals in response to visual stimuli. Thus, they may not be useful to people with limited vision, such as those with severe paralysis. One important approach for overcoming this issue is auditory streaming, an approach whereby a BCI system is driven by shifts of attention between two simultaneously presented auditory stimulus streams. Motivated by the long-term goal of translating such a system into a reliable, simple yes-no interface for clinical usage, we aim to answer two main questions. First, we asked which of two previously published variants provides superior performance: a fixed-phase (FP) design in which the streams have equal period and opposite phase, or a drifting-phase (DP) design where the periods are unequal. We found FP to be superior to DP (p = 0.002): average performance levels were 80 and 72% correct, respectively. We were also able to show, in a pilot with one subject, that auditory streaming can support continuous control and neurofeedback applications: by shifting attention between ongoing left and right auditory streams, the subject was able to control the position of a paddle in a computer game. Second, we examined whether the system is dependent on eye movements, since it is known that eye movements and auditory attention may influence each other, and any dependence on the ability to move one’s eyes would be a barrier to translation to paralyzed users. We discovered that, despite instructions, some subjects did make eye movements that were indicative of the direction of attention. However, there was no correlation, across subjects, between the reliability of the eye movement signal and the reliability of the BCI system, indicating that our system was configured to work independently of eye movement. Together, these findings are an encouraging step forward toward BCIs that provide practical communication and control options for the most severely paralyzed users.
Keywords: auditory attention; auditory event-related potentials; brain-computer interface; dichotic listening; N1 potential; P3 potential

Cortical stimulation causes long-term changes in H-reflexes and spinal motoneuron GABA receptors. - Wang, Yu; Yi Chen; Lu Chen; Jonathan Wolpaw; Xiang Yang Chen (Journal of neurophysiology, 2012)
The cortex gradually modifies the spinal cord during development, throughout later life, and in response to trauma or disease. The mechanisms of this essential function are not well understood. In this study, weak electrical stimulation of rat sensorimotor cortex increased the soleus H-reflex, increased the numbers and sizes of GABAergic spinal interneurons and GABAergic terminals on soleus motoneurons, and decreased GABA(A) and GABA(B) receptor labeling in these motoneurons. Several months after the stimulation ended the interneuron and terminal increases had disappeared, but the H-reflex increase and the receptor decreases remained. The changes in GABAergic terminals and GABA(B) receptors accurately predicted the changes in H-reflex size. The results reveal a new long-term dimension to cortical-spinal interactions and raise new therapeutic possibilities.
Keywords: Spinal Cord

Decoding covert spatial attention using electrocorticographic (ECoG) signals in humans. - Gunduz, Aysegul; Peter Brunner; Amy Daitch; Leuthardt, E C; A L Ritaccio; Pesaran, Bijan; Gerwin Schalk (Neuroimage, 2012)
This study shows that electrocorticographic (ECoG) signals recorded from the surface of the brain provide detailed information about shifting of visual attention and its directional orientation in humans. ECoG allows for the identification of the cortical areas and time periods that hold the most information about covert attentional shifts. Our results suggest a transient distributed fronto-parietal mechanism for orienting of attention that is represented by different physiological processes. This neural mechanism encodes not only whether or not a subject shifts their attention to a location, but also the locus of attention. This work contributes to our understanding of the electrophysiological representation of attention in humans. It may also eventually lead to brain-computer interfaces (BCIs) that optimize user interaction with their surroundings or that allow people to communicate choices simply by shifting attention to them.
Keywords: covert attention; electrocorticography (ECoG); visual spatial attention

Decoding Onset and Direction of Movements using Electrocorticographic (ECoG) Signals in Humans. - Wang, Z.; Gunduz, Aysegul; Peter Brunner; A L Ritaccio; Ji, Q; Gerwin Schalk (Frontiers in Neuroengineering, 2012)
Communication of intent usually requires motor function. This requirement can be limiting when a person is engaged in a task, or prohibitive for some people suffering from neuromuscular disorders. Determining a person's intent, e.g., where and when to move, from brain signals rather than from muscles would have important applications in clinical or other domains. For example, detection of the onset and direction of intended movements may provide the basis for restoration of simple grasping function in people with chronic stroke, or could be used to optimize a user's interaction with the surrounding environment. Detecting the onset and direction of actual movements are a first step in this direction. In this study, we demonstrate that we can detect the onset of intended movements and their direction using electrocorticographic (ECoG) signals recorded from the surface of the cortex in humans. We also demonstrate in a simulation that the information encoded in ECoG about these movements may improve performance in a targeting task. In summary, the results in this paper suggest that detection of intended movement is possible, and may serve useful functions.
Keywords: brain computer interface; ECoG; movement direction prediction; movement onset prediction; neurorehabilitation; performance augmentation

Dynamics of electrocorticographic (ECoG) activity in human temporal and frontal cortical areas during music listening. - Potes, Cristhian; Gunduz, Aysegul; Peter Brunner; Gerwin Schalk (Neuroimage, 2012)
Previous studies demonstrated that brain signals encode information about specific features of simple auditory stimuli or of general aspects of natural auditory stimuli. How brain signals represent the time course of specific features in natural auditory stimuli is not well understood. In this study, we show in eight human subjects that signals recorded from the surface of the brain (electrocorticography (ECoG)) encode information about the sound intensity of music. ECoG activity in the high gamma band recorded from the posterior part of the superior temporal gyrus as well as from an isolated area in the precentral gyrus was observed to be highly correlated with the sound intensity of music. These results not only confirm the role of auditory cortices in auditory processing but also point to an important role of premotor and motor cortices. They also encourage the use of ECoG activity to study more complex acoustic features of simple or natural auditory stimuli.
Keywords: auditory processing; electrocorticography (ECoG); high gamma activity; sound intensity

ECoG: A Step Closer to the Brain @ The Brain Computer Interfacing Workshop, University Old dominion, Norfolk, VA - Disha Gupta (2012)

ECoG-Based Neuroscience and Neuroengineering - Gerwin Schalk (2012)
BBCI Workshop 2012, Advances in Neurotechnology, Berlin, Germany

EEG correlates of P300-based brain-computer interface (BCI) performance in people with amyotrophic lateral sclerosis. - Mak, Joseph N.; Dennis J. McFarland; Theresa M Vaughan; McCane, Lynn M.; Tsui, Phillippa Z.; Zeitlin, Debra J.; Sellers, Eric W.; Jonathan Wolpaw (Journal of neural engineering, 2012)
The purpose of this study was to identify electroencephalography (EEG) features that correlate with P300-based brain-computer interface (P300 BCI) performance in people with amyotrophic lateral sclerosis (ALS). Twenty people with ALS used a P300 BCI spelling application in copy-spelling mode. Three types of EEG features were found to be good predictors of P300 BCI performance: (1) the root-mean-square amplitude and (2) the negative peak amplitude of the event-related potential to target stimuli (target ERP) at Fz, Cz, P3, Pz, and P4; and (3) EEG theta frequency (4.5-8 Hz) power at Fz, Cz, P3, Pz, P4, PO7, PO8 and Oz. A statistical prediction model that used a subset of these features accounted for >60% of the variance in copy-spelling performance (p < 0.001, mean R(2)?= 0.6175). The correlations reflected between-subject, rather than within-subject, effects. The results enhance understanding of performance differences among P300 BCI users. The predictors found in this study might help in: (1) identifying suitable candidates for long-term P300 BCI operation; (2) assessing performance online. Further work on within-subject effects needs to be done to establish whether P300 BCI user performance could be improved by optimizing one or more of these EEG features.
Keywords: User-Computer Interface

Electrocorticographic (ECoG) Correlates of Human Arm Movements. - Nicholas R Anderson; Blakely, Timothy; Gerwin Schalk; Leuthardt, E C; Moran, Daniel W (Exp Brain Res, 2012)
Invasive and non-invasive brain-computer interface (BCI) studies have long focused on the motor cortex for kinematic control of artificial devices. Most of these studies have used single-neuron recordings or electroencephalography (EEG). Electrocorticography (ECoG) is a relatively new recording modality in BCI research that has primarily been built on successes in EEG recordings. We built on prior experiments related to single-neuron recording and quantitatively compare the extent to which different brain regions reflect kinematic tuning parameters of hand speed, direction, and velocity in both a reaching and tracing task in humans. Hand and arm movement experiments using ECoG have shown positive results before, but the tasks were not designed to tease out which kinematics are encoded. In non-human primates, the relationships among these kinematics have been more carefully documented, and we sought to begin elucidating that relationship in humans using ECoG. The largest modulation in ECoG activity for direction, speed, and velocity representation was found in the primary motor cortex. We also found consistent cosine tuning across both tasks, to hand direction and velocity in the high gamma band (70-160 Hz). Thus, the results of this study clarify the neural substrates involved in encoding aspects of motor preparation and execution and confirm the important role of the motor cortex in BCI applications.
Keywords: arm tuning; brain-computer interfaces; cosine tuning; Electrocorticography; Motor Cortex; subdural electroencephalography

Exciting Adventures in Neuroscience and Neuroengineering - Gerwin Schalk (2012)
Colloquium at Electrical Engineering and Computer Science Department, Case Western Reserve University, Cleveland OH

Exciting Directions in Neuroscience and Neuroengineering - Gerwin Schalk (2012)
Kent State University, Kent, OH

Exciting Opportunities in Neuroscience and Neuroengineering - Gerwin Schalk (2012)
University of Washington, Seattle, WA

The Exciting World of Brain-Computer Interfaces - Gerwin Schalk (2012)
Wadsworth Center Research Experience for Undergraduates (REU) program

The Exciting World of Brain-Computer Interfaces - Gerwin Schalk (2012)
Lecture in course Science in the News, Sage College, Albany, NY

The Exciting World of Brain-Computer Interfacing - Gerwin Schalk (2012)
Keynote Address, Workshop in "Solving the Mystery of how the Brian Works." Walt Disney Pavilion, Florida Hospital for Children, FL

Future Aspects of Functional Mapping - Gerwin Schalk (2012)
1st International Workshop on Functional Mapping with ECoG, New Orleans, LA

Future Aspects of Functional Mapping - Gerwin Schalk (2012)

Hardware and Software Technologies. - Gerwin Schalk; Guger, C; Adam J Wilson (Brain-Computer Interfaces: Principles and Practice, 2012)

Harnessing neuroplasticity for clinical applications. - Jonathan Wolpaw (Brain : a journal of neurology, 2012)
Keywords: Neuronal Plasticity

H-reflex modulation in the human medial and lateral gastrocnemii during standing and walking. - Makihara, Yukiko; Segal, Richard L.; Jonathan Wolpaw; Thompson, Aiko K. (Muscle & nerve, 2012)
INTRODUCTION: The soleus H-reflex is dynamically modulated during walking. However, modulation of the gastrocnemii H-reflexes has not been studied systematically. METHODS: The medial and lateral gastrocnemii (MG and LG) and soleus H-reflexes were measured during standing and walking in humans. RESULTS: Maximum H-reflex amplitude was significantly smaller in MG (mean 1.1 mV) or LG (1.1 mV) than in soleus (3.3 mV). Despite these size differences, the reflex amplitudes of the three muscles were positively correlated. The MG and LG H-reflexes were phase- and task-dependently modulated in ways similar to the soleus H-reflex. CONCLUSIONS: Although there are anatomical and physiological differences between the soleus and gastrocnemii muscles, the reflexes of the three muscles are similarly modulated during walking and between standing and walking. Our findings support the hypothesis that these reflexes are synergistically modulated during walking to facilitate ongoing movement.
Keywords: Locomotion; phase-dependent modulation; spinal reflex; synergist; task-dependent modulation

Learning with Target Prior - Wang, Z.; Lyu, S.; Gerwin Schalk; Ji, Q (Neural Information Processing Systems (NIPS) Conference, 2012)

An online brain-computer interface based on shifting attention to concurrent streams of auditory stimuli. - Jeremy Jeremy Hill; Schölkopf, B (J Neural Eng, 2012)
We report on the development and online testing of an electroencephalogram-based brain-computer interface (BCI) that aims to be usable by completely paralysed users-for whom visual or motor-system-based BCIs may not be suitable, and among whom reports of successful BCI use have so far been very rare. The current approach exploits covert shifts of attention to auditory stimuli in a dichotic-listening stimulus design. To compare the efficacy of event-related potentials (ERPs) and steady-state auditory evoked potentials (SSAEPs), the stimuli were designed such that they elicited both ERPs and SSAEPs simultaneously. Trial-by-trial feedback was provided online, based on subjects' modulation of N1 and P3 ERP components measured during single 5 s stimulation intervals. All 13 healthy subjects were able to use the BCI, with performance in a binary left/right choice task ranging from 75% to 96% correct across subjects (mean 85%). BCI classification was based on the contrast between stimuli in the attended stream and stimuli in the unattended stream, making use of every stimulus, rather than contrasting frequent standard and rare 'oddball' stimuli. SSAEPs were assessed offline: for all subjects, spectral components at the two exactly known modulation frequencies allowed discrimination of pre-stimulus from stimulus intervals, and of left-only stimuli from right-only stimuli when one side of the dichotic stimulus pair was muted. However, attention modulation of SSAEPs was not sufficient for single-trial BCI communication, even when the subject's attention was clearly focused well enough to allow classification of the same trials via ERPs. ERPs clearly provided a superior basis for BCI. The ERP results are a promising step towards the development of a simple-to-use, reliable yes/no communication system for users in the most severely paralysed states, as well as potential attention-monitoring and -training applications outside the context of assistive technology.

Past and Present Aspects of Functional Mapping - Gerwin Schalk (2012)
1st International Workshop on Functional Mapping with ECoG, New Orleans, LA

Perspectives on ECoG Research and Application - Gerwin Schalk (2012)
4th International Workshop on Advances in Electrocorticography, New Orleans, LA

Principles of Real-Time Passive Functional Mapping - Gerwin Schalk (2012)
Department of Neurology, Yale University, New Haven, CT

Proceedings of the Third International Workshop on Advances in Electrocorticography. - A L Ritaccio; Beauchamp, Michael; Bosman, Conrado; Peter Brunner; Chang, Edward; Nathan E. Crone; Gunduz, Aysegul; Disha Gupta; Robert T. Knight; Leuthardt, Eric; Litt, Brian; Moran, Daniel; et al. (Epilepsy Behav, 2012)
The Third International Workshop on Advances in Electrocorticography (ECoG) was convened in Washington, DC, on November 10-11, 2011. As in prior meetings, a true multidisciplinary fusion of clinicians, scientists, and engineers from many disciplines gathered to summarize contemporary experiences in brain surface recordings. The proceedings of this meeting serve as evidence of a very robust and transformative field but will yet again require revision to incorporate the advances that the following year will surely bring.
Keywords: Brain Mapping; brain-computer interface; Electrocorticography; Gamma-frequency electroencephalography; high-frequency oscillation; Neuroprosthetics; Seizure detection; Subdural grid

Questionable reliability of the speech-evoked auditory brainstem response (sABR) in typically-developing children. - Dennis J. McFarland; Cacace, Anthony T (Hear Res, 2012)
Keywords: Evoked Potentials, Auditory, Brain Stem; Female; Hearing Tests; Humans; Male; Speech Perception

Real-Time Functional Mapping Using ECoG - Gerwin Schalk (2012)
g.tec ECoG/Spike Workshop, New Orleans, LA

Recording Human Electrocorticographic (ECoG) Signals for Neuroscientific Research and Real-time Functional Cortical Mapping. - Jeremy Jeremy Hill; Disha Gupta; Peter Brunner; Gunduz, Aysegul; Adamo, Matthew A; A L Ritaccio; Gerwin Schalk (J Vis Exp, 2012)
Neuroimaging studies of human cognitive, sensory, and motor processes are usually based on noninvasive techniques such as electroencephalography (EEG), magnetoencephalography or functional magnetic-resonance imaging. These techniques have either inherently low temporal or low spatial resolution, and suffer from low signal-to-noise ratio and/or poor high-frequency sensitivity. Thus, they are suboptimal for exploring the short-lived spatio-temporal dynamics of many of the underlying brain processes. In contrast, the invasive technique of electrocorticography (ECoG) provides brain signals that have an exceptionally high signal-to-noise ratio, less susceptibility to artifacts than EEG, and a high spatial and temporal resolution (i.e., <1 cm/<1 millisecond, respectively). ECoG involves measurement of electrical brain signals using electrodes that are implanted subdurally on the surface of the brain. Recent studies have shown that ECoG amplitudes in certain frequency bands carry substantial information about task-related activity, such as motor execution and planning, auditory processing and visual-spatial attention. Most of this information is captured in the high gamma range (around 70-110 Hz). Thus, gamma activity has been proposed as a robust and general indicator of local cortical function. ECoG can also reveal functional connectivity and resolve finer task-related spatial-temporal dynamics, thereby advancing our understanding of large-scale cortical processes. It has especially proven useful for advancing brain-computer interfacing (BCI) technology for decoding a user's intentions to enhance or improve communication and control. Nevertheless, human ECoG data are often hard to obtain because of the risks and limitations of the invasive procedures involved, and the need to record within the constraints of clinical settings. Still, clinical monitoring to localize epileptic foci offers a unique and valuable opportunity to collect human ECoG data. We describe our methods for collecting recording ECoG, and demonstrate how to use these signals for important real-time applications such as clinical mapping and brain-computer interfacing. Our example uses the BCI2000 software platform and the SIGFRIED method, an application for real-time mapping of brain functions. This procedure yields information that clinicians can subsequently use to guide the complex and laborious process of functional mapping by electrical stimulation. PREREQUISITES AND PLANNING: Patients with drug-resistant partial epilepsy may be candidates for resective surgery of an epileptic focus to minimize the frequency of seizures. Prior to resection, the patients undergo monitoring using subdural electrodes for two purposes: first, to localize the epileptic focus, and second, to identify nearby critical brain areas (i.e., eloquent cortex) where resection could result in long-term functional deficits. To implant electrodes, a craniotomy is performed to open the skull. Then, electrode grids and/or strips are placed on the cortex, usually beneath the dura. A typical grid has a set of 8 x 8 platinum-iridium electrodes of 4 mm diameter (2.3 mm exposed surface) embedded in silicon with an inter-electrode distance of 1cm. A strip typically contains 4 or 6 such electrodes in a single line. The locations for these grids/strips are planned by a team of neurologists and neurosurgeons, and are based on previous EEG monitoring, on a structural MRI of the patient's brain, and on relevant factors of the patient's history. Continuous recording over a period of 5-12 days serves to localize epileptic foci, and electrical stimulation via the implanted electrodes allows clinicians to map eloquent cortex. At the end of the monitoring period, explantation of the electrodes and therapeutic resection are performed together in one procedure. In addition to its primary clinical purpose, invasive monitoring also provides a unique opportunity to acquire human ECoG data for neuroscientific research. The decision to include a prospective patient in the research is based on the planned location of their electrodes, on the patient's performance scores on neuropsychological assessments, and on their informed consent, which is predicated on their understanding that participation in research is optional and is not related to their treatment. As with all research involving human subjects, the research protocol must be approved by the hospital's institutional review board. The decision to perform individual experimental tasks is made day-by-day, and is contingent on the patient's endurance and willingness to participate. Some or all of the experiments may be prevented by problems with the clinical state of the patient, such as post-operative facial swelling, temporary aphasia, frequent seizures, post-ictal fatigue and confusion, and more general pain or discomfort. At the Epilepsy Monitoring Unit at Albany Medical Center in Albany, New York, clinical monitoring is implemented around the clock using a 192-channel Nihon-Kohden Neurofax monitoring system. Research recordings are made in collaboration with the Wadsworth Center of the New York State Department of Health in Albany. Signals from the ECoG electrodes are fed simultaneously to the research and the clinical systems via splitter connectors. To ensure that the clinical and research systems do not interfere with each other, the two systems typically use separate grounds. In fact, an epidural strip of electrodes is sometimes implanted to provide a ground for the clinical system. Whether research or clinical recording system, the grounding electrode is chosen to be distant from the predicted epileptic focus and from cortical areas of interest for the research. Our research system consists of eight synchronized 16-channel g.USBamp amplifier/digitizer units (g.tec, Graz, Austria). These were chosen because they are safety-rated and FDA-approved for invasive recordings, they have a very low noise-floor in the high-frequency range in which the signals of interest are found, and they come with an SDK that allows them to be integrated with custom-written research software. In order to capture the high-gamma signal accurately, we acquire signals at 1200Hz sampling rate-considerably higher than that of the typical EEG experiment or that of many clinical monitoring systems. A built-in low-pass filter automatically prevents aliasing of signals higher than the digitizer can capture. The patient's eye gaze is tracked using a monitor with a built-in Tobii T-60 eye-tracking system (Tobii Tech., Stockholm, Sweden). Additional accessories such as joystick, bluetooth Wiimote (Nintendo Co.), data-glove (5(th) Dimension Technologies), keyboard, microphone, headphones, or video camera are connected depending on the requirements of the particular experiment. Data collection, stimulus presentation, synchronization with the different input/output accessories, and real-time analysis and visualization are accomplished using our BCI2000 software. BCI2000 is a freely available general-purpose software system for real-time biosignal data acquisition, processing and feedback. It includes an array of pre-built modules that can be flexibly configured for many different purposes, and that can be extended by researchers' own code in C++, MATLAB or Python. BCI2000 consists of four modules that communicate with each other via a network-capable protocol: a Source module that handles the acquisition of brain signals from one of 19 different hardware systems from different manufacturers; a Signal Processing module that extracts relevant ECoG features and translates them into output signals; an Application module that delivers stimuli and feedback to the subject; and the Operator module that provides a graphical interface to the investigator. A number of different experiments may be conducted with any given patient. The priority of experiments will be determined by the location of the particular patient's electrodes. However, we usually begin our experimentation using the SIGFRIED (SIGnal modeling For Realtime Identification and Event Detection) mapping method, which detects and displays significant task-related activity in real time. The resulting functional map allows us to further tailor subsequent experimental protocols and may also prove as a useful starting point for traditional mapping by electrocortical stimulation (ECS). Although ECS mapping remains the gold standard for predicting the clinical outcome of resection, the process of ECS mapping is time consuming and also has other problems, such as after-discharges or seizures. Thus, a passive functional mapping technique may prove valuable in providing an initial estimate of the locus of eloquent cortex, which may then be confirmed and refined by ECS. The results from our passive SIGFRIED mapping technique have been shown to exhibit substantial concurrence with the results derived using ECS mapping. The protocol described in this paper establishes a general methodology for gathering human ECoG data, before proceeding to illustrate how experiments can be initiated using the BCI2000 software platform. Finally, as a specific example, we describe how to perform passive functional mapping using the BCI2000-based SIGFRIED system.
Keywords: BCI2000; brain-computer interfacing; Electrocorticography; epilepsy monitoring; functional brain mapping; issue 64; Magnetic Resonance Imaging; MRI; neuroscience; SIGFRIED

Review of the BCI Competition IV. - Tangermann, M.; Muller, K.R.; Aertsen, A.; Niels Birbaumer; Christoph Braun; Brunner, Clemens; Leeb, R.; Mehring, C.; Miller, K.J.; Mueller-Putz, G.; Nolte, G.; Pfurtscheller, G.; et al. (Frontiers in Neuroprosthetics, 2012)
The BCI competition IV stands in the tradition of prior BCI competitions that aim to provide high quality neuroscientific data for open access to the scientific community. As experienced already in prior competitions not only scientists from the narrow field of BCI compete, but scholars with a broad variety of backgrounds and nationalities. They include high specialists as well as students. The goals of all BCI competitions have always been to challenge with respect to novel paradigms and complex data. We report on the following challenges: (1) asynchronous data, (2) synthetic, (3) multi-class continuous data, (4) session-to-session transfer, (5) directionally modulated MEG, (6) finger movements recorded by ECoG. As after past competitions, our hope is that winning entries may enhance the analysis methods of future BCIs.
Keywords: BCI; brain-computer interface; competition

Silent Communication: toward using brain signals. - Pei, Xiao-Mei; Jeremy Jeremy Hill; Gerwin Schalk (IEEE Pulse, 2012)
From the 1980s movie Firefox to the more recent Avatar, popular science fiction has speculated about the possibility of a persons thoughts being read directly from his or her brain. Such braincomputer interfaces (BCIs) might allow people who are paralyzed to communicate with and control their environment, and there might also be applications in military situations wherever silent user-to-user communication is desirable. Previous studies have shown that BCI systems can use brain signals related to movements and movement imagery or attention-based character selection. Although these systems have successfully demonstrated the possibility to control devices using brain function, directly inferring which word a person intends to communicate has been elusive. A BCI using imagined speech might provide such a practical, intuitive device. Toward this goal, our studies to date addressed two scientific questions: (1) Can brain signals accurately characterize different aspects of speech? (2) Is it possible to predict spoken or imagined words or their components using brain signals?
Keywords: Animals; Brain; Brain Waves; Humans; Movement; User-Computer Interface

A single g factor is not necessary to simulate positive correlations between cognitive tests. - Dennis J. McFarland (J Clin Exp Neuropsychol, 2012)
In the area of abilities testing, one issue of continued dissent is whether abilities are best conceptualized as manifestations of a single underlying general factor or as reflecting the combination of multiple traits that may be dissociable. The fact that diverse cognitive tests tend to be positively correlated has been taken as evidence for a single general ability or "g" factor. In the present study, simulations of test performance were run to evaluate the hypothesis that multiple independent abilities that affect test performance in a consistent manner will produce a positive manifold. Correlation matrices were simulated from models using either one or eight independent factors. The extent to which these factors operated in a consistent manner across tests (i.e., that a factor that facilitates performance on one test tends to facilitate performance on other tests) was manipulated by varying the mean value of the randomly selected weights. The tendency of both a single factor and eight independent factors to produce positive correlations increased as the randomly selected weights operated in a more consistent fashion. Thus the presence of a positive manifold in the correlations between diverse cognitive tests does not provide differential support for either single factor or multiple factor models of general abilities.
Keywords: Aptitude; Cognition; Humans; Models, Theoretical; Neuropsychological Tests

Temporal evolution of gamma activity in human cortex during an overt and covert word repetition task. - Leuthardt, E C; Pei, Xiao-Mei; Breshears, Jonathan; Charles M Gaona; Sharma, Mohit; Zachary V. Freudenberg; Barbour, Dennis L; Gerwin Schalk (Front Hum Neurosci, 2012)
Several scientists have proposed different models for cortical processing of speech. Classically, the regions participating in language were thought to be modular with a linear sequence of activations. More recently, modern theoretical models have posited a more hierarchical and distributed interaction of anatomic areas for the various stages of speech processing. Traditional imaging techniques can only define the location or time of cortical activation, which impedes the further evaluation and refinement of these models. In this study, we take advantage of recordings from the surface of the brain [electrocorticography (ECoG)], which can accurately detect the location and timing of cortical activations, to study the time course of ECoG high gamma (HG) modulations during an overt and covert word repetition task for different cortical areas. For overt word production, our results show substantial perisylvian cortical activations early in the perceptual phase of the task that were maintained through word articulation. However, this broad activation is attenuated during the expressive phase of covert word repetition. Across the different repetition tasks, the utilization of the different cortical sites within the perisylvian region varied in the degree of activation dependent on which stimulus was provided (auditoryor visual cue) and whether the word was to be spoken or imagined. Taken together, the data support current models of speech that have been previously described with functional imaging. Moreover, this study demonstrates that the broad perisylvian speech network activates early and maintains suprathreshold activation throughout the word repetition task that appears to be modulated by the demands of different conditions.
Keywords: cortex; Electrocorticography; gamma rhythms; human; Speech

Treatments/Interventions for Autism @ Autism Outreach Albany Workshop www.autism-outreach.com - Disha Gupta (2012)

Use of SPIDER and SPIRE in Image Reconstruction. - Leith, ArDean; Baxter, Bill; Frank, Joachim (International Tables for Crystallography, 2012)
SPIDER is a comprehensive command-operated suite of programs for image processing in electron microscopy, with special emphasis on single-particle reconstruction. This chapter provides an outline of the way SPIDER and SPIRE, its interactive graphical user interface, may be used to obtain a three-dimensional reconstruction from projections of many randomly oriented realizations of a biological molecule.

Using Machines to Read the Mind - Gerwin Schalk (2012)
Department of Neurology and Neurological Services, Stanford University School of Medicine, Palo Alto, CA

Value of amplitude, phase, and coherence features for a sensorimotor rhythm-based brain-computer interface. - Krusienski, Dean J; Dennis J. McFarland; Jonathan Wolpaw (Brain Res Bull, 2012)
Measures that quantify the relationship between two or more brain signals are drawing attention as neuroscientists explore the mechanisms of large-scale integration that enable coherent behavior and cognition. Traditional Fourier-based measures of coherence have been used to quantify frequency-dependent relationships between two signals. More recently, several off-line studies examined phase-locking value (PLV) as a possible feature for use in brain-computer interface (BCI) systems. However, only a few individuals have been studied and full statistical comparisons among the different classes of features and their combinations have not been conducted. The present study examines the relative BCI performance of spectral power, coherence, and PLV, alone and in combination. The results indicate that spectral power produced classification at least as good as PLV, coherence, or any possible combination of these measures. This may be due to the fact that all three measures reflect mainly the activity of a single signal source (i.e., an area of sensorimotor cortex). This possibility is supported by the finding that EEG signals from different channels generally had near-zero phase differences. Coherence, PLV, and other measures of inter-channel relationships may be more valuable for BCIs that use signals from more than one distinct cortical source.
Keywords: Algorithms; Brain; Electroencephalography; Humans; Motor Cortex; User-Computer Interface

Advanced BCI2000 Concepts - Gerwin Schalk (2011)
8th BCI2000 Workshop, University Medical Center, Utrecht, The Netherlands

Anatomically Constrained Decoding of Finger Flexion from Electrocorticographic Signals - Zuoguan Wang; Gerwin Schalk; Ji, Q (NIPS, 2011)

Auditory Processing and Anticipation @ The 3rd International Workshop on Advances in Electrocorticography - Disha Gupta (2011)

BCI2000 - Gerwin Schalk (2011)
FBNCI Cluster Workshop for Roadmap Development, Graz University of Technology

BCI2000: A General-Purpose BCI System and its Application to ECoG Signals - Gerwin Schalk (2011)
g.tec Brain-Computer Interface Workshop, IEEE EMBC Conference, Boston, MA

BCI2000: A General-Purpose BCI System and its Application to ECoG Signals - Gerwin Schalk (2011)
g.tec Brain-Computer Interface Workshop, Washington, DC

Brain-Computer Interfaces for Communication and Control. - Dennis J. McFarland; Jonathan Wolpaw (Communications of the ACM, 2011)

Brain-Computer Interfaces: Integrating Bioengineering and Neuroscience Research - Gerwin Schalk (2011)
Keynote, 37th Annual Northeast Bioengineering Conference, Rensselaer Polytechnic Institute, Troy, New York

Brain-Computer Interfaces: The Hope, The Hype, The Power, and The Pain - Gerwin Schalk (2011)
Brain-Computer Interfacing in 2011, Rudolf Magnus Institute for Neuroscience, Utrecht, The Netherlands

Brain-computer interfaces using electrocorticographic signals. - Gerwin Schalk; Leuthardt, E C (IEEE Rev Biomed Eng, 2011)
Many studies over the past two decades have shown that people and animals can use brain signals to convey their intent to a computer using brain-computer interfaces (BCIs). BCI systems measure specific features of brain activity and translate them into control signals that drive an output. The sensor modalities that have most commonly been used in BCI studies have been electroencephalographic (EEG) recordings from the scalp and single-neuron recordings from within the cortex. Over the past decade, an increasing number of studies has explored the use of electrocorticographic (ECoG) activity recorded directly from the surface of the brain. ECoG has attracted substantial and increasing interest, because it has been shown to reflect specific details of actual and imagined actions, and because its technical characteristics should readily support robust and chronic implementations of BCI systems in humans. This review provides general perspectives on the ECoG platform; describes the different electrophysiological features that can be detected in ECoG; elaborates on the signal acquisition issues, protocols, and online performance of ECoG-based BCI studies to date; presents important limitations of current ECoG studies; discusses opportunities for further research; and finally presents a vision for eventual clinical implementation. In summary, the studies presented to date strongly encourage further research using the ECoG platform for basic neuroscientific research, as well as for translational neuroprosthetic applications.
Keywords: Brain-computer interface (BCI); brain-machine interface (BMI); electrocorticography (ECoG)

Causal influence of gamma oscillations on the sensorimotor rhythm. - Grosse-Wentrup, Moritz; Schölkopf, B; Jeremy Jeremy Hill (Neuroimage, 2011)
Gamma oscillations of the electromagnetic field of the brain are known to be involved in a variety of cognitive processes, and are believed to be fundamental for information processing within the brain. While gamma oscillations have been shown to be correlated with brain rhythms at different frequencies, to date no empirical evidence has been presented that supports a causal influence of gamma oscillations on other brain rhythms. In this work, we study the relation of gamma oscillations and the sensorimotor rhythm (SMR) in healthy human subjects using electroencephalography. We first demonstrate that modulation of the SMR, induced by motor imagery of either the left or right hand, is positively correlated with the power of frontal and occipital gamma oscillations, and negatively correlated with the power of centro-parietal gamma oscillations. We then demonstrate that the most simple causal structure, capable of explaining the observed correlation of gamma oscillations and the SMR, entails a causal influence of gamma oscillations on the SMR. This finding supports the fundamental role attributed to gamma oscillations for information processing within the brain, and is of particular importance for brain-computer interfaces (BCIs). As modulation of the SMR is typically used in BCIs to infer a subject's intention, our findings entail that gamma oscillations have a causal influence on a subject's capability to utilize a BCI for means of communication.
Keywords: Adult; Cerebral Cortex; Electroencephalography; Female; Humans; Imagination; Male; Signal Processing, Computer-Assisted; User-Computer Interface

Closing the sensorimotor loop: haptic feedback facilitates decoding of motor imagery. - Gomez-Rodriguez, M; Peters, J; Jeremy Jeremy Hill; Schölkopf, B; Gharabaghi, A; Grosse-Wentrup, Moritz (J Neural Eng, 2011)
The combination of brain-computer interfaces (BCIs) with robot-assisted physical therapy constitutes a promising approach to neurorehabilitation of patients with severe hemiparetic syndromes caused by cerebrovascular brain damage (e.g. stroke) and other neurological conditions. In such a scenario, a key aspect is how to reestablish the disrupted sensorimotor feedback loop. However, to date it is an open question how artificially closing the sensorimotor feedback loop influences the decoding performance of a BCI. In this paper, we answer this issue by studying six healthy subjects and two stroke patients. We present empirical evidence that haptic feedback, provided by a seven degrees of freedom robotic arm, facilitates online decoding of arm movement intention. The results support the feasibility of future rehabilitative treatments based on the combination of robot-assisted physical therapy with BCIs.
Keywords: Brain; Evoked Potentials, Motor; Evoked Potentials, Somatosensory; Feedback, Physiological; Female; Humans; Imagination; Male; Movement; Robotics; Touch; User-Computer Interface

Communicating Directly from the Brain - Gerwin Schalk (2011)
EmTech Conference, MIT Campus

Covariance is the proper measure of test-retest reliability. - Dennis J. McFarland; Anthony T. Cacace (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2011)
Keywords: Speech Perception

Current Trends in Hardware and Software for Brain-Computer Interfaces (BCIs). - Peter Brunner; Bianchi, L; Guger, C; Cincotti, F; Gerwin Schalk (J Neural Eng, 2011)
A brain-computer interface (BCI) provides a non-muscular communication channel to people with and without disabilities. BCI devices consist of hardware and software. BCI hardware records signals from the brain, either invasively or non-invasively, using a series of device components. BCI software then translates these signals into device output commands and provides feedback. One may categorize different types of BCI applications into the following four categories: basic research, clinical/translational research, consumer products, and emerging applications. These four categories use BCI hardware and software, but have different sets of requirements. For example, while basic research needs to explore a wide range of system configurations, and thus requires a wide range of hardware and software capabilities, applications in the other three categories may be designed for relatively narrow purposes and thus may only need a very limited subset of capabilities. This paper summarizes technical aspects for each of these four categories of BCI applications. The results indicate that BCI technology is in transition from isolated demonstrations to systematic research and commercial development. This process requires several multidisciplinary efforts, including the development of better integrated and more robust BCI hardware and software, the definition of standardized interfaces, and the developmentof certification, dissemination and reimbursement procedures.
Keywords: Biofeedback, Psychology; Brain; Brain Mapping; Electroencephalography; Equipment Design; Equipment Failure Analysis; Humans; Man-Machine Systems; Software; User-Computer Interface

Decoding vowels and consonants in spoken and imagined words using electrocorticographic signals in humans. - Pei, Xiao-Mei; Barbour, Dennis L; Leuthardt, E C; Gerwin Schalk (J Neural Eng, 2011)
Several stories in the popular media have speculated that it may be possible to infer from the brain which word a person is speaking or even thinking. While recent studies have demonstrated that brain signals can give detailed information about actual and imagined actions, such as different types of limb movements or spoken words, concrete experimental evidence for the possibility to 'read the mind', i.e. to interpret internally-generated speech, has been scarce. In this study, we found that it is possible to use signals recorded from the surface of the brain (electrocorticography) to discriminate the vowels and consonants embedded in spoken and in imagined words, and we defined the cortical areas that held the most information about discrimination of vowels and consonants. The results shed light on the distinct mechanisms associated with production of vowels and consonants, and could provide the basis for brain-based communication using imagined speech.
Keywords: Adolescent; Adult; Brain; Brain Mapping; Cerebral Cortex; Communication Aids for Disabled; Data Interpretation, Statistical; Discrimination (Psychology); Electrodes, Implanted; Electroencephalography; Epilepsy; Female; Functional Laterality; Humans; Male; Middle Aged; Movement; Speech Perception; User-Computer Interface

Defense-related insights and solutions from neuroscience and neuroengineering. - Gunduz, Aysegul; Gerwin Schalk (2011)
Communication of intent usually requires motor function, which can be limiting during military missions. Determining a soldier's intent from brain signals rather than using muscles would have numerous applications for tactical combat. Brain-computer interfaces (BCIs) translate brain signals into machine readable form and could optimize a soldier's interaction with the surrounding environment. However, current BCI devices have largely remained laboratory curiosities, because current techniques either require extended training or do not have the requisite signal fidelity, because they are highly invasive and thus not safe or practical for use in humans, or because they rely on equipment (such as magnetic resonance imaging scanners) that do not allow for real-time applications and/or field deployment. The objective of our research program is to create a prototype of a system for communication and monitoring of orientation that uses brain signals to provide, in real time, an accurate assessment of the users intentional focus and imagined speech. We expect that our efforts will provide a prototype of the first intuitive brain-based communication and orientation system for human use.

Defense-related insights and solutions from neuroscience and neuroengineering - Gunduz, Aysegul; Gerwin Schalk (2011)
Communication of intent usually requires motor function, which can be limiting during military missions. Determining a soldier's intent from brain signals rather than using muscles would have numerous applications for tactical combat. Brain-computer interfaces (BCIs) translate brain signals into machine readable form and could optimize a soldier's interaction with the surrounding environment. However, current BCI devices have largely remained laboratory curiosities, because current techniques either require extended training or do not have the requisite signal fidelity, because they are highly invasive and thus not safe or practical for use in humans, or because they rely on equipment (such as magnetic resonance imaging scanners) that do not allow for real-time applications and/or field deployment. The objective of our research program is to create a prototype of a system for communication and monitoring of orientation that uses brain signals to provide, in real time, an accurate assessment of the users intentional focus and imagined speech. We expect that our efforts will provide a prototype of the first intuitive brain-based communication and orientation system for human use.

Dichotic and dichoptic digit perception in normal adults. - Lawfield, Angela; Dennis J. McFarland; Cacace, Anthony T (J Am Acad Audiol, 2011)
BACKGROUND: Verbally based dichotic-listening experiments and reproduction-mediated response-selection strategies have been used for over four decades to study perceptual/cognitive aspects of auditory information processing and make inferences about hemispheric asymmetries and language lateralization in the brain. Test procedures using dichotic digits have also been used to assess for disorders of auditory processing. However, with this application, limitations exist and paradigms need to be developed to improve specificity of the diagnosis. Use of matched tasks in multiple sensory modalities is a logical approach to address this issue. Herein, we use dichotic listening and dichoptic viewing of visually presented digits for making this comparison. PURPOSE: To evaluate methodological issues involved in using matched tasks of dichotic listening and dichoptic viewing in normal adults. RESEARCH DESIGN: A multivariate assessment of the effects of modality (auditory vs. visual), digit-span length (1-3 pairs), response selection (recognition vs. reproduction), and ear/visual hemifield of presentation (left vs. right) on dichotic and dichoptic digit perception. STUDY SAMPLE: Thirty adults (12 males, 18 females) ranging in age from 18 to 30 yr with normal hearing sensitivity and normal or corrected-to-normal visual acuity. DATA COLLECTION AND ANALYSIS: A computerized, custom-designed program was used for all data collection and analysis. A four-way repeated measures analysis of variance (ANOVA) evaluated the effects of modality, digit-span length, response selection, and ear/visual field of presentation. RESULTS: The ANOVA revealed that performances on dichotic listening and dichoptic viewing tasks were dependent on complex interactions between modality, digit-span length, response selection, and ear/visual hemifield of presentation. Correlation analysis suggested a common effect on overall accuracy of performance but isolated only an auditory factor for a laterality index. CONCLUSIONS: The variables used in this experiment affected performances in the auditory modality to a greater extent than in the visual modality. The right-ear advantage observed in the dichotic-digits task was most evident when reproduction mediated response selection was used in conjunction with three-digit pairs. This effect implies that factors such as "speech related output mechanisms" and digit-span length (working memory) contribute to laterality effects in dichotic listening performance with traditional paradigms. Thus, the use of multiple-digit pairs to avoid ceiling effects and the application of verbal reproduction as a means of response selection may accentuate the role of nonperceptual factors in performance. Ideally, tests of perceptual abilities should be relatively free of such effects.
Keywords: Adolescent; Adult; Auditory Perception; Dichotic Listening Tests; Female; Functional Laterality; Humans; Male; Recognition (Psychology); Reference Values; Reproducibility of Results; Task Performance and Analysis; Visual Perception; Young Adult

Editorial: Current Trends in Brain-Computer Interface (BCI) Research and Development. - Nam, C.S.; Gerwin Schalk; Moore-Jackson, M. (International Journal of Human-Computer Interaction, 2011)

Electrocorticography: A New Window into Brain Function - Gerwin Schalk (2011)
Department of Brain and Cognitive Sciences, Massachusetts Institute of Technology, Boston, MA

Exciting Adventures in Neuroscience and Neuroengineering - Gerwin Schalk (2011)
Department of Biomedical Engineering, Rensselaer Polytechnic Institute, Troy, New York

Exciting Adventures in Neuroscience and Neuroengineering - Gerwin Schalk (2011)
Institute for Knowledge Discovery, Graz Technical University, Graz, Austria

Exciting Adventures in Neuroscience and Neuroengineering - Gerwin Schalk (2011)
Electrical and Computer Engineering Department, University of Houston, Houston, Texas

A graphical model framework for decoding in the visual ERP-based BCI speller. - Martens, S M M; Mooij, J M; Jeremy Jeremy Hill; Farquhar, Jason; Schölkopf, B (Neural Comput, 2011)
We present a graphical model framework for decoding in the visual ERP-based speller system. The proposed framework allows researchers to build generative models from which the decoding rules are obtained in a straightforward manner. We suggest two models for generating brain signals conditioned on the stimulus events. Both models incorporate letter frequency information but assume different dependencies between brain signals and stimulus events. For both models, we derive decoding rules and perform a discriminative training. We show on real visual speller data how decoding performance improves by incorporating letter frequency information and using a more realistic graphical model for the dependencies between the brain signals and the stimulus events. Furthermore, we discuss how the standard approach to decoding can be seen as a special case of the graphical model framework. The letter also gives more insight into the discriminative approach for decoding in the visual speller system.
Keywords: Artificial Intelligence; Computer User Training; Discrimination Learning; Electroencephalography; Evoked Potentials; Evoked Potentials, Visual; Humans; Language; Models, Neurological; Models, Theoretical; Reading; Signal Processing, Computer-Assisted; User-Computer Interface; Visual Cortex; Visual Perception

Introduction to BCI2000 - Gerwin Schalk (2011)
8th BCI2000 Workshop, University Medical Center, Utrecht, The Netherlands

Neural Correlates of Covert Attention in Electrocorticographic (ECoG) Signals in Humans. - Gunduz, Aysegul; Peter Brunner; Amy Daitch; Leuthardt, E C; A L Ritaccio; Pesaran, Bijan; Gerwin Schalk (Front Hum Neurosci, 2011)
Attention is a cognitive selection mechanism that allocates the limited processing resources of the brain to the sensory streams most relevant to our immediate goals, thereby enhancing responsiveness and behavioral performance. The underlying neural mechanisms of orienting attention are distributed across a widespread cortical network. While aspects of this network have been extensively studied, details about the electrophysiological dynamics of this network are scarce. In this study, we investigated attentional networks using electrocorticographic (ECoG) recordings from the surface of the brain, which combine broad spatial coverage with high temporal resolution, in five human subjects. ECoG was recorded when subjects covertly attended to a spatial location and responded to contrast changes in the presence of distractors in a modified Posner cueing task. ECoG amplitudes in the alpha, beta, and gamma bands identified neural changes associated with covert attention and motor preparation/execution in the different stages of the task. The results show that attentional engagement was primarily associated with ECoG activity in the visual, prefrontal, premotor, and parietal cortices. Motor preparation/execution was associated with ECoG activity in premotor/sensorimotor cortices. In summary, our results illustrate rich and distributed cortical dynamics that are associated with orienting attention and the subsequent motor preparation and execution. These findings are largely consistent with and expand on primate studies using intracortical recordings and human functional neuroimaging studies.
Keywords: covert attention; Electrocorticography; intention; motor response; visual-spatial attention

Neurological principles and rehabilitation of action disorders: rehabilitation interventions. - Pomeroy, Valerie; Aglioti, Salvatore M; Mark, Victor W; Dennis J. McFarland; Stinear, Cathy; Wolf, Steven L; Corbetta, Maurizio; Fitzpatrick, Susan M (Neurorehabil Neural Repair, 2011)
This third chapter discusses the evidence for the rehabilitation of the most common movement disorders of the upper extremity. The authors also present a framework, building on the computation, anatomy, and physiology (CAP) model, for incorporating some of the principles discussed in the 2 previous chapters by Frey et al and Sathian et al in the practice of rehabilitation and for discussing potentially helpful interventions based on emergent neuroscience principles.
Keywords: Humans; Models, Neurological; Movement Disorders; Recovery of Function; Upper Extremity

Neurological principles and rehabilitation of action disorders: rehabilitation interventions. - Pomeroy, Valerie; Aglioti, Salvatore M.; Mark, Victor W.; Dennis J. McFarland; Stinear, Cathy; Wolf, Steven L.; Corbetta, Maurizio; Fitzpatrick, Susan M. (Neurorehabilitation and neural repair, 2011)
This third chapter discusses the evidence for the rehabilitation of the most common movement disorders of the upper extremity. The authors also present a framework, building on the computation, anatomy, and physiology (CAP) model, for incorporating some of the principles discussed in the 2 previous chapters by Frey et al and Sathian et al in the practice of rehabilitation and for discussing potentially helpful interventions based on emergent neuroscience principles.
Keywords: Upper Extremity

Nonuniform high-gamma (60-500 Hz) power changes dissociate cognitive task and anatomy in human cortex. - Charles M Gaona; Sharma, Mohit; Zachary V. Freudenberg; Breshears, Jonathan; Bundy, David T; Roland, Jarod; Barbour, Dennis L; Gerwin Schalk; Leuthardt, E C (J Neurosci, 2011)
High-gamma-band (>60 Hz) power changes in cortical electrophysiology are a reliable indicator of focal, event-related cortical activity. Despite discoveries of oscillatory subthreshold and synchronous suprathreshold activity at the cellular level, there is an increasingly popular view that high-gamma-band amplitude changes recorded from cellular ensembles are the result of asynchronous firing activity that yields wideband and uniform power increases. Others have demonstrated independence of power changes in the low- and high-gamma bands, but to date, no studies have shown evidence of any such independence above 60 Hz. Based on nonuniformities in time-frequency analyses of electrocorticographic (ECoG) signals, we hypothesized that induced high-gamma-band (60-500 Hz) power changes are more heterogeneous than currently understood. Using single-word repetition tasks in six human subjects, we showed that functional responsiveness of different ECoG high-gamma sub-bands can discriminate cognitive task (e.g., hearing, reading, speaking) and cortical locations. Power changes in these sub-bands of the high-gamma range are consistently present within single trials and have statistically different time courses within the trial structure. Moreover, when consolidated across all subjects within three task-relevant anatomic regions (sensorimotor, Broca's area, and superior temporal gyrus), these behavior- and location-dependent power changes evidenced nonuniform trends across the population. Together, the independence and nonuniformity of power changes across a broad range of frequencies suggest that a new approach to evaluating high-gamma-band cortical activity is necessary. These findings show that in addition to time and location, frequency is another fundamental dimension of high-gamma dynamics.
Keywords: Acoustic Stimulation; Adolescent; Adult; Analysis of Variance; Brain Mapping; Brain Waves; Cerebral Cortex; Cognition Disorders; Electroencephalography; Epilepsy; Evoked Potentials; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Nonlinear Dynamics; Photic Stimulation; Reaction Time; Spectrum Analysis; Time Factors; Vocabulary

Operant conditioning of rat soleus H-reflex oppositely affects another H-reflex and changes locomotor kinematics. - Yi Chen; Lu Chen; Wang, Yu; Jonathan Wolpaw; Xiang Yang Chen (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2011)
H-reflex conditioning is a model for studying the plasticity associated with a new motor skill. We are exploring its effects on other reflexes and on locomotion. Rats were implanted with EMG electrodes in both solei (SOL(R) and SOL(L)) and right quadriceps (QD(R)), and stimulating cuffs on both posterior tibial (PT) nerves and right posterior femoral nerve. When SOL(R) EMG remained in a defined range, PT(R) stimulation just above M-response threshold elicited the SOL(R) H-reflex. Analogous procedures elicited the QD(R) and SOL(L) H-reflexes. After a control period, each rat was exposed for 50 d to a protocol that rewarded SOL(R) H-reflexes that were above (HRup rats) or below (HRdown rats) a criterion. HRup conditioning increased the SOL(R) H-reflex to 214 ± 37% (mean ± SEM) of control (p = 0.02) and decreased the QD(R) H-reflex to 71 ± 26% (p = 0.06). HRdown conditioning decreased the SOL(R) H-reflex to 69 ± 2% (p < 0.001) and increased the QD(R) H-reflex to 121 ± 7% (p = 0.02). These changes remained during locomotion. The SOL(L) H-reflex did not change. During the stance phase of locomotion, ankle plantarflexion increased in HRup rats and decreased in HRdown rats, hip extension did the opposite, and hip height did not change. The plasticity that changes the QD(R) H-reflex and locomotor kinematics may be inevitable (i.e., reactive) due to the ubiquity of activity-dependent CNS plasticity, and/or necessary (i.e., compensatory) to preserve other behaviors (e.g., locomotion) that would otherwise be disturbed by the change in the SOL(R) H-reflex pathway. The changes in joint angles, coupled with the preservation of hip height, suggest that compensatory plasticity did occur.
Keywords: Rats; Sprague-Dawley

Opportunities for Clinical Application of Emerging Neuroscientific and Neuroengineering Understanding - Gerwin Schalk (2011)
Neruophysiology Seminar Series, Baylor Hospital, Houston, TX

The P300-based brain-computer interface (BCI): effects of stimulus rate. - Dennis J. McFarland; Sarnacki, William A.; Townsend, George; Theresa M Vaughan; Jonathan Wolpaw (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2011)
OBJECTIVE: Brain-computer interface technology can restore communication and control to people who are severely paralyzed. We have developed a non-invasive BCI based on the P300 event-related potential that uses an 8×9 matrix of 72 items that flash in groups of 6. Stimulus presentation rate (i.e., flash rate) is one of several parameters that could affect the speed and accuracy of performance. We studied performance (i.e., accuracy and characters/min) on copy spelling as a function of flash rate. METHODS: In the first study of six BCI users, stimulus-on and stimulus-off times were equal and flash rate was 4, 8, 16, or 32 Hz. In the second study of five BCI users, flash rate was varied by changing either the stimulus-on or stimulus-off time. RESULTS: For all users, lower flash rates gave higher accuracy. The flash rate that gave the highest characters/min varied across users, ranging from 8 to 32 Hz. However, variations in stimulus-on and stimulus-off times did not themselves significantly affect accuracy. Providing feedback did not affect results in either study suggesting that offline analyses should readily generalize to online performance. However there do appear to be session-specific effects that can influence the generalizability of classifier results. CONCLUSIONS: The results show that stimulus presentation (i.e., flash) rate affects the accuracy and speed of P300 BCI performance. SIGNIFICANCE: These results extend the range over which slower flash rates increase the amplitude of the P300. Considering also presentation time, the optimal rate differs among users, and thus should be set empirically for each user. Optimal flash rate might also vary with other parameters such as the number of items in the matrix.
Keywords: brain-computer interface; neuroprosthesis; P300

Perspectives on ECoG Research and Application - Gerwin Schalk (2011)
3rd International Workshop on Advances in Electrocorticography, Washington, DC

Prior knowledge improves decoding of finger flexion from electrocorticographic signals. - Zuoguan Wang; Ji, Q; Miller, John W; Gerwin Schalk (Front Neurosci, 2011)
Brain-computer interfaces (BCIs) use brain signals to convey a user's intent. Some BCI approaches begin by decoding kinematic parameters of movements from brain signals, and then proceed to using these signals, in absence of movements, to allow a user to control an output. Recent results have shown that electrocorticographic (ECoG) recordings from the surface of the brain in humans can give information about kinematic parameters (e.g., hand velocity or finger flexion). The decoding approaches in these studies usually employed classical classification/regression algorithms that derive a linear mapping between brain signals and outputs. However, they typically only incorporate little prior information about the target movement parameter. In this paper, we incorporate prior knowledge using a Bayesian decoding method, and use it to decode finger flexion from ECoG signals. Specifically, we exploit the constraints that govern finger flexion and incorporate these constraints in the construction, structure, and the probabilistic functions of the prior model of a switched non-parametric dynamic system (SNDS). Given a measurement model resulting from a traditional linear regression method, we decoded finger flexion using posterior estimation that combined the prior and measurement models. Our results show that the application of the Bayesian decoding model, which incorporates prior knowledge, improves decoding performance compared to the application of a linear regression model, which does not incorporate prior knowledge. Thus, the results presented in this paper may ultimately lead to neurally controlled hand prostheses with full fine-grained finger articulation.
Keywords: brain-computer interface; decoding algorithm; electrocorticographic; finger flexion; machine learning; prior knowledge

Proceedings of the Second International Workshop on Advances in Electrocorticography. - A L Ritaccio; Boatman-Reich, Dana; Peter Brunner; Cervenka, Mackenzie C; Cole, Andrew J; Nathan E. Crone; Duckrow, Robert; Korzeniewska, Anna; Litt, Brian; Miller, John W; Moran, D; Parvizi, Josef; et al. (Epilepsy Behav, 2011)
The Second International Workshop on Advances in Electrocorticography (ECoG) was convened in San Diego, CA, USA, on November 11-12, 2010. Between this meeting and the inaugural 2009 event, a much clearer picture has been emerging of cortical ECoG physiology and its relationship to local field potentials and single-cell recordings. Innovations in material engineering are advancing the goal of a stable long-term recording interface. Continued evolution of ECoG-driven brain-computer interface technology is determining innovation in neuroprosthetics. Improvements in instrumentation and statistical methodologies continue to elucidate ECoG correlates of normal human function as well as the ictal state. This proceedings document summarizes the current status of this rapidly evolving field.
Keywords: Brain; Brain Mapping; Brain Waves; Diagnosis, Computer-Assisted; Electroencephalography; Epilepsy; Humans; United States; User-Computer Interface

Rapid Communication with a "P300" Matrix Speller Using Electrocorticographic Signals (ECoG). - Peter Brunner; A L Ritaccio; Emrich, Joseph F; H Bischof; Gerwin Schalk (Front Neurosci, 2011)
A brain-computer interface (BCI) can provide a non-muscular communication channel to severely disabled people. One particular realization of a BCI is the P300 matrix speller that was originally described by Farwell and Donchin (1988). This speller uses event-related potentials (ERPs) that include the P300 ERP. All previous online studies of the P300 matrix speller used scalp-recorded electroencephalography (EEG) and were limited in their communication performance to only a few characters per minute. In our study, we investigated the feasibility of using electrocorticographic (ECoG) signals for online operation of the matrix speller, and determined associated spelling rates. We used the matrix speller that is implemented in the BCI2000 system. This speller used ECoG signals that were recorded from frontal, parietal, and occipital areas in one subject. This subject spelled a total of 444 characters in online experiments. The results showed that the subject sustained a rate of 17 characters/min (i.e., 69 bits/min), and achieved a peak rate of 22 characters/min (i.e., 113 bits/min). Detailed analysis of the results suggests that ERPs over visual areas (i.e., visual evoked potentials) contribute significantly to the performance of the matrix speller BCI system. Our results also point to potential reasons for the apparent advantages in spelling performance of ECoG compared to EEG. Thus, with additional verification in more subjects, these results may further extend the communication options for people with serious neuromuscular disabilities.
Keywords: brain-computer interface; Electrocorticography; event-related potential; P300; speller

Real-Time Functional Mapping Using ECoG - Gerwin Schalk (2011)
g.tec ECoG/Spike Workshop, Washington, DC

Should the parameters of a BCI translation algorithm be continually adapted?. - Dennis J. McFarland; Sarnacki, William A.; Jonathan Wolpaw (Journal of neuroscience methods, 2011)
People with or without motor disabilities can learn to control sensorimotor rhythms (SMRs) recorded from the scalp to move a computer cursor in one or more dimensions or can use the P300 event-related potential as a control signal to make discrete selections. Data collected from individuals using an SMR-based or P300-based BCI were evaluated offline to estimate the impact on performance of continually adapting the parameters of the translation algorithm during BCI operation. The performance of the SMR-based BCI was enhanced by adaptive updating of the feature weights or adaptive normalization of the features. In contrast, P300 performance did not benefit from either of these procedures.
Keywords: adaptation; brain-computer interface; EEG

Space–time network connectivity and cortical activations preceding spike wave discharges in human absence epilepsy: a MEG study. - Disha Gupta; Pauly Ossenblok; Gilles van Luijtelaar (Medical and Biological Engineering and Computing, 2011)
To describe the spatial and temporal profiles of connectivity networks and sources preceding generalized spike-and-wave discharges (SWDs) in human absence epilepsy. Nonlinear associations of MEG signals and cluster indices obtained within the framework of graph theory were determined, while source localization in the frequency domain was performed in the low frequency bands with dynamic imaging of coherent sources. The results were projected on a three-dimensional surface rendering of the brain using a semi-realistic head model and MRI images obtained for each of the five patients studied. An increase in clustering and a decrease in path length preceding SWD onset and a rhythmic pattern of increasing and decreasing connectivity were seen during SWDs. Beamforming showed a consistent appearance of a low frequency frontal cortical source prior to the first generalized spikes. This source was preceded by a low frequency occipital source. The changes in the connectivity networks with the onset of SWDs suggest a pathologically predisposed state towards synchronous seizure networks with increasing connectivity from interictal to preictal and ictal state, while the occipital and frontal low frequency early preictal sources demonstrate that SWDs are not suddenly arising but gradually build up in a dynamic network.
Keywords: Absence epilepsy; Beamforming; Connectivity; Magnetoencephalography; Nonlinear association analysis; Small world networks; Spike wave discharge

Spatiotemporal dynamics of electrocorticographic high gamma activity during overt and covert word repetition. - Pei, Xiao-Mei; Leuthardt, E C; Charles M Gaona; Peter Brunner; Jonathan Wolpaw; Gerwin Schalk (Neuroimage, 2011)
Language is one of the defining abilities of humans. Many studies have characterized the neural correlates of different aspects of language processing. However, the imaging techniques typically used in these studies were limited in either their temporal or spatial resolution. Electrocorticographic (ECoG) recordings from the surface of the brain combine high spatial with high temporal resolution and thus could be a valuable tool for the study of neural correlates of language function. In this study, we defined the spatiotemporal dynamics of ECoG activity during a word repetition task in nine human subjects. ECoG was recorded while each subject overtly or covertly repeated words that were presented either visually or auditorily. ECoG amplitudes in the high gamma (HG) band confidently tracked neural changes associated with stimulus presentation and with the subject's verbal response. Overt word production was primarily associated with HG changes in the superior and middle parts of temporal lobe, Wernicke's area, the supramarginal gyrus, Broca's area, premotor cortex (PMC), primary motor cortex. Covert word production was primarily associated with HG changes in superior temporal lobe and the supramarginal gyrus. Acoustic processing from both auditory stimuli as well as the subject's own voice resulted in HG power changes in superior temporal lobe and Wernicke's area. In summary, this study represents a comprehensive characterization of overt and covert speech using electrophysiological imaging with high spatial and temporal resolution. It thereby complements the findings of previous neuroimaging studies of language and thus further adds to current understanding of word processing in humans.
Keywords: Adolescent; Adult; Brain; Brain Mapping; Electroencephalography; Female; Humans; Male; Middle Aged; Signal Processing, Computer-Assisted; Verbal Behavior

Special issue containing contributions from the Fourth International Brain-Computer Interface Meeting. - Theresa M Vaughan; Jonathan Wolpaw (Journal of neural engineering, 2011)
Keywords: User-Computer Interface

State-of-the-Art in BCI Research: BCI Award 2010. - Guger, C; Gerwin Schalk (Recent Advances in Brain-Computer Interface Systems, 2011)

Toward a gaze-independent matrix speller brain-computer interface. - Peter Brunner; Gerwin Schalk (Clin Neurophysiol, 2011)
Keywords: Attention; Brain; Fixation, Ocular; Humans; User-Computer Interface

Trained modulation of sensorimotor rhythms can affect reaction time. - Chadwick B. Boulay; Sarnacki, W. A.; Jonathan Wolpaw; Dennis J. McFarland (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2011)
OBJECTIVE: Brain-computer interface (BCI) technology might be useful for rehabilitation of motor function. This speculation is based on the premise that modifying the EEG will modify behavior, a proposition for which there is limited empirical data. The present study examined the possibility that voluntary modulation of sensorimotor rhythm (SMR) can affect motor behavior in normal human subjects. METHODS: Six individuals performed a cued-reaction task with variable warning periods. A typical variable foreperiod effect was associated with SMR desynchronization. SMR features that correlated with reaction times were then used to control a two-target cursor movement BCI task. Following successful BCI training, an uncued reaction time task was embedded within the cursor movement task. RESULTS: Voluntarily increasing SMR beta rhythms was associated with longer reaction times than decreasing SMR beta rhythms. CONCLUSIONS: Voluntary modulation of EEG SMR can affect motor behavior. SIGNIFICANCE: These results encourage studies that integrate BCI training into rehabilitation protocols and examine its capacity to augment restoration of useful motor function.
Keywords: brain-computer interface; EEG; Reaction Time

Transition from the locked in to the completely locked-in state: a physiological analysis. - Murguialday, A Ramos; Jeremy Jeremy Hill; Bensch, M; Martens, S M M; S Halder; Nijboer, F; Schoelkopf, Bernhard; Niels Birbaumer; Gharabaghi, A (Clin Neurophysiol, 2011)
OBJECTIVE:  To clarify the physiological and behavioral boundaries between locked-in (LIS) and the completely locked-in state (CLIS) (no voluntary eye movements, no communication possible) through electrophysiological data and to secure brain-computer-interface (BCI) communication. METHODS:  Electromyography from facial muscles, external anal sphincter (EAS), electrooculography and electrocorticographic data during different psychophysiological tests were acquired to define electrophysiological differences in an amyotrophic lateral sclerosis (ALS) patient with an intracranially implanted grid of 112 electrodes for nine months while the patient passed from the LIS to the CLIS. RESULTS:  At the very end of the LIS there was no facial muscle activity, nor external anal sphincter but eye control. Eye movements were slow and lasted for short periods only. During CLIS event related brainpotentials (ERP) to passive limb movements and auditory stimuli were recorded, vibrotactile stimulation of different body parts resulted in no ERP response. CONCLUSIONS:  The results presented contradict the commonly accepted assumption that the EAS is the last remaining muscle under voluntary control and demonstrate complete loss of eye movements in CLIS. The eye muscle was shown to be the last muscle group under voluntary control. The findings suggest ALS as a multisystem disorder, even affecting afferent sensory pathways. SIGNIFICANCE:  Auditory and proprioceptive brain-computer-interface (BCI) systems are the only remaining communication channels in CLIS.
Keywords: Adult; Amyotrophic Lateral Sclerosis; Area Under Curve; Brain; Communication Aids for Disabled; Disease Progression; Electroencephalography; Electromyography; Humans; Male; Signal Processing, Computer-Assisted; User-Computer Interface

Using the electrocorticographic speech network to control a brain-computer interface in humans. - Leuthardt, E C; Charles M Gaona; Sharma, Mohit; Szrama, Nicholas; Roland, Jarod; Zachary V. Freudenberg; Solisb, Jamie; Breshears, Jonathan; Gerwin Schalk (J Neural Eng, 2011)
Electrocorticography (ECoG) has emerged as a new signal platform for brain-computer interface (BCI) systems. Classically, the cortical physiology that has been commonly investigated and utilized for device control in humans has been brain signals from the sensorimotor cortex. Hence, it was unknown whether other neurophysiological substrates, such as the speech network, could be used to further improve on or complement existing motor-based control paradigms. We demonstrate here for the first time that ECoG signals associated with different overt and imagined phoneme articulation can enable invasively monitored human patients to control a one-dimensional computer cursor rapidly and accurately. This phonetic content was distinguishable within higher gamma frequency oscillations and enabled users to achieve final target accuracies between 68% and 91% within 15 min. Additionally, one of the patients achieved robust control using recordings from a microarray consisting of 1 mm spaced microwires. These findings suggest that the cortical network associated with speech could provide an additional cognitive and physiologic substrate for BCI operation and that these signals can be acquired from a cortical array that is small and minimally invasive.
Keywords: Adult; Brain; Brain Mapping; Computer Peripherals; Electroencephalography; Evoked Potentials; Feedback, Physiological; Female; Humans; Imagination; Male; Middle Aged; Nerve Net; Speech Production Measurement; User-Computer Interface

WITHDRAWN: H-reflex up-conditioning after sciatic nerve transection and regeneration may increase VGLUT-1 terminals and GluR2/3 immunoreactivity in spinal motoneurons. - Sun, Chenyou; Wang, Yu; Xiang Yang Chen (Neuroscience letters, 2011)
This article has been withdrawn at the request of the author(s) and/or editor. The Publisher apologizes for any inconvenience this may cause. The full Elsevier Policy on Article Withdrawal can be found at http://www.elsevier.com/locate/withdrawalpolicy.

Advanced BCI2000 Concepts - Gerwin Schalk (2010)
7th BCI2000 Workshop, Asilomar Conference Center, Monterey, California

A brain-based communication and orientation system - Gerwin Schalk (2010)
2010 US Army DDRE MURI Conference in Arlington, VA

A brain-computer interface for long-term independent home use. - Sellers, Eric W.; Theresa M Vaughan; Jonathan Wolpaw (Amyotrophic lateral sclerosis : official publication of the World Federation of Neurology Research Group on Motor Neuron Diseases, 2010)
Our objective was to develop and validate a new brain-computer interface (BCI) system suitable for long-term independent home use by people with severe motor disabilities. The BCI was used by a 51-year-old male with ALS who could no longer use conventional assistive devices. Caregivers learned to place the electrode cap, add electrode gel, and turn on the BCI. After calibration, the system allowed the user to communicate via EEG. Re-calibration was performed remotely (via the internet), and BCI accuracy assessed in periodic tests. Reports of BCI usefulness by the user and the family were also recorded. Results showed that BCI accuracy remained at 83% (r = -.07, n.s.) for over 2.5 years (1.4% expected by chance). The BCI user and his family state that the BCI had restored his independence in social interactions and at work. He uses the BCI to run his NIH-funded research laboratory and to communicate via e-mail with family, friends, and colleagues. In addition to this first user, several other similarly disabled people are now using the BCI in their daily lives. In conclusion, long-term independent home use of this BCI system is practical for severely disabled people, and can contribute significantly to quality of life and productivity.
Keywords: User-Computer Interface

Brain-computer interface research comes of age: traditional assumptions meet emerging realities. - Jonathan Wolpaw (Journal of motor behavior, 2010)
Brain-computer interfaces (BCIs) could provide important new communication and control options for people with severe motor disabilities. Most BCI research to date has been based on 4 assumptions that: (a) intended actions are fully represented in the cerebral cortex; (b) neuronal action potentials can provide the best picture of an intended action; (c) the best BCI is one that records action potentials and decodes them; and (d) ongoing mutual adaptation by the BCI user and the BCI system is not very important. In reality, none of these assumptions is presently defensible. Intended actions are the products of many areas, from the cortex to the spinal cord, and the contributions of each area change continually as the CNS adapts to optimize performance. BCIs must track and guide these adaptations if they are to achieve and maintain good performance. Furthermore, it is not yet clear which category of brain signals will prove most effective for BCI applications. In human studies to date, low-resolution electroencephalography-based BCIs perform as well as high-resolution cortical neuron-based BCIs. In sum, BCIs allow their users to develop new skills in which the users control brain signals rather than muscles. Thus, the central task of BCI research is to determine which brain signals users can best control, to maximize that control, and to translate it accurately and reliably into actions that accomplish the users' intentions.
Keywords: brain-computer interface; brain-machine interface; EEG; human; neuroprosthesis

Brain-Computer Interfaces: Prospects and Problems - Gerwin Schalk (2010)
Cog Sci Issues Colloquium, Department of Cognitive Sciences, Rensselaer Polytechnic Institute, Troy, New York

Brain-computer interfacing based on cognitive control. - Vansteensel, Mariska J; Hermes, Dora; Aarnoutse, Erik J; Bleichner, Martin G; Gerwin Schalk; van Rijen, Peter C; Leijten, Frans S S; Ramsey, Nick F (Ann Neurol, 2010)
OBJECTIVE:  Brain-computer interfaces (BCIs) translate deliberate intentions and associated changes in brain activity into action, thereby offering patients with severe paralysis an alternative means of communication with and control over their environment. Such systems are not available yet, partly due to the high performance standard that is required. A major challenge in the development of implantable BCIs is to identify cortical regions and related functions that an individual can reliably and consciously manipulate. Research predominantly focuses on the sensorimotor cortex, which can be activated by imagining motor actions. However, because this region may not provide an optimal solution to all patients, other neuronal networks need to be examined. Therefore, we investigated whether the cognitive control network can be used for BCI purposes. We also determined the feasibility of using functional magnetic resonance imaging (fMRI) for noninvasive localization of the cognitive control network. METHODS:  Three patients with intractable epilepsy, who were temporarily implanted with subdural grid electrodes for diagnostic purposes, attempted to gain BCI control using the electrocorticographic (ECoG) signal of the left dorsolateral prefrontal cortex (DLPFC). RESULTS:  All subjects quickly gained accurate BCI control by modulation of gamma-power of the left DLPFC. Prelocalization of the relevant region was performed with fMRI and was confirmed using the ECoG signals obtained during mental calculation localizer tasks. INTERPRETATION:  The results indicate that the cognitive control network is a suitable source of signals for BCI applications. They also demonstrate the feasibility of translating understanding about cognitive networks derived from functional neuroimaging into clinical applications.
Keywords: Cognition; Computers; Electrodes; Electroencephalography; Epilepsy; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Neuropsychological Tests; Oxygen; Prefrontal Cortex; Psychomotor Performance; Spectrum Analysis; Time Factors; User-Computer Interface

Can Electrocorticography (ECoG) Support Robust and Powerful Brain-Computer Interfaces?. - Gerwin Schalk (Front Neuroeng, 2010)

A comparison of regression techniques for a two-dimensional sensorimotor rhythm-based brain-computer interface. - Fruitet, Joan; Dennis J. McFarland; Jonathan Wolpaw (Journal of neural engineering, 2010)
People can learn to control electroencephalogram (EEG) features consisting of sensorimotor-rhythm amplitudes and use this control to move a cursor in one, two or three dimensions to a target on a video screen. This study evaluated several possible alternative models for translating these EEG features into two-dimensional cursor movement by building an offline simulation using data collected during online performance. In offline comparisons, support-vector regression (SVM) with a radial basis kernel produced somewhat better performance than simple multiple regression, the LASSO or a linear SVM. These results indicate that proper choice of a translation algorithm is an important factor in optimizing brain-computer interface (BCI) performance, and provide new insight into algorithm choice for multidimensional movement control.
Keywords: Young Adult

Cortical activity during motor execution, motor imagery, and imagery-based online feedback. - Miller, K.J.; Gerwin Schalk; Fetz, Eberhard E; den Nijs, Marcel; Ojemann, J G; Rao, Rajesh P N (Proc Natl Acad Sci U S A, 2010)
Imagery of motor movement plays an important role in learning of complex motor skills, from learning to serve in tennis to perfecting a pirouette in ballet. What and where are the neural substrates that underlie motor imagery-based learning? We measured electrocorticographic cortical surface potentials in eight human subjects during overt action and kinesthetic imagery of the same movement, focusing on power in "high frequency" (76-100 Hz) and "low frequency" (8-32 Hz) ranges. We quantitatively establish that the spatial distribution of local neuronal population activity during motor imagery mimics the spatial distribution of activity during actual motor movement. By comparing responses to electrocortical stimulation with imagery-induced cortical surface activity, we demonstrate the role of primary motor areas in movement imagery. The magnitude of imagery-induced cortical activity change was approximately 25% of that associated with actual movement. However, when subjects learned to use this imagery to control a computer cursor in a simple feedback task, the imagery-induced activity change was significantly augmented, even exceeding that of overt movement.
Keywords: Adolescent; Adult; Biofeedback, Psychology; Cerebral Cortex; Child; Electric Stimulation; Electrocardiography; Female; Humans; Male; Middle Aged; Motor Activity; Young Adult

Decoding finger flexion from electrocorticographic signals using sparse Gaussian process. - Zuoguan Wang; Ji, Q; Kai J. Miller; Gerwin Schalk (International Conference on Pattern Recognition - ICPR, 2010)
A brain-computer interface (BCI) creates a direct communication pathway between the brain and an external device, and can thereby restore function in people with severe motor disabilities. A core component in a BCI system is the decoding algorithm that translates brain signals into action commands of an output device. Most of current decoding algorithms are based on linear models (e.g., derived using linear regression) that may have important shortcomings. The use of nonlinear models (e.g., neural networks) could overcome some of these shortcomings, but has difficulties with high dimensional feature spaces. Here we propose another decoding algorithm that is based on the sparse gaussian process with pseudo-inputs (SPGP). As a nonparametric method, it can model more complex relationships compared to linear methods. As a kernel method, it can readily deal with high dimensional feature space. The evaluations shown in this paper demonstrate that SPGP can decode the flexion of finger movements from electrocorticographic (ECoG) signals more accurately than a previously described algorithm that used a linear model. In addition, by formulating problems in the bayesian probabilistic framework, SPGP can provide estimation of the prediction uncertainty. Furthermore, the trained SPGP offers a very effective way for identifying important features.

Does the 'P300' speller depend on eye gaze?. - Peter Brunner; Joshi, S; S Briskin; Jonathan Wolpaw; H Bischof; Gerwin Schalk (J Neural Eng, 2010)
Many people affected by debilitating neuromuscular disorders such as amyotrophic lateral sclerosis, brainstem stroke or spinal cord injury are impaired in their ability to, or are even unable to, communicate. A brain-computer interface (BCI) uses brain signals, rather than muscles, to re-establish communication with the outside world. One particular BCI approach is the so-called 'P300 matrix speller' that was first described by Farwell and Donchin (1988 Electroencephalogr. Clin. Neurophysiol. 70 510-23). It has been widely assumed that this method does not depend on the ability to focus on the desired character, because it was thought that it relies primarily on the P300-evoked potential and minimally, if at all, on other EEG features such as the visual-evoked potential (VEP). This issue is highly relevant for the clinical application of this BCI method, because eye movements may be impaired or lost in the relevant user population. This study investigated the extent to which the performance in a 'P300' speller BCI depends on eye gaze. We evaluated the performance of 17 healthy subjects using a 'P300' matrix speller under two conditions. Under one condition ('letter'), the subjects focused their eye gaze on the intended letter, while under the second condition ('center'), the subjects focused their eye gaze on a fixation cross that was located in the center of the matrix. The results show that the performance of the 'P300' matrix speller in normal subjects depends in considerable measure on gaze direction. They thereby disprove a widespread assumption in BCI research, and suggest that this BCI might function more effectively for people who retain some eye-movement control. The applicability of these findings to people with severe neuromuscular disabilities (particularly in eye-movements) remains to be determined.
Keywords: Adult; Event-Related Potentials, P300; Eye Movements; Female; Humans; Male; Middle Aged; Models, Neurological; Photic Stimulation; User-Computer Interface; Young Adult

Dynamic imaging of ‘generalized’ seizure activity: clinical MEG workshop @ Sleep and Epilepsy update: 12th annual international clinical symposium Kempenhaeghe - Disha Gupta (2010)

Electrocorticographic frequency alteration mapping for extraoperative localization of speech cortex. - Wu, Melinda; Wisneski, Kimberly; Gerwin Schalk; Sharma, Mohit; Roland, Jarod; Breshears, Jonathan; Charles M Gaona; Leuthardt, E C (Neurosurgery, 2010)
OBJECTIVE:  Electrocortical stimulation (ECS) has long been established for delineating eloquent cortex in extraoperative mapping. However, ECS is still coarse and inefficient in delineating regions of functional cortex and can be hampered by afterdischarges. Given these constraints, an adjunct approach to defining motor cortex is the use of electrocorticographic (ECoG) signal changes associated with active regions of cortex. The broad range of frequency oscillations are categorized into 2 main groups with respect to sensorimotor cortex: low-frequency bands (LFBs) and high-frequency bands (HFBs). The LFBs tend to show a power reduction, whereas the HFBs show power increases with cortical activation. These power changes associated with activated cortex could potentially provide a powerful tool in delineating areas of speech cortex. We explore ECoG signal alterations as they occur with activated region of speech cortex and its potential in clinical brain mapping applications. METHODS:  We evaluated 7 patients who underwent invasive monitoring for seizure localization. Each had extraoperative ECS mapping to identify speech cortex. Additionally, all subjects performed overt speech tasks with an auditory or a visual cue to identify associated frequency power changes in regard to location and degree of concordance with ECS results. RESULTS:  Electrocorticographic frequency alteration mapping (EFAM) had an 83.9% sensitivity and a 40.4% specificity in identifying any language site when considering both frequency bands and both stimulus cues. Electrocorticographic frequency alteration mapping was more sensitive in identifying the Wernicke area (100%) than the Broca area (72.2%). The HFB is uniquely suited to identifying the Wernicke area, whereas a combination of the HFB and LFB is important for Broca localization. CONCLUSION:  The concordance between stimulation and spectral power changes demonstrates the possible utility of EFAM as an adjunct method to improve the efficiency and resolution of identifying speech cortex.
Keywords: Acoustic Stimulation; Adolescent; Adult; Brain Mapping; Cerebral Cortex; Chi-Square Distribution; Electroencephalography; Epilepsy; Female; Humans; Male; Mass Spectrometry; Middle Aged; Photic Stimulation; Speech; Verbal Behavior; Young Adult

Electroencephalographic (EEG) control of three-dimensional movement. - Dennis J. McFarland; Sarnacki, William A.; Jonathan Wolpaw (Journal of neural engineering, 2010)
Brain-computer interfaces (BCIs) can use brain signals from the scalp (EEG), the cortical surface (ECoG), or within the cortex to restore movement control to people who are paralyzed. Like muscle-based skills, BCIs' use requires activity-dependent adaptations in the brain that maintain stable relationships between the person's intent and the signals that convey it. This study shows that humans can learn over a series of training sessions to use EEG for three-dimensional control. The responsible EEG features are focused topographically on the scalp and spectrally in specific frequency bands. People acquire simultaneous control of three independent signals (one for each dimension) and reach targets in a virtual three-dimensional space. Such BCI control in humans has not been reported previously. The results suggest that with further development noninvasive EEG-based BCIs might control the complex movements of robotic arms or neuroprostheses.
Keywords: User-Computer Interface

Emerging Opportunities in Neuroengineering - Gerwin Schalk (2010)
Department of Electrical Engineering and Computer Science, Technical University of Berlin, Berlin, Germany

Emerging Opportunities in Neuroengineering - Gerwin Schalk (2010)
Graduate School of Biomedical Engineering, The University of New South Wales, Sydney, Australia

Encoding of Perception and Cognition in Human Electrocorticographic Signals - Gerwin Schalk (2010)
Keynote Address, Bernstein Conference on Computational Neuroscience, Berlin, Germany

Exciting Directions in Human Electrocorticography - Gerwin Schalk (2010)
Small Scale Systems and Integration and Packaging Center's Seminar Series, Binghamton University, Binghamton, New York

Exciting Directions in Human Electrocorticography - Gerwin Schalk (2010)
University of California San Francisco Medical School, San Francisco, California

Exciting Directions in Neuroscience and Neuroengineering - Gerwin Schalk (2010)
Department of Physical Therapy and Human Movement Sciences, Northwestern University, Feinberg School of Medicine, Chicago, IL

External urethral sphincter motoneuron properties in adult female rats studied in vitro. - Jonathan S. Carp; Tennissen, Ann M.; Liebschutz, Jennifer E.; Xiang Yang Chen; Jonathan Wolpaw (Journal of neurophysiology, 2010)
The external urethral sphincter (EUS) muscle plays a crucial role in lower urinary tract function: its activation helps maintain continence, whereas its relaxation contributes to micturition. To determine how the intrinsic properties of its motoneurons contribute to its physiological function, we have obtained intracellular current-clamp recordings from 49 EUS motoneurons in acutely isolated spinal cord slices from adult female rats. In all, 45% of EUS motoneurons fired spontaneously and steadily (average rate = 12-27 pulses/s). EUS motoneurons were highly excitable, having lower rheobase, higher input resistance, and smaller threshold depolarization than those of rat hindlimb motoneurons recorded in vitro. Correlations between these properties and afterhyperpolarization half-decay time are consistent with EUS motoneurons having characteristics of both fast and slow motor unit types. EUS motoneurons with a slow-like spectrum of properties exhibited spontaneous firing more often than those with fast-like characteristics. During triangular current ramp-induced repetitive firing, recruitment typically occurred at lower current levels than those at derecruitment, although the opposite pattern occurred in 10% of EUS motoneurons. This percentage was likely underestimated due to firing rate adaptation. These findings are consistent with the presence of a basal level of persistent inward current (PIC) in at least some EUS motoneurons. The low EUS motoneuron current and voltage thresholds make them readily recruitable, rendering them well suited to their physiological role in continence. The expression of firing behaviors consistent with PIC activation in this highly reduced preparation raises the possibility that in the intact animal, PICs contribute to urinary function not only through neuromodulator-dependent but also through neuromodulator-independent mechanisms.
Keywords: Urethra

H-reflex up-conditioning encourages recovery of EMG activity and H-reflexes after sciatic nerve transection and repair in rats. - Yi Chen; Wang, Yu; Lu Chen; Sun, Chenyou; English, Arthur W.; Jonathan Wolpaw; Xiang Yang Chen (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2010)
Operant conditioning of the spinal stretch reflex or its electrical analog, the H-reflex, produces spinal cord plasticity and can thereby affect motoneuron responses to primary afferent input. To explore whether this conditioning can affect the functional outcome after peripheral nerve injury, we assessed the effect of up-conditioning soleus (SOL) H-reflex on SOL and tibialis anterior (TA) function after sciatic nerve transection and repair. Sprague Dawley rats were implanted with EMG electrodes in SOL and TA and stimulating cuffs on the posterior tibial nerve. After control data collection, the sciatic nerve was transected and repaired and the rat was exposed for 120 d to continued control data collection (TC rats) or SOL H-reflex up-conditioning (TU rats). At the end of data collection, motoneurons that had reinnervated SOL and TA were labeled retrogradely. Putative primary afferent terminals [i.e., terminals containing vesicular glutamate transporter-1 (VGLUT1)] on SOL motoneurons were studied immunohistochemically. SOL (and probably TA) background EMG activity recovered faster in TU rats than in TC rats, and the final recovered SOL H-reflex was significantly larger in TU than in TC rats. TU and TC rats had significantly fewer labeled motoneurons and higher proportions of double-labeled motoneurons than untransected rats. VGLUT1 terminals were significantly more numerous on SOL motoneurons of TU than TC rats. Combined with the larger H-reflexes in TU rats, this anatomical finding supports the hypothesis that SOL H-reflex up-conditioning strengthened primary afferent reinnervation of SOL motoneurons. These results suggest that H-reflex up-conditioning may improve functional recovery after nerve injury and repair.
Keywords: conditioning; peripheral nerve; plasticity; Reflex; regeneration; Spinal Cord

Inferring Detailed Aspects of COgnition Using Electrocorticographic (ECoG) Signals in Humans - Gerwin Schalk (2010)
Seattle Children's Research Institute, Seattle, WA

Introduction to BCI2000 - Gerwin Schalk (2010)
7th BCI2000 Workshop, Asilomar Conference Center, Monterey, California

Neuroscience and Brain-Computer Interface Research Using Signals Recorded from the Surface of the Brain - Gerwin Schalk (2010)
Hudson Valley-Berkshire Chapter of the Society for Neuroscience, Albany, New York

Novel Methods and Applications in Brain-Computer Interface Research - Gerwin Schalk (2010)
U.S. Army Research Laboratory, Aberdeen Proving Ground, Aberdeen MD

A novel P300-based brain-computer interface stimulus presentation paradigm: moving beyond rows and columns. - Townsend, G.; LaPallo, B. K.; Chadwick B. Boulay; Krusienski, D. J.; Frye, G. E.; Hauser, C. K.; Schwartz, N. E.; Theresa M Vaughan; Jonathan Wolpaw; Sellers, E. W. (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2010)
OBJECTIVE: An electroencephalographic brain-computer interface (BCI) can provide a non-muscular means of communication for people with amyotrophic lateral sclerosis (ALS) or other neuromuscular disorders. We present a novel P300-based BCI stimulus presentation - the checkerboard paradigm (CBP). CBP performance is compared to that of the standard row/column paradigm (RCP) introduced by Farwell and Donchin (1988). METHODS: Using an 8x9 matrix of alphanumeric characters and keyboard commands, 18 participants used the CBP and RCP in counter-balanced fashion. With approximately 9-12 min of calibration data, we used a stepwise linear discriminant analysis for online classification of subsequent data. RESULTS: Mean online accuracy was significantly higher for the CBP, 92%, than for the RCP, 77%. Correcting for extra selections due to errors, mean bit rate was also significantly higher for the CBP, 23 bits/min, than for the RCP, 17 bits/min. Moreover, the two paradigms produced significantly different waveforms. Initial tests with three advanced ALS participants produced similar results. Furthermore, these individuals preferred the CBP to the RCP. CONCLUSIONS: These results suggest that the CBP is markedly superior to the RCP in performance and user acceptability. SIGNIFICANCE: The CBP has the potential to provide a substantially more effective BCI than the RCP. This is especially important for people with severe neuromuscular disabilities.
Keywords: brain-computer interface; brain-machine interface; EEG; event-related potential; P300; Rehabilitation

Passive real-time identification of speech and motor cortex during an awake craniotomy. - Roland, Jarod; Peter Brunner; Johnston, James; Gerwin Schalk; Leuthardt, E C (Epilepsy Behav, 2010)
Precise localization of eloquent cortex is a clinical necessity prior to surgical resections adjacent to speech or motor cortex. In the intraoperative setting, this traditionally requires inducing temporary lesions by direct electrocortical stimulation (DECS). In an attempt to increase efficiency and potentially reduce the amount of necessary stimulation, we used a passive mapping procedure in the setting of an awake craniotomy for tumor in two patients resection. We recorded electrocorticographic (ECoG) signals from exposed cortex while patients performed simple cue-directed motor and speech tasks. SIGFRIED, a procedure for real-time event detection, was used to identify areas of cortical activation by detecting task-related modulations in the ECoG high gamma band. SIGFRIED's real-time output quickly localized motor and speech areas of cortex similar to those identified by DECS. In conclusion, real-time passive identification of cortical function using SIGFRIED may serve as a useful adjunct to cortical stimulation mapping in the intraoperative setting.
Keywords: Brain Mapping; Brain Neoplasms; Cerebral Cortex; Craniotomy; Electric Stimulation; Electroencephalography; Humans; Neurologic Examination

A Practical Guide to Brain-Computer Interfacing with BCI2000. - Gerwin Schalk; Mellinger, Jürgen (Springer London Dordrecht Heidelberg New York, 2010)

A procedure for measuring latencies in brain-computer interfaces. - Adam J Wilson; Mellinger, Jürgen; Gerwin Schalk; Williams, Justin C (IEEE Trans Biomed Eng, 2010)
Brain-computer interface (BCI) systems must process neural signals with consistent timing in order to support adequate system performance. Thus, it is important to have the capability to determine whether a particular BCI configuration (i.e., hardware and software) provides adequate timing performance for a particular experiment. This report presents a method of measuring and quantifying different aspects of system timing in several typical BCI experiments across a range of settings, and presents comprehensive measures of expected overall system latency for each experimental configuration.
Keywords: Brain; Computer Systems; Electroencephalography; Evoked Potentials; Humans; Models, Neurological; Reproducibility of Results; Signal Processing, Computer-Assisted; Time Factors; User-Computer Interface

Proceedings of the first international workshop on advances in electrocorticography. - A L Ritaccio; Peter Brunner; Cervenka, Mackenzie C; Nathan E. Crone; Guger, C; Leuthardt, E C; Oostenveld, Robert; Stacey, William; Gerwin Schalk (Epilepsy Behav, 2010)
In October 2009, a group of neurologists, neurosurgeons, computational neuroscientists, and engineers congregated to present novel developments transforming human electrocorticography (ECoG) beyond its established relevance in clinical epileptology. The contents of the proceedings advanced the role of ECoG in seizure detection and prediction, neurobehavioral research, functional mapping, and brain-computer interface technology. The meeting established the foundation for future work on the methodology and application of surface brain recordings.
Keywords: Brain; Brain Mapping; Diagnosis, Computer-Assisted; Electroencephalography; Humans; International Cooperation; Seizures; Signal Detection, Psychological

Real-Time Functional Mapping Using Electrocorticographic Signals - Gerwin Schalk (2010)
Department of Neurology, Seattle Children's Hospital, Seattle, WA

Reflex conditioning: a new strategy for improving motor function after spinal cord injury. - Xiang Yang Chen; Yi Chen; Wang, Yu; Thompson, Aiko; Jonathan S. Carp; Segal, Richard L.; Jonathan Wolpaw (Annals of the New York Academy of Sciences, 2010)
Spinal reflex conditioning changes reflex size, induces spinal cord plasticity, and modifies locomotion. Appropriate reflex conditioning can improve walking in rats after spinal cord injury (SCI). Reflex conditioning offers a new therapeutic strategy for restoring function in people with SCI. This approach can address the specific deficits of individuals with SCI by targeting specific reflex pathways for increased or decreased responsiveness. In addition, once clinically significant regeneration can be achieved, reflex conditioning could provide a means of reeducating the newly (and probably imperfectly) reconnected spinal cord.
Keywords: H-Reflex; learning and memory; Locomotion; plasticity; reflex conditioning; Rehabilitation; spinal cord injury

Symptoms as latent variables. - Dennis J. McFarland; Malta, Loretta S (Behav Brain Sci, 2010)
In the target article, Cramer et al. suggest that diagnostic classification is improved by modeling the relationship between manifest variables (i.e., symptoms) rather than modeling unobservable latent variables (i.e., diagnostic categories such as Generalized Anxiety Disorder). This commentary discusses whether symptoms represent manifest or latent variables and the implications of this distinction for diagnosis and treatment.
Keywords: Diagnostic and Statistical Manual of Mental Disorders; Humans; Interview, Psychological; Mental Disorders; Models, Psychological; Sleep Disorders; Stress Disorders, Post-Traumatic

Toward Brain-Computer Symbiosis - Gerwin Schalk (2010)
Keynote Address, X-Prize Workshop on Brain-Computer Interfaces, MIT Campus, Cambridge, MA

Using BCI2000 for HCI-Centered BCI Research. - Adam J Wilson; Gerwin Schalk (Brain-Computer Interfaces: Applying our Minds to Human-Computer Interaction, 2010)
BCI2000 is a general-purpose software suite designed for brain-computer interface (BCI) and related research. BCI2000 has been in development since 2000 and is currently used in close to 500 laboratories around the world. BCI2000 can provide stimulus presentation while simultaneously recording brain signals and subject responses from a number of data acquisition and input devices, respectively. Furthermore, BCI2000 provides a number of services (such as a generic data format that can accommodate any hardware or experimental setup) that can greatly facilitate research. In summary, BCI2000 is ideally suited to support investigations in the area of human-computer interfaces (HCI), in particular those that include recording and processing of brain signals. This chapter provides an overview of the BCI2000 system, and gives examples of its utility for HCI research.

Using BCI2000 in BCI Research. - Mellinger, Jürgen; Gerwin Schalk (Brain-Computer Interfaces: Revolutionizing Human-Computer Interaction, 2010)
BCI2000 is a general-purpose system for brain–computer interface (BCI) research. It can also be used for data acquisition, stimulus presentation, and brain monitoring applications [18,27]. The mission of the BCI2000 project is to facilitate research and applications in these areas. BCI2000 has been in development since 2000 in a collaboration between the Wadsworth Center of the New York State Department of Health in Albany, New York, and the Institute of Medical Psychology and Behavioral Neurobiology at the University of Tübingen, Germany. Many other individuals at different institutions world-wide have contributed to this project.

Using Neuroscience and Neuroengineering to Augment Human Performance - Gerwin Schalk (2010)
Topical Panel on Neuroscience, 27th Army Science Conference Orlando, FL

What can the spinal cord teach us about learning and memory?. - Jonathan Wolpaw (The Neuroscientist : a review journal bringing neurobiology, neurology and psychiatry, 2010)
The work of recent decades has shown that the nervous system changes continually throughout life. Activity-dependent central nervous system (CNS) plasticity has many different mechanisms and involves essentially every region, from the cortex to the spinal cord. This new knowledge radically changes the challenge of explaining learning and memory and greatly increases the relevance of the spinal cord. The challenge is now to explain how continual and ubiquitous plasticity accounts for the initial acquisition and subsequent stability of many different learned behaviors. The spinal cord has a key role because it is the final common pathway for all behavior and is a site of substantial plasticity. Furthermore, because it is simple, accessible, distant from the rest of the CNS, and directly connected to behavior, the spinal cord is uniquely suited for identifying sites and mechanisms of plasticity and for determining how they account for behavioral change. Experimental models based on spinal cord reflexes facilitate study of the gradual plasticity that makes possible most rapid learning phenomena. These models reveal principles and generate concepts that are likely to apply to learning and memory throughout the CNS. In addition, they offer new approaches to guiding activity-dependent plasticity so as to restore functions lost to injury or disease.
Keywords: Spinal Cord

Acquisition of a simple motor skill: task-dependent adaptation plus long-term change in the human soleus H-reflex. - Thompson, Aiko K.; Xiang Yang Chen; Jonathan Wolpaw (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2009)
Activity-dependent plasticity occurs throughout the CNS. However, investigations of skill acquisition usually focus on cortex. To expand the focus, we analyzed in humans the development of operantly conditioned H-reflex change, a simple motor skill that develops gradually and involves plasticity in both the brain and the spinal cord. Each person completed 6 baseline and 24 conditioning sessions over 10 weeks. In each conditioning session, the soleus H-reflex was measured while the subject was or was not asked to increase (HRup subjects) or decrease (HRdown subjects) it. When the subject was asked to change H-reflex size, immediate visual feedback indicated whether a size criterion had been satisfied. Over the 24 conditioning sessions, H-reflex size gradually increased in six of eight HRup subjects and decreased in eight of nine HRdown subjects, resulting in final sizes of 140 +/- 12 and 69 +/- 6% of baseline size, respectively. The final H-reflex change was the sum of within-session (i.e., task-dependent) adaptation and across-session (i.e., long-term) change. Task-dependent adaptation appeared within four to six sessions and persisted thereafter, averaging +13% in HRup subjects and -15% in HRdown subjects. In contrast, long-term change began after 10 sessions and increased gradually thereafter, reaching +27% in HRup subjects and -16% in HRdown subjects. Thus, the acquisition of H-reflex conditioning consists of two phenomena, task-dependent adaptation and long-term change, that together constitute the new motor skill. In combination with previous data, this new finding further elucidates the interaction of plasticity in brain and spinal cord that underlies the acquisition and maintenance of motor skills.
Keywords: H-Reflex; motor learning; motor skill; operant conditioning; plasticity; Spinal Cord

Advances in the application of technology to epilepsy: the CIMIT/NIO Epilepsy Innovation Summit. - Schachter, Steven C; Guttag, John; Schiff, Steven J; Schomer, Donald L (Epilepsy Behav, 2009)
In 2008, a group of clinicians, scientists, engineers, and industry representatives met to discuss advances in the application of engineering technologies to the diagnosis and treatment of patients with epilepsy. The presentations also provided a guide for further technological development, specifically in the evaluation of patients for epilepsy surgery, seizure onset detection and seizure prediction, intracranial treatment systems, and extracranial treatment systems. This article summarizes the discussions and demonstrates that cross-disciplinary interactions can catalyze collaborations between physicians and engineers to address and solve many of the pressing unmet needs in epilepsy.
Keywords: Adult; Anticonvulsants; Brain Mapping; Child; Drug Resistance; Electric Stimulation Therapy; Electroencephalography; Engineering; Epilepsy; Humans; Magnetic Resonance Imaging; Medical Laboratory Science; Microelectrodes; Nanoparticles; Neurons; Neurosurgery; Neurotoxins; Predictive Value of Tests; Seizures; Spectroscopy, Near-Infrared; Tomography, Emission-Computed, Single-Photon; Tomography, Optical; Transcranial Magnetic Stimulation

Assessment of Human Muscle Fatigue from Surface EMG Signals Recorded during Isometric Voluntary Contractions - Potes, Cristhian (Twenty-Fifth Southern Biomedical Engineering Conference, 2009)

BCI2000: A General-Purpose BCI System and its Application to ECoG Signals - Gerwin Schalk (2009)
g.tec Brain-Computer Interface Workshop, Society for Neuroscience Annual Meeting, Chicago, IL

BCI2000: A General-Purpose BCI System and its Application to ECoG Signals - Gerwin Schalk (2009)
Tutorial T02: Brain-Computer Interface, HCI International, San Diego, California

The BCI2000 Framework - Gerwin Schalk (2009)
5th BCI2000 Workshop, The Sagamore Conference Center, Bolton Landing, new York

Brain-Computer Interaction - Gerwin Schalk (2009)
Session Applications and Challenges in Neurally-Driven System Interfaces, Intl. Conference on Augmented Cognition, San Diego, California

Brain-Computer Interaction. - Peter Brunner; Gerwin Schalk (5th Intl. Conference on Augmented Cognition, 2009)
Detection and automated interpretation of attention-related or intention-related brain activity carries significant promise for many military and civilian applications. This interpretation of brain activity could provide information about a person’s intended movements, imagined movements, or attentional focus, and thus could be valuable for optimizing or replacing traditional motor-based communication between a person and a computer or other output devices. We describe here the objective and preliminary results of our studies in this area.
Keywords: BCI; brain-computer interface; neural engineering; neural prosthesis

Brain-computer interface research at the wadsworth center developments in noninvasive communication and control. - Krusienski, Dean J.; Jonathan Wolpaw (International review of neurobiology, 2009)
Brain-computer interface (BCI) research at the Wadsworth Center focuses on noninvasive, electroencephalography (EEG)-based BCI methods for helping severely disabled individuals communicate and interact with their environment. We have demonstrated that these individuals, as well as able-bodied individuals, can learn to use sensorimotor rhythms (SMRs) to move a cursor rapidly and accurately in one and two dimensions. We have also developed a practical P300-based BCI that enables users to access and control the full functionality of their personal computer. We are currently translating this laboratory-proved BCI technology into a system that can be used by severely disabled individuals in their homes with minimal ongoing technical oversight. Our comprehensive approach to BCI design has led to several innovations that are applicable in other BCI contexts, such as space missions.
Keywords: User-Computer Interface

Brain-Computer Interfacing Using Electrocorticography (ECoG) - Gerwin Schalk (2009)
Beijing BCI20009 Symposium, Tsinghua University, Beijing, China

Brain-Computer Interfacing Using Electrocorticography (ECoG) - Gerwin Schalk (2009)
Swartz Center for Computational Neuroscience, Institute for Neural Computation, University of California San Diego, La Jolla, California

Brain-Computer Interfacing Using P300 Evoked Potentials - Gerwin Schalk (2009)
Guest lecture in course Brain-Computer Interfaces, Departments of Neurosurgery/Bioengineering, University of Pennsylvania, Philadelphia, Pennsylvania

Brain-COmputer Interfacing Using P300 Evoked Potentials - Gerwin Schalk (2009)
Guest lecture in course Brain-Computer Interface Systems, Department of Cognitive Sciences, University of California San Diego, La Jolla, California

Brain-Computer Interfacing Using P300 Evoked Potentials (2009)
Guest lecture in course Brain-Computer Interface Systems, Department of Cognitive Sciences, University of California San Diego, La Jolla, California

Clinical Applications of Brain-Computer Interfaces: Current State and Future Prospects. - Mak, Joseph N.; Jonathan Wolpaw (IEEE reviews in biomedical engineering, 2009)
Brain-computer interfaces (BCIs) allow their users to communicate or control external devices using brain signals rather than the brain's normal output pathways of peripheral nerves and muscles. Motivated by the hope of restoring independence to severely disabled individuals and by interest in further extending human control of external systems, researchers from many fields are engaged in this challenging new work. BCI research and development have grown explosively over the past two decades. Efforts have recently begun to provide laboratory-validated BCI systems to severely disabled individuals for real-world applications. In this review, we discuss the current status and future prospects of BCI technology and its clinical applications. We will define BCI, review the BCI-relevant signals from the human brain, and describe the functional components of BCIs. We will also review current clinical applications of BCI technology, and identify potential users and potential applications. Finally, we will discuss current limitations of BCI technology, impediments to its widespread clinical use, and expectations for the future.

Compressive Sensing Reconstruction with Prior Information by Iteratively reweighted Least-Squares. - Miosso C. J.; von Borries R.; Argaez M.; Velazquez L.; Quintero C.; Potes, Cristhian (Signal Processing, IEEE Transactions on, 2009)
Iteratively reweighted least-squares (IRLS) algorithms have been successfully used in compressive sensing to reconstruct sparse signals from incomplete linear measurements taken in nonsparse domains. The underlying optimization problem corresponds to finding the vector that solves the lp minimization while explaining the measurements, and IRLS allows to easily control the used value of p, with effect on the number of required measurements. In this paper, we propose a weighting strategy in the reconstruction method based on IRLS in order to add prior information on the support of the sparse domain. Our simulation results show that the use of prior knowledge about positions of at least some of the nonzero coefficients in the sparse domain leads to a reduction in the number of linear measurements required for unambiguous reconstruction. This reduction occurs for all values of p , so that a further reduction can be achieved by decreasing p and using prior information. The proposed weighting scheme also reduces the computational complexity with respect to the IRLS with no prior information, both in terms of number of iterations and computation time.

Correntropy as a novel measure for nonlinearity tests. - Gunduz, Aysegul; Principe, Jose (Signal Processing, 2009)
<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">Nonlinearity tests have become an essential step in system analysis and modeling due to the computational demands and complexity of analysis involved in nonlinear modeling. Standard nonlinear measures are either too complicated to estimate accurately (such as Lyapunov exponents and correlation dimension), or not able to capture sufficient but not necessary conditions of nonlinearity (such as time asymmetry). Correntropy is a kernel-based similarity measure which contains the information of both statistical and temporal structure of the underlying dataset. The capability of preserving nonlinear characteristics makes correntropy a suitable candidate as a measure for determining nonlinear dynamics. Moreover, since correntropy makes use of kernel methods, its estimation is computationally efficient. Using correntropy as the test statistic, nonlinearity tests based on the null hypothesis that signals of interest are realizations of linear Gaussian stochastic processes are carried out via surrogate data methods. Experiments performed on linear Gaussian, linear non-Gaussian, and nonlinear systems with varying in-band noise levels, data lengths, and kernel sizes confirm that correntropy can be employed as a discriminative measure for detecting nonlinear characteristics in time series. Results of tests performed on data collected from natural systems are in agreement with findings in time series analysis literature.
Keywords: Correntropy; kernel methods; nonlinearity tests; surrogate methods

Decoding flexion of individual fingers using electrocorticographic signals in humans. - Kubánek, J; Miller, John W; Ojemann, J G; Jonathan Wolpaw; Gerwin Schalk (J Neural Eng, 2009)
Brain signals can provide the basis for a non-muscular communication and control system, a brain-computer interface (BCI), for people with motor disabilities. A common approach to creating BCI devices is to decode kinematic parameters of movements using signals recorded by intracortical microelectrodes. Recent studies have shown that kinematic parameters of hand movements can also be accurately decoded from signals recorded by electrodes placed on the surface of the brain (electrocorticography (ECoG)). In the present study, we extend these results by demonstrating that it is also possible to decode the time course of the flexion of individual fingers using ECoG signals in humans, and by showing that these flexion time courses are highly specific to the moving finger. These results provide additional support for the hypothesis that ECoG could be the basis for powerful clinically practical BCI systems, and also indicate that ECoG is useful for studying cortical dynamics related to motor function.
Keywords: Adolescent; Adult; Biomechanics; Brain; Electrodiagnosis; Epilepsy; Female; Fingers; Humans; Male; Microelectrodes; Middle Aged; Motor Activity; Rest; Thumb; Time Factors; Young Adult

Detecting Detailed Aspects of Behavior in ECoG Signals - Gerwin Schalk (2009)
International Workshop on Advances in Electrocorticography, Bolton Landing, New York

Detection of spontaneous class-specific visual stimuli with high temporal accuracy in human electrocorticography. - Miller, John W; Hermes, Dora; Gerwin Schalk; Ramsey, Nick F; Jagadeesh, Bharathi; den Nijs, Marcel; Ojemann, J G; Rao, Rajesh P N (Conf Proc IEEE Eng Med Biol Soc, 2009)
Most brain-computer interface classification experiments from electrical potential recordings have been focused on the identification of classes of stimuli or behavior where the timing of experimental parameters is known or pre-designated. Real world experience, however, is spontaneous, and to this end we describe an experiment predicting the occurrence, timing, and types of visual stimuli perceived by a human subject from electrocorticographic recordings. All 300 of 300 presented stimuli were correctly detected, with a temporal precision of order 20 ms. The type of stimulus (face/house) was correctly identified in 95% of these cases. There were approximately 20 false alarm events, corresponding to a late 2nd neuronal response to a previously identified event.
Keywords: Algorithms; Electrocardiography; Evoked Potentials, Visual; Humans; Male; Pattern Recognition, Automated; Pattern Recognition, Visual; Photic Stimulation; Reproducibility of Results; Sensitivity and Specificity; User-Computer Interface; Visual Cortex

Determination of signal-to-noise ratios and spectral SNRs in cryo-EM low-dose imaging of molecules. - Baxter, Bill; Grassucci, Robert A; Gao, Haixiao; Frank, Joachim (J Struct Biol, 2009)
Attempts to develop efficient classification approaches to the problem of heterogeneity in single-particle reconstruction of macromolecules require phantom data with realistic noise models. We have estimated the signal-to-noise ratios and spectral signal-to-noise ratios for three steps in the electron microscopic image formation from data obtained experimentally. An important result is that structural noise, i.e., the irreproducible component of the object prior to image formation, is substantial, and of the same order of magnitude as the reproducible signal. Based on this result, the noise modeling for testing new classification techniques can be improved.
Keywords: Cryoelectron Microscopy; Image Processing, Computer-Assisted

EEG/ECoG-based BCIs for People with Little or No Motor Function - Gerwin Schalk (2009)
Seminar Brain-Computer Interfaces: Frontiers in Neurology and Neuroscience, American Academy of Neurology Meeting, Seattle, Washington

Effective brain-computer interfacing using BCI2000. - Gerwin Schalk (Conf Proc IEEE Eng Med Biol Soc, 2009)
To facilitate research and development in Brain-Computer Interface (BCI) research, we have been developing a general-purpose BCI system, called BCI2000, over the past nine years. This system has enjoyed a growing adoption in BCI and related areas and has been the basis for some of the most impressive studies reported to date. This paper gives an update on the status of this project by describing the principles of the BCI2000 system, its benefits, and impact on the field to date.
Keywords: Algorithms; Brain; Electrocardiography; Equipment Design; Equipment Failure Analysis; Rehabilitation; Reproducibility of Results; Sensitivity and Specificity; Signal Processing, Computer-Assisted; User-Computer Interface

Effective Brain-Computer Interfacing Using BCI2000 - Gerwin Schalk (2009)
Session Brain-Machine Interface I, 31st Annual International IEEE EMBS Conference, Minneapolis, Minnesota

Emerging Opportunities in Neuroengineering - Gerwin Schalk (2009)
University of Pennsylvania, Philadelphia, Pennsylvania

Engineering the Future in Biomedicine: Using Brain Signals for Communication and Diagnosis - Gerwin Schalk (2009)
IEEE Schenectady Section, Niskayuna, New York

Evolution of brain-computer interfaces: going beyond classic motor physiology. - Leuthardt, E C; Gerwin Schalk; Roland, Jarod; Rouse, Adam; Moran, D (Neurosurg Focus, 2009)
The notion that a computer can decode brain signals to infer the intentions of a human and then enact those intentions directly through a machine is becoming a realistic technical possibility. These types of devices are known as brain-computer interfaces (BCIs). The evolution of these neuroprosthetic technologies could have significant implications for patients with motor disabilities by enhancing their ability to interact and communicate with their environment. The cortical physiology most investigated and used for device control has been brain signals from the primary motor cortex. To date, this classic motor physiology has been an effective substrate for demonstrating the potential efficacy of BCI-based control. However, emerging research now stands to further enhance our understanding of the cortical physiology underpinning human intent and provide further signals for more complex brain-derived control. In this review, the authors report the current status of BCIs and detail the emerging research trends that stand to augment clinical applications in the future.
Keywords: Brain; Cerebral Cortex; Humans; Man-Machine Systems; Motor Cortex; Movement; Movement Disorders; Neuronal Plasticity; Prostheses and Implants; Research; Signal Processing, Computer-Assisted; User-Computer Interface

Homology modeling of human alpha 1 beta 2 gamma 2 and house fly beta 3 GABA receptor channels and Surflex-docking of fipronil. - Cheng, Jin; Ju, Xiu-Lian; Xiang Yang Chen; Liu, Gen-Yan (Journal of molecular modeling, 2009)
To further explore the mechanism of selective binding of the representative gamma-aminobutyric acid receptors (GABARs) noncompetitive antagonist (NCA) fipronil to insect over mammalian GABARs, three-dimensional models of human alpha 1 beta 2 gamma 2 and house fly beta 3 GABAR were generated by homology modeling, using the cryo-electron microscopy structure of the nicotinic acetylcholine receptor (nAChR) of Torpedo marmorata as a template. Fipronil was docked into the putative binding site of the human alpha 1 beta 2 gamma 2 and house fly beta 3 receptors by Surflex-docking, and the calculated docking energies are in agreement with experimental results. The GABA receptor antagonist fipronil exhibited higher potency with house fly beta 3 GABAR than with human alpha 1 beta 2 gamma 2 GABAR. Furthermore, analyses of Surflex-docking suggest that the H-bond interaction of fipronil with Ala2 and Thr6 in the second transmembrane segment (TM2) of these GABARs plays a relatively important role in ligand selective binding. The different subunit assemblies of human alpha 1 beta 2 gamma 2 and house fly beta 3 GABARs may result in differential selectivity for fipronil.
Keywords: fipronil; homology modeling; house fly beta 3 GABA receptor; human alpha 1 beta 2 gamma 2 GABAA receptor; selectivity; surflex-docking

H-reflex down-conditioning greatly increases the number of identifiable GABAergic interneurons in rat ventral horn. - Wang, Yu; Pillai, Shreejith; Jonathan Wolpaw; Xiang Yang Chen (Neuroscience letters, 2009)
H-reflex down-conditioning increases GABAergic terminals on spinal cord motoneurons. To explore the origins of these terminals, we studied the numbers and distributions of spinal cord GABAergic interneurons. The number of identifiable GABAergic interneurons in the ventral horn was 78% greater in rats in which down-conditioning was successful than in naive rats or rats in which down-conditioning failed. No increase occurred in other spinal lamina or on the contralateral side. This finding supports the hypothesis that the corticospinal tract influence that induces the motoneuron plasticity underlying down-conditioning reaches the motoneuron through GABAergic interneurons in the ventral horn.
Keywords: activity-dependent plasticity; GABAergic interneurons; H-reflex conditioning; learning and memory; Motor control; Spinal Cord

Introduction to BCI2000 - Gerwin Schalk (2009)
6th BCI2000 Workshop, Tsinghua University, Beijing, China

Mapping broadband electrocorticographic recordings to two-dimensional hand trajectories in humans Motor control features. - Gunduz, Aysegul; Sanchez, Justin C; Carney, Paul R; Principe, Jose (Neural Netw, 2009)
Brain-machine interfaces (BMIs) aim to translate the motor intent of locked-in patients into neuroprosthetic control commands. Electrocorticographical (ECoG) signals provide promising neural inputs to BMIs as shown in recent studies. In this paper, we utilize a broadband spectrum above the fast gamma ranges and systematically study the role of spectral resolution, in which the broadband is partitioned, on the reconstruction of the patients' hand trajectories. Traditionally, the power of ECoG rhythms (<200-300 Hz) has been computed in short duration bins and instantaneously and linearly mapped to cursor trajectories. Neither time embedding, nor nonlinear mappings have been previously implemented in ECoG neuroprosthesis. Herein, mapping of neural modulations to goal-oriented motor behavior is achieved via linear adaptive filters with embedded memory depths and as a novelty through echo state networks (ESNs), which provide nonlinear mappings without compromising training complexity or increasing the number of model parameters, with up to 85% correlation. Reconstructed hand trajectories are analyzed through spatial, spectral and temporal sensitivities. The superiority of nonlinear mappings in the cases of low spectral resolution and abundance of interictal activity is discussed.
Keywords: Algorithms; Brain; Brain Mapping; Electrodes, Implanted; Electrodiagnosis; Epilepsy; Feasibility Studies; Hand; Humans; Linear Models; Motor Activity; Neural Networks (Computer); Nonlinear Dynamics; Signal Processing, Computer-Assisted

Microscale recording from human motor cortex: implications for minimally invasive electrocorticographic brain-computer interfaces. - Leuthardt, E C; Zachary V. Freudenberg; Bundy, David T; Roland, Jarod (Neurosurg Focus, 2009)
OBJECT:  There is a growing interest in the use of recording from the surface of the brain, known as electrocorticography (ECoG), as a practical signal platform for brain-computer interface application. The signal has a combination of high signal quality and long-term stability that may be the ideal intermediate modality for future application. The research paradigm for studying ECoG signals uses patients requiring invasive monitoring for seizure localization. The implanted arrays span cortex areas on the order of centimeters. Currently, it is unknown what level of motor information can be discerned from small regions of human cortex with microscale ECoG recording. METHODS:  In this study, a patient requiring invasive monitoring for seizure localization underwent concurrent implantation with a 16-microwire array (1-mm electrode spacing) placed over primary motor cortex. Microscale activity was recorded while the patient performed simple contra- and ipsilateral wrist movements that were monitored in parallel with electromyography. Using various statistical methods, linear and nonlinear relationships between these microcortical changes and recorded electromyography activity were defined. RESULTS:  Small regions of primary motor cortex (< 5 mm) carry sufficient information to separate multiple aspects of motor movements (that is, wrist flexion/extension and ipsilateral/contralateral movements). CONCLUSIONS:  These findings support the conclusion that small regions of cortex investigated by ECoG recording may provide sufficient information about motor intentions to support brain-computer interface operations in the future. Given the small scale of the cortical region required, the requisite implanted array would be minimally invasive in terms of surgical placement of the electrode array.
Keywords: brain-computer interface; Electrocorticography; Motor Cortex

A note on ethical aspects of BCI. - Haselager, Pim; Vlek, Rutger; Jeremy Jeremy Hill; Nijboer, F (Neural Netw, 2009)
This paper focuses on ethical aspects of BCI, as a research and a clinical tool, that are challenging for practitioners currently working in the field. Specifically, the difficulties involved in acquiring informed consent from locked-in patients are investigated, in combination with an analysis of the shared moral responsibility in BCI teams, and the complications encountered in establishing effective communication with media.
Keywords: Bioethics; Brain; Communication; Communications Media; Cooperative Behavior; Humans; Informed Consent; Professional-Patient Relations; Quadriplegia; User-Computer Interface

Overlap and refractory effects in a brain-computer interface speller based on the visual P300 event-related potential. - Martens, S M M; Jeremy Jeremy Hill; Farquhar, Jason; Schölkopf, B (J Neural Eng, 2009)
We reveal the presence of refractory and overlap effects in the event-related potentials in visual P300 speller datasets, and we show their negative impact on the performance of the system. This finding has important implications for how to encode the letters that can be selected for communication. However, we show that such effects are dependent on stimulus parameters: an alternative stimulus type based on apparent motion suffers less from the refractory effects and leads to an improved letter prediction performance.
Keywords: Algorithms; Brain; Cognition; Computer Simulation; Electroencephalography; Event-Related Potentials, P300; Humans; Models, Neurological; Pattern Recognition, Automated; Photic Stimulation; Semantics; Signal Processing, Computer-Assisted; Task Performance and Analysis; User-Computer Interface; Writing

Overview of Available BCI2000 Components - Gerwin Schalk (2009)
5th BCI2000 Workshop, The Sagamore Conference Center, Bolton Landing, New York

Power spectrum analysis on the multiparameter electroencephalogram features of physiological mental fatigue. - Zhang, Ai-hua; Zheng, Shi Dong; Pei, Xiao-Mei; Ouyang, Yi (Sheng Wu Yi Xue Gong Cheng Xue Za Zhi, 2009)
The aim of this experiment is to find a feasible impersonal index for analyzing the physiological mental fatigue level. Three characteristic parameters, relative power in different rhythm, barycenter frequency and power spectral entropy, are extracted from two channels' electroencephalogram (EEG) under two physiological mental fatigue states. Then relationships between such three parameters and physiological mental fatigue are analyzed to explore whether they can be of use for detecting (or monitoring) the mental fatigue level. The experiment results show that the relative power, barycenter frequency and power spectral entropy of EEG exhibit strong correlation with physiological mental fatigue level. While physiological mental fatigue level increases, the relative power in theta, alpha and beta rhythms, barycenter frequency and power spectral entropy of EEG decrease, but the relative power in delta rhythm of EEG increases. The relative power in four rhythms, barycenter frequency and power spectral entropy of EEG reflect the change of physiological mental fatigue level sensitively, and may hopefully be used as indexes for detecting physiological mental fatigue level.
Keywords: Adult; Electroencephalography; Entropy; Humans; Male; Mental Fatigue; Signal Processing, Computer-Assisted; Young Adult

A practical procedure for real-time functional mapping of eloquent cortex using electrocorticographic signals in humans. - Peter Brunner; A L Ritaccio; Lynch, Timothy M; Emrich, Joseph F; Adam J Wilson; Williams, Justin C; Aarnoutse, Erik J; Ramsey, Nick F; Leuthardt, E C; H Bischof; Gerwin Schalk (Epilepsy Behav, 2009)
Functional mapping of eloquent cortex is often necessary prior to invasive brain surgery, but current techniques that derive this mapping have important limitations. In this article, we demonstrate the first comprehensive evaluation of a rapid, robust, and practical mapping system that uses passive recordings of electrocorticographic signals. This mapping procedure is based on the BCI2000 and SIGFRIED technologies that we have been developing over the past several years. In our study, we evaluated 10 patients with epilepsy from four different institutions and compared the results of our procedure with the results derived using electrical cortical stimulation (ECS) mapping. The results show that our procedure derives a functional motor cortical map in only a few minutes. They also show a substantial concurrence with the results derived using ECS mapping. Specifically, compared with ECS maps, a next-neighbor evaluation showed no false negatives, and only 0.46 and 1.10% false positives for hand and tongue maps, respectively. In summary, we demonstrate the first comprehensive evaluation of a practical and robust mapping procedure that could become a new tool for planning of invasive brain surgeries.
Keywords: Adult; Brain Mapping; Cerebral Cortex; Electric Stimulation; Electrodes, Implanted; Electroencephalography; Epilepsy; Female; Humans; Male; Middle Aged; Practice Guidelines as Topic; Signal Processing, Computer-Assisted; Young Adult

Real-Time Data Acquisition, Signal Processing, and Stimulus Presentation Using BCI2000 - Gerwin Schalk (2009)
Workshop Neural Engineering in Real Time, Pittsburgh, Pennsylvania

Real-Time Functional Mapping Using Electrocorticographic Signals - Gerwin Schalk (2009)
Clinical Neurophysiology Research Seminar, Langone Medical Center, New York University, New York, New York

Research and Clinical Application of Electrocorticographic Signals in Humans - Gerwin Schalk (2009)
Helen Wills Neuroscience Institute, University of California Berkeley, Berkeley, CA

Ribosome-induced changes in elongation factor Tu conformation control GTP hydrolysis. - Villa, Elizabeth; Sengupta, Jayati; Trabuco, Leonardo G; LeBarron, Jamie; Baxter, Bill; Shaikh, Tanvir R; Grassucci, Robert A; Nissen, Poul; Ehrenberg, Måns; Schulten, Klaus; Frank, Joachim (Proc Natl Acad Sci U S A, 2009)
In translation, elongation factor Tu (EF-Tu) molecules deliver aminoacyl-tRNAs to the mRNA-programmed ribosome. The GTPase activity of EF-Tu is triggered by ribosome-induced conformational changes of the factor that play a pivotal role in the selection of the cognate aminoacyl-tRNAs. We present a 6.7-A cryo-electron microscopy map of the aminoacyl-tRNA x EF-Tu x GDP x kirromycin-bound Escherichia coli ribosome, together with an atomic model of the complex obtained through molecular dynamics flexible fitting. The model reveals the conformational changes in the conserved GTPase switch regions of EF-Tu that trigger hydrolysis of GTP, along with key interactions, including those between the sarcin-ricin loop and the P loop of EF-Tu, and between the effector loop of EF-Tu and a conserved region of the 16S rRNA. Our data suggest that GTP hydrolysis on EF-Tu is controlled through a hydrophobic gate mechanism.
Keywords: Cryoelectron Microscopy; Enzyme Activation; Escherichia coli; Escherichia coli Proteins; Guanosine Triphosphate; Histidine; Hydrolysis; Hydrophobic and Hydrophilic Interactions; Models, Molecular; Peptide Elongation Factor Tu; Protein Structure, Secondary; Ribosomal Proteins; Ribosomes; RNA, Transfer; Signal Transduction

A scanning protocol for a sensorimotor rhythm-based brain-computer interface. - Friedrich, Elisabeth V. C.; Dennis J. McFarland; Neuper, Christa; Theresa M Vaughan; Peter Brunner; Jonathan Wolpaw (Biological psychology, 2009)
The scanning protocol is a novel brain-computer interface (BCI) implementation that can be controlled with sensorimotor rhythms (SMRs) of the electroencephalogram (EEG). The user views a screen that shows four choices in a linear array with one marked as target. The four choices are successively highlighted for 2.5s each. When a target is highlighted, the user can select it by modulating the SMR. An advantage of this method is the capacity to choose among multiple choices with just one learned SMR modulation. Each of 10 naive users trained for ten 30 min sessions over 5 weeks. User performance improved significantly (p<0.001) over the sessions and ranged from 30 to 80% mean accuracy of the last three sessions (chance accuracy=25%). The incidence of correct selections depended on the target position. These results suggest that, with further improvements, a scanning protocol can be effective. The ultimate goal is to expand it to a large matrix of selections.
Keywords: BCI; brain-computer interface; scanning protocol; sensorimotor rhythm

Seizure prediction for epilepsy using a multi-stage phase synchrony based system. - Christopher J James; Disha Gupta (Conf Proc IEEE Eng Med Biol Soc, 2009)
Seizure onset prediction in epilepsy is a challenge which is under investigation using many and varied signal processing techniques. Here we present a multi-stage phase synchrony based system that brings to bear the advantages of many techniques in each substage. The 1(st) stage of the system unmixes continuous long-term (2-4 days) multichannel scalp EEG using spatially constrained Independent Component Analysis and estimates the long term significant phase synchrony dynamics of narrowband (2-8 Hz and 8-14 Hz) seizure components. It then projects multidimensional features onto a 2-D map using Neuroscale and evaluates the probability of predictive events using Gaussian Mixture Models. We show the possibility of seizure onset prediction within a prediction window of 35-65 minutes with a sensitivity of 65-100% and specificity of 65-80% across epileptic patients.
Keywords: Algorithms; Artificial Intelligence; Diagnosis, Computer-Assisted; Electroencephalography; Epilepsy; Humans; Pattern Recognition, Automated; Reproducibility of Results; Sensitivity and Specificity

Sensor Modalities for Brain-Computer Interfacing - Gerwin Schalk (13th Intl. Conference on Human-Computer Interaction, 2009)
Many people have neuromuscular conditions or disorders that impair the neural pathways that control muscles. Those most severely affected lose all voluntary muscle control and hence lose the ability to communicate. Brain-computer interfaces (BCIs) might be able to restore some communication or control functions for these people by creating a new communication channel – directly from the brain to an output device. Many studies over the past two decades have shown that such BCI communication is possible and that it can serve useful functions. This paper reviews the different sensor methodologies that have been explored in these studies.

Sensor Modalities for Brain-Computer Interfacing - Gerwin Schalk (2009)
Session Brain-Computer Interface (BCI); Towards Understanding Neural Bases of Human-Computer Interaction, HCI International, San Diego, California

Technical Basis for Real-Time Functional Mapping of Eloquent Cortex - Gerwin Schalk (2009)
Department of Neurology, Weill Cornell Medical Center, New York City, New York

Theory and Application of Electrocorticographic (ECoG) Signals in Humans - Gerwin Schalk (2009)
Invited 1.5 hour tutorial, BBCI Workshop 2009, Advances in Neurotechnology, Berlin, Germany

Toward a high-throughput auditory P300-based brain-computer interface. - Klobassa, D. S.; Theresa M Vaughan; Peter Brunner; Schwartz, N. E.; Jonathan Wolpaw; Neuper, C.; Sellers, E. W. (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2009)
OBJECTIVE: Brain-computer interface (BCI) technology can provide severely disabled people with non-muscular communication. For those most severely disabled, limitations in eye mobility or visual acuity may necessitate auditory BCI systems. The present study investigates the efficacy of the use of six environmental sounds to operate a 6x6 P300 Speller. METHODS: A two-group design was used to ascertain whether participants benefited from visual cues early in training. Group A (N=5) received only auditory stimuli during all 11 sessions, whereas Group AV (N=5) received simultaneous auditory and visual stimuli in initial sessions after which the visual stimuli were systematically removed. Stepwise linear discriminant analysis determined the matrix item that elicited the largest P300 response and thereby identified the desired choice. RESULTS: Online results and offline analyses showed that the two groups achieved equivalent accuracy. In the last session, eight of 10 participants achieved 50% or more, and four of these achieved 75% or more, online accuracy (2.8% accuracy expected by chance). Mean bit rates averaged about 2 bits/min, and maximum bit rates reached 5.6 bits/min. CONCLUSIONS: This study indicates that an auditory P300 BCI is feasible, that reasonable classification accuracy and rate of communication are achievable, and that the paradigm should be further evaluated with a group of severely disabled participants who have limited visual mobility. SIGNIFICANCE: With further development, this auditory P300 BCI could be of substantial value to severely disabled people who cannot use a visual BCI.
Keywords: brain-computer interface; brain-machine interface; EEG; event-related potential; P300; Rehabilitation

Using an EEG-based brain-computer interface for virtual cursor movement with BCI2000. - Adam J Wilson; Gerwin Schalk; Walton, Léo M; Williams, Justin C (J Vis Exp, 2009)
A brain-computer interface (BCI) functions by translating a neural signal, such as the electroencephalogram (EEG), into a signal that can be used to control a computer or other device. The amplitude of the EEG signals in selected frequency bins are measured and translated into a device command, in this case the horizontal and vertical velocity of a computer cursor. First, the EEG electrodes are applied to the user s scalp using a cap to record brain activity. Next, a calibration procedure is used to find the EEG electrodes and features that the user will learn to voluntarily modulate to use the BCI. In humans, the power in the mu (8-12 Hz) and beta (18-28 Hz) frequency bands decrease in amplitude during a real or imagined movement. These changes can be detected in the EEG in real-time, and used to control a BCI ([1],[2]). Therefore, during a screening test, the user is asked to make several different imagined movements with their hands and feet to determine the unique EEG features that change with the imagined movements. The results from this calibration will show the best channels to use, which are configured so that amplitude changes in the mu and beta frequency bands move the cursor either horizontally or vertically. In this experiment, the general purpose BCI system BCI2000 is used to control signal acquisition, signal processing, and feedback to the user [3].
Keywords: Brain; Calibration; Electrodes; Electroencephalography; Humans; User-Computer Interface

Using Electrocorticographic (ECoG) Signals in Humans for Communication and Diagnosis - Gerwin Schalk (2009)
University of Pennsylvania, Philadelphia, Pennsylvania

Using Subdural Signals in Humans for Communication and Diagnosis - Gerwin Schalk (2009)
Epilepsy Research Program, Georgetown University, Washington, DC.

Advanced neurotechnologies for chronic neural interfaces: new horizons and clinical opportunities. - Kipke, Daryl R; Shain, William; Buzsáki, György; Fetz, Eberhard E; Henderson, Jaimie M; Hetke, Jamille F; Gerwin Schalk (J Neurosci, 2008)
Keywords: Cerebral Cortex; Electrodes, Implanted; Electroencephalography; Electronics, Medical; Electrophysiology; Evoked Potentials; Movement Disorders; Neurons; Prostheses and Implants; User-Computer Interface

Assessment of Muscle Fatigue from TF Distributions of SEMG Signals - Potes, Cristhian; von Borries R.; Miosso C. J.; Pierluissi J. H. (Twenty-Fourth Southern Biomedical Engineering Conference, 2008)

An auditory brain-computer interface (BCI). - Nijboer, Femke; Adrian Furdea; Gunst, Ingo; Mellinger, Jürgen; Dennis J. McFarland; Niels Birbaumer; Kübler, Andrea (Journal of neuroscience methods, 2008)
Brain-computer interfaces (BCIs) translate brain activity into signals controlling external devices. BCIs based on visual stimuli can maintain communication in severely paralyzed patients, but only if intact vision is available. Debilitating neurological disorders however, may lead to loss of intact vision. The current study explores the feasibility of an auditory BCI. Sixteen healthy volunteers participated in three training sessions consisting of 30 2-3 min runs in which they learned to increase or decrease the amplitude of sensorimotor rhythms (SMR) of the EEG. Half of the participants were presented with visual and half with auditory feedback. Mood and motivation were assessed prior to each session. Although BCI performance in the visual feedback group was superior to the auditory feedback group there was no difference in performance at the end of the third session. Participants in the auditory feedback group learned slower, but four out of eight reached an accuracy of over 70% correct in the last session comparable to the visual feedback group. Decreasing performance of some participants in the visual feedback group is related to mood and motivation. We conclude that with sufficient training time an auditory BCI may be as efficient as a visual BCI. Mood and motivation play a role in learning to use a BCI.
Keywords: auditory feedback; brain-computer interface; EEG; locked-in state; motivation; sensorimotor rhythm

BCI2000: A General-Purpose BCI System and its Application to ECoG Signals - Gerwin Schalk (2008)
g.tec Brain-Computer Interface Workshop, Society for Neuroscience Annual Meeting, Washington, DC

BCI2000: A General-Purpose Brain-Computer Interface System - Gerwin Schalk (2008)
4th BCI2000 Workshop, Utrecht, The Netherlands

The BCI2000 Framework - Gerwin Schalk (2008)
4th BCI2000 Workshop, Utrecht, The Netherlands

Brain-Based Communication and Orientation - Gerwin Schalk (2008)
Multi-disciplinary University Research Initiative sponsored by the US Army Research Office. University of Maryland College Park, College Park, Maryland.

Brain-computer interfaces (BCIs): Detection Instead of Classification. - Gerwin Schalk; Peter Brunner; Lester A Gerhardt; H Bischof; Jonathan Wolpaw (J Neurosci Methods, 2008)
Many studies over the past two decades have shown that people can use brain signals to convey their intent to a computer through brain-computer interfaces (BCIs). These devices operate by recording signals from the brain and translating these signals into device commands. They can be used by people who are severely paralyzed to communicate without any use of muscle activity. One of the major impediments in translating this novel technology into clinical applications is the current requirement for preliminary analyses to identify the brain signal features best suited for communication. This paper introduces and validates signal detection, which does not require such analysis procedures, as a new concept in BCI signal processing. This detection concept is realized with Gaussian mixture models (GMMs) that are used to model resting brain activity so that any change in relevant brain signals can be detected. It is implemented in a package called SIGFRIED (SIGnal modeling For Real-time Identification and Event Detection). The results indicate that SIGFRIED produces results that are within the range of those achieved using a common analysis strategy that requires preliminary identification of signal features. They indicate that such laborious analysis procedures could be replaced by merely recording brain signals during rest. In summary, this paper demonstrates how SIGFRIED could be used to overcome one of the present impediments to translation of laboratory BCI demonstrations into clinically practical applications.
Keywords: Adult; Algorithms; Brain; Brain Mapping; Electrocardiography; Electroencephalography; Humans; Male; Man-Machine Systems; Normal Distribution; Online Systems; Signal Detection, Psychological; Signal Processing, Computer-Assisted; Software Validation; User-Computer Interface

Brain-computer interfaces in neurological rehabilitation. - Janis J. Daly; Jonathan Wolpaw (Lancet neurology, 2008)
Recent advances in analysis of brain signals, training patients to control these signals, and improved computing capabilities have enabled people with severe motor disabilities to use their brain signals for communication and control of objects in their environment, thereby bypassing their impaired neuromuscular system. Non-invasive, electroencephalogram (EEG)-based brain-computer interface (BCI) technologies can be used to control a computer cursor or a limb orthosis, for word processing and accessing the internet, and for other functions such as environmental control or entertainment. By re-establishing some independence, BCI technologies can substantially improve the lives of people with devastating neurological disorders such as advanced amyotrophic lateral sclerosis. BCI technology might also restore more effective motor control to people after stroke or other traumatic brain disorders by helping to guide activity-dependent brain plasticity by use of EEG brain signals to indicate to the patient the current state of brain activity and to enable the user to subsequently lower abnormal activity. Alternatively, by use of brain signals to supplement impaired muscle control, BCIs might increase the efficacy of a rehabilitation protocol and thus improve muscle control for the patient.
Keywords: User-Computer Interface

Brain-Computer Interfacing Using Electrocorticography and Electrocorticography - Gerwin Schalk (2008)
EuroNeuro (European Congress on Neurology, Neurosurgery, Intensive Care and Anesthesiology), Maastricht, The Netherlands

Brain-Computer Interfacing Using Electrocorticography (ECoG) - Gerwin Schalk (2008)
University of Pittsburgh, Pittsburgh, Pennsylvania

Brain-Computer Interfacing Using Electrocorticography (ECoG) - Gerwin Schalk (2008)
MEG Center, Eberhard Karls University of Tübingen, Tübingen, Germany

Brain-Computer Interfacing Using Electrocorticography (ECoG) - Gerwin Schalk (2008)
Bernstein Seminar, Bernstein Center for Computation Neuroscience, Albert-Ludwigs-Universitaet Freiburg, Freiburg, Germany

Brain-Computer Interfacing Using Electrocorticography (ECoG) - Gerwin Schalk (2008)
Institute for Automation, University of Bremen, Bremen, Germany

Brain-Computer Interfacing Using Non-Invasive and Invasive Methods - Gerwin Schalk (2008)
Institute for Computer Graphics and Vision, Graz University of Technology, Graz, Austria

Brain-Computer Interfacing Using Non-Invasive and Invasive Methods - Gerwin Schalk (2008)
Workshop Brain-Computer Interfacing in 2008, Utrecht, The Netherlands

Brain-computer symbiosis. - Gerwin Schalk (J Neural Eng, 2008)
The theoretical groundwork of the 1930s and 1940s and the technical advance of computers in the following decades provided the basis for dramatic increases in human efficiency. While computers continue to evolve, and we can still expect increasing benefits from their use, the interface between humans and computers has begun to present a serious impediment to full realization of the potential payoff. This paper is about the theoretical and practical possibility that direct communication between the brain and the computer can be used to overcome this impediment by improving or augmenting conventional forms of human communication. It is about the opportunity that the limitations of our body's input and output capacities can be overcome using direct interaction with the brain, and it discusses the assumptions, possible limitations and implications of a technology that I anticipate will be a major source of pervasive changes in the coming decades.
Keywords: Brain; Computers; Humans; User-Computer Interface

Combining Fidelity With Practicality: Interrogation of the Brain Using Electrocorticography (ECoG) - Gerwin Schalk (2008)
Symposium Advanced Neurotechnologies for Chronic Neural Interfaces: New Horizons and Clinical Opportunities, Society for Neuroscience Annual Meeting, Washington, DC

Decoding Detailed Information fromt he Brain Using Electrocorticographic (ECoG) Signals in Humans - Gerwin Schalk (2008)
Lecture in Workshop on Research Efforts and Future Directions in Neuroergonamics and Neuromorphics sponsored by the US Army Research Office. University of Maryland Colelge Park, College Park, Maryland

A Device For Real-Time Functional Mapping Using ECoG - Gerwin Schalk (2008)
CIMIT Epilepsy Innovation Summit, Boston, Massachusetts

Direct Interaction With The Brain - Gerwin Schalk (2008)
Guest lecture in Business Issues for Engineers and Scientists, Department of Information Technology, Rensselaer Polytechnic Institute, Troy, New York

Direct Interaction With The Brain - Gerwin Schalk (2008)
Guest lecture in Information Technology Capstone Course, Department of Information Technology, Rensselaer Polytechnic Institute, Troy, New York, 11/24/2008

Effects of H-reflex up-conditioning on GABAergic terminals on rat soleus motoneurons. - Pillai, Shreejith; Wang, Yu; Jonathan Wolpaw; Xiang Yang Chen (The European journal of neuroscience, 2008)
To explore the role of spinal cord plasticity in motor learning, we evaluated the effects of H-reflex operant conditioning on GABAergic input to rat spinal motoneurons. Previous work indicated that down-conditioning of soleus H-reflex increases GABAergic input to soleus motoneurons. This study explored the effect of H-reflex up-conditioning on GABAergic input. Of nine rats exposed to H-reflex up-conditioning, up-conditioning was successful (H-reflex increase >or= 20%) in seven and failed (change < 20%) in two. These rats and eight naive control (i.e. unconditioned) rats were injected with cholera toxin subunit B-conjugated Alexa fluor 488 into the soleus muscle to retrogradely label soleus motoneurons. Sections containing soleus motoneurons were processed for GAD(67) [one of the two principal forms of the GABA-synthesizing enzyme glutamic acid decarboxylase (GAD)] with an ABC-peroxidase system. Two blinded independent raters counted and measured GABAergic terminals on these motoneurons. Unlike successful down-conditioning, which greatly increased the number of identifiable GABAergic terminals on the motoneurons, up-conditioning did not significantly change GABAergic terminal number. Successful up-conditioning did produce slight but statistically significant increases in GABAergic terminal diameter and soma coverage. These results are consistent with other data indicating that up- and down-conditioning are not mirror images of each other, but rather have different mechanisms. Although the marked changes in GABAergic terminals with down-conditioning probably contribute to H-reflex decrease, the modest changes in GABAergic terminals associated with up-conditioning may be compensatory or reactive plasticity, rather than the plasticity responsible for H-reflex increase. As a variety of spinal and supraspinal GABAergic neurons innervate motoneurons, the changes found with up-conditioning may be in terminals other than those affected in successful down-conditioning.
Keywords: activity-dependent plasticity; Learning; Memory; Motor control; Spinal Cord

Electrocorticographic interictal spike removal via denoising source separation for improved neuroprosthesis control. - Gunduz, Aysegul; Sanchez, Justin C; Principe, Jose (Conf Proc IEEE Eng Med Biol Soc, 2008)
Electrocorticographic (ECoG) neuroprosthesis is a promising area of research that could provide channels of communication and control for patients who have lost their motor functions due to damage to the nervous system. However, implantation of subdural electrodes are clinically restricted to diagnostics of pre-surgical epileptic patients. Hence, interictal activity is present in the recordings across various areas of the sensorimotor cortex and suppresses the amplitude modulated features extracted to model hand trajectories. Denoising source separation is a recently introduced framework which extracts hidden structures of interest within the data through denoising the source estimates with filters designed around prior knowledge on the observations. Herein, we exploit the high amplitude quasiperiodic nature of the observed interictal spikes and show that removal of the interictal activity improves linear prediction of hand trajectories.
Keywords: Algorithms; Artifacts; Diagnosis, Computer-Assisted; Electroencephalography; Epilepsy; Evoked Potentials, Motor; Motor Cortex; Reproducibility of Results; Sensitivity and Specificity; User-Computer Interface

Electrophysiological markers of skill-related neuroplasticity. - Romero, Stephen G.; Dennis J. McFarland; Faust, Robert; Farrell, Lori; Anthony T. Cacace (Biological psychology, 2008)
Neuroplasticity involved in acquiring a new cognitive skill was investigated with standard time domain event-related potentials (ERPs) of scalp-recorded electroencephalographic (EEG) activity and frequency domain analysis of EEG oscillations looking at the event-related synchronization (ERS) and desynchronization (ERD) of neural activity. Electroencephalographic activity was recorded before and after practice, while participants performed alphabet addition (i.e., E+3=G, true or false?). Participant's performance became automated with practice through a switch in cognitive strategy from mentally counting-up in the alphabet to retrieving the answer from memory. Time domain analysis of the ERPs revealed a prominent positive peak at approximately 300 ms that was not reactive to problem attributes but was reduced with practice. A second prominent positive peak observed at approximately 500 ms was found to be larger after practice, mainly for problems presented with correct answers. Frequency domain spectral analyses yielded two distinct findings: (1) a frontal midline ERS of theta activity that was greater after practice, and (2) a beta band ERD that increased with problem difficulty before, but not after practice. Because the EEG oscillations were not phase locked to the stimulus, they were viewed as being independent of the time domain results. Consequently, use of time and frequency domain analyses provides a more comprehensive account of the underlying electrophysiological data than either method alone. When used in combination with a well-defined cognitive/behavioral paradigm, this approach serves to constrain the interpretations of EEG data and sets a new standard for studying the neuroplasticity involved in skill acquisition.
Keywords: EEG; ERP; neuroplasticity; skill learning

Emulation of computer mouse control with a noninvasive brain-computer interface. - Dennis J. McFarland; Krusienski, Dean J.; Sarnacki, William A.; Jonathan Wolpaw (Journal of neural engineering, 2008)
Brain-computer interface (BCI) technology can provide nonmuscular communication and control to people who are severely paralyzed. BCIs can use noninvasive or invasive techniques for recording the brain signals that convey the user's commands. Although noninvasive BCIs are used for simple applications, it has frequently been assumed that only invasive BCIs, which use electrodes implanted in the brain, will be able to provide multidimensional sequential control of a robotic arm or a neuroprosthesis. The present study shows that a noninvasive BCI using scalp-recorded electroencephalographic (EEG) activity and an adaptive algorithm can provide people, including people with spinal cord injuries, with two-dimensional cursor movement and target selection. Multiple targets were presented around the periphery of a computer screen, with one designated as the correct target. The user's task was to use EEG to move a cursor from the center of the screen to the correct target and then to use an additional EEG feature to select the target. If the cursor reached an incorrect target, the user was instructed not to select it. Thus, this task emulated the key features of mouse operation. The results indicate that people with severe motor disabilities could use brain signals for sequential multidimensional movement and selection.
Keywords: User-Computer Interface

Exploration of parameters in cryo-EM leading to an improved density map of the E. coli ribosome. - LeBarron, Jamie; Grassucci, Robert A; Shaikh, Tanvir R; Baxter, Bill; Sengupta, Jayati; Frank, Joachim (J Struct Biol, 2008)
A number of image processing parameters in the 3D reconstruction of a ribosome complex from a cryo-EM data set were varied to test their effects on the final resolution. The parameters examined were pixel size, window size, and mode of Fourier amplitude enhancement at high spatial frequencies. In addition, the strategy of switching from large to small pixel size during angular refinement was explored. The relationship between resolution (in Fourier space) and the number of particles was observed to follow a lin-log dependence, a relationship that appears to hold for other data, as well. By optimizing the above parameters, and using a lin-log extrapolation to the full data set in the estimation of resolution from half-sets, we obtained a 3D map from 131,599 ribosome particles at 6.7A resolution (FSC=0.5).
Keywords: Cryoelectron Microscopy; Escherichia coli; Image Enhancement; Image Processing, Computer-Assisted; Ribosomes

Extraction and localization of mesoscopic motor control signals for human ECoG neuroprosthetics. - Sanchez, Justin C; Gunduz, Aysegul; Carney, Paul R; Principe, Jose (J Neurosci Methods, 2008)
Electrocorticogram (ECoG) recordings for neuroprosthetics provide a mesoscopic level of abstraction of brain function between microwire single neuron recordings and the electroencephalogram (EEG). Single-trial ECoG neural interfaces require appropriate feature extraction and signal processing methods to identify and model in real-time signatures of motor events in spontaneous brain activity. Here, we develop the clinical experimental paradigm and analysis tools to record broadband (1Hz to 6kHz) ECoG from patients participating in a reaching and pointing task. Motivated by the significant role of amplitude modulated rate coding in extracellular spike based brain-machine interfaces (BMIs), we develop methods to quantify spatio-temporal intermittent increased ECoG voltages to determine if they provide viable control inputs for ECoG neural interfaces. This study seeks to explore preprocessing modalities that emphasize amplitude modulation across frequencies and channels in the ECoG above the level of noisy background fluctuations in order to derive the commands for complex, continuous control tasks. Preliminary experiments show that it is possible to derive online predictive models and spatially localize the generation of commands in the cortex for motor tasks using amplitude modulated ECoG.
Keywords: Adolescent; Biofeedback, Psychology; Brain Mapping; Cerebral Cortex; Electroencephalography; Epilepsies, Partial; Female; Hand; Humans; Magnetic Resonance Imaging; Physical Therapy Modalities; Psychomotor Performance; Signal Processing, Computer-Assisted; Spectrum Analysis; User-Computer Interface

General Clinical Issues Relevant to Brain-Computer Interfaces. - Leuthardt, E C; Ojemann, J G; Gerwin Schalk; Moran, D (Neuroengineering, 2008)

An in vitro protocol for recording from spinal motoneurons of adult rats. - Jonathan S. Carp; Tennissen, Ann M.; Mongeluzi, Donna L.; Dudek, Christopher J.; Xiang Yang Chen; Jonathan Wolpaw (Journal of neurophysiology, 2008)
In vitro slice preparations of CNS tissue are invaluable for studying neuronal function. However, up to now, slice protocols for adult mammal spinal motoneurons–the final common pathway for motor behaviors–have been available for only limited portions of the spinal cord. In most cases, these preparations have not been productive due to the poor viability of motoneurons in vitro. This report describes and validates a new slice protocol that for the first time provides reliable intracellular recordings from lumbar motoneurons of adult rats. The key features of this protocol are: preexposure to 100% oxygen; laminectomy prior to perfusion; anesthesia with ketamine/xylazine; embedding the spinal cord in agar prior to slicing; and, most important, brief incubation of spinal cord slices in a 30% solution of polyethylene glycol to promote resealing of the many motoneuron dendrites cut during sectioning. Together, these new features produce successful recordings in 76% of the experiments and an average action potential amplitude of 76 mV. Motoneuron properties measured in this new slice preparation (i.e., voltage and current thresholds for action potential initiation, input resistance, afterhyperpolarization size and duration, and onset and offset firing rates during current ramps) are comparable to those recorded in vivo. Given the mechanical stability and precise control over the extracellular environment afforded by an in vitro preparation, this new protocol can greatly facilitate electrophysiological and pharmacological study of these uniquely important neurons and other delicate neuronal populations in adult mammals.
Keywords: Tissue and Organ Harvesting

Inferring Details of Motor/Language Function Using ECoG Signals in Humans - Gerwin Schalk (2008)
Workshop Advances in Theory and Clinical Application of Subdural Recordings, American Epilepsy Society Annual Meeting, Seattle, Washington

Interferon-gamma limits the availability of iron for intramacrophage Salmonella typhimurium. - Nairz, Manfred; Fritsche, Gernot; Peter Brunner; Talasz, Heribert; Hantke, Klaus; Weiss, Günter (Eur J Immunol, 2008)
In stimulating effector functions of mononuclear phagocytes, IFN-gamma is of pivotal importance in host defense against intramacrophage pathogens including salmonellae. As the activity of IFN-gamma is modulated by iron and since a sufficient availability of iron is essential for the growth of pathogens, we investigated the regulatory effects of IFN-gamma on iron homeostasis and immune function in murine macrophages infected with Salmonella typhimurium. In Salmonella-infected phagocytes, IFN-gamma caused a significant reduction of iron uptake via transferrin receptor 1 and resulted in an increased iron efflux caused by an enhanced expression of the iron exporter ferroportin 1. Moreover, the expression of haem oxygenase 1 and of the siderophore-capturing antimicrobial peptide lipocalin 2 was markedly elevated following bacterial invasion, with IFN-gamma exerting a super-inducing effect. This observed regulatory impact of IFN-gamma reduced the intracellular iron pools within infected phagocytes, thus restricting the acquisition of iron by engulfed Salmonella typhimurium while concomitantly promoting NO and TNF-alpha production. Our data suggest that the modulation of crucial pathways of macrophage iron metabolism in response to IFN-gamma concordantly aims at withdrawing iron from intracellular Salmonella and at strengthening macrophage immune response functions. These regulations are thus consistent with the principles of nutritional immunity.
Keywords: Acute-Phase Proteins; Animals; Antimicrobial Cationic Peptides; Cation Transport Proteins; Cell Line; Ferritins; Heme Oxygenase (Decyclizing); Hepcidins; Interferon-gamma; Iron; Lipocalins; Macrophages; Mice; Nitric Oxide; Oncogene Proteins; Salmonella typhimurium; Transferrin; Tumor Necrosis Factor-alpha

Movement Control Using Field Potentials Recorded on the Surface of the Brain - Gerwin Schalk (2008)
Workshop on Real-Time Brain Interfacing Applications, Mathematical Biosciences Institute, The Ohio State University, Columbus, Ohio

Non-invasive brain-computer interface system: towards its application as assistive technology. - Cincotti, F; Mattia, Donatella; Aloise, Fabio; Bufalari, Simona; Gerwin Schalk; Oriolo, Giuseppe; Cherubini, Andrea; Marciani, Maria Grazia; Babiloni, Fabio (Brain Res Bull, 2008)
The quality of life of people suffering from severe motor disabilities can benefit from the use of current assistive technology capable of ameliorating communication, house-environment management and mobility, according to the user's residual motor abilities. Brain-computer interfaces (BCIs) are systems that can translate brain activity into signals that control external devices. Thus they can represent the only technology for severely paralyzed patients to increase or maintain their communication and control options. Here we report on a pilot study in which a system was implemented and validated to allow disabled persons to improve or recover their mobility (directly or by emulation) and communication within the surrounding environment. The system is based on a software controller that offers to the user a communication interface that is matched with the individual's residual motor abilities. Patients (n=14) with severe motor disabilities due to progressive neurodegenerative disorders were trained to use the system prototype under a rehabilitation program carried out in a house-like furnished space. All users utilized regular assistive control options (e.g., microswitches or head trackers). In addition, four subjects learned to operate the system by means of a non-invasive EEG-based BCI. This system was controlled by the subjects' voluntary modulations of EEG sensorimotor rhythms recorded on the scalp; this skill was learnt even though the subjects have not had control over their limbs for a long time. We conclude that such a prototype system, which integrates several different assistive technologies including a BCI system, can potentially facilitate the translation from pre-clinical demonstrations to a clinical useful BCI.
Keywords: Activities of Daily Living; Adolescent; Adult; Brain; Child; Electroencephalography; Evoked Potentials, Motor; Female; Humans; Learning; Male; Middle Aged; Motor Skills; Muscular Dystrophy, Duchenne; Pilot Projects; Prostheses and Implants; Robotics; Self-Help Devices; Software; Spinal Muscular Atrophies of Childhood; User-Computer Interface; Volition

Overview of Available BCI2000 Components - Gerwin Schalk (2008)
4th BCI2000 Workshop, Utrecht, The Netherlands

A P300-based brain-computer interface for people with amyotrophic lateral sclerosis. - Nijboer, F.; Sellers, E. W.; Mellinger, J.; Jordan, M. A.; Matuz, T.; Adrian Furdea; S Halder; Mochty, U.; Krusienski, D. J.; Theresa M Vaughan; Jonathan Wolpaw; Niels Birbaumer; et al. (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2008)
OBJECTIVE: The current study evaluates the efficacy of a P300-based brain-computer interface (BCI) communication device for individuals with advanced ALS. METHODS: Participants attended to one cell of a N x N matrix while the N rows and N columns flashed randomly. Each cell of the matrix contained one character. Every flash of an attended character served as a rare event in an oddball sequence and elicited a P300 response. Classification coefficients derived using a stepwise linear discriminant function were applied to the data after each set of flashes. The character receiving the highest discriminant score was presented as feedback. RESULTS: In Phase I, six participants used a 6 x 6 matrix on 12 separate days with a mean rate of 1.2 selections/min and mean online and offline accuracies of 62% and 82%, respectively. In Phase II, four participants used either a 6 x 6 or a 7 x 7 matrix to produce novel and spontaneous statements with a mean online rate of 2.1 selections/min and online accuracy of 79%. The amplitude and latency of the P300 remained stable over 40 weeks. CONCLUSIONS: Participants could communicate with the P300-based BCI and performance was stable over many months. SIGNIFICANCE: BCIs could provide an alternative communication and control technology in the daily lives of people severely disabled by ALS.
Keywords: Amyotrophic Lateral Sclerosis; brain-computer interface; electroencephalogram; event-related potentials; P300; Rehabilitation

Particle-verification for single-particle, reference-based reconstruction using multivariate data analysis and classification. - Shaikh, Tanvir R; Trujillo, Ramon; LeBarron, Jamie; Baxter, Bill; Frank, Joachim (J Struct Biol, 2008)
As collection of electron microscopy data for single-particle reconstruction becomes more efficient, due to electronic image capture, one of the principal limiting steps in a reconstruction remains particle-verification, which is especially costly in terms of user input. Recently, some algorithms have been developed to window particles automatically, but the resulting particle sets typically need to be verified manually. Here we describe a procedure to speed up verification of windowed particles using multivariate data analysis and classification. In this procedure, the particle set is subjected to multi-reference alignment before the verification. The aligned particles are first binned according to orientation and are binned further by K-means classification. Rather than selection of particles individually, an entire class of particles can be selected, with an option to remove outliers. Since particles in the same class present the same view, distinction between good and bad images becomes more straightforward. We have also developed a graphical interface, written in Python/Tkinter, to facilitate this implementation of particle-verification. For the demonstration of the particle-verification scheme presented here, electron micrographs of ribosomes are used.
Keywords: Algorithms; Artificial Intelligence; Classification; Image Enhancement; Image Processing, Computer-Assisted; Microscopy, Electron; Multivariate Analysis; Ribosomes

Phase synchronization with ICA for epileptic seizure onset prediction in the long term EEG. - Disha Gupta; Christopher J James; William P Gray (4th IET International Conference on Advances in Medical, Signal and Information Processing, 2008)
The apparently unpredictable nature of epileptic seizures can be devastating for people with epilepsy. Current medical interventions can help 75% of patients while 25% have to live with uncontrolled seizures. This motivates the search for a seizure prediction prototype using electroencephalograms (electrical signals that capture brain activity). The concept of phase synchrony has attracted much attention recently in the context of seizure prediction but is still in need of further study. The basis of our analysis is to track changes in synchrony in brain signals at and before seizure onset. The novel concept in our analysis is the use of unmixed signals as opposed to scalp EEG signals for phase synchrony analysis. The unmixing is performed by a Blind Source Separation technique called Independent component Analysis (ICA). ICA seeks underlying independent source signals from the EEG and it allows multivariate analysis using spatial as well as temporal information inherent to EEG signals. The present study on long-term continuous EEG data sets indicates that the concept of using phase synchronization with ICA may prove useful for predicting seizures.

Phase-alignment of delayed sensory signals by adaptive filters. - Dennis J. McFarland (The Behavioral and brain sciences, 2008)
Correction of sensory transmission delays is an intractable problem because there is no absolute reference for calibration. Phase alignment is a practical alternative solution and can be realized by adaptive filters that operate locally with simple error signals.

Real-time detection of event-related brain activity. - Gerwin Schalk; Leuthardt, E C; Peter Brunner; Ojemann, J G; Lester A Gerhardt; Jonathan Wolpaw (Neuroimage, 2008)
The complexity and inter-individual variation of brain signals impedes real-time detection of events in raw signals. To convert these complex signals into results that can be readily understood, current approaches usually apply statistical methods to data from known conditions after all data have been collected. The capability to provide meaningful visualization of complex brain signals without the requirement to initially collect data from all conditions would provide a new tool, essentially a new imaging technique, that would open up new avenues for the study of brain function. Here we show that a new analysis approach, called SIGFRIED, can overcome this serious limitation of current methods. SIGFRIED can visualize brain signal changes without requiring prior data collection from all conditions. This capacity is particularly well suited to applications in which comprehensive prior data collection is impossible or impractical, such as intraoperative localization of cortical function or detection of epileptic seizures.
Keywords: Adult; Algorithms; Brain Mapping; Computer Systems; Diagnosis, Computer-Assisted; Electroencephalography; Epilepsy; Evoked Potentials; Female; Humans; Male; Pattern Recognition, Automated; Reproducibility of Results; Sensitivity and Specificity

Sensorimotor rhythm-based brain-computer interface (BCI): model order selection for autoregressive spectral analysis. - Dennis J. McFarland; Jonathan Wolpaw (Journal of neural engineering, 2008)
People can learn to control EEG features consisting of sensorimotor rhythm amplitudes and can use this control to move a cursor in one or two dimensions to a target on a screen. Cursor movement depends on the estimate of the amplitudes of sensorimotor rhythms. Autoregressive models are often used to provide these estimates. The order of the autoregressive model has varied widely among studies. Through analyses of both simulated and actual EEG data, the present study examines the effects of model order on sensorimotor rhythm measurements and BCI performance. The results show that resolution of lower frequency signals requires higher model orders and that this requirement reflects the temporal span of the model coefficients. This is true for both simulated EEG data and actual EEG data during brain-computer interface (BCI) operation. Increasing model order, and decimating the signal were similarly effective in increasing spectral resolution. Furthermore, for BCI control of two-dimensional cursor movement, higher model orders produced better performance in each dimension and greater independence between horizontal and vertical movements. In sum, these results show that autoregressive model order selection is an important determinant of BCI performance and should be based on criteria that reflect system performance.
Keywords: User-Computer Interface

SPIDER image processing for single-particle reconstruction of biological macromolecules from electron micrographs. - Shaikh, Tanvir R; Gao, Haixiao; Baxter, Bill; Asturias, Francisco J; Boisset, Nicolas; Leith, ArDean; Frank, Joachim (Nat Protoc, 2008)
This protocol describes the reconstruction of biological molecules from the electron micrographs of single particles. Computation here is performed using the image-processing software SPIDER and can be managed using a graphical user interface, termed the SPIDER Reconstruction Engine. Two approaches are described to obtain an initial reconstruction: random-conical tilt and common lines. Once an existing model is available, reference-based alignment can be used, a procedure that can be iterated. Also described is supervised classification, a method to look for homogeneous subsets when multiple known conformations of the molecule may coexist.
Keywords: Image Processing, Computer-Assisted; Microscopy, Electron; Models, Molecular; Molecular Structure; Software; User-Computer Interface

Theory and Application of Subdural Recordings in Humans - Gerwin Schalk (2008)
Neurosciences Grand Rounds, The Neurosciences Institute, Albany Medical Center, Albany, New York

Three cases of feature correlation in an electrocorticographic BCI. - Miller, Kai J; Blakely, Timothy; Gerwin Schalk; den Nijs, Marcel; Rao, Rajesh PN; Ojemann, Jeffrey G (Engineering in Medicine and Biology Society, 2008., 2008)
Three human subjects participated in a closed-loop brain computer interface cursor control experiment mediated by implanted subdural electrocorticographic arrays. The paradigm consisted of several stages: baseline recording, hand and tongue motor tasks as the basis for feature selection, two closed-loop one-dimensional feedback experiments with each of these features, and a two-dimensional feedback experiment using both of the features simultaneously. The two selected features were simple channel and frequency band combinations associated with change during hand and tongue movement. Inter-feature correlation and cross-correlation between features during different epochs of each task were quantified for each stage of the experiment. Our anecdotal, three subject, result suggests that while high correlation between horizontal and vertical control signal can initially preclude successful two-dimensional cursor control, a feedback-based learning strategy can be successfully employed by the subject to overcome this limitation and progressively decorrelate these control signals.
Keywords: Adolescent; Adult; Algorithms; automated pattern recognition; control systems; decorrelation; Electrocardiography; Electrodes; Electroencephalography; evoked motor potentials; Feedback; Female; frequency; hospitals; Humans; Male; Middle Aged; Motor Cortex; Signal Processing; Statistics as Topic; Task Performance and Analysis; Tongue; User-Computer Interface

Three cases of feature correlation in an electrocorticographic BCI. - Miller, John W; Blakely, Timothy; Gerwin Schalk; den Nijs, Marcel; Rao, Rajesh P N; Ojemann, J G (Conf Proc IEEE Eng Med Biol Soc, 2008)
Three human subjects participated in a closed-loop brain computer interface cursor control experiment mediated by implanted subdural electrocorticographic arrays. The paradigm consisted of several stages: baseline recording, hand and tongue motor tasks as the basis for feature selection, two closed-loop one-dimensional feedback experiments with each of these features, and a two-dimensional feedback experiment using both of the features simultaneously. The two selected features were simple channel and frequency band combinations associated with change during hand and tongue movement. Inter-feature correlation and cross-correlation between features during different epochs of each task were quantified for each stage of the experiment. Our anecdotal, three subject, result suggests that while high correlation between horizontal and vertical control signal can initially preclude successful two-dimensional cursor control, a feedback-based learning strategy can be successfully employed by the subject to overcome this limitation and progressively decorrelate these control signals.
Keywords: Adolescent; Adult; Algorithms; Electrocardiography; Evoked Potentials, Motor; Female; Humans; Male; Middle Aged; Motor Cortex; Pattern Recognition, Automated; Statistics as Topic; Task Performance and Analysis; User-Computer Interface

Toward enhanced P300 speller performance. - Krusienski, D. J.; Sellers, E. W.; Dennis J. McFarland; Theresa M Vaughan; Jonathan Wolpaw (Journal of neuroscience methods, 2008)
This study examines the effects of expanding the classical P300 feature space on the classification performance of data collected from a P300 speller paradigm [Farwell LA, Donchin E. Talking off the top of your head: toward a mental prosthesis utilizing event-related brain potentials. Electroenceph Clin Neurophysiol 1988;70:510-23]. Using stepwise linear discriminant analysis (SWLDA) to construct a classifier, the effects of spatial channel selection, channel referencing, data decimation, and maximum number of model features are compared with the intent of establishing a baseline not only for the SWLDA classifier, but for related P300 speller classification methods in general. By supplementing the classical P300 recording locations with posterior locations, online classification performance of P300 speller responses can be significantly improved using SWLDA and the favorable parameters derived from the offline comparative analysis.
Keywords: brain-computer interface; event related potentials; P300 speller; stepwise linear discriminant analysis

Towards an independent brain-computer interface using steady state visual evoked potentials. - Brendan Z. Allison; Dennis J. McFarland; Gerwin Schalk; Zheng, Shi Dong; Moore-Jackson, Melody; Jonathan Wolpaw (Clin Neurophysiol, 2008)
OBJECTIVE:  Brain-computer interface (BCI) systems using steady state visual evoked potentials (SSVEPs) have allowed healthy subjects to communicate. However, these systems may not work in severely disabled users because they may depend on gaze shifting. This study evaluates the hypothesis that overlapping stimuli can evoke changes in SSVEP activity sufficient to control a BCI. This would provide evidence that SSVEP BCIs could be used without shifting gaze. METHODS:  Subjects viewed a display containing two images that each oscillated at a different frequency. Different conditions used overlapping or non-overlapping images to explore dependence on gaze function. Subjects were asked to direct attention to one or the other of these images during each of 12 one-minute runs. RESULTS:  Half of the subjects produced differences in SSVEP activity elicited by overlapping stimuli that could support BCI control. In all remaining users, differences did exist at corresponding frequencies but were not strong enough to allow effective control. CONCLUSIONS:  The data demonstrate that SSVEP differences sufficient for BCI control may be elicited by selective attention to one of two overlapping stimuli. Thus, some SSVEP-based BCI approaches may not depend on gaze control. The nature and extent of any BCI's dependence on muscle activity is a function of many factors, including the display, task, environment, and user. SIGNIFICANCE:  SSVEP BCIs might function in severely disabled users unable to reliably control gaze. Further research with these users is necessary to explore the optimal parameters of such a system and validate online performance in a home environment.
Keywords: Adolescent; Adult; Attention; Brain; Brain Mapping; Dose-Response Relationship, Radiation; Electroencephalography; Evoked Potentials, Visual; Female; Humans; Male; Pattern Recognition, Visual; Photic Stimulation; Spectrum Analysis; User-Computer Interface

Two-dimensional movement control using electrocorticographic signals in humans. - Gerwin Schalk; Miller, K.J.; Nicholas R Anderson; Adam J Wilson; Smyth, Matt; Ojemann, J G; Moran, D; Jonathan Wolpaw; Leuthardt, E C (J Neural Eng, 2008)
We show here that a brain-computer interface (BCI) using electrocorticographic activity (ECoG) and imagined or overt motor tasks enables humans to control a computer cursor in two dimensions. Over a brief training period of 12-36 min, each of five human subjects acquired substantial control of particular ECoG features recorded from several locations over the same hemisphere, and achieved average success rates of 53-73% in a two-dimensional four-target center-out task in which chance accuracy was 25%. Our results support the expectation that ECoG-based BCIs can combine high performance with technical and clinical practicality, and also indicate promising directions for further research.
Keywords: Adolescent; Adult; Brain Mapping; Data Interpretation, Statistical; Drug Resistance; Electrocardiography; Electrodes, Implanted; Electroencephalography; Epilepsy; Female; Humans; Male; Movement; User-Computer Interface

Unique cortical physiology associated with ipsilateral hand movements and neuroprosthetic implications. - Wisneski, Kimberly; Nicholas R Anderson; Gerwin Schalk; Smyth, Matt; Moran, D; Leuthardt, E C (Stroke, 2008)
BACKGROUND AND PURPOSE:  Brain computer interfaces (BCIs) offer little direct benefit to patients with hemispheric stroke because current platforms rely on signals derived from the contralateral motor cortex (the same region injured by the stroke). For BCIs to assist hemiparetic patients, the implant must use unaffected cortex ipsilateral to the affected limb. This requires the identification of distinct electrophysiological features from the motor cortex associated with ipsilateral hand movements. METHODS:  In this study we studied 6 patients undergoing temporary placement of intracranial electrode arrays. Electrocorticographic (ECoG) signals were recorded while the subjects engaged in specific ipsilateral or contralateral hand motor tasks. Spectral changes were identified with regards to frequency, location, and timing. RESULTS:  Ipsilateral hand movements were associated with electrophysiological changes that occur in lower frequency spectra, at distinct anatomic locations, and earlier than changes associated with contralateral hand movements. In a subset of 3 patients, features specific to ipsilateral and contralateral hand movements were used to control a cursor on a screen in real time. In ipsilateral derived control this was optimal with lower frequency spectra. CONCLUSIONS:  There are distinctive cortical electrophysiological features associated with ipsilateral movements which can be used for device control. These findings have implications for patients with hemispheric stroke because they offer a potential methodology for which a single hemisphere can be used to enhance the function of a stroke induced hemiparesis.
Keywords: Adolescent; Adult; Artificial Limbs; Bionics; Brain Mapping; Child; Dominance, Cerebral; Electroencephalography; Female; Hand; Humans; Male; Middle Aged; Motor Cortex; Movement; Paresis; Prosthesis Design; Psychomotor Performance; Stroke; User-Computer Interface; Volition

Using Brain Signals for Clinical Diagnosis and Communication - Gerwin Schalk (2008)
Center for Neuropharmacology & Neuroscience, Albany Medical College, Albany, New York

Using Electrocorticographic (ECoG) Signals in Humans for Communication and Diagnosis - Gerwin Schalk (2008)
Technical University of Berlin, Berlin, Germany

Using Electrocorticographic (ECoG) Signals in Humans for Communication and Diagnosis - Gerwin Schalk (2008)
Department of Physiology and Biophysics, University of Washington, Seattle, Washington

Using Electrocorticography for Brain-Computer Interfacing and Detailed Single-Trial Decoding of Human Behavior - Gerwin Schalk (2008)
Brain Gain Lecture, F.C. Donders Center for Cognitive Neuroimaging, Radboud University Nijmegen, Nijmegen, The Netherlands

Voluntary brain regulation and communication with electrocorticogram signals. - Hinterberger, T.; Widman, Guido; Lal, T.N; Jeremy Jeremy Hill; Tangermann, Michael; Rosenstiel, W.; Schölkopf, B; Elger, Christian; Niels Birbaumer (Epilepsy Behav, 2008)
Brain-computer interfaces (BCIs) can be used for communication in writing without muscular activity or for learning to control seizures by voluntary regulation of brain signals such as the electroencephalogram (EEG). Three of five patients with epilepsy were able to spell their names with electrocorticogram (ECoG) signals derived from motor-related areas within only one or two training sessions. Imagery of finger or tongue movements was classified with support-vector classification of autoregressive coefficients derived from the ECoG signals. After training of the classifier, binary classification responses were used to select letters from a computer-generated menu. Offline analysis showed increased theta activity in the unsuccessful patients, whereas the successful patients exhibited dominant sensorimotor rhythms that they could control. The high spatial resolution and increased signal-to-noise ratio in ECoG signals, combined with short training periods, may offer an alternative for communication in complete paralysis, locked-in syndrome, and motor restoration.
Keywords: Adult; Biofeedback, Psychology; Cerebral Cortex; Communication Aids for Disabled; Dominance, Cerebral; Electroencephalography; Epilepsies, Partial; Female; Humans; Imagination; Male; Middle Aged; Motor Activity; Motor Cortex; Signal Processing, Computer-Assisted; Software; Somatosensory Cortex; Theta Rhythm; User-Computer Interface; Writing

BCI2000: A General-Purpose Brain-Computer Interface System - Gerwin Schalk (2007)
2nd BCI2000 Workshop, Beijing, China

BCI2000: A General-Purpose Software Platform for BCI Research. - Mellinger, Jürgen; Gerwin Schalk (Brain-Computer Interfaces, 2007)

Brain Computer Interfaces for Communication in Paralysis: a Clinical-Experimental Approach. - Hinterberger, T.; Nijboer, F; Kübler, A.; Matuz, T.; Adrian Furdea; Mochty, Ursula; Jordan, M.; Lal, T.N; Jeremy Jeremy Hill; Mellinger, Jürgen; Bensch, M; Tangermann, Michael; et al. (Virtual Library of Psychology at Saarland University and State Library, GERMANY, PsyDok [http://psydok.sulb.uni-saarland.de/phpoai/oai2.php] (Germany), 2007)
An overview of different approaches to brain-computer interfaces (BCIs) developed in our laboratory is given. An important clinical application of BCIs is to enable communication or environmental control in severely paralyzed patients. The BCI “Thought-Translation Device (TTD)” allows verbal communication through the voluntary self-regulation of brain signals (e.g., slow cortical potentials (SCPs)), which is achieved by operant feedback training. Humans' ability to self-regulate their SCPs is used to move a cursor toward a target that contains a selectable letter set. Two different approaches were followed to developWeb browsers that could be controlled with binary brain responses. Implementing more powerful classification methods including different signal parameters such as oscillatory features improved our BCI considerably. It was also tested on signals with implanted electrodes. Most BCIs provide the user with a visual feedback interface. Visually impaired patients require an auditory feedback mode. A procedure using auditory (sonified) feedback of multiple EEG parameters was evaluated. Properties of the auditory systems are reported and the results of two experiments with auditory feedback are presented. Clinical data of eight ALS patients demonstrated that all patients were able to acquire efficient brain control of one of the three available BCI systems (SCP, µ-rhythm, and P300), most of them used the SCP-BCI. A controlled comparison of the three systems in a group of ALS patients, however, showed that P300-BCI and the µ-BCI are faster and more easily acquired than SCP-BCI, at least in patients with some rudimentary motor control left. Six patients who started BCI training after entering the completely locked-in state did not achieve reliable communication skills with any BCI system. One completely locked-in patient was able t o communicate shortly with a ph-meter, but lost control afterward.
Keywords: brain-computer interfaces; EEG; experiment; Medical sciences Medicine; paralyzed patients; slow cortical potentials; Thought-Translation Device

Brain-computer interface systems: progress and prospects. - Brendan Z. Allison; Wolpaw, Elizabeth Winter; Jonathan Wolpaw (Expert review of medical devices, 2007)
Brain-computer interface (BCI) systems support communication through direct measures of neural activity without muscle activity. BCIs may provide the best and sometimes the only communication option for users disabled by the most severe neuromuscular disorders and may eventually become useful to less severely disabled and/or healthy individuals across a wide range of applications. This review discusses the structure and functions of BCI systems, clarifies terminology and addresses practical applications. Progress and opportunities in the field are also identified and explicated.
Keywords: ALS; assistive communication; BCI; BMI; brain-acuated control; brain-computer interface; brain-machine interface; EEG; ERP; locked-in syndrome; slow cortical potential; SSVEP; Stroke

Brain-computer interfaces as new brain output pathways. - Jonathan Wolpaw (The Journal of physiology, 2007)
Brain-computer interfaces (BCIs) can provide non-muscular communication and control for people with severe motor disabilities. Current BCIs use a variety of invasive and non-invasive methods to record brain signals and a variety of signal processing methods. Whatever the recording and processing methods used, BCI performance (e.g. the ability of a BCI to control movement of a computer cursor) is highly variable and, by the standards applied to neuromuscular control, could be described as ataxic. In an effort to understand this imperfection, this paper discusses the relevance of two principles that underlie the brain's normal motor outputs. The first principle is that motor outputs are normally produced by the combined activity of many CNS areas, from the cortex to the spinal cord. Together, these areas produce appropriate control of the spinal motoneurons that activate muscles. The second principle is that the acquisition and life-long preservation of motor skills depends on continual adaptive plasticity throughout the CNS. This plasticity optimizes the control of spinal motoneurons. In the light of these two principles, a BCI may be viewed as a system that changes the outcome of CNS activity from control of spinal motoneurons to, instead, control of the cortical (or other) area whose signals are used by the BCI to determine the user's intent. In essence, a BCI attempts to assign to cortical neurons the role normally performed by spinal motoneurons. Thus, a BCI requires that the many CNS areas involved in producing normal motor actions change their roles so as to optimize the control of cortical neurons rather than spinal motoneurons. The disconcerting variability of BCI performance may stem in large part from the challenge presented by the need for this unnatural adaptation. This difficulty might be reduced, and BCI development might thereby benefit, by adopting a 'goal-selection' rather than a 'process- control' strategy. In 'process control', a BCI manages all the intricate high-speed interactions involved in movement. In 'goal selection', by contrast, the BCI simply communicates the user's goal to software that handles the high-speed interactions needed to achieve the goal. Not only is 'goal selection' less demanding, but also, by delegating lower-level aspects of motor control to another structure (rather than requiring that the cortex do everything), it more closely resembles the distributed operation characteristic of normal motor control.
Keywords: User-Computer Interface

Brain-Computer Interfaces: Controlling A Computer With Your Thought - Gerwin Schalk (2007)
Science Today Seminar Series. Bethlehem High School, Delmar, New York.

Brain-Computer Interfacing Using Electrocorticography (ECoG) - Gerwin Schalk (2007)
International Workshop on Brain-Computer Interface Technology, Beijing, China

Brain-Computer Interfacing Using Non-Invasive and Invasive Methods - Gerwin Schalk (2007)
Computer Science and Electrical Engineering Department, Orgegon Health & Science University, Beaverton, Oregon

Brain-Computer Interfacing Using Non-Invasive, Intra-Cortical, and Subdural Methods - Gerwin Schalk (2007)
Max-Planck-Institute for Brain Research, Frankfurt, Germany

Communicating Directly from the Brain: Brain-Computer Interfaces (BCIs) - Gerwin Schalk (2007)
Wadsworth Center Research Experience for Undergraduates Program, Albany, New York

Compressed Sensing Using Prior Information - von Borries R.; Miosso C. J.; Potes, Cristhian (The Second International Workshop on Computational Advances in MultiSensor Adaptive Processing, 2007)

Decoding two-dimensional movement trajectories using electrocorticographic signals in humans. - Gerwin Schalk; Kubánek, J; Miller, John W; Nicholas R Anderson; Leuthardt, E C; Ojemann, J G; Limbrick, D; Moran, D; Lester A Gerhardt; Jonathan Wolpaw (J Neural Eng, 2007)
Signals from the brain could provide a non-muscular communication and control system, a brain-computer interface (BCI), for people who are severely paralyzed. A common BCI research strategy begins by decoding kinematic parameters from brain signals recorded during actual arm movement. It has been assumed that these parameters can be derived accurately only from signals recorded by intracortical microelectrodes, but the long-term stability of such electrodes is uncertain. The present study disproves this widespread assumption by showing in humans that kinematic parameters can also be decoded from signals recorded by subdural electrodes on the cortical surface (ECoG) with an accuracy comparable to that achieved in monkey studies using intracortical microelectrodes. A new ECoG feature labeled the local motor potential (LMP) provided the most information about movement. Furthermore, features displayed cosine tuning that has previously been described only for signals recorded within the brain. These results suggest that ECoG could be a more stable and less invasive alternative to intracortical electrodes for BCI systems, and could also prove useful in studies of motor function.
Keywords: Adult; Algorithms; Arm; Brain Mapping; Cerebral Cortex; Electroencephalography; Evoked Potentials, Motor; Female; Humans; Male; Movement

Definition of Motor Responses and Brain-Computer Interfacing Using Electrocorticography - Gerwin Schalk (2007)
Neuroscience Group, Laborator of Nervous System Disorders, Wadsworth Center, New York State Department of Health, Albany New York

Direct Communication From the Brain - Gerwin Schalk (2007)
Guest lecture for BS in IT Capstone Course. Department of Information Technology, Rensselaer Polytechnic Institute, Troy, New York

Directional Filter Banks for Wavelet Decomposition of Images Based on the Radon Transform - von Borries R.; Miosso C. J.; Potes, Cristhian (Forty-First Asilomar Conference on Signals, Systems and Computers, 2007)

Electrocorticographic Frequency Alteration Mapping: A Clinical Technique for Mapping the Motor Cortex. - Leuthardt, E C; Miller, John W; Nicholas R Anderson; Gerwin Schalk; Dowling, Joshua; Miller, John W; Moran, D; Ojemann, J G (Neurosurgery, 2007)
OBJECTIVE:  Electrocortical stimulation (ECS) has been well established for delineating the eloquent cortex. However, ECS is still coarse and inefficient in delineating regions of the functional cortex and can be hampered by after-discharges. Given these constraints, an adjunct approach to defining the motor cortex is the use of electrocorticographic signal changes associated with active regions of the cortex. The broad range of frequency oscillations are categorized into two main groups with respect to the sensorimotor cortex: low and high frequency bands. The low frequency bands tend to show a power reduction with cortical activation, whereas the high frequency bands show power increases. These power changes associated with the activated cortex could potentially provide a powerful tool in delineating areas of the motor cortex. We explore electrocorticographic signal alterations as they occur with activated regions of the motor cortex, as well as its potential in clinical brain mapping applications. METHODS:  We evaluated seven patients who underwent invasive monitoring for seizure localization. Each patient had extraoperative ECS mapping to identify the motor cortex. All patients also performed overt hand and tongue motor tasks to identify associated frequency power changes in regard to location and degree of concordance with ECS results that localized either hand or tongue motor function. RESULTS:  The low frequency bands had a high sensitivity (88.9-100%) and a lower specificity (79.0-82.6%) for identifying electrodes with either hand or tongue ECS motor responses. The high frequency bands had a lower sensitivity (72.7-88.9%) and a higher specificity (92.4-94.9%) in correlation with the same respective ECS positive electrodes. CONCLUSION:  The concordance between stimulation and spectral power changes demonstrate the possible utility of electrocorticographic frequency alteration mapping as an adjunct method to improve the efficiency and resolution of identifying the motor cortex.
Keywords: Adult; Biological Clocks; Brain Mapping; Electric Stimulation; Electrodes, Implanted; Electroencephalography; Female; Hand; Humans; Male; Middle Aged; Motor Cortex; Oscillometry; Signal Processing, Computer-Assisted; Tongue

Electrocorticography (ECoG) for Feedback and Decoding of Function - Gerwin Schalk (2007)
Workshop on Large Scale Brain Dynamics, Neural Information Processing Systems (NIPS), Whistler, British Columbia, Canada

Electrocorticography for Brain-Computer Interfacing and Motor/Language Mapping - Gerwin Schalk (2007)
Neurosciences Grand Rounds, The Neurosciences Institute, Albany Medical Center, Albany, New York.

Flux-continuous schemes for solving EEG source localization problems. - Mayur Pal; Disha Gupta; M G Edwards; Christopher J James (15th UK Conference of the Association of Computational Mechanics in Engineering 2007, 2007)
Keywords: control volume distributed; electroencephalographic; finite element method; flux-continuous schemes; independent component analysis; Poisson's equation; source localization

An MEG-based brain-computer interface (BCI). - Mellinger, Jürgen; Gerwin Schalk; Christoph Braun; Preissl, Hubert; Rosenstiel, W.; Niels Birbaumer; Kübler, A. (Neuroimage, 2007)
Brain-computer interfaces (BCIs) allow for communicating intentions by mere brain activity, not involving muscles. Thus, BCIs may offer patients who have lost all voluntary muscle control the only possible way to communicate. Many recent studies have demonstrated that BCIs based on electroencephalography(EEG) can allow healthy and severely paralyzed individuals to communicate. While this approach is safe and inexpensive, communication is slow. Magnetoencephalography (MEG) provides signals with higher spatiotemporal resolution than EEG and could thus be used to explore whether these improved signal properties translate into increased BCI communication speed. In this study, we investigated the utility of an MEG-based BCI that uses voluntary amplitude modulation of sensorimotor mu and beta rhythms. To increase the signal-to-noise ratio, we present a simple spatial filtering method that takes the geometric properties of signal propagation in MEG into account, and we present methods that can process artifacts specifically encountered in an MEG-based BCI. Exemplarily, six participants were successfully trained to communicate binary decisions by imagery of limb movements using a feedback paradigm. Participants achieved significant mu rhythm self control within 32 min of feedback training. For a subgroup of three participants, we localized the origin of the amplitude modulated signal to the motor cortex. Our results suggest that an MEG-based BCI is feasible and efficient in terms of user training.
Keywords: Adult; Algorithms; Artifacts; Brain; Electroencephalography; Electromagnetic Fields; Electromyography; Feedback; Female; Foot; Hand; Head Movements; Humans; Magnetic Resonance Imaging; Magnetoencephalography; Male; Movement; Principal Component Analysis; Signal Processing, Computer-Assisted; User-Computer Interface

Narrowband vs. broadband phase synchronization analysis applied to independent components of ictal and interictal EEG. - Disha Gupta; Christopher J James (Conf Proc IEEE Eng Med Biol Soc, 2007)
This paper presents a comparison of the use of broadband and narrow band signals for phase synchronization analysis as applied to Independent Components of ictal and interictal scalp EEG in the context of seizure onset detection and prediction. Narrow band analysis for phase synchronization is found to be better performed in the present context than the broad band signal analysis. It has been observed that the phase synchronization of Independent Components in a narrow band (particularly the Gamma band) shows a prominent trend of increasing and decreasing synchronization at seizure onset near the epileptogenic area (spatially). This information is not always found to be consistent in analysis with the raw EEG signals, which may show spurious synchronization happening due to volume conduction effects. These observations lead us to believe that tracking changes in phase synchronization of narrow band activity, on continuous data records will be of great value in the context of seizure prediction.
Keywords: Algorithms; Electroencephalography; Humans; Predictive Value of Tests; Seizures; Signal Processing, Computer-Assisted

Non-invasive brain-computer interface system to operate assistive devices. - Cincotti, F; Aloise, Fabio; Bufalari, Simona; Gerwin Schalk; Oriolo, Giuseppe; Cherubini, Andrea; Davide, Fabrizio; Babiloni, Fabio; Marciani, Maria Grazia; Mattia, Donatella (Conf Proc IEEE Eng Med Biol Soc, 2007)
In this pilot study, a system that allows disabled persons to improve or recover their mobility and communication within the surrounding environment was implemented and validated. The system is based on a software controller that offers to the user a communication interface that is matched with the individual's residual motor abilities. Fourteen patients with severe motor disabilities due to progressive neurodegenerative disorders were trained to use the system prototype under a rehabilitation program. All users utilized regular assistive control options (e.g., microswitches or head trackers) while four patients learned to operate the system by means of a non-invasive EEG-based Brain-Computer Interface, based on the subjects' voluntary modulations of EEG sensorimotor rhythms recorded on the scalp.
Keywords: Brain; Communication Aids for Disabled; Computer Systems; Humans; Neurodegenerative Diseases; Quality of Life; Self-Help Devices; Software; User-Computer Interface

Recovery of electromyographic activity after transection and surgical repair of the rat sciatic nerve. - English, Arthur W.; Yi Chen; Jonathan S. Carp; Jonathan Wolpaw; Xiang Yang Chen (Journal of neurophysiology, 2007)
The recovery of soleus (SOL), gastrocnemius (GAS), and tibialis anterior (TA) electromyographic activity (EMG) after transection and surgical repair of the sciatic nerve was studied in Sprague-Dawley rats using chronically implanted stimulation and recording electrodes. Spontaneous EMG activity in SOL and GAS and direct muscle (M) responses to posterior tibial nerve stimulation persisted for < or =2 days after sciatic nerve transection, but SOL and GAS H-reflexes disappeared immediately. Spontaneous EMG activity began to return 2-3 wk after transection, rose nearly to pretransection levels by 60 days, and persisted for the duration of the study period (120 days). Recovery of stimulus-evoked EMG responses began about 30 days after sciatic nerve transection as multiple small responses with a wide range of latencies. Over time, the latencies of these fractionated responses shortened, their amplitudes increased, and they merged into a distinct short-latency component (the putative M response) and a distinct long-latency component (the putative H-reflex). The extent of recovery of stimulation-evoked EMG was modest: even 100 days after sciatic nerve transection, the responses were still much smaller than those before transection. Similar gradual development of responses to posterior tibial nerve stimulation was also seen in TA, suggesting that some regenerating fibers sent branches into both tibial and common peroneal nerves.
Keywords: Tibial Nerve

Space-time ICA versus Ensemble ICA for ictal EEG analysis with component differentiation via Lempel-Ziv complexity. - Christopher J James; Abásolo, Daniel; Disha Gupta (Conf Proc IEEE Eng Med Biol Soc, 2007)
In this proof-of-principle study we analyzed intracranial electroencephalogram recordings in patients with intractable focal epilepsy. We contrast two implementations of Independent Component Analysis (ICA) - Ensemble (or spatial) ICA (E-ICA) and Space-Time ICA (ST-ICA) in separating out the ictal components underlying the measurements. In each case we assess the outputs of the ICA algorithms by means of a non-linear method known as the Lempel-Ziv (LZ) complexity. LZ complexity quantifies the complexity of a time series and is well suited to the analysis of non-stationary biomedical signals of short length. Our results show that for small numbers of intracranial recordings, standard E-ICA results in marginal improvements in the separation as measured by the LZ complexity changes. ST-ICA using just 2 recording channels both near and far from the epileptic focus result in more distinct ictal components--although at this stage there is a subjective element to the separation process for ST-ICA. Our results are promising showing that it is possible to extract meaningful information from just 2 recording electrodes through ST-ICA, even if they are not directly over the seizure focus. This work is being further expanded for seizure onset analysis.
Keywords: Algorithms; Artificial Intelligence; Diagnosis, Computer-Assisted; Electroencephalography; Epilepsy; Humans; Pattern Recognition, Automated; Principal Component Analysis; Reproducibility of Results; Sensitivity and Specificity

Spectral Changes in Cortical Surface Potentials During Motor Movement. - Miller, John W; Leuthardt, E C; Gerwin Schalk; Rao, Rajesh P N; Nicholas R Anderson; Moran, D; Miller, John W; Ojemann, J G (J Neurosci, 2007)
In the first large study of its kind, we quantified changes in electrocorticographic signals associated with motor movement across 22 subjects with subdural electrode arrays placed for identification of seizure foci. Patients underwent a 5-7 d monitoring period with array placement, before seizure focus resection, and during this time they participated in the study. An interval-based motor-repetition task produced consistent and quantifiable spectral shifts that were mapped on a Talairach-standardized template cortex. Maps were created independently for a high-frequency band (HFB) (76-100 Hz) and a low-frequency band (LFB) (8-32 Hz) for several different movement modalities in each subject. The power in relevant electrodes consistently decreased in the LFB with movement, whereas the power in the HFB consistently increased. In addition, the HFB changes were more focal than the LFB changes. Sites of power changes corresponded to stereotactic locations in sensorimotor cortex and to the results of individual clinical electrical cortical mapping. Sensorimotor representation was found to be somatotopic, localized in stereotactic space to rolandic cortex, and typically followed the classic homunculus with limited extrarolandic representation.
Keywords: Adult; Brain Mapping; Female; Humans; Male; Middle Aged; Motor Cortex; Movement

Spinal and supraspinal effects of long-term stimulation of sensorimotor cortex in rats. - Xiang Yang Chen; Pillai, Shreejith; Yi Chen; Wang, Yu; Lu Chen; Jonathan S. Carp; Jonathan Wolpaw (Journal of neurophysiology, 2007)
Sensorimotor cortex (SMC) modifies spinal cord reflex function throughout life and is essential for operant conditioning of the H-reflex. To further explore this long-term SMC influence over spinal cord function and its possible clinical uses, we assessed the effect of long-term SMC stimulation on the soleus H-reflex. In freely moving rats, the soleus H-reflex was measured 24 h/day for 12 wk. The soleus background EMG and M response associated with H-reflex elicitation were kept stable throughout. SMC stimulation was delivered in a 20-day-on/20-day-off/20-day-on protocol in which a train of biphasic 1-ms pulses at 25 Hz for 1 s was delivered every 10 s for the on-days. The SMC stimulus was automatically adjusted to maintain a constant descending volley. H-reflex size gradually increased during the 20 on-days, stayed high during the 20 off-days, and rose further during the next 20 on-days. In addition, the SMC stimulus needed to maintain a stable descending volley rose steadily over days. It fell during the 20 off-days and rose again when stimulation resumed. These results suggest that SMC stimulation, like H-reflex operant conditioning, induces activity-dependent plasticity in both the brain and the spinal cord and that the plasticity responsible for the H-reflex increase persists longer after the end of SMC stimulation than that underlying the change in the SMC response to stimulation.
Keywords: Time Factors

Spinal cord plasticity in acquisition and maintenance of motor skills. - Jonathan Wolpaw (Acta physiologica (Oxford, England), 2007)
Throughout normal life, activity-dependent plasticity occurs in the spinal cord as well as in brain. Like other central nervous system (CNS) plasticity, spinal cord plasticity can occur at numerous neuronal and synaptic sites and through a variety of mechanisms. Spinal cord plasticity is prominent early in life and contributes to mastery of standard behaviours like locomotion and rapid withdrawal from pain. Later in life, spinal cord plasticity has a role in acquisition and maintenance of new motor skills, and in compensation for peripheral and central changes accompanying ageing, disease and trauma. Mastery of the simplest behaviours is accompanied by complex spinal and supraspinal plasticity. This complexity is necessary, in order to preserve the complete behavioural repertoire, and is also inevitable, due to the ubiquity of activity-dependent CNS plasticity. Explorations of spinal cord plasticity are necessary for understanding motor skills. Furthermore, the spinal cord's comparative simplicity and accessibility makes it a logical starting point for studying skill acquisition. Induction and guidance of activity-dependent spinal cord plasticity will probably play an important role in realization of effective new rehabilitation methods for spinal cord injuries, cerebral palsy and other motor disorders.
Keywords: conditioning; H-Reflex; Learning; Memory; motor function; plasticity; Rehabilitation; spinal cord injury

SPIRE: the SPIDER reconstruction engine. - Baxter, Bill; Leith, ArDean; Frank, Joachim (J Struct Biol, 2007)
SPIRE is a Python program written to modernize the user interaction with SPIDER, the image processing system for electron microscopical reconstruction projects. SPIRE provides a graphical user interface (GUI) to SPIDER for executing batch files of SPIDER commands. It also lets users quickly view the status of a project by showing the last batch files that were run, as well as the data files that were generated. SPIRE handles the flexibility of the SPIDER programming environment through configuration files: XML-tagged documents that describe the batch files, directory trees, and presentation of the GUI for a given type of reconstruction project. It also provides the capability to connect to a laboratory database, for downloading parameters required by batch files at the start of a project, and uploading reconstruction results at the end of a project.
Keywords: Computational Biology; Image Processing, Computer-Assisted; Software; Software Design

A µ-rhythm Matched Filter for Continuous Control of a Brain-Computer Interface. - Krusienski, Dean J; Gerwin Schalk; Dennis J. McFarland; Jonathan Wolpaw (IEEE Trans Biomed Eng, 2007)
A brain-computer interface (BCI) is a system that provides an alternate nonmuscular communication/control channel for individuals with severe neuromuscular disabilities. With proper training, individuals can learn to modulate the amplitude of specific electroencephalographic (EEG) components (e.g., the 8-12 Hz mu rhythm and 18-26 Hz beta rhythm) over the sensorimotor cortex and use them to control a cursor on a computer screen. Conventional spectral techniques for monitoring the continuousamplitude fluctuations fail to capture essential amplitude/phase relationships of the mu and beta rhythms in a compact fashion and, therefore, are suboptimal. By extracting the characteristic mu rhythm for a user, the exact morphology can be characterized and exploited as a matched filter. A simple, parameterized model for the characteristic mu rhythm is proposed and its effectiveness as a matched filter is examined online for a one-dimensional cursor control task. The results suggest that amplitude/phase coupling exists between the mu and beta bands during event-related desynchronization, and that an appropriate matched filter can provide improved performance.
Keywords: Algorithms; Cerebral Cortex; Cortical Synchronization; Electroencephalography; Evoked Potentials; Humans; Imagination; Pattern Recognition, Automated; User-Computer Interface

Analysis of the correlation between local field potentials and neuronal firing rate in the motor cortex. - Wang, Yiwen; Sanchez, Justin C; Principe, Jose; Mitzelfelt, Jeremiah D; Gunduz, Aysegul (Conf Proc IEEE Eng Med Biol Soc, 2006)
Neuronal firing rate has been the signal of choice for invasive motor brain machine interfaces (BMI). The use of local field potentials (LFP) in BMI experiments may provide additional dendritic information about movement intent and may improve performance. Here we study the time-varying amplitude modulated relationship between local field potentials (LFP) and single unit activity (SUA) in the motor cortex. We record LFP and SUA in the primary motor cortex of rats trained to perform a lever pressing task, and evaluate the correlation between pairs of peri-event time histograms (PETH) and movement evoked local field potentials (mEP) at the same electrode. Three different correlation coefficients were calculated and compared between the neuronal PETH and the magnitude and power of the mEP. Correlation as high as 0.7 for some neurons occurred between the PETH and the mEP magnitude. As expected, the correlations between the single trial LFP and SUV are much lower due to the inherent variability of both signals.
Keywords: Action Potentials; Animals; Brain; Brain Mapping; Electric Stimulation; Electrodes; Evoked Potentials, Motor; Male; Models, Statistical; Motor Cortex; Neurons; Rats; Rats, Sprague-Dawley; Signal Processing, Computer-Assisted; Synaptic Transmission

The BCI competition III: Validating alternative approaches to actual BCI problems. - Benjamin Blankertz; Müller, Klaus-Robert; Krusienski, Dean J; Gerwin Schalk; Jonathan Wolpaw; Schlögl, Alois; Pfurtscheller, Gert; Millán, José del R; Schröder, Michael; Niels Birbaumer (IEEE Trans Neural Syst Rehabil Eng, 2006)
A brain-computer interface (BCI) is a system that allows its users to control external devices with brainactivity. Although the proof-of-concept was given decades ago, the reliable translation of user intent into device control commands is still a major challenge. Success requires the effective interaction of two adaptive controllers: the user's brain, which produces brain activity that encodes intent, and the BCI system, which translates that activity into device control commands. In order to facilitate this interaction, many laboratories are exploring a variety of signal analysis techniques to improve the adaptation of the BCI system to the user. In the literature, many machine learning and pattern classification algorithms have been reported to give impressive results when applied to BCI data in offline analyses. However, it is more difficult to evaluate their relative value for actual online use. BCI data competitions have been organized to provide objective formal evaluations of alternative methods. Prompted by the great interest in the first two BCI Competitions, we organized the third BCI Competition to address several of the most difficult and important analysis problems in BCI research. The paper describes the data sets that were provided to the competitors and gives an overview of the results.
Keywords: Algorithms; Brain; Communication Aids for Disabled; Databases, Factual; Electroencephalography; Evoked Potentials; Humans; Neuromuscular Diseases; Software Validation; Technology Assessment, Biomedical; User-Computer Interface

BCI meeting 2005 - Workshop on Technology: Hardware and Software. - Cincotti, F; Bianchi, L; Birch, Gary; Guger, C; Mellinger, Jürgen; Scherer, Reinhold; Schmidt, Robert N; Yáñez Suárez, Oscar; Gerwin Schalk (IEEE Trans Neural Syst Rehabil Eng, 2006)
This paper describes the outcome of discussions held during the Third International BCI Meeting at a workshop to review and evaluate the current state of BCI-related hardware and software. Technical requirements and current technologies, standardization procedures and future trends are covered. The main conclusion was recognition of the need to focus technical requirements on the users' needs and the need for consistent standards in BCI research.
Keywords: Algorithms; Biotechnology; Brain; Communication Aids for Disabled; Computers; Electroencephalography; Equipment Design; Humans; Internationality; Man-Machine Systems; Neuromuscular Diseases; Software; User-Computer Interface

BCI Meeting 2005–workshop on BCI signal processing: feature extraction and translation. - Dennis J. McFarland; Anderson, Charles W.; Müller, Klaus-Robert; Schlögl, Alois; Krusienski, Dean J. (IEEE transactions on neural systems and rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2006)
This paper describes the outcome of discussions held during the Third International BCI Meeting at a workshop charged with reviewing and evaluating the current state of and issues relevant to brain-computer interface (BCI) feature extraction and translation. The issues discussed include a taxonomy of methods and applications, time-frequency spatial analysis, optimization schemes, the role of insight in analysis, adaptation, and methods for quantifying BCI feedback.
Keywords: Brain-computer interface (BCI); prediction; Signal Processing

BCI Meeting 2005–workshop on signals and recording methods. - Jonathan Wolpaw; Loeb, Gerald E.; Brendan Z. Allison; Emanuel Donchin; do Nascimento, Omar Feix; Heetderks, William J.; Nijboer, Femke; Shain, William G.; Turner, James N. (IEEE transactions on neural systems and rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2006)
This paper describes the highlights of presentations and discussions during the Third International BCI Meeting in a workshop that evaluated potential brain-computer interface (BCI) signals and currently available recording methods. It defined the main potential user populations and their needs, addressed the relative advantages and disadvantages of noninvasive and implanted (i.e., invasive) methodologies, considered ethical issues, and focused on the challenges involved in translating BCI systems from the laboratory to widespread clinical use. The workshop stressed the critical importance of developing useful applications that establish the practical value of BCI technology.
Keywords: Brain-computer interface (BCI); electrophysiological signals; Rehabilitation

BCI2000: Software for Brain-Computer Interface Research - Gerwin Schalk (2006)
Neuroscience Group, Laboratory of Nervous System Disorders, Wadsworth Center, New York State Department of Health, Albany, New York.

Brain Interfacing with Materials - Gerwin Schalk (2006)
Task group presentation, National Academy of Sciences Keck Futures Initiative "Smart Prosthetics." Beckman Center, Irvine, California.

Brain-computer interface signal processing at the Wadsworth Center: mu and sensorimotor beta rhythms. - Dennis J. McFarland; Krusienski, Dean J.; Jonathan Wolpaw (Progress in brain research, 2006)
The Wadsworth brain-computer interface (BCI), based on mu and beta sensorimotor rhythms, uses one- and two-dimensional cursor movement tasks and relies on user training. This is a real-time closed-loop system. Signal processing consists of channel selection, spatial filtering, and spectral analysis. Feature translation uses a regression approach and normalization. Adaptation occurs at several points in this process on the basis of different criteria and methods. It can use either feedforward (e.g., estimating the signal mean for normalization) or feedback control (e.g., estimating feature weights for the prediction equation). We view this process as the interaction between a dynamic user and a dynamic system that coadapt over time. Understanding the dynamics of this interaction and optimizing its performance represent a major challenge for BCI research.
Keywords: adaptation; BCI; Signal Processing

Brain-Computer Interfaces (BCIs): Towards Clinical Applications - Gerwin Schalk (2006)
Biomedical Engineering Colloquium, Washington University in St. Louis, St. Louis, Missouri.

Brain-Computer Interfaces: Challenges and Perspectives - Gerwin Schalk (2006)
Rudolf Magnus Institute of Neuroscience, University Medical Center, Utrecht, The Netherlands

Brain-Computer Interfaces: Ready for Clinical Use? - Gerwin Schalk (2006)
Center for Disability Services, Albany, New York

Brain-Computer Interfacing Using BCI2000 - Gerwin Schalk (2006)
Keynote address, g.tec Brain-Computer Interface Workshop, Graz, Austria

The cerebellum in maintenance of a motor skill: a hierarchy of brain and spinal cord plasticity underlies H-reflex conditioning. - Jonathan Wolpaw; Xiang Yang Chen (Learning & memory (Cold Spring Harbor, N.Y.), 2006)
Operant conditioning of the H-reflex, the electrical analog of the spinal stretch reflex, is a simple model of skill acquisition and involves plasticity in the spinal cord. Previous work showed that the cerebellum is essential for down-conditioning the H-reflex. This study asks whether the cerebellum is also essential for maintaining down-conditioning. After rats decreased the soleus H-reflex over 50 d in response to the down-conditioning protocol, the cerebellar output nuclei dentate and interpositus (DIN) were ablated, and down-conditioning continued for 50-100 more days. In naive (i.e., unconditioned) rats, DIN ablation itself has no significant long-term effect on H-reflex size. During down-conditioning prior to DIN ablation, eight Sprague-Dawley rats decreased the H-reflex to 57% (+/-4 SEM) of control. It rose after ablation, stabilizing within 2 d at about 75% and remaining there until approximately 40 d after ablation. It then rose to approximately 130%, where it remained through the end of study 100 d after ablation. Thus, DIN ablation in down-conditioned rats caused an immediate increase and a delayed increase in the H-reflex. The final result was an H-reflex significantly larger than that prior to down-conditioning. Combined with previous work, these remarkable results suggest that the spinal cord plasticity directly responsible for down-conditioning, which survives only 5-10 d on its own, is maintained by supraspinal plasticity that survives approximately 40 d after loss of cerebellar output. Thus, H-reflex conditioning seems to depend on a hierarchy of brain and spinal cord plasticity to which the cerebellum makes an essential contribution.
Keywords: Spinal Cord

Classifying EEG and ECoG signals without subject training for fast BCI implementation: comparison of nonparalyzed and completely paralyzed subjects. - Jeremy Jeremy Hill; Lal, T.N; Schröder, Michael; Hinterberger, T.; Wilhelm, Barbara; Nijboer, F; Mochty, Ursula; Widman, Guido; Elger, Christian; Schölkopf, B; Kübler, A.; Niels Birbaumer (IEEE Trans Neural Syst Rehabil Eng, 2006)
We summarize results from a series of related studies that aim to develop a motor-imagery-based brain-computer interface using a single recording session of electroencephalogram (EEG) or electrocorticogram (ECoG) signals for each subject. We apply the same experimental and analytical methods to 11 nonparalysed subjects (eight EEG, three ECoG), and to five paralyzed subjects (four EEG, one ECoG) who had been unable to communicate for some time. While it was relatively easy to obtain classifiable signals quickly from most of the nonparalyzed subjects, it proved impossible to classify the signals obtained from the paralyzed patients by the same methods. This highlights the fact that though certain BCI paradigms may work well with healthy subjects, this does not necessarily indicate success with the target user group. We outline possible reasons for this failure to transfer.
Keywords: Algorithms; Artificial Intelligence; Cluster Analysis; Computer User Training; Electroencephalography; Evoked Potentials; Female; Humans; Imagination; Male; Middle Aged; Paralysis; Pattern Recognition, Automated; User-Computer Interface

Classifying Event-Related Desynchronization in EEG, ECoG and MEG Signals. - Jeremy Jeremy Hill; Lal, T.N; Schröder, Michael; Hinterberger, T.; Widman, Guido; Elger, Christian; Schölkopf, B; Niels Birbaumer (Pattern Recognition, 2006)
We employed three different brain signal recording methods to perform Brain-Computer Interface studies on untrained subjects. In all cases, we aim to develop a system that could be used for fast, reliable preliminary screening in clinical BCI application, and we are interested in knowing how long screening sessions need to be. Good performance could be achieved, on average, after the first 200 trials in EEG, 75–100 trials in MEG, or 25–50 trials in ECoG. We compare the performance of Independent Component Analysis and the Common Spatial Pattern algorithm in each of the three sensor types, finding that spatial filtering does not help in MEG, helps a little in ECoG, and improves performance a great deal in EEG. In all cases the unsupervised ICA algorithm performed at least as well as the supervised CSP algorithm, which can suffer from poor generalization performance due to overfitting, particularly in ECoG and MEG.

A comparison of classification techniques for the P300 Speller. - Krusienski, Dean J.; Sellers, Eric W.; Cabestaing, François; Bayoudh, Sabri; Dennis J. McFarland; Theresa M Vaughan; Jonathan Wolpaw (Journal of neural engineering, 2006)
This study assesses the relative performance characteristics of five established classification techniques on data collected using the P300 Speller paradigm, originally described by Farwell and Donchin (1988 Electroenceph. Clin. Neurophysiol. 70 510). Four linear methods: Pearson's correlation method (PCM), Fisher's linear discriminant (FLD), stepwise linear discriminant analysis (SWLDA) and a linear support vector machine (LSVM); and one nonlinear method: Gaussian kernel support vector machine (GSVM), are compared for classifying offline data from eight users. The relative performance of the classifiers is evaluated, along with the practical concerns regarding the implementation of the respective methods. The results indicate that while all methods attained acceptable performance levels, SWLDA and FLD provide the best overall performance and implementation characteristics for practical classification of P300 Speller data.
Keywords: Normal Distribution

Corticospinal tract transection permanently abolishes H-reflex down-conditioning in rats. - Xiang Yang Chen; Yi Chen; Lu Chen; Tennissen, Ann M.; Jonathan Wolpaw (Journal of neurotrauma, 2006)
Previous studies have shown that corticospinal tract (CST) transection, but not transection of other major spinal cord tracts, prevents down-conditioning of the H-reflex, the electrical analog of the spinal stretch reflex. This study set out to determine whether the loss of the capacity for H-reflex down-conditioning caused by CST transection is permanent. Female Sprague-Dawley rats received CST, lateral column (LC), or dorsal column ascending tract (DA) transection at T8-9; 9-10 months later, they were exposed to the H-reflex down-conditioning protocol for 50 days. In the LC and DA rats, H-reflex size fell to 60 (+/- 9 SEM)% and 60 (+/- 19)%, respectively, of its initial size. This down-conditioning was comparable to that of normal rats. In contrast, H-reflex size in the CST rats rose to 170 (+/- 42)% of its initial size. A similar rise does not occur in rats exposed to down-conditioning shortly after CST transection. These results indicate that CST transection permanently eliminates the capacity for H-reflex down-conditioning and has gradual long-term effects on sensorimotor cortex function. They imply that H-reflex down-conditioning can be a reliable measure of CST function for long-term studies of the effects of spinal cord injury and/or for evaluations of the efficacy of experimental therapeutic procedures, such as those intended to promote CST regeneration. The results also suggest that the role of sensorimotor cortex in down-conditioning extends beyond generation of the essential CST activity.
Keywords: corticospinal tract; H-reflex conditioning; plasticity; rat; spinal cord injury

De-noising epileptic EEG using ICA and phase synchrony. - Disha Gupta; Christopher J James; William P Gray (3rd International Conference on Advances in Medical, Signal and Information Processing, IET, 2006)
A multi-channel recording of scalp electroencephalogram (EEG) is a non-invasive tool important for analysis and treatment of patients with epilepsy. These recordings are usually contaminated with artifacts and background activity, which may sometimes render them misleading or useless. Epileptic EEG is also useful for seizure detection, localisation and prediction. It would be useful to de-noise epileptic EEG in order to improve the efficiency of such diagnostic and prognostic procedures. The basic method of denoising a signal is through filtering, but filtering physiological signals is not trivial and highly subjective as the information is spread over different frequency bands and different measurement channels. This paper demonstrates a system for objectively de-noising epileptic EEG using Independent Component Analysis (ICA). In the standard implementation of ICA it is generally required to subjectively choose independent components (ICs) relevant to the epileptic activity; here we automate this process through the concept of phase synchronisation between ICs. In this manner de-noising the epileptic EEG with ICA becomes an objective (and automated) process.

Direct Communication From the Brain - Gerwin Schalk (2006)
Guest lecture for course Services Science, Management, and Engineering. Department of Information Technology, Rensselaer Polytechnic Institute, Troy, New York.

Diurnal H-reflex variation in mice. - Jonathan S. Carp; Tennissen, Ann M.; Xiang Yang Chen; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2006)
Mice exhibit diurnal variation in complex motor behaviors, but little is known about diurnal variation in simple spinally mediated functions. This study describes diurnal variation in the H-reflex (HR), a wholly spinal and largely monosynaptic reflex. Six mice were implanted with tibial nerve cuff electrodes and electrodes in the soleus and gastrocnemius muscles, for recording of ongoing and nerve-evoked electromyographic activity (EMG). Stimulation and recording were under computer control 24 h/day. During a 10-day recording period, HR amplitude varied throughout the day, usually being larger in the dark than in the light. This diurnal HR variation could not be attributed solely to differences in the net ongoing level of descending and segmental excitation to the spinal cord or stimulus intensity. HRs were larger in the dark than in the light even after restricting the evoked responses to subsets of trials having similar ongoing EMG and M-responses. The diurnal variation in the HR was out of phase with that reported previously for rats, but was in phase with that observed in monkeys. These data, supported by those in other species, suggest that the supraspinal control of the excitability of the HR pathway varies throughout the day in a species-specific pattern. This variation should be taken into account in experimental and clinical studies of spinal reflexes recorded at different times of day.
Keywords: circadian rhythm; Electromyography; implanted electrodes; Monosynaptic; Reflex; Spinal Cord

ECoG factors underlying multimodal control of a brain-computer interface. - Adam J Wilson; Felton, Elizabeth A; Garell, P Charles; Gerwin Schalk; Williams, Justin C (IEEE Trans Neural Syst Rehabil Eng, 2006)
Most current brain-computer interface (BCI) systems for humans use electroencephalographic activity recorded from the scalp, and may be limited in many ways. Electrocorticography (ECoG) is believed to be a minimally-invasive alternative to electroencephalogram (EEG) for BCI systems, yielding superior signal characteristics that could allow rapid user training and faster communication rates. In addition, our preliminary results suggest that brain regions other than the sensorimotor cortex, such as auditory cortex, may be trained to control a BCI system using similar methods as those used to train motor regions of the brain. This could prove to be vital for users who have neurological disease, head trauma, or other conditions precluding the use of sensorimotor cortex for BCI control.
Keywords: Adult; Brain Mapping; Cerebral Cortex; Communication Aids for Disabled; Computer Peripherals; Evoked Potentials; Female; Humans; Imagination; Male; Man-Machine Systems; Neuromuscular Diseases; Systems Integration; User-Computer Interface; Volition

The education and re-education of the spinal cord. - Jonathan Wolpaw (Progress in brain research, 2006)
In normal life, activity-dependent plasticity occurs in the spinal cord as well as in the brain. Like CNS plasticity elsewhere, this spinal cord plasticity can occur at many neuronal and synaptic sites and by a variety of mechanisms. Spinal cord plasticity is prominent in postnatal development and contributes to acquisition of standard behaviors such as locomotion and rapid withdrawal from pain. Later on in life, spinal cord plasticity contributes to acquisition and maintenance of specialized motor skills, and to compensation for the peripheral and central changes associated with aging, disease, and trauma. Mastery of even the simplest behaviors is accompanied by complex spinal and supraspinal plasticity. This complexity is necessary, to preserve the full roster of behaviors, and is also inevitable, due to the ubiquity of activity-dependent plasticity in the CNS. Careful investigation of spinal cord plasticity is essential for understanding motor skills; and, because of the relative simplicity and accessibility of the spinal cord, is a logical and convenient starting point for exploring skill acquisition. Appropriate induction and guidance of activity-dependent plasticity in the spinal cord is likely to be a key part of the realization of effective new rehabilitation methods for spinal cord injuries, cerebral palsy, and other chronic motor disorders.
Keywords: behavior; conditioning; Learning; Memory; plasticity; Spinal Cord; spinal cord injury

Electrocorticography-based brain computer interface--the Seattle experience. - Leuthardt, E C; Miller, John W; Gerwin Schalk; Rao, Rajesh P N; Ojemann, J G (IEEE Trans Neural Syst Rehabil Eng, 2006)
Electrocorticography (ECoG) has been demonstrated to be an effective modality as a platform for brain-computer interfaces (BCIs). Through our experience with ten subjects, we further demonstrate evidence to support the power and flexibility of this signal for BCI usage. In a subset of four patients, closed-loop BCI experiments were attempted with the patient receiving online feedback that consisted of one-dimensional cursor movement controlled by ECoG features that had shown correlation with various real and imagined motor and speech tasks. All four achieved control, with final target accuracies between 73%-100%. We assess the methods for achieving control and the manner in which enhancing online control can be accomplished by rescreening during online tasks. Additionally, we assess the relevant issues of the current experimental paradigm in light of their clinical constraints.
Keywords: Cerebral Cortex; Electroencephalography; Epilepsy; Evoked Potentials; Humans; Therapy, Computer-Assisted; User-Computer Interface; Washington

The emerging world of motor neuroprosthetics: a neurosurgical perspective. - Leuthardt, E C; Gerwin Schalk; Moran, D; Ojemann, J G (Neurosurgery, 2006)
A MOTOR NEUROPROSTHETIC device, or brain computer interface, is a machine that can take some type of signal from the brain and convert that information into overt device control such that it reflects the intentions of the user's brain. In essence, these constructs can decode the electrophysiological signals representing motor intent. With the parallel evolution of neuroscience, engineering, and rapid computing, the era of clinical neuroprosthetics is approaching as a practical reality for people with severe motor impairment. Patients with such diseases as spinal cord injury, stroke, limb loss, and neuromuscular disorders may benefit through the implantation of these brain computer interfaces that serve to augment their ability to communicate and interact with their environment. In the upcoming years, it will be important for the neurosurgeon to understand what a brain computer interface is, its fundamental principle of operation, and what the salient surgical issues are when considering implantation. We review the current state of the field of motor neuroprosthetics research, the early clinical applications, and the essential considerations from a neurosurgical perspective for the future.
Keywords: Brain; Humans; Man-Machine Systems; Movement; Neurosurgery; Prostheses and Implants; User-Computer Interface

An evaluation of autoregressive spectral estimation model order for brain-computer interface applications. - Krusienski, D. J.; Dennis J. McFarland; Jonathan Wolpaw (Conference proceedings : ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Conference, 2006)
Autoregressive (AR) spectral estimation is a popular method for modeling the electroencephalogram (EEG), and therefore the frequency domain EEG phenomena that are used for control of a brain-computer interface (BCI). Several studies have been conducted to evaluate the optimal AR model order for EEG, but the criteria used in these studies does not necessarily equate to the optimal AR model order for sensorimotor rhythm (SMR)-based BCI control applications. The present study confirms this by evaluating the EEG spectra of data obtained during control of SMR-BCI using different AR model orders and model evaluation criteria. The results indicate that the AR model order that optimizes SMR-BCI control performance is generally higher than the model orders that are frequently used in SMR-BCI studies.
Keywords: User-Computer Interface

H-reflex operant conditioning in mice. - Jonathan S. Carp; Tennissen, Ann M.; Xiang Yang Chen; Jonathan Wolpaw (Journal of neurophysiology, 2006)
Rats, monkeys, and humans can alter the size of their spinal stretch reflex and its electrically induced analog, the H-reflex (HR), when exposed to an operant conditioning paradigm. Because this conditioning induces plasticity in the spinal cord, it offers a unique opportunity to identify the neuronal sites and mechanisms that underlie a well-defined change in a simple behavior. To facilitate these studies, we developed an HR operant conditioning protocol in mice, which are better suited to genetic manipulation and electrophysiological spinal cord study in vitro than rats or primates. Eleven mice under deep surgical anesthesia were implanted with tibial nerve stimulating electrodes and soleus and gastrocnemius intramuscular electrodes for recording ongoing and stimulus-evoked EMG activity. During the 24-h/day computer-controlled experiment, mice received a liquid reward for either increasing (up-conditioning) or decreasing (down-conditioning) HR amplitude while maintaining target levels of ongoing EMG and directly evoked EMG (M-responses). After 3-7 wk of conditioning, the HR amplitude was 133 +/- 7% (SE) of control for up-conditioning and 71 +/- 8% of control for down-conditioning. HR conditioning was successful (i.e., > or =20% change in HR amplitude in the appropriate direction) in five of six up-conditioned animals (mean final HR amplitude = 139 +/- 5% of control HR for successful mice) and in four of five down-conditioned animals (mean final HR amplitude = 63 +/- 8% of control HR for successful mice). These effects were not attributable to differences in the net level of motoneuron pool excitation, stimulation strength, or distribution of HR trials throughout the day. Thus mice exhibit HR operant conditioning comparable with that observed in rats and monkeys.
Keywords: Spinal Cord

Modulation in spinal circuits and corticospinal connections following nerve stimulation and operant conditioning. - Thompson, Aiko K.; Stein, Richard B.; Xiang Yang Chen; Jonathan Wolpaw (Conference proceedings : ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Conference, 2006)
Neural plasticity occurs throughout adult life. In healthy individuals, different spinal pathways are differently modulated during different daily activities. Drastic changes to nervous system activity and connections caused by injuries or diseases alter spinal reflexes, and this is often related to disturbed motor functions. In both health and disease, spinal reflexes are subject to substantial modifications. Plasticity in supraspinal descending connections is even more remarkable; corticospinal connectivity has been shown to be extremely plastic. In this session, we describe two approaches for possibly improving recovery after central nervous system (CNS) lesions. They are very different, but both involve repetitive nerve stimulation and CNS plasticity. The first approach is functional electrical stimulation (FES) of the common peroneal nerve, which has been used to treat foot drop in patients with CNS lesions. The second approach is operant conditioning of a spinal reflex. Spinal reflex operant conditioning studies in animal models have shown plastic changes in spinal cord neurons associated with this form of learning and improved locomotor function in incomplete spinal cord injured rats. Thus, reflex conditioning might be a robust approach to inducing plasticity at spinal and supraspinal levels. As a first step in establishing this approach and characterizing its effects in the human adult CNS, we are currently investigating the extent and time course of operant conditioning of the soleus H-reflex in healthy subjects. In results to date, all subjects (n=5) have changed reflex size in the correct direction to various degree (16-36%) over 2-3 months of conditioning, indicating possibility that H-reflex conditioning can occur in humans. At the same time, the substantial inter-subject variation in the time course and extent of conditioning suggest that additional data are needed to establish its principal features. We hope that studying modulation and modification o- f the CNS by different approaches will help us further understand the plasticity of the human adult nervous system.
Keywords: Spinal Cord

Motor learning changes GABAergic terminals on spinal motoneurons in normal rats. - Wang, Yu; Pillai, Shreejith; Jonathan Wolpaw; Xiang Yang Chen (The European journal of neuroscience, 2006)
The role of spinal cord plasticity in motor learning is largely unknown. This study explored the effects of H-reflex operant conditioning, a simple model of motor learning, on GABAergic input to spinal motoneurons in rats. Soleus motoneurons were labeled by retrograde transport of a fluorescent tracer and GABAergic terminals on them were identified by glutamic acid decarboxylase (GAD)67 immunoreactivity. Three groups were studied: (i) rats in which down-conditioning had reduced the H-reflex (successful HRdown rats); (ii) rats in which down-conditioning had not reduced the H-reflex (unsuccessful HRdown rats) and (iii) unconditioned (naive) rats. The number, size and GAD density of GABAergic terminals, and their coverage of the motoneuron, were significantly greater in successful HRdown rats than in unsuccessful HRdown or naive rats. It is likely that these differences are due to modifications in terminals from spinal interneurons in lamina VI-VII and that the increased terminal number, size, GAD density and coverage in successful HRdown rats reflect and convey a corticospinal tract influence that changes motoneuron firing threshold and thereby decreases the H-reflex. GABAergic terminals in spinal cord change after spinal cord transection. The present results demonstrate that such spinal cord plasticity also occurs in intact rats in the course of motor learning and suggest that this plasticity contributes to skill acquisition.
Keywords: activity-dependent plasticity; GABA; H-Reflex; Memory; Motor control; Spinal Cord

Multi-channel linear descriptors for event-related EEG collected in brain computer interface. - Pei, Xiao-Mei; Zheng, Shi Dong; Xu, Jin; Bin, Guang-yu; Zuoguan Wang (J Neural Eng, 2006)
By three multi-channel linear descriptors, i.e. spatial complexity (omega), field power (sigma) and frequency of field changes (phi), event-related EEG data within 8-30 Hz were investigated during imagination of left or right hand movement. Studies on the event-related EEG data indicate that a two-channel version of omega, sigma and phi could reflect the antagonistic ERD/ERS patterns over contralateral and ipsilateral areas and also characterize different phases of the changing brain states in the event-related paradigm. Based on the selective two-channel linear descriptors, the left and right hand motor imagery tasks are classified to obtain satisfactory results, which testify the validity of the three linear descriptors omega, sigma and phi for characterizing event-related EEG. The preliminary results show that omega, sigma together with phi have good separability for left and right hand motor imagery tasks, which could be considered for classification of two classes of EEG patterns in the application of brain computer interfaces.
Keywords: Algorithms; Electroencephalography; Evoked Potentials, Motor; Humans; Imagination; Motor Cortex; Movement; Pattern Recognition, Automated; Reproducibility of Results; Sensitivity and Specificity; User-Computer Interface

Operant conditioning of H-reflex can correct a locomotor abnormality after spinal cord injury in rats. - Yi Chen; Xiang Yang Chen; Jakeman, Lyn B.; Lu Chen; Stokes, Bradford T.; Jonathan Wolpaw (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2006)
This study asked whether operant conditioning of the H-reflex can modify locomotion in spinal cord-injured rats. Midthoracic transection of the right lateral column of the spinal cord produced a persistent asymmetry in the muscle activity underlying treadmill locomotion. The rats were then either exposed or not exposed to an H-reflex up-conditioning protocol that greatly increased right soleus motoneuron response to primary afferent input, and locomotion was reevaluated. H-reflex up-conditioning increased the right soleus burst and corrected the locomotor asymmetry. In contrast, the locomotor asymmetry persisted in the control rats. These results suggest that appropriately selected reflex conditioning protocols might improve function in people with partial spinal cord injuries. Such protocols might be especially useful when significant regeneration becomes possible and precise methods for reeducating the regenerated spinal cord neurons and synapses are needed for restoring effective function.
Keywords: H-reflex conditioning; Learning; Locomotion; Memory; Motor control; Rehabilitation; spinal cord injury; spinal cord plasticity

Operant conditioning of reciprocal inhibition in rat soleus muscle. - Xiang Yang Chen; Lu Chen; Yi Chen; Jonathan Wolpaw (Journal of neurophysiology, 2006)
Operant conditioning of the H-reflex, the electrical analog of the spinal stretch reflex (SSR), induces activity-dependent plasticity in the spinal cord and might be used to improve locomotion after spinal cord injury. To further assess the potential clinical significance of spinal reflex conditioning, this study asks whether another well-defined spinal reflex pathway, the disynaptic pathway underlying reciprocal inhibition (RI), can also be operantly conditioned. Sprague-Dawley rats were implanted with electromyographic (EMG) electrodes in right soleus (SOL) and tibialis anterior (TA) muscles and a stimulating cuff on the common peroneal (CP) nerve. When background EMG in both muscles remained in defined ranges, CP stimulation elicited the TA H-reflex and SOL RI. After collection of control data for 20 days, each rat was exposed for 50 days to up-conditioning (RIup mode) or down-conditioning (RIdown mode) in which food reward occurred if SOL RI evoked by CP stimulation was more (RIup mode) or less (RIdown mode) than a criterion. TA and SOL background EMG and TA M response remained stable. In every rat, RI conditioning was successful (i.e., change > or =20% in the correct direction). In the RIup rats, final SOL RI averaged 171+/- 28% (mean +/- SE) of control, and final TA H-reflex averaged 114 +/- 14%. In the RIdown rats, final SOL RI averaged 37 +/- 13% of control, and final TA H-reflex averaged 60 +/- 18%. Final SOL RI and TA H-reflex sizes were significantly correlated. Thus like the SSR and the H-reflex, RI can be operantly conditioned; and conditioning one reflex can affect another reflex as well.
Keywords: Reflex; Stretch

Optimizing Spatial Filters for BCI: Margin- and Evidence-Maximization Approaches. - Farquhar, Jason; Jeremy Jeremy Hill; Schölkopf, B (2006)
We present easy-to-use alternatives to the often-used two-stage Common Spatial Pattern + classifier approach for spatial filtering and classification of Event-Related Desynchronization signals in BCI. We report two algorithms that aim to optimize the spatial filters according to a criterion more directly related to the ability of the algorithms to generalize to unseen data. Both are based upon the idea of treating the spatial filter coefficients as hyperparameters of a kernel or covariance function. We then optimize these hyper-parameters directly along side the normal classifier parameters with respect to our chosen learning objective function. The two objectives considered are margin maximization as used in Support-Vector Machines and the evidence maximization framework used in Gaussian Processes. Our experiments assessed generalization error as a function of the number of training points used, on 9 BCI competition data sets and 5 offline motor imagery data sets measured in Tubingen. Both our approaches sho w consistent improvements relative to the commonly used CSP+linear classifier combination. Strikingly, the improvement is most significant in the higher noise cases, when either few trails are used for training, or with the most poorly performing subjects. This a reversal of the usual "rich get richer" effect in the development of CSP extensions, which tend to perform best when the signal is strong enough to accurately find their additional parameters. This makes our approach particularly suitable for clinical application where high levels of noise are to be expected.
Keywords: Brain Computer Interfaces

A P300 event-related potential brain-computer interface (BCI): the effects of matrix size and inter stimulus interval on performance. - Sellers, Eric W.; Krusienski, Dean J.; Dennis J. McFarland; Theresa M Vaughan; Jonathan Wolpaw (Biological psychology, 2006)
We describe a study designed to assess properties of a P300 brain-computer interface (BCI). The BCI presents the user with a matrix containing letters and numbers. The user attends to a character to be communicated and the rows and columns of the matrix briefly intensify. Each time the attended character is intensified it serves as a rare event in an oddball sequence and it elicits a P300 response. The BCI works by detecting which character elicited a P300 response. We manipulated the size of the character matrix (either 3 x 3 or 6 x 6) and the duration of the inter stimulus interval (ISI) between intensifications (either 175 or 350 ms). Online accuracy was highest for the 3 x 3 matrix 175-ms ISI condition, while bit rate was highest for the 6 x 6 matrix 175-ms ISI condition. Average accuracy in the best condition for each subject was 88%. P300 amplitude was significantly greater for the attended stimulus and for the 6 x 6 matrix. This work demonstrates that matrix size and ISI are important variables to consider when optimizing a BCI system for individual users and that a P300-BCI can be used for effective communication.
Keywords: Amyotrophic Lateral Sclerosis; brain-computer interface; electroencephalogram; event-related potentials; P300; Rehabilitation

Plastic changes in the human H-reflex pathway at rest following skillful cycling training. - Mazzocchio, Riccardo; Kitago, Tomoko; Liuzzi, Gianpiero; Jonathan Wolpaw; Cohen, Leonardo G. (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2006)
OBJECTIVE: The spinal cord is capable of activity-dependent plasticity, but the extent of its participation in human motor learning is not known. Here, we tested the hypothesis that acquisition of a locomotor-related skill modulates the pathway of the H-reflex, a measure of spinal cord excitability that is susceptible to plastic changes. METHODS: Subjects were tested on their ability to establish a constant cycling speed on a recumbent bike despite frequent changes in pedal resistance. The coefficient of variation of speed (CV(speed)) measured their ability to acquire this skill (decreasing CV(speed) with training reflects performance improvements). Soleus H-reflexes were taken at rest before and after cycling. RESULTS: Ability to establish a target speed increased and H-reflex size decreased more after cycling training involving frequent changes in pedal resistance that required calibrated locomotor compensatory action than with training involving constant pedal resistances and lesser compensation. The degree of performance improvement correlated with the reduction in the amplitude of the H-reflex. CONCLUSIONS: Skillful establishment of a constant cycling speed despite changing pedal resistances is associated with persistent modulation of activity in spinal pathways. SIGNIFICANCE: Recalibration of activity in the H-reflex pathway may be part of the control strategy required for locomotor-related skill acquisition.
Keywords: H-Reflex; Locomotion; Memory; plasticity; Spinal Cord

Plasticity from muscle to brain. - Jonathan Wolpaw; Jonathan S. Carp (Progress in neurobiology, 2006)
Recognition that the entire central nervous system (CNS) is highly plastic, and that it changes continually throughout life, is a relatively new development. Until very recently, neuroscience has been dominated by the belief that the nervous system is hardwired and changes at only a few selected sites and by only a few mechanisms. Thus, it is particularly remarkable that Sir John Eccles, almost from the start of his long career nearly 80 years ago, focused repeatedly and productively on plasticity of many different kinds and in many different locations. He began with muscles, exploring their developmental plasticity and the functional effects of the level of motor unit activity and of cross-reinnervation. He moved into the spinal cord to study the effects of axotomy on motoneuron properties and the immediate and persistent functional effects of repetitive afferent stimulation. In work that combined these two areas, Eccles explored the influences of motoneurons and their muscle fibers on one another. He studied extensively simple spinal reflexes, especially stretch reflexes, exploring plasticity in these reflex pathways during development and in response to experimental manipulations of activity and innervation. In subsequent decades, Eccles focused on plasticity at central synapses in hippocampus, cerebellum, and neocortex. His endeavors extended from the plasticity associated with CNS lesions to the mechanisms responsible for the most complex and as yet mysterious products of neuronal plasticity, the substrates underlying learning and memory. At multiple levels, Eccles' work anticipated and helped shape present-day hypotheses and experiments. He provided novel observations that introduced new problems, and he produced insights that continue to be the foundation of ongoing basic and clinical research. This article reviews Eccles' experimental and theoretical contributions and their relationships to current endeavors and concepts. It emphasizes aspects of his contributions that are less well known at present and yet are directly relevant to contemporary issues.
Keywords: activity-dependent; John Eccles; Learning; Memory; motor unit; muscle; plasticity; Spinal Cord

Progress of brain-neural function informatics. - Zheng, Shi Dong; Pei, Xiao-Mei; Xu, Jin (Zhongguo Yi Liao Qi Xie Za Zhi, 2006)
Firstly the fundamental concept and research hotspots of Brain-Neural Function Informatics (BNFI) are described. Then the main study fields and progresses of BNFI are expounded. Finally the prospects of BNFI research are given. Studies on BNFI not only promote the "Brain Science" progress, but also boost the industry of a new kind of medical instruments - function rehabilitation equipment and artificial functional prostheses.
Keywords: Animals; Biomedical Engineering; Brain; Brain Diseases; Computing Methodologies; Humans; Informatics; Nervous System Physiological Phenomena

Quantitative measure of complexity of the dynamic event-related EEG data. - Pei, Xiao-Mei; Zheng, Shi Dong; Wei-xing He; Xu, Jin (Neurocomputing, 2006)
<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">Currently, the quantification of event-related <a class="linkText" style="color: #316c9d; text-decoration: none; border-width: 0px 0px 1px; border-bottom-color: #ba0000; font-size: 13px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px; cursor: pointer;" href="http://www.sciencedirect.com/science/article/pii/S0925231206001184?np=y#NEU3973">EEG<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;"> is usually based on power feature with the classical band power method. In this paper, the method quantifying the complexity and irregularity of event-related EEG data in relation to hand motor imagery is presented. Two groups of the complexity indexes: Kolmogorov complexity (<em style="border: 0px; font-size: 13px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; color: #2e2e2e; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">Kc<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">) and Fourier spectral entropy (<em style="border: 0px; font-size: 13px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; color: #2e2e2e; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">FSE<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">) are discussed. The event-related desynchronization/synchronization (ERD/ERS) time course is analyzed and characterized by two parameters <em style="border: 0px; font-size: 13px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; color: #2e2e2e; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">Kc<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;"> and <em style="border: 0px; font-size: 13px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; color: #2e2e2e; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">FSE<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">, respectively. The percentage of EEG complexity during imagination of the unilateral hand movement relative to that during reference period is calculated for quantifying the complexity measure of ERD/ERS time course. The method is applied to two sets of movement-related EEG data recorded over the primary <a class="linkText" style="color: #316c9d; text-decoration: none; border-width: 0px 0px 1px; border-bottom-color: #ba0000; font-size: 13px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px; cursor: pointer;" href="http://www.sciencedirect.com/science/article/pii/S0925231206001184?np=y#NEU10724">sensorimotor<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;"> area from two subjects. In addition, the validity of the quantitative measure of complexity of the event-related EEG is testified by evaluating the performance of feature extraction and classification. The results show that both <em style="border: 0px; font-size: 13px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; color: #2e2e2e; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">Kc<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;"> and <em style="border: 0px; font-size: 13px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; color: #2e2e2e; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">FSE<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">can effectively describe the dynamic complexity of event-related EEG and also display the consistent and similar behaviors. The relative increase and decrease of event-related EEG complexity could be an indicator of ERD/ERS, which is also independent of the power changes. Thus, the dynamic complexity measure of event-related EEG quantified by <em style="border: 0px; font-size: 13px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; color: #2e2e2e; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">Kc<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;"> and <em style="border: 0px; font-size: 13px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; color: #2e2e2e; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">FSE<span style="color: #2e2e2e; font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;"> provides another evidence for ERD/ERS and can be meaningful for analyzing the event-related EEG.
Keywords: complexity indexes Kc and FSE; ERD/ERS time course; event-related EEG; Hand motor imagery

Regularised CSP for Sensor Selection in BCI. - Farquhar, Jason; Jeremy Jeremy Hill; Lal, T.N; Schölkopf, B (2006)
The Common Spatial Pattern (CSP) algorithm is a highly successful method for efficiently calculating spatial filters for brain signal classification. Spatial filtering can improve classification performance considerably, but demands that a large number of electrodes be mounted, which is inconvenient in day-to-day BCI usage. The CSP algorithm is also known for its tendency to overfit, i.e. to learn the noise in the training set rather than the signal. Both problems motivate an approach in which spatial filters are sparsified. We briefly sketch a reformulation of the problem which allows us to do this, using 1-norm regularisation. Focusing on the electrode selection issue, we present preliminary results on EEG data sets that suggest that effective spatial filters may be computed with as few as 10–20 electrodes, hence offering the potential to simplify the practical realisation of BCI systems significantly.

Sensorimotor cortex ablation prevents H-reflex up-conditioning and causes a paradoxical response to down-conditioning in rats. - Xiang Yang Chen; Jonathan S. Carp; Lu Chen; Jonathan Wolpaw (Journal of neurophysiology, 2006)
Operant conditioning of the H-reflex, a simple model for skill acquisition, requires the corticospinal tract (CST) and does not require other major descending pathways. To further explore its mechanisms, we assessed the effects of ablating contralateral sensorimotor cortex (cSMC). In 22 Sprague-Dawley rats, the hindlimb area of left cSMC was ablated. EMG electrodes were implanted in the right soleus muscle and a stimulating cuff was placed around the right posterior tibial nerve. When EMG remained in a specified range, nerve stimulation just above the M response threshold elicited the H-reflex. In control mode, no reward occurred. In conditioning mode, reward occurred if H-reflex size was above (HRup mode) or below (HRdown mode) a criterion value. After exposure to the control mode for > or = 10 days, each rat was exposed for another 50 days to the control mode, the HRup mode, or the HRdown mode. In control and HRup rats, final H-reflex size was not significantly different from initial H-reflex size. In contrast, in HRdown rats, final H-reflex size was significantly increased to an average of 136% of initial size. Thus like recent CST transection, cSMC ablation greatly impaired up-conditioning. However, unlike recent CST transection, cSMC produced a paradoxical response to down-conditioning: the H-reflex actually increased. These results confirm the critical role of cSMC in H-reflex conditioning and suggest that this role extends beyond producing essential CST activity. Its interactions with ipsilateral SMC or other areas contribute to the complex pattern of spinal and supraspinal plasticity that underlies H-reflex conditioning.
Keywords: Somatosensory Cortex

The Third International Meeting on Brain-Computer Interface Technology: making a difference. - Theresa M Vaughan; Jonathan Wolpaw (IEEE transactions on neural systems and rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2006)
This special issue of the IEEE TRANSACTIONS ON NEURAL SYSTEMS AND REHABILITATION ENGINEERING provides a representative and comprehensive bird's-eye view of the most recent developments in brain-computer interface (BCI) technology from laboratories around the world. The 30 research communications and papers are the direct outcome of the Third International Meeting on Brain-Computer Interface Technology held at the Rensselaerville Institute, Rensselaerville, NY, in June 2005. Fifty-three research groups from North and South America, Europe, and Asia, representing the majority of all the existing BCI laboratories around the world, participated in this highly focused meeting sponsored by the National Institutes of Health and organized by the BCI Laboratory of the Wadsworth Center of the New York State Department of Health. As demonstrated by the papers in this special issue, the rapid advances in BCI research and development make this technology capable of providing communication and control to people severely disabled by amyotrophic lateral sclerosis (ALS), brainstem stroke, cerebral palsy, and other neuromuscular disorders. Future work is expected to improve the performance and utility of BCIs, and to focus increasingly on making them a viable, practical, and affordable communication alternative for many thousands of severely disabled people worldwide.
Keywords: User-Computer Interface

Time-Dependent Demixing of Task-Relevant EEG Signals. - Jeremy Jeremy Hill; Farquhar, Jason; Lal, T.N; Schölkopf, B (2006)
Given a spatial filtering algorithm that has allowed us to identify task-relevant EEG sources, we present a simple approach for monitoring the activity of these sources while remaining relatively robust to changes in other (task-irrelevant) brain activity. The idea is to keep spatial *patterns* fixed rather than spatial filters, when transferring from training to test sessions or from one time window to another. We show that a fixed spatial pattern (FSP) approach, using a moving-window estimate of signal covariances, can be more robust to non-stationarity than a fixed spatial filter (FSF) approach.

Treadmill training after spinal cord injury: good but not better. - Jonathan Wolpaw (Neurology, 2006)
Keywords: Walking

The Wadsworth BCI Research and Development Program: At Home with BCI. - Theresa M Vaughan; Dennis J. McFarland; Gerwin Schalk; Sarnacki, William A; Krusienski, Dean J; Sellers, Eric W; Jonathan Wolpaw (IEEE Trans Neural Syst Rehabil Eng, 2006)
The ultimate goal of brain-computer interface (BCI) technology is to provide communication and control capacities to people with severe motor disabilities. BCI research at the Wadsworth Center focuses primarily on noninvasive, electroencephalography (EEG)-based BCI methods. We have shown that people, including those with severe motor disabilities, can learn to use sensorimotor rhythms (SMRs) to move a cursor rapidly and accurately in one or two dimensions. We have also improved P300-based BCI operation. We are now translating this laboratory-proven BCI technology into a system that can be used by severely disabled people in their homes with minimal ongoing technical oversight. To accomplish this, we have: improved our general-purpose BCI software (BCI2000); improved online adaptation and feature translation for SMR-based BCI operation; improved the accuracy and bandwidth of P300-based BCI operation; reduced the complexity of system hardware and software and begun to evaluate home system use in appropriate users. These developments have resulted in prototype systems for every day use in people's homes.
Keywords: Animals; Brain; Electroencephalography; Evoked Potentials; Humans; Neuromuscular Diseases; New York; Research; Switzerland; Therapy, Computer-Assisted; Universities; User-Computer Interface

Ablation of cerebellar nuclei prevents H-reflex down-conditioning in rats. - Xiang Yang Chen; Jonathan Wolpaw (Learning & memory (Cold Spring Harbor, N.Y.), 2005)
While studies of cerebellar involvement in learning and memory have described plasticity within the cerebellum, its role in acquisition of plasticity elsewhere in the CNS is largely unexplored. This study set out to determine whether the cerebellum is needed for acquisition of the spinal cord plasticity that underlies operantly conditioned decrease in the H-reflex, the electrical analog of the spinal stretch reflex. Rats in which the cerebellar output nuclei dentate and interpositus (DIN) had been ablated were exposed for 50 d to the H-reflex down-conditioning protocol. DIN ablation, which in itself had no significant long-term effect on H-reflex size, entirely prevented acquisition of a smaller H-reflex. Since previous studies show that corticospinal tract (CST) transection also prevents down-conditioning while transection of the rubrospinal tract and other major descending tracts does not, this result implies that DIN output that affects cortex is essential for generation of the CST activity that induces the spinal cord plasticity, which is, in turn, directly responsible for the smaller H-reflex. The result extends the role of the cerebellum in learning and memory to include participation in induction of plasticity elsewhere in the CNS, specifically in the spinal cord. The cerebellum might simply support processes in sensorimotor cortex or elsewhere that change the spinal cord, or the cerebellum itself might undergo plasticity similar to that occurring with vestibulo-ocular reflex (VOR) or eyeblink conditioning.
Keywords: Reflex; Vestibulo-Ocular

A Brain Computer Interface with Online Feedback based on Magnetoencephalography. - Lal, T.N; Schroeder, Michael; Jeremy Jeremy Hill; Preissl, Hubert; Hinterberger, T.; Mellinger, Jürgen; Bogdan, Martin; Rosenstiel, W.; Niels Birbaumer; Schoelkopf, Bernhard (2005)
The aim of this paper is to show that machine learning techniques can be used to derive a classifying function for human brain signal data measured by magnetoencephalography (MEG), for the use in a brain computer interface (BCI). This is especially helpful for evaluating quickly whether a BCI approach based on electroencephalography, on which training may be slower due to lower signalto-noise ratio, is likely to succeed. We apply RCE and regularized SVMs to the experimental data of ten healthy subjects performing a motor imagery task. Four subjects were able to use a trained classifier to write a short name. Further analysis gives evidence that the proposed imagination task is suboptimal for the possible extension to a multiclass interface. To the best of our knowledge this paper is the first working online MEG-based BCI and is therefore a “proof of concept”.
Keywords: Brain Computer Interfaces; User Modelling for Computer Human Interaction

Brain-computer interface (BCI) operation: signal and noise during early training sessions. - Dennis J. McFarland; Sarnacki, William A.; Theresa M Vaughan; Jonathan Wolpaw (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2005)
OBJECTIVE: People can learn to control mu (8-12 Hz) or beta (18-25 Hz) rhythm amplitude in the electroencephalogram (EEG) recorded over sensorimotor cortex and use it to move a cursor to a target on a video screen. The recorded signal may also contain electromyogram (EMG) and other non-EEG artifacts. This study examines the presence and characteristics of EMG contamination during new users' initial brain-computer interface (BCI) training sessions, as they first attempt to acquire control over mu or beta rhythm amplitude and to use that control to move a cursor to a target. METHODS: In the standard one-dimensional format, a target appears along the right edge of the screen and 1s later the cursor appears in the middle of the left edge and moves across the screen at a fixed rate with its vertical movement controlled by a linear function of mu or beta rhythm amplitude. In the basic two-choice version, the target occupies the upper or lower half of the right edge. The user's task is to move the cursor vertically so that it hits the target when it reaches the right edge. The present data comprise the first 10 sessions of BCI training from each of 7 users. Their data were selected to illustrate the variations seen in EMG contamination across users. RESULTS: Five of the 7 users learned to change rhythm amplitude appropriately, so that the cursor hit the target. Three of these 5 showed no evidence of EMG contamination. In the other two of these 5, EMG was prominent in early sessions, and tended to be associated with errors rather than with hits. As EEG control improved over the 10 sessions, this EMG contamination disappeared. In the remaining two users, who never acquired actual EEG control, EMG was prominent in initial sessions and tended to move the cursor to the target. This EMG contamination was still detectable by Session 10. CONCLUSIONS: EMG contamination arising from cranial muscles is often present early in BCI training and gradually wanes. In those users who eventually acquire EEG control, early target-related EMG contamination may be most prominent for unsuccessful trials, and may reflect user frustration. In those users who never acquire EEG control, EMG may initially serve to move the cursor toward the target. Careful and comprehensive topographical and spectral analyses throughout user training are essential for detecting EMG contamination and differentiating between cursor control provided by EEG control and cursor control provided by EMG contamination. SIGNIFICANCE: Artifacts such as EMG are common in EEG recordings. Comprehensive spectral and topographical analyses are necessary to detect them and ensure that they do not masquerade as, or interfere with acquisition of, actual EEG-based cursor control.
Keywords: brain-computer interface; EEG; Electroencephalography; Learning; mu rhythm; sensorimotor cortex

Communicating Directly from the Brain: Brain-Computer Interfaces - Gerwin Schalk (2005)
Condensed Matter Physics Seminar Series. Rensselaer Polytechnic Institute, Troy, New York

Discussion on "Towards a quantitative characterization of functional states of the brain: from the non-linear methodology to the global linear description" by J. Wackermann. - Pei, Xiao-Mei; Zheng, Shi Dong; Zhang, Ai-hua; Duan, Fu-jian; Bin, Guang-yu (Int J Psychophysiol, 2005)
Wackermann (1999) [Wackermann, J., 1999. Towards a quantitative characterization of functional states of the brain: from the non-linear methodology to the global linear description. Int. J. Psychophysiol. 34, 65-80] proposed Sigma-phi-Omega system for describing the global brain macro-state, in which Omega complexity was used to quantify the degree of synchrony between spatially distributed EEG processes. In this paper the effect of signal power on Omega complexity is discussed, which was not considered in Wackermann's paper (1999). Then an improved method for eliminating the effect of signal power on Omega complexity is proposed. Finally a case study on the degree of synchrony between two-channel EEG signals over different brain regions during hand motor imagery is given. The results show that the improved Omega complexity measure would characterize the true degree of synchrony among the EEG signals by eliminating the influence of signal power.
Keywords: Algorithms; Brain; Diagnostic Imaging; Functional Laterality; Humans; Linear Models; Models, Neurological; Nonlinear Dynamics

The importance of modality specificity in diagnosing central auditory processing disorder. - Anthony T. Cacace; Dennis J. McFarland (American journal of audiology, 2005)
PURPOSE: This article argues for the use of modality specificity as a unifying framework by which to conceptualize and diagnose central auditory processing disorder (CAPD). The intent is to generate dialogue and critical discussion in this area of study. METHOD: Research in the cognitive, behavioral, and neural sciences that relates to the concept of modality specificity was reviewed and synthesized. RESULTS: Modality specificity has a long history as an organizing construct within a diverse collection of mainstream scientific disciplines. The principle of modality specificity was contrasted with the unimodal inclusive framework, which holds that auditory tests alone are sufficient to make the CAPD diagnosis. Evidence from a large body of data demonstrated that the unimodal framework was unable to delineate modality-specific processes from more generalized dysfunction; it lacked discriminant validity and resulted in an incomplete assessment. Consequently, any hypothetical model resulting from incomplete assessments or potential therapies that are based on indeterminate diagnoses are themselves questionable, and caution should be used in their application. CONCLUSIONS: Improving specificity of diagnosis is an imperative core issue to the area of CAPD. Without specificity, the concept has little explanatory power. Because of serious flaws in concept and design, the unimodal inclusive framework should be abandoned in favor of a more valid approach that uses modality specificity.
Keywords: central auditory processing disorder; modality specificity

The interaction of a new motor skill and an old one: H-reflex conditioning and locomotion in rats. - Yi Chen; Xiang Yang Chen; Jakeman, Lyn B.; Gerwin Schalk; Stokes, Bradford T.; Jonathan Wolpaw (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2005)
New and old motor skills can interfere with each other or interact in other ways. Because each skill entails a distributed pattern of activity-dependent plasticity, investigation of their interactions is facilitated by simple models. In a well characterized model of simple learning, rats and monkeys gradually change the size of the H-reflex, the electrical analog of the spinal stretch reflex. This study evaluates in normal rats the interactions of this new skill of H-reflex conditioning with the old well established skill of overground locomotion. In rats in which the soleus H-reflex elicited in the conditioning protocol (i.e., the conditioning H-reflex) had been decreased by down-conditioning, the H-reflexes elicited during the stance and swing phases of locomotion (i.e., the locomotor H-reflexes) were also smaller. Similarly, in rats in which the conditioning H-reflex had been increased by up-conditioning, the locomotor H-reflexes were also larger. Soleus H-reflex conditioning did not affect the duration, length, or right/left symmetry of the step cycle. However, the conditioned change in the stance H-reflex was positively correlated with change in the amplitude of the soleus locomotor burst, and the correlation was consistent with current estimates of the contribution of primary afferent input to the burst. Although H-reflex conditioning and locomotion did not interfere with each other, H-reflex conditioning did affect how locomotion was produced: it changed soleus burst amplitude and may have induced compensatory changes in the activity of other muscles. These results illustrate and clarify the subtlety and complexity of skill interactions. They also suggest that H-reflex conditioning might be used to improve the abnormal locomotion produced by spinal cord injury or other disorders of supraspinal control.
Keywords: H-reflex conditioning; Learning; Locomotion; memory consolidation; Motor control; Rehabilitation; spinal cord plasticity

Long-term spinal reflex studies in awake behaving mice. - Jonathan S. Carp; Tennissen, Ann M.; Xiang Yang Chen; Gerwin Schalk; Jonathan Wolpaw (Journal of neuroscience methods, 2005)
The increasing availability of genetic variants of mice has facilitated studies of the roles of specific molecules in specific behaviors. The contributions of such studies could be strengthened and extended by correlation with detailed information on the patterns of motor commands throughout the course of specific behaviors in freely moving animals. Previously reported methodologies for long-term recording of electromyographic activity (EMG) in mice using implanted electrodes were designed for intermittent, but not continuous operation. This report describes the fabrication, implantation, and utilization of fine wire electrodes for continuous long-term recordings of spontaneous and nerve-evoked EMG in mice. Six mice were implanted with a tibial nerve cuff electrode and EMG electrodes in soleus and gastrocnemius muscles. Wires exited through a skin button and traveled through an armored cable to an electrical commutator. In mice implanted for 59-144 days, ongoing EMG was monitored continuously (i.e., 24 h/day, 7 days/week) by computer for 18-92 days (total intermittent recording for 25-130 days). When the ongoing EMG criteria were met, the computer applied the nerve stimulus, recorded the evoked EMG response, and determined the size of the M-response (MR) and the H-reflex (HR). It continually adjusted stimulation intensity to maintain a stable MR size. Stable recordings of ongoing EMG, MR, and HR were obtained typically 3 weeks after implantation. This study demonstrates the feasibility of long-term continuous EMG recordings in mice for addressing a variety of neurophysiological and behavioral issues.
Keywords: Electromyography; implanted electrodes; Monosynaptic; Spinal Cord

Methods Towards Invasive Human Brain Computer Interfaces. - Lal, T.N; Hinterberger, T.; Widman, Guido; Schroeder, Michael; Jeremy Jeremy Hill; Rosenstiel, W.; Elger, Christian; Schölkopf, B; Niels Birbaumer (2005)
During the last ten years there has been growing interest in the develop- ment of Brain Computer Interfaces (BCIs). The field has mainly been driven by the needs of completely paralyzed patients to communicate. With a few exceptions, most human BCIs are based on extracranial elec- troencephalography (EEG). However, reported bit rates are still low. One reason for this is the low signal-to-noise ratio of the EEG [16]. We are currently investigating if BCIs based on electrocorticography (ECoG) are a viable alternative. In this paper we present the method and examples of intracranial EEG recordings of three epilepsy patients with electrode grids placed on the motor cortex. The patients were asked to repeat- edly imagine movements of two kinds, e.g., tongue or finger movements. We analyze the classifiability of the data using Support Vector Machines (SVMs) [18, 21] and Recursive Channel Elimination (RCE) [11].
Keywords: Brain Computer Interfaces

News from the Wadsworth BCI R&D Program: Pushing the Envelope - Gerwin Schalk (2005)
Eberhard-Karls University, Tübingen, Germany

On-line Detection of Perceptual Signatures in Multichannel ECoG. - Gunduz, Aysegul; Principe, Jose; Freeman, Walter (Conf Proc IEEE Eng Med Biol Soc, 2005)
Neocortical ECoG studies have unveiled the presence of active states - spatial patterns of amplitude modulation- in the beta- gamma ranges in the presence of conditioned stimuli that resemble cinematographic frames. These sequences of active frames emerge with abrupt phase resettings, followed by resynchronization and stabilization over channels, and magnified intensity. An online pattern recognizer that captures the spatial and spectral characteristics of the active frames is presented. The results of detection are confirmed via high occurrences of pragmatic information, defined by the ratio of pattern intensity to pattern stability.

Particle picking by segmentation: a comparative study with SPIDER-based manual particle picking. - Adiga, Umesh; Baxter, Bill; Hall, Richard J; Rockel, Beate; Rath, Bimal K; Frank, Joachim; Glaeser, Robert M (J Struct Biol, 2005)
Boxing hundreds of thousands of particles in low-dose electron micrographs is one of the major bottle-necks in advancing toward achieving atomic resolution reconstructions of biological macromolecules. We have shown that a combination of pre-processing operations and segmentation can be used as an effective, automatic tool for identifying and boxing single-particle images. This paper provides a brief description of how this method has been applied to a large data set of micrographs of ice-embedded ribosomes, including a comparative analysis of the efficiency of the method. Some results on processing micrographs of tripeptidyl peptidase II particles are also shown. In both cases, we have achieved our goal of selecting at least 80% of the particles that an expert would select with less than 10% false positives.
Keywords: Algorithms; Aminopeptidases; Cryoelectron Microscopy; Dipeptidyl-Peptidases and Tripeptidyl-Peptidases; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Internet; Particle Size; Ribosomes; Serine Endopeptidases; Software; Software Validation

Pathways for the regulation of body iron homeostasis in response to experimental iron overload. - Theurl, Igor; Ludwiczek, Susanne; Eller, Philipp; Seifert, Markus; Artner, Erika; Peter Brunner; Weiss, Günter (J Hepatol, 2005)
BACKGROUND/AIMS: Secondary iron overload is a frequent clinical condition found in association with multiple blood transfusions. METHODS: To gain insight into adaptive changes in the expression of iron genes in duodenum, liver and spleen upon experimental iron overload we studied C57BL/6 mice receiving repetitive daily injections of iron-dextran for up to 5 days. RESULTS: Iron initially accumulated in spleen macrophages but with subsequent increase in macrophage ferroportin and ferritin expression its content in the spleen decreased while a progressive storage of iron occurred within hepatocytes which was paralleled by a significant increase in hepcidin and hemojuvelin expression. Under these conditions, iron was still absorbed from the duodenal lumen as divalent metal transporter-1 expressions were high, however, most of the absorbed iron was incorporated into duodenal ferritin, while ferroportin expression drastically decreased and iron transfer to the circulation was reduced. CONCLUSIONS: Experimental iron overload results in iron accumulation in macrophages and later in hepatocytes. In parallel, the transfer of iron from the gut to the circulation is diminished which may be referred to interference of hepcidin with ferroportin mediated iron export, thus preventing body iron accumulation.
Keywords: Animals; Disease Models, Animal; Disease Progression; DNA Primers; Duodenum; Gene Expression Regulation; Hepatocytes; Homeostasis; Iron; Iron Overload; Macrophages; Mice; Mice, Inbred C57BL; Polymerase Chain Reaction; RNA

Patients with ALS can use sensorimotor rhythms to operate a brain-computer interface. - Kübler, A.; Nijboer, F.; Mellinger, J.; Theresa M Vaughan; Pawelzik, H.; Gerwin Schalk; Dennis J. McFarland; Niels Birbaumer; Jonathan Wolpaw (Neurology, 2005)
People with severe motor disabilities can maintain an acceptable quality of life if they can communicate. Brain-computer interfaces (BCIs), which do not depend on muscle control, can provide communication. Four people severely disabled by ALS learned to operate a BCI with EEG rhythms recorded over sensorimotor cortex. These results suggest that a sensorimotor rhythm-based BCI could help maintain quality of life for people with ALS.
Keywords: User-Computer Interface

Patients with ALS can use sensorimotor rhythms to operate a brain-computer interface. - Kübler, A.; Nijboer, F; Mellinger, Jürgen; Theresa M Vaughan; Pawelzik, H; Gerwin Schalk; Dennis J. McFarland; Niels Birbaumer; Jonathan Wolpaw (Neurology, 2005)
People with severe motor disabilities can maintain an acceptable quality of life if they can communicate. Brain-computer interfaces (BCIs), which do not depend on muscle control, can provide communication. Four people severely disabled by ALS learned to operate a BCI with EEG rhythms recorded over sensorimotor cortex. These results suggest that a sensorimotor rhythm-based BCI could help maintain quality of life for people with ALS.
Keywords: Aged; Amyotrophic Lateral Sclerosis; Electroencephalography; Evoked Potentials, Motor; Evoked Potentials, Somatosensory; Female; Humans; Imagination; Male; Middle Aged; Motor Cortex; Movement; Paralysis; Photic Stimulation; Prostheses and Implants; Somatosensory Cortex; Treatment Outcome; User-Computer Interface

Recording Options for Brain-Computer Interfaces - Gerwin Schalk (2005)
Augmented Cognition Conference / Satellite to 11th International Conference on Human-Computer Interaction, Caesars Palace, Las Vegas, Nevada

Recording Options for Brain-Computer Interfaces. - Gerwin Schalk; Jonathan Wolpaw (Proceedings to the 1st Conference on Augmented Cognition, 2005)

Recording Options for Brain-Computer Interfaces - Gerwin Schalk; Jonathan Wolpaw (Proceedings to the 1st Conference on Augmented Cognition, 2005)

Robust EEG Channel Selection across Subjects for Brain-Computer Interfaces. - Schröder, Michael; Lal, T.N; Hinterberger, T.; Bogdan, Martin; Jeremy Jeremy Hill; Niels Birbaumer; Rosenstiel, W.; Schölkopf, B (EURASIP Journal on Advances in Signal Processing, 2005)
Most EEG-based brain-computer interface (BCI) paradigms come along with specific electrode positions, for example, for a visual-based BCI, electrode positions close to the primary visual cortex are used. For new BCI paradigms it is usually not known where task relevant activity can be measured from the scalp. For individual subjects, Lal et al. in 2004 showed that recording positions can be found without the use of prior knowledge about the paradigm used. However it remains unclear to what extent their method of recursive channel elimination (RCE) can be generalized across subjects. In this paper we transfer channel rankings from a group of subjects to a new subject. For motor imagery tasks the results are promising, although cross-subject channel selection does not quite achieve the performance of channel selection on data of single subjects. Although the RCE method was not provided with prior knowledge about the mental task, channels that are well known to be important (from a physiological point of view) were consistently selected whereas task-irrelevant channels were reliably disregarded.
Keywords: brain-computer interface; channel selection; Electroencephalography; feature selection; recursive channel elimination; support vector machine

Sensorimotor rhythm-based brain-computer interface (BCI): feature selection by regression improves performance. - Dennis J. McFarland; Jonathan Wolpaw (IEEE transactions on neural systems and rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2005)
People can learn to control electroencephalogram (EEG) features consisting of sensorimotor rhythm amplitudes and can use this control to move a cursor in one or two dimensions to a target on a screen. In the standard one-dimensional application, the cursor moves horizontally from left to right at a fixed rate while vertical cursor movement is continuously controlled by sensorimotor rhythm amplitude. The right edge of the screen is divided among 2-6 targets, and the user's goal is to control vertical cursor movement so that the cursor hits the correct target when it reaches the right edge. Up to the present, vertical cursor movement has been a linear function of amplitude in a specific frequency band [i.e., 8-12 Hz (mu) or 18-26 Hz (beta)] over left and/or right sensorimotor cortex. The present study evaluated the effect of controlling cursor movement with a weighted combination of these amplitudes in which the weights were determined by an regression algorithm on the basis of the user's past performance. Analyses of data obtained from a representative set of trained users indicated that weighted combinations of sensorimotor rhythm amplitudes could support cursor control significantly superior to that provided by a single feature. Inclusion of an interaction term further improved performance. Subsequent online testing of the regression algorithm confirmed the improved performance predicted by the offline analyses. The results demonstrate the substantial value for brain-computer interface applications of simple multivariate linear algorithms. In contrast to many classification algorithms, such linear algorithms can easily incorporate multiple signal features, can readily adapt to changes in the user's control of these features, and can accommodate additional targets without major modifications.

Towards 2D Brain Control Using ECoG - Gerwin Schalk (2005)
11th International Conference on Human-Computer Interaction, Caesars Palace, Las Vegas, Nevada

Towards two-dimensional cursor control using electrocorticographic signals - Gerwin Schalk; Leuthardt, E C; Moran, D; Miller, K.J.; Ojemann, J G; Jonathan Wolpaw (Proceedings to the 11th International Conference on Human-Computer Interaction, 2005)

Towards two-dimensional cursor control using electrocorticographic signals. - Gerwin Schalk; Leuthardt, E C; Moran, D; Miller, K.J.; Ojemann, J G; Jonathan Wolpaw (Proceedings to the 11th International Conference on Human-Computer Interaction, 2005)

Tracking of the mu rhythm using an empirically derived matched filter. - Krusienski, Dean J; Gerwin Schalk; Dennis J. McFarland; Jonathan Wolpaw (Proc. IEEE International Conference of Neural Engineering, 2005)
Keywords: bioelectric potentials; Brain Computer Interfaces; brain modeling; brain-computer interface; communication device; communication system control; cortical mu rhythm modulation; EEG; Electroencephalography; empirically derived matched filter; handicapped aids; laboratories; matched filters; medical signal detection; medical signal processing; monitoring; motor imagery; mu rhythm tracking; noninvasive treatment; rhythm; synchronous motors; two-dimensional cursor control data

Tracking of the mu rhythm using an empirically derived matched filter - Krusienski, Dean J; Gerwin Schalk; Dennis J. McFarland; Jonathan Wolpaw (Proc. IEEE International Conference of Neural Engineering, 2005)

An Auditory Paradigm for Brain–Computer Interfaces. - Jeremy Jeremy Hill; Lal, T.N; Bierig, K.; Niels Birbaumer; Schölkopf, B (2004)
Motivated by the particular problems involved in communicating with “locked-in” paralysed patients, we aim to develop a brain- computer interface that uses auditory stimuli. We describe a paradigm that allows a user to make a binary decision by focusing attention on one of two concurrent auditory stimulus sequences. Using Support Vector Machine classification and Recursive Chan- nel Elimination on the independent components of averaged event- related potentials, we show that an untrained user’s EEG data can be classified with an encouragingly high level of accuracy. This suggests that it is possible for users to modulate EEG signals in a single trial by the conscious direction of attention, well enough to be useful in BCI.
Keywords: Brain Computer Interfaces

The BCI Competition 2003: Progress and perspectives in detection and discrimination of EEG single trials. - Benjamin Blankertz; Müller, Klaus-Robert; Curio, Gabriel; Theresa M Vaughan; Gerwin Schalk; Jonathan Wolpaw; Schlögl, Alois; Neuper, Christa; Pfurtscheller, Gert; Hinterberger, T.; Schröder, Michael; Niels Birbaumer (IEEE Trans Biomed Eng, 2004)
Interest in developing a new method of man-to-machine communication--a brain-computer interface (BCI)--has grown steadily over the past few decades. BCIs create a new communication channel between the brain and an output device by bypassing conventional motor output pathways of nerves and muscles. These systems use signals recorded from the scalp, the surface of the cortex, or from inside the brain to enable users to control a variety of applications including simple word-processing software and orthotics. BCI technology could therefore provide a new communication and control option for individuals who cannot otherwise express their wishes to the outside world. Signal processing and classification methods are essential tools in the development of improved BCI technology. We organized the BCI Competition 2003 to evaluate the current state of the art of these tools. Four laboratories well versed in EEG-based BCI research provided six data sets in a documented format. We made these data sets (i.e., labeled training sets and unlabeled test sets) and their descriptions available on the Internet. The goal in the competition was to maximize the performance measure for the test labels. Researchers worldwide tested their algorithms and competed for the best classification results. This paper describes the six data sets and the results and function of the most successful algorithms.
Keywords: Adult; Algorithms; Amyotrophic Lateral Sclerosis; Artificial Intelligence; Brain; Cognition; Databases, Factual; Electroencephalography; Evoked Potentials; Humans; Reproducibility of Results; Sensitivity and Specificity; User-Computer Interface

The BCI Competition 2003: progress and perspectives in detection and discrimination of EEG single trials. - Benjamin Blankertz; Müller, Klaus-Robert; Curio, Gabriel; Theresa M Vaughan; Gerwin Schalk; Jonathan Wolpaw; Schlögl, Alois; Neuper, Christa; Pfurtscheller, Gert; Hinterberger, Thilo; Schröder, Michael; Niels Birbaumer (IEEE transactions on bio-medical engineering, 2004)
Interest in developing a new method of man-to-machine communication–a brain-computer interface (BCI)–has grown steadily over the past few decades. BCIs create a new communication channel between the brain and an output device by bypassing conventional motor output pathways of nerves and muscles. These systems use signals recorded from the scalp, the surface of the cortex, or from inside the brain to enable users to control a variety of applications including simple word-processing software and orthotics. BCI technology could therefore provide a new communication and control option for individuals who cannot otherwise express their wishes to the outside world. Signal processing and classification methods are essential tools in the development of improved BCI technology. We organized the BCI Competition 2003 to evaluate the current state of the art of these tools. Four laboratories well versed in EEG-based BCI research provided six data sets in a documented format. We made these data sets (i.e., labeled training sets and unlabeled test sets) and their descriptions available on the Internet. The goal in the competition was to maximize the performance measure for the test labels. Researchers worldwide tested their algorithms and competed for the best classification results. This paper describes the six data sets and the results and function of the most successful algorithms.
Keywords: augmentative communication; BCI; beta-rhythm; brain-computer interface; EEG; ERP; imagined hand movements; lateralized readiness potential; mu-rhythm; P300; Rehabilitation; single-trial classification; slow cortical potentials

BCI2000: a general-purpose brain-computer interface (BCI) system. - Gerwin Schalk; Dennis J. McFarland; Hinterberger, Thilo; Niels Birbaumer; Jonathan Wolpaw (IEEE transactions on bio-medical engineering, 2004)
Many laboratories have begun to develop brain-computer interface (BCI) systems that provide communication and control capabilities to people with severe motor disabilities. Further progress and realization of practical applications depends on systematic evaluations and comparisons of different brain signals, recording methods, processing algorithms, output formats, and operating protocols. However, the typical BCI system is designed specifically for one particular BCI method and is, therefore, not suited to the systematic studies that are essential for continued progress. In response to this problem, we have developed a documented general-purpose BCI research and development platform called BCI2000. BCI2000 can incorporate alone or in combination any brain signals, signal processing methods, output devices, and operating protocols. This report is intended to describe to investigators, biomedical engineers, and computer scientists the concepts that the BC12000 system is based upon and gives examples of successful BCI implementations using this system. To date, we have used BCI2000 to create BCI systems for a variety of brain signals, processing methods, and applications. The data show that these systems function well in online operation and that BCI2000 satisfies the stringent real-time requirements of BCI systems. By substantially reducing labor and cost, BCI2000 facilitates the implementation of different BCI systems and other psychophysiological experiments. It is available with full documentation and free of charge for research or educational purposes and is currently being used in a variety of studies by many research groups.
Keywords: User-Computer Interface

BCI2000: a general-purpose brain-computer interface (BCI) system. - Gerwin Schalk; Dennis J. McFarland; Hinterberger, T.; Niels Birbaumer; Jonathan Wolpaw (IEEE Trans Biomed Eng, 2004)
Many laboratories have begun to develop brain-computer interface (BCI) systems that provide communication and control capabilities to people with severe motor disabilities. Further progress and realization of practical applications depends on systematic evaluations and comparisons of different brain signals, recording methods, processing algorithms, output formats, and operating protocols. However, the typical BCI system is designed specifically for one particular BCI method and is, therefore, not suited to the systematic studies that are essential for continued progress. In response to this problem, we have developed a documented general-purpose BCI research and development platform called BCI2000. BCI2000 can incorporate alone or in combination any brain signals, signal processing methods, output devices, and operating protocols. This report is intended to describe to investigators, biomedical engineers, and computer scientists the concepts that the BC12000 system is based upon and gives examples of successful BCI implementations using this system. To date, we have used BCI2000 to create BCI systems for a variety of brain signals, processing methods, and applications. The data show that these systems function well in online operation and that BCI2000 satisfies the stringent real-time requirements of BCI systems. By substantially reducing labor and cost, BCI2000 facilitates the implementation of different BCI systems and other psychophysiological experiments. It is available with full documentation and free of charge for research or educational purposes and is currently being used in a variety of studies by many research groups.
Keywords: Algorithms; Brain; Cognition; Communication Aids for Disabled; Computer Peripherals; Electroencephalography; Equipment Design; Equipment Failure Analysis; Evoked Potentials; Humans; Systems Integration; User-Computer Interface

A binary segmentation approach for boxing ribosome particles in cryo EM micrographs. - Adiga, Umesh; Malladi, Ravi; Baxter, Bill; Glaeser, Robert M (J Struct Biol, 2004)
Three-dimensional reconstruction of ribosome particles from electron micrographs requires selection of many single-particle images. Roughly 100,000 particles are required to achieve approximately 10 A resolution. Manual selection of particles, by visual observation of the micrographs on a computer screen, is recognized as a bottleneck in automated single-particle reconstruction. This paper describes an efficient approach for automated boxing of ribosome particles in micrographs. Use of a fast, anisotropic non-linear reaction-diffusion method to pre-process micrographs and rank-leveling to enhance the contrast between particles and the background, followed by binary and morphological segmentation constitute the core of this technique. Modifying the shape of the particles to facilitate segmentation of individual particles within clusters and boxing the isolated particles is successfully attempted. Tests on a limited number of micrographs have shown that over 80% success is achieved in automatic particle picking.
Keywords: Algorithms; Anisotropy; Automatic Data Processing; Cryoelectron Microscopy; Image Enhancement; Image Processing, Computer-Assisted; Particle Size; Pattern Recognition, Automated; Ribosomes; Software Design

A brain-computer interface using electrocorticographic signals in humans. - Leuthardt, E C; Gerwin Schalk; Jonathan Wolpaw; Ojemann, J G; Moran, D (J Neural Eng, 2004)
Brain-computer interfaces (BCIs) enable users to control devices with electroencephalographic (EEG) activity from the scalp or with single-neuron activity from within the brain. Both methods have disadvantages: EEG has limited resolution and requires extensive training, while single-neuron recording entails significant clinical risks and has limited stability. We demonstrate here for the first time that electrocorticographic (ECoG) activity recorded from the surface of the brain can enable users to control a one-dimensional computer cursor rapidly and accurately. We first identified ECoG signals that were associated with different types of motor and speech imagery. Over brief training periods of 3-24 min, four patients then used these signals to master closed-loop control and to achieve success rates of 74-100% in a one-dimensional binary task. In additional open-loop experiments, we found that ECoG signals at frequencies up to 180 Hz encoded substantial information about the direction of two-dimensional joystick movements. Our results suggest that an ECoG-based BCI could provide for people with severe motor disabilities a non-muscular communication and control option that is more powerful than EEG-based BCIs and is potentially more stable and less traumatic than BCIs that use electrodes penetrating the brain.
Keywords: Adult; Brain; Communication Aids for Disabled; Computer Peripherals; Diagnosis, Computer-Assisted; Electrodes, Implanted; Electroencephalography; Evoked Potentials; Female; Humans; Imagination; Male; Movement Disorders; User-Computer Interface

Brain-computer interfaces (BCIs) for communication and control: a mini-review. - Jonathan Wolpaw (Supplements to Clinical neurophysiology, 2004)
Keywords: augmentative communication and control; brain-computer interfaces; neuro-muscular disorders

Brain-Computer Interfaces; EGI Amp Server; Event-Detection - Gerwin Schalk (2004)
Electrical Geodesics, Eugene, Oregon

Brain-Computer Interfaces: Present and Future - Gerwin Schalk (2004)
"BrainDays" Symposium, Rudolf Magnus Institute of Neuroscience, University Medical Center, Utrecht, The Netherlands

Brain-Computer Interfaces: Present and Future - Gerwin Schalk (2004)
University of Washington, Seattle, Washington

Brain-Computer Interfaces: Present and Future - Gerwin Schalk (2004)
Fondazione Santa Lucia, Rome, Italy

Brain-Computer Interfaces: Signals, Methods, and Systems - Gerwin Schalk (2004)
Seminar SeriesNew Frontiers in Brain Machine Interfaces Research. Institute for Infocomm Research(I2R), Singapore

Business in Austria - Gerwin Schalk (2004)
International Business Panel, Executive MBA Program, Lally School of Management, Rensselaer Polytechnic Institute, Troy, NY

Control of a two-dimensional movement signal by a noninvasive brain-computer interface in humans. - Jonathan Wolpaw; Dennis J. McFarland (Proceedings of the National Academy of Sciences of the United States of America, 2004)
Brain-computer interfaces (BCIs) can provide communication and control to people who are totally paralyzed. BCIs can use noninvasive or invasive methods for recording the brain signals that convey the user's commands. Whereas noninvasive BCIs are already in use for simple applications, it has been widely assumed that only invasive BCIs, which use electrodes implanted in the brain, can provide multidimensional movement control of a robotic arm or a neuroprosthesis. We now show that a noninvasive BCI that uses scalp-recorded electroencephalographic activity and an adaptive algorithm can provide humans, including people with spinal cord injuries, with multidimensional point-to-point movement control that falls within the range of that reported with invasive methods in monkeys. In movement time, precision, and accuracy, the results are comparable to those with invasive BCIs. The adaptive algorithm used in this noninvasive BCI identifies and focuses on the electroencephalographic features that the person is best able to control and encourages further improvement in that control. The results suggest that people with severe motor disabilities could use brain signals to operate a robotic arm or a neuroprosthesis without needing to have electrodes implanted in their brains.
Keywords: brain-machine interface; Electroencephalography

Conversion of EEG activity into cursor movement by a brain-computer interface (BCI). - Fabiani, Georg E.; Dennis J. McFarland; Jonathan Wolpaw; Pfurtscheller, Gert (IEEE transactions on neural systems and rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2004)
The Wadsworth electroencephalogram (EEG)-based brain-computer interface (BCI) uses amplitude in mu or beta frequency bands over sensorimotor cortex to control cursor movement. Trained users can move the cursor in one or two dimensions. The primary goal of this research is to provide a new communication and control option for people with severe motor disabilities. Currently, cursor movements in each dimension are determined 10 times/s by an empirically derived linear function of one or two EEG features (i.e., spectral bands from different electrode locations). This study used offline analysis of data collected during system operation to explore methods for improving the accuracy of cursor movement. The data were gathered while users selected among three possible targets by controlling vertical [i.e., one-dimensional (1-D)] cursor movement. The three methods analyzed differ in the dimensionality of the cursor movement [1-D versus two-dimensional (2-D)] and in the type of the underlying function (linear versus nonlinear). We addressed two questions: Which method is best for classification (i.e., to determine from the EEG which target the user wants to hit)? How does the number of EEG features affect the performance of each method? All methods reached their optimal performance with 10-20 features. In offline simulation, the 2-D linear method and the 1-D nonlinear method improved performance significantly over the 1-D linear method. The 1-D linear method did not do so. These offline results suggest that the 1-D nonlinear or the 2-D linear cursor function will improve online operation of the BCI system.
Keywords: augmentative communication; Brain-computer interface (BCI); Electroencephalography; Feedback

Introduction to Brain-Computer Interfaces - Gerwin Schalk (2004)
University of Rome "La Sapienza," Rome, Italy

P300 for communication: Evidence from patients with amyotrophic lateral sclerosis (ALS). - Mellinger, Jürgen; Nijboer, F; Pawelzik, H; Gerwin Schalk; Dennis J. McFarland; Theresa M Vaughan; Jonathan Wolpaw; Niels Birbaumer; Kuebler, A. (Biomedizinische Technik, 2004)

Separating stimulus-locked and unlocked components of the auditory event-related potential. - Dennis J. McFarland; Anthony T. Cacace (Hearing research, 2004)
A new method is evaluated for separating stimulus-locked and unlocked components of auditory event-related EEG activity. The new method uses a regression based subtraction procedure as a way to account for latency and amplitude variability within individual trials. It was applied using the oddball paradigm under conditions of active and passive listening and analyzed as spectral correlations (normalized differences) between post-stimulus epochs of standard, target or deviant stimulus conditions and silent pre-stimulus baseline activity. The regression-subtraction procedure accounted for a greater amount of variance than a method that uses linear subtraction alone. The major component of the response to auditory stimulation was an event-related synchronization in the delta and theta (2-4 Hz) frequency range. Event-related desynchronizations were also observed in the 10 Hz (alpha/mu) and in the 20-30 Hz (beta) frequency range. The regression based subtraction procedure provides better separation of stimulus-locked and unlocked components of event-related EEG activity then linear subtraction alone. Stimulus-locked and unlocked components show different patterns and topographies of effects related to attention and active discrimination. Studying both stimulus-locked and unlocked components of event-related EEG reactivity in the frequency domain provides a more comprehensive account of dynamic brain activity subserving auditory information processing.
Keywords: event-related desynchronization; event-related potentials; event-related synchronization; phase; spectral dynamics

Brain-computer interface (BCI) operation: optimizing information transfer rates. - Dennis J. McFarland; Sarnacki, William A.; Jonathan Wolpaw (Biological psychology, 2003)
People can learn to control mu (8-12 Hz) or beta (18-25 Hz) rhythm amplitude in the EEG recorded over sensorimotor cortex and use it to move a cursor to a target on a video screen. In the present version of the cursor movement task, vertical cursor movement is a linear function of mu or beta rhythm amplitude. At the same time the cursor moves horizontally from left to right at a fixed rate. A target occupies 50% (2-target task) to 20% (5-target task) of the right edge of the screen. The user's task is to move the cursor vertically so that it hits the target when it reaches the right edge. The goal of the present study was to optimize system performance. To accomplish this, we evaluated the impact on system performance of number of targets (i.e. 2-5) and trial duration (i.e. horizontal movement time from 1 to 4 s). Performance was measured as accuracy (percent of targets selected correctly) and also as bit rate (bits/min) (which incorporates, in addition to accuracy, speed and the number of possible targets). Accuracy declined as target number increased. At the same time, for six of eight users, four targets yielded the maximum bit rate. Accuracy increased as movement time increased. At the same time, the movement time with the highest bit rate varied across users from 2 to 4 s. These results indicate that task parameters such as target number and trial duration can markedly affect system performance. They also indicate that optimal parameter values vary across users. Selection of parameters suited both to the specific user and the requirements of the specific application is likely to be a key factor in maximizing the success of EEG-based communication and control.
Keywords: augmentative communication; Electroencephalography; information; Learning; mu rhythm; operant conditioning; prosthesis; Rehabilitation; sensorimotor cortex

Brain-computer interface technology: a review of the Second International Meeting. - Theresa M Vaughan; Heetderks, William J.; Trejo, Leonard J.; Rymer, William Z.; Weinrich, Michael; Moore, Melody M.; Kübler, Andrea; Dobkin, Bruce H.; Niels Birbaumer; Emanuel Donchin; Wolpaw, Elizabeth Winter; Jonathan Wolpaw (IEEE transactions on neural systems and rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2003)
This paper summarizes the Brain-Computer Interfaces for Communication and Control, The Second International Meeting, held in Rensselaerville, NY, in June 2002. Sponsored by the National Institutes of Health and organized by the Wadsworth Center of the New York State Department of Health, the meeting addressed current work and future plans in brain-computer interface (BCI) research. Ninety-two researchers representing 38 different research groups from the United States, Canada, Europe, and China participated. The BCIs discussed at the meeting use electroencephalographic activity recorded from the scalp or single-neuron activity recorded within cortex to control cursor movement, select letters or icons, or operate neuroprostheses. The central element in each BCI is a translation algorithm that converts electrophysiological input from the user into output that controls external devices. BCI operation depends on effective interaction between two adaptive controllers, the user who encodes his or her commands in the electrophysiological input provided to the BCI, and the BCI that recognizes the commands contained in the input and expresses them in device control. Current BCIs have maximum information transfer rates of up to 25 b/min. Achievement of greater speed and accuracy requires improvements in signal acquisition and processing, in translation algorithms, and in user training. These improvements depend on interdisciplinary cooperation among neuroscientists, engineers, computer programmers, psychologists, and rehabilitation specialists, and on adoption and widespread application of objective criteria for evaluating alternative methods. The practical use of BCI technology will be determined by the development of appropriate applications and identification of appropriate user groups, and will require careful attention to the needs and desires of individual users.
Keywords: augmentative communication; Brain-computer interface (BCI); electroencephalography (EEG); Rehabilitation

Brain-Computer Interfaces: Signals, Methods, and Systems - Gerwin Schalk (2003)
World Congress on Medical Physics and Biomedical Engineering, Sydney, Australia

Brain-Computer Interfaces: Signals, Methods, and Systems - Gerwin Schalk (2003)
Eberhard Karls University of Tübingen, Tübingen, Germany

Brain-Computer Interfaces: Signals, Methods, and Systems - Gerwin Schalk (2003)
NASA Ames Research Center, Moffett Field, CA

Brain-Computer Interfaces: Signals, Methods, and Systems - Gerwin Schalk (2003)
Society for Neuroscience Hudson-Berkshire Chapter, State University of Albany, Albany, NY

Business in Austria - Gerwin Schalk (2003)
International Business Panel, Executive MBA Program, Lally School of Management, Rensselaer Polytechnic Institute, Troy, NY

Conditioned H-reflex increase persists after transection of the main corticospinal tract in rats. - Xiang Yang Chen; Lu Chen; Jonathan Wolpaw (Journal of neurophysiology, 2003)
The brain shapes spinal cord function throughout life. Operant conditioning of the H-reflex, the electrical analog of the spinal stretch reflex (SSR), is a relatively simple model for exploring the spinal cord plasticity underlying this functional change and may provide a new method for modifying spinal cord reflexes after spinal cord injury. In response to an operant conditioning protocol, rats can gradually increase (i.e., up-training mode) or decrease (i.e., down-training mode) the soleus H-reflex. This study explored the effects of midthoracic transection of the ipsilateral lateral column (LC) (rubrospinal, vestibulospinal, and reticulospinal tracts), the dorsal column corticospinal tract (CST), or the dorsal column ascending tract (DA) on maintenance of an H-reflex increase that has already occurred. Rats were implanted with EMG electrodes in the right soleus muscle and a nerve-stimulating cuff on the right posterior tibial nerve. After initial (i.e., control) H-reflex size was determined, the rats were exposed for 50 days to the up-training mode, in which reward was given when the H-reflex was above a criterion value. H-reflex size gradually rose to 168 +/- 12% (mean +/- SE) of its initial value. Each rat then received an LC, CST, or DA transection and continued under the up-training mode for 50 more days. None of the transections abolished the H-reflex increase. H-reflex size increased further to 197 +/- 19% of its initial value and did not differ significantly among LC, CST, and DA rats (P > 0.78 by ANOVA). Although earlier studies show that the main CST is needed for acquisition of H-reflex up-training and down-training and for maintenance of down-training, this study shows that it is not needed for maintenance of up-training. It adds to the evidence that H-reflex conditioning changes the spinal cord and that the spinal cord plasticity associated with up-training is different from that associated with down-training.
Keywords: Spinal Cord Injuries

Conduction velocity is inversely related to action potential threshold in rat motoneuron axons. - Jonathan S. Carp; Tennissen, Ann M.; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2003)
Intra-axonal recordings were performed in ventral roots of rats in vitro to study the conduction velocity and firing threshold properties of motoneuron axons. Mean values +/- SD were 30.5+/-5.6 m/s for conduction velocity and 11.6+/-4.5 mV for the depolarization from the resting potential required to reach firing threshold (threshold depolarization). Conduction velocity varied inversely and significantly with threshold depolarization ( P=0.0002 by linear regression). This relationship was evident even after accounting for variation in conduction velocity associated with action potential amplitude, injected current amplitude, or body weight. Conduction velocity also varied inversely with the time to action potential onset during just-threshold current pulse injection. These data suggest that the time course of depolarization leading to action potential initiation contributes to the speed of conduction in motoneuron axons.
Keywords: action potential; conduction velocity; intra-axonal recording; myelinated axon; threshold

EEG-based communication and control: speed-accuracy relationships. - Dennis J. McFarland; Jonathan Wolpaw (Applied psychophysiology and biofeedback, 2003)
People can learn to control mu (8-12 Hz) or beta (18-25 Hz) rhythm amplitude in the EEG recorded over sensorimotor cortex and use it to move a cursor to a target on a video screen. In our current EEG-based brain-computer interface (BCI) system, cursor movement is a linear function of mu or beta rhythm amplitude. In order to maximize the participant's control over the direction of cursor movement, the intercept in this equation is kept equal to the mean amplitude of recent performance. Selection of the optimal slope, or gain, which determines the magnitude of the individual cursor movements, is a more difficult problem. This study examined the relationship between gain and accuracy in a 1-dimensional EEG-based cursor movement task in which individuals select among 2 or more choices by holding the cursor at the desired choice for a fixed period of time (i.e., the dwell time). With 4 targets arranged in a vertical column on the screen, large gains favored the end targets whereas smaller gains favored the central targets. In addition, manipulating gain and dwell time within participants produces results that are in agreement with simulations based on a simple theoretical model of performance. Optimal performance occurs when correct selection of targets is uniform across position. Thus, it is desirable to remove any trend in the function relating accuracy to target position. We evaluated a controller that is designed to minimize the linear and quadratic trends in the accuracy with which participants hit the 4 targets. These results indicate that gain should be adjusted to the individual participants, and suggest that continual online gain adaptation could increase the speed and accuracy of EEG-based cursor control.
Keywords: Video Recording

Electroencephalographic(EEG)-based communication: EEG control versus system performance in humans. - Sheikh, Hesham; Dennis J. McFarland; Sarnacki, William A.; Jonathan Wolpaw (Neuroscience letters, 2003)
People can learn to control electroencephalographic (EEG) sensorimotor rhythm amplitude so as to move a cursor to select among choices on a computer screen. We explored the dependence of system performance on EEG control. Users moved the cursor to reach a target at one of four possible locations. EEG control was measured as the correlation (r(2)) between rhythm amplitude and target location. Performance was measured as accuracy (% of targets hit) and as information transfer rate (bits/trial). The relationship between EEG control and accuracy can be approximated by a linear function that is constant for all users. The results facilitate offline predictions of the effects on performance of using different EEG features or combinations of features to control cursor movement.
Keywords: augmentative communication; brain-computer interface; brain-machine interface; Electroencephalography; mu and beta rhythms; neuroprosthesis; Rehabilitation

EMG contamination of EEG: spectral and topographical characteristics. - Goncharova, I. I.; Dennis J. McFarland; Theresa M Vaughan; Jonathan Wolpaw (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2003)
OBJECTIVE: Electromyogram (EMG) contamination is often a problem in electroencephalogram (EEG) recording, particularly, for those applications such as EEG-based brain-computer interfaces that rely on automated measurements of EEG features. As an essential prelude to developing methods for recognizing and eliminating EMG contamination of EEG, this study defines the spectral and topographical characteristics of frontalis and temporalis muscle EMG over the entire scalp. It describes both average data and the range of individual differences. METHODS: In 25 healthy adults, signals from 64 scalp and 4 facial locations were recorded during relaxation and during defined (15, 30, or 70% of maximum) contractions of frontalis or temporalis muscles. RESULTS: In the average data, EMG had a broad frequency distribution from 0 to >200 Hz. Amplitude was greatest at 20-30 Hz frontally and 40-80 Hz temporally. Temporalis spectra also showed a smaller peak around 20 Hz. These spectral components attenuated and broadened centrally. Even with weak (15%) contraction, EMG was detectable (P<0.001) near the vertex at frequencies >12 Hz in the average data and >8 Hz in some individuals. CONCLUSIONS: Frontalis or temporalis muscle EMG recorded from the scalp has spectral and topographical features that vary substantially across individuals. EMG spectra often have peaks in the beta frequency range that resemble EEG beta peaks. SIGNIFICANCE: While EMG contamination is greatest at the periphery of the scalp near the active muscles, even weak contractions can produce EMG that obscures or mimics EEG alpha, mu, or beta rhythms over the entire scalp. Recognition and elimination of this contamination is likely to require recording from an appropriate set of peripheral scalp locations.
Keywords: artifact; brain-computer interface; electroencephalogram; electromyogram; Rehabilitation

Potential problems in the differential diagnosis of (central) auditory processing disorder (CAPD or APD) and attention-deficit hyperactivity disorder (ADHD). - Dennis J. McFarland; Anthony T. Cacace (Journal of the American Academy of Audiology, 2003)
Keywords: Humans

Quantifying signal-to-noise ratio of mismatch negativity in humans. - Anthony T. Cacace; Dennis J. McFarland (Neuroscience letters, 2003)
Mismatch negativity (MMN) is thought to represent a neurophysiological index of auditory information processing that is independent of attention. Because this measure does not require an overt behavioral response, MMN has potential to evaluate higher order perceptual abilities in infants, young children and difficult-to-test populations, thereby extending results obtained from more basic physiologic and electroacoustic measures (auditory brainstem responses, ABRs; otoacoustic emissions, OAEs). Whereas the basic tenet of MMN is appealing, several issues-of-contention remain to be solved before this event related potential (ERP) can be applicable for routine clinical use. These issues include the consistent identification of MMN within individuals (vs. groups), its stability over time, and its reportedly poor signal-to-noise ratio (SNR). Herein, we focus on the issue of SNR, by comparing and contrasting SNR of MMN with other long latency auditory ERPs.
Keywords: auditory brainstem responses; event related potential; mismatch negativity; otoacoustic emissions; signal-to-noise ratio

Spectral dynamics of electroencephalographic activity during auditory information processing. - Anthony T. Cacace; Dennis J. McFarland (Hearing research, 2003)
Dynamics of electroencephalographic (EEG) activity during auditory information processing were evaluated in response to changes in stimulus complexity, stimulus discriminability and attention using the oddball paradigm. In comparison to pre-stimulus baseline conditions, auditory stimulation synchronized EEG activity in delta, theta and alpha frequency bands. Event-related synchronization (ERS) effects were greatest at approximately 3 Hz (theta frequency band), and their magnitude depended on stimulus and task demands. Event-related desynchronization (ERD) of EEG activity was observed in the beta frequency band. This effect was greatest at approximately 21 Hz but occurred only for easily discriminable stimuli in attention-related target conditions. Because active discrimination tasks also required a button-press response with the right hand, ERDs involved more complex responses that may be related to a combination of perceptual, motor and cognitive processes. These results demonstrate that oddball and attention-related EEG responses to auditory stimulation could be characterized in the frequency domain. The specific design and analysis features described herein may prove useful since they provide a simple index of the brain's response to stimulation while at the same time provide powerful information not contained in typical time domain analysis.
Keywords: Electroencephalography; event-related brain dynamics; event-related desynchronization; event-related synchronization; psychophysics; spectral analysis; time domain analysis

The Wadsworth Center brain-computer interface (BCI) research and development program. - Jonathan Wolpaw; Dennis J. McFarland; Theresa M Vaughan; Gerwin Schalk (IEEE Trans Neural Syst Rehabil Eng, 2003)
Brain-computer interface (BCI) research at the Wadsworth Center has focused primarily on using electroencephalogram (EEG) rhythms recorded from the scalp over sensorimotor cortex to control cursor movement in one or two dimensions. Recent and current studies seek to improve the speed and accuracy of this control by improving the selection of signal features and their translation into device commands, by incorporating additional signal features, and by optimizing the adaptive interaction between the user and system. In addition, to facilitate the evaluation, comparison, and combination of alternative BCI methods, we have developed a general-purpose BCI system called BCI-2000 and have made it available to other research groups. Finally, in collaboration with several other groups, we are developing simple BCI applications and are testing their practicality and long-term value for people with severe motor disabilities.
Keywords: Academic Medical Centers; Adult; Algorithms; Artifacts; Brain; Brain Mapping; Electroencephalography; Evoked Potentials, Visual; Feedback; Humans; Middle Aged; Nervous System Diseases; Research; Research Design; User-Computer Interface; Visual Perception

Brain-Computer Interfaces and BCI2000 - Gerwin Schalk (2002)
Georgia State University, Atlanta, Georgia

Brain-Computer Interfaces for Communication and Control - Gerwin Schalk (2002)
8th International Conference on Functional Mapping of the Human Brain, Sendai, Japan

Brain-computer interfaces for communication and control. - Jonathan Wolpaw; Niels Birbaumer; Dennis J. McFarland; Pfurtscheller, Gert; Theresa M Vaughan (Clin Neurophysiol, 2002)
For many years people have speculated that electroencephalographic activity or other electrophysiological measures of brain function might provide a new non-muscular channel for sending messages and commands to the external world - a brain-computer interface (BCI). Over the past 15 years, productive BCI research programs have arisen. Encouraged by new understanding of brain function, by the advent of powerful low-cost computer equipment, and by growing recognition of the needs and potentials of people with disabilities, these programs concentrate on developing new augmentative communication and controltechnology for those with severe neuromuscular disorders, such as amyotrophic lateral sclerosis, brainstem stroke, and spinal cord injury. The immediate goal is to provide these users, who may be completely paralyzed, or 'locked in', with basic communication capabilities so that they can express their wishes to caregivers or even operate word processing programs or neuroprostheses. Present-day BCIs determine the intent of the user from a variety of different electrophysiological signals. These signals include slow cortical potentials, P300 potentials, and mu or beta rhythms recorded from the scalp, and cortical neuronal activity recorded by implanted electrodes. They are translated in real-time into commands that operate a computer display or other device. Successful operation requires that the user encode commands in these signals and that the BCI derive the commands from the signals. Thus, the user and the BCI system need to adapt to each other both initially and continually so as to ensure stable performance. Current BCIs have maximum information transfer rates up to 10-25bits/min. This limited capacity can be valuable for people whose severe disabilities prevent them from using conventional augmentative communication methods. At the same time, many possible applications of BCI technology, such as neuroprosthesis control, may require higher information transfer rates. Future progress will depend on: recognition that BCI research and development is an interdisciplinary problem, involving neurobiology, psychology, engineering, mathematics, and computer science; identification of those signals, whether evoked potentials, spontaneous rhythms, or neuronal firing rates, that users are best able to control independent of activity in conventional motor output pathways; development of training methods for helping users to gain and maintain that control; delineation of the best algorithms for translating these signals into device commands; attention to the identification and elimination of artifacts such as electromyographic and electro-oculographic activity; adoption of precise and objective procedures for evaluating BCI performance; recognition of the need for long-term as well as short-term assessment of BCI performance; identification of appropriate BCI applications and appropriate matching of applications and users; and attention to factors that affect user acceptance of augmentative technology, including ease of use, cosmesis, and provision of those communication and control capacities that are most important to the user. Development of BCI technology will also benefit from greater emphasis on peer-reviewed research publications and avoidance of the hyperbolic and often misleading media attention that tends to generate unrealistic expectations in the public and skepticism in other researchers. With adequate recognition and effective engagement of all these issues, BCI systems could eventually provide an important new communication and control option for those with motor disabilities and might also give those without disabilities a supplementary control channel or a control channel useful in special circumstances.
Keywords: Brain Diseases; Communication Aids for Disabled; Computer Systems; Electroencephalography; Humans; User-Computer Interface

Corticospinal tract transection prevents operantly conditioned H-reflex increase in rats. - Xiang Yang Chen; Jonathan S. Carp; Lu Chen; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2002)
Operant conditioning of the H-reflex, the electrical analog of the spinal stretch reflex, in freely moving rats is a relatively simple model for studying long-term supraspinal control over spinal cord function. Motivated by food reward, rats can gradually increase (i.e., up-condition) or decrease (i.e., down-condition) the soleus H-reflex. Earlier work showed that corticospinal tract transection prevents acquisition and maintenance of H-reflex down-conditioning while transection of other major spinal cord tracts does not. This study explores the effects on acquisition of up-conditioning of the right soleus H-reflex of mid-thoracic transection of: the right lateral column (LC, five rats) (containing the rubrospinal, vestibulospinal, and reticulospinal tracts); the entire dorsal column (DC, six rats) [containing the main corticospinal tract (CST) and the dorsal ascending tract (DA)]; the CST alone (five rats); or the DA alone (seven rats). After initial (i.e., control) H-reflex amplitude was determined, the rat was exposed for 50 days to the up-conditioning mode in which reward was given when the H-reflex was above a criterion value. H-reflex amplitude at the end of up-conditioning was compared to initial H-reflex amplitude. An increase > or =20% was defined as successful up-conditioning. In intact rats, H-reflex amplitude at the end of up-conditioning averaged 164% (+/-10%, SE), and 81% were successful. In the present study, LC and DA rats were similar to intact rats in final H-reflex amplitude and percent successful. In contrast, results for DC and CST rats were significantly different from those of intact rats. In the six DC rats, final H-reflex amplitude averaged 105% (+/-3)% of control and none was successful; and in the five CST rats, final H-reflex amplitude averaged 94% (+/-3)% and none was successful. The results indicate that the main CST, located in the dorsal column, is essential for H-reflex up-conditioning as it is for down-conditioning, while the dorsal column ascending tract and the ipsilateral lateral column (containing the main rubrospinal, vestibulospinal, and reticulospinal tracts) do not appear to be essential.
Keywords: dorsal column; lateral column; Learning; plasticity; spinal cord injury

Corticospinal tract transection reduces H-reflex circadian rhythm in rats. - Xiang Yang Chen; Lu Chen; Jonathan Wolpaw; Jakeman, Lyn B. (Brain research, 2002)
In freely moving rats and monkeys, H-reflex amplitude displays a marked circadian variation without change in background motoneuron tone. In rats, the H-reflex is largest around noon and smallest around midnight. The present study evaluated in rats the effects on this rhythm of calibrated contusions of mid-thoracic spinal cord and mid-thoracic transection of specific spinal cord pathways. In 33 control rats, rhythm amplitude averaged 29.0(+/-2.6 S.E.)% of H-reflex amplitude. Contusion injuries at T8-9 that destroyed 53-88% of the white matter significantly reduced the rhythm to 18.9(+/-2.4)% of H-reflex amplitude. Transection of the ipsilateral lateral column, which contains the rubrospinal, vestibulospinal, and reticulospinal tracts, or bilateral transection of the dorsal column ascending tract did not affect rhythm amplitude or phase. In contrast, bilateral transection of the main corticospinal tract significantly reduced the rhythm to 14.7(+/-6.6)%. These results indicate that the H-reflex circadian rhythm depends in part on descending influence from the brain and that this influence is conveyed by the main corticospinal tract.
Keywords: circadian rhythms; corticospinal tract; diurnal rhythm; H-Reflex; rat; spinal cord injury

Corticospinal transmission to motoneurons in cervical spinal cord slices from adult rats. - Hori, N.; Jonathan S. Carp; Carpenter, D. O.; Akaike, N. (Life sciences, 2002)
Cervical spinal cord slices were prepared from adult rats. Intracellular recordings from motoneurons revealed that electrical stimulation of the ventralmost part of the dorsal funiculus (which contains primarily descending corticospinal axons) elicited EPSPs in 75% of the neurons. The latencies of these EPSPs tended to be shorter than those elicited by dorsal horn gray matter stimulation. Pairs of subthreshold dorsal funiculus stimuli were able to elicit action potentials in motoneurons. These data are consistent with previous morphological and electrophysiological studies indicating that cervical motoneurons receive both mono-and polysynaptic corticospinal inputs. In addition, motoneurons were markedly depolarized by iontophoretic application of AMPA or KA (7 out of 7 neurons), but only weakly depolarized by NMDA (1 out of 6 neurons). CNQX (but not AP-5) blocked EPSPs elicited by dorsal funiculus stimulation. Thus, corticospinal transmission to motoneurons is mediated primarily by non-NMDA glutamate receptors.
Keywords: adult rat; cervical spinal cord; motoneuron; slice

Factor analysis in CAPD and the "unimodal" test battery: do we have a model that will satisfy?. - Dennis J. McFarland; Anthony T. Cacace (American journal of audiology, 2002)
Keywords: Reproducibility of Results

General-Purpose Brain-Computer Interfaces (BCI) System - Gerwin Schalk (2002)
33rd Neural Prosthesis Workshop, National Library of Medicine / NIH, Bethesda, Maryland

Memory in neuroscience: rhetoric versus reality. - Jonathan Wolpaw (Behavioral and cognitive neuroscience reviews, 2002)
The central point of this article is that the concept of memory as information storage in the brain is inadequate for and irrelevant to understanding the nervous system. Beginning from the sensorimotor hypothesis that underlies neuroscience–that the entire function of the nervous system is to connect experience to appropriate behavior–the paper defines memories as sequences of events that connect remote experience to present behavior. Their essential components are (a) persistent events that bridge the time from remote experience to present behavior and (b) junctional events in which connections from remote experience and recent experience merge to produce behavior. The sequences comprising even the simplest memories are complex. This is both necessary–to preserve previously learned behaviors–and inevitable–due to secondary activity-driven plasticity. This complexity further highlights the inadequacy of the information storage concept and the importance of extreme simplicity in models used to study memory.
Keywords: Psychological Theory

Probable corticospinal tract control of spinal cord plasticity in the rat. - Xiang Yang Chen; Jonathan Wolpaw (Journal of neurophysiology, 2002)
Descending activity from the brain shapes spinal cord reflex function throughout life, yet the mechanisms responsible for this spinal cord plasticity are poorly understood. Operant conditioning of the H-reflex, the electrical analogue of the spinal stretch reflex, is a simple model for investigating these mechanisms. An earlier study in the Sprague-Dawley rat showed that acquisition of an operantly conditioned decrease in the soleus H-reflex is not prevented by mid-thoracic transection of the ipsilateral lateral column (LC), which contains the rubrospinal, reticulospinal, and vestibulospinal tracts, and is prevented by transection of the dorsal column, which contains the main corticospinal tract (CST) and the dorsal column ascending tract (DA). The present study explored the effects of CST or DA transection on acquisition of an H-reflex decrease, and the effects of LC, CST, or DA transection on maintenance of an established decrease. CST transection prior to conditioning prevented acquisition of H-reflex decrease, while DA transection did not do so. CST transection after H-reflex decrease had been acquired led to gradual loss of the decrease over 10 days, and resulted in an H-reflex that was significantly larger than the original, naive H-reflex. In contrast, LC or DA transection after H-reflex decrease had been acquired did not affect maintenance of the decrease. These results, in combination with the earlier study, strongly imply that in the rat the corticospinal tract (CST) is essential for acquisition and maintenance of operantly conditioned decrease in the H-reflex and that other major spinal cord pathways are not essential. This previously unrecognized aspect of CST function gives insight into the processes underlying acquisition and maintenance of motor skills and could lead to novel methods for inducing, guiding, and assessing recovery of function after spinal cord injury.
Keywords: Spinal Cord Injuries

A scripting language approach to control software for cryo-electron microscopy. - Baxter, Bill; Leith, ArDean; Frank, Joachim (Proc IEEE Int. Symp. Biomed. Imag., 2002)
Cryo-electron microscopy (Cryo-EM) of single particles has developed into a widely used technique for determining the 3-dimensional structure of large molecules and molecular assemblies. The low signal-to-noise ratio of cryo-EM requires thousands of images of single molecules to be averaged together. The field has matured to the point where realization of high-resolution structures is limited primarily by computational constraints. These constraints are at the algorithmic level, as well as the control level, where dozens of complex procedures and thousands of mathematical operations are applied to the raw data. SPIDER is a highly modular and flexible software package for single particle reconstruction. A typical reconstruction project involves dozens of procedure files, which in turn draw on hundreds of available low-level operations. In the present system, it is virtually impossible to rerun the system from selected branching points in the process flow to determine the effects of various parameters values. A Reconstruction Engine (RE) is being developed as a high-level "shell" for controlling processes in the SPIDER software system. The RE allows backtracking, optimization of parameters, and automation of processing flow. The RE is implemented in a scripting language, Python, which provides an overall management capability at the global level of the project.

Temporal transformation of multiunit activity improves identification of single motor units. - Gerwin Schalk; Jonathan S. Carp; Jonathan Wolpaw (J Neurosci Methods, 2002)
This report describes a temporally based method for identifying repetitive firing of motor units. This approach is ideally suited to spike trains with negative serially correlated inter-spike intervals (ISIs). It can also be applied to spike trains in which ISIs exhibit little serial correlation if their coefficient of variation (COV) is sufficiently low. Using a novel application of the Hough transform, this method (i.e. the modified Hough transform (MHT)) maps motor unit action potential (MUAP) firing times into a feature space with ISI and offset (defined as the latency from an arbitrary starting time to the first MUAP in the train) as dimensions. Each MUAP firing time corresponds to a pattern in the feature space that represents all possible MUAP trains with a firing at that time. Trains with stable ISIs produce clusters in the feature space, whereas randomly firing trains do not. The MHT provides a direct estimate of mean firing rate and its variability for the entire data segment, even if several individual MUAPs are obscured by firings from other motor units. Addition of this method to a shape-based classification approach markedly improved rejection of false positives using simulated data and identified spike trains in whole muscle electromyographic recordings from rats. The relative independence of the MHT from the need to correctly classify individual firings permits a global description of stable repetitive firing behavior that is complementary to shape-based approaches to MUAP classification.
Keywords: Action Potentials; Animals; Electromyography; H-Reflex; Motor Neurons; Muscle, Skeletal; Rats; Signal Processing, Computer-Assisted

Activity-dependent spinal cord plasticity in health and disease. - Jonathan Wolpaw; Tennissen, A. M. (Annual review of neuroscience, 2001)
Activity-dependent plasticity occurs in the spinal cord throughout life. Driven by input from the periphery and the brain, this plasticity plays an important role in the acquisition and maintenance of motor skills and in the effects of spinal cord injury and other central nervous system disorders. The responses of the isolated spinal cord to sensory input display sensitization, long-term potentiation, and related phenomena that contribute to chronic pain syndromes; they can also be modified by both classical and operant conditioning protocols. In animals with transected spinal cords and in humans with spinal cord injuries, treadmill training gradually modifies the spinal cord so as to improve performance. These adaptations by the isolated spinal cord are specific to the training regimen and underlie new approaches to restoring function after spinal cord injury. Descending inputs from the brain that occur during normal development, as a result of supraspinal trauma, and during skill acquisition change the spinal cord. The early development of adult spinal cord reflex patterns is driven by descending activity; disorders that disrupt descending activity later in life gradually change spinal cord reflexes. Athletic training, such as that undertaken by ballet dancers, is associated with gradual alterations in spinal reflexes that appear to contribute to skill acquisition. Operant conditioning protocols in animals and humans can produce comparable reflex changes and are associated with functional and structural plasticity in the spinal cord, including changes in motoneuron firing threshold and axonal conduction velocity, and in synaptic terminals on motoneurons. The corticospinal tract has a key role in producing this plasticity. Behavioral changes produced by practice or injury reflect the combination of plasticity at multiple spinal cord and supraspinal sites. Plasticity at multiple sites is both necessary-to insure continued performance of previously acquired behaviors-and inevitable-due to the ubiquity of the capacity for activity-dependent plasticity in the central nervous system. Appropriate induction and guidance of activity-dependent plasticity in the spinal cord is an essential component of new therapeutic approaches aimed at maximizing function after spinal cord injury or restoring function to a newly regenerated spinal cord. Because plasticity in the spinal cord contributes to skill acquisition and because the spinal cord is relatively simple and accessible, this plasticity is a logical and practical starting point for studying the acquisition and maintenance of skilled behaviors.
Keywords: behavior; conditioning; Learning; Memory; Rehabilitation; spinal cord injury

Brain-computer communication: unlocking the locked in. - Kübler, A.; Kotchoubey, B.; Kaiser, J.; Jonathan Wolpaw; Niels Birbaumer (Psychological bulletin, 2001)
With the increasing efficiency of life-support systems and better intensive care, more patients survive severe injuries of the brain and spinal cord. Many of these patients experience locked-in syndrome: The active mind is locked in a paralyzed body. Consequently, communication is extremely restricted or impossible. A muscle-independent communication channel overcomes this problem and is realized through a brain-computer interface, a direct connection between brain and computer. The number of technically elaborated brain-computer interfaces is in contrast with the number of systems used in the daily life of locked-in patients. It is hypothesized that a profound knowledge and consideration of psychological principles are necessary to make brain-computer interfaces feasible for locked-in patients.
Keywords: User-Computer Interface

Brain-Computer Interfaces for Communication and Control - Gerwin Schalk (2001)
NIPS*2001 Brain-Computer Interface Workshop, Whistler, British Columbia, Canda

Effects of chronic nerve cuff and intramuscular electrodes on rat triceps surae motor units. - Jonathan S. Carp; Xiang Yang Chen; Sheikh, H.; Jonathan Wolpaw (Neuroscience letters, 2001)
In order to assess the long-term effects of implanted electrodes on motor unit properties, we studied triceps surae (TS) motor units in rats implanted for 3-10 months with a tibial nerve cuff electrode for H-reflex elicitation and intramuscular electrodes for recording TS electromyographic activity. Motor units with sag from implanted rats displayed greater tetanic force than those from unimplanted rats. Motor units without sag had shorter twitch contraction times. This disrupted the relationship between sag and contraction time that was always present in unimplanted rats. These differences were consistent with a small degree of muscle denervation and subsequent reinnervation. Further analyses ascribed this effect to the nerve cuff rather than to the intramuscular electrodes. Comparable changes in motor unit properties may occur in humans with implanted nerve cuffs.
Keywords: chronic recording; contraction time; H-Reflex; implanted electrodes; motor units; nerve cuff; reinnervation; sag

Improved Motor Unit Detection Using the Hough Transform - Gerwin Schalk; Jonathan Carp (2001)
Neuro-Muscular Research Center, Boston University

Motor unit properties after operant conditioning of rat H-reflex. - Jonathan S. Carp; Xiang Yang Chen; Sheikh, H.; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2001)
Operant conditioning of the H-reflex produces plasticity at several sites in the spinal cord, including the motoneuron. This study assessed whether this spinal cord plasticity is accompanied by changes in motor unit contractile properties. Thirty-one adult male Sprague-Dawley rats implanted for chronic recording of triceps surae electromyographic activity and H-reflex elicitation were exposed for at least 40 days to HRup or HRdown training, in which reward occurred when the H-reflex was greater than (12 HRup rats) or less than (12 HRdown rats) a criterion value, or continued under the control mode in which the H-reflex was simply measured (7 HRcon rats). At the end of H-reflex data collection, rats were anesthetized and the contractile properties of 797 single triceps surae motor units activated by intraaxonal (or intramyelin) current injection were determined. Motor units were classified as S, FR, Fint, or FF on the basis of sag and fatigue properties. Maximum tetanic force and twitch contraction time were also measured. HRdown rats exhibited a significant increase in the fatigue index of fast-twitch motor units. This resulted in a significant decrease in the percentage of Fint motor units and a significant increase in that of FR motor units. HRup conditioning had no effect on fatigue index. Neither HRup nor HRdown conditioning affected maximum tetanic force or twitch contraction time. These data are consistent with the hypothesis that conditioning mode-specific change in motoneuron firing patterns causes activity-dependent change in muscle properties.
Keywords: H-Reflex; motor unit type; operant conditioning; plasticity; triceps surae

Operant conditioning of rat H-reflex affects motoneuron axonal conduction velocity. - Jonathan S. Carp; Xiang Yang Chen; Sheikh, H.; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2001)
This study assessed the effects of operant conditioning of the H-reflex on motoneuron axonal conduction velocity in the rat. After measurement of the control H-reflex size, rats were either exposed for at least 40 days to the HRup or HRdown conditioning mode, in which reward occurred only if the soleus H-reflex was greater than (HRup mode) or less than (HRdown mode) a criterion or continued under the control condition (HRcon mode) in which the H-reflex was simply measured. We then measured axonal conduction velocity of triceps surae motor units of HRup, HRdown, and HRcon rats by stimulating the axon in the ventral root and recording from the tibial nerve. Conduction velocity was 8% less in successful HRdown rats than in HRcon rats (P=0.02). Conduction velocity in HRup rats and unsuccessful HRdown rats was not significantly different from that in HRcon rats. Since recording bypassed the intra-spinal portion of the motoneuron, the change was clearly in the axon. This decrease was similar to the 6% decrease previously found in successful HRdown monkeys. Unsuccessful HRdown rats and monkeys did not show this decrease. This result suggests that the mechanism of HRdown conditioning is similar in rats and monkeys and provides further support for the hypothesis that HRdown conditioning decreases motoneuron excitability by producing a positive shift in firing threshold. While traditional theories of learning emphasize synaptic plasticity, neuronal plasticity may also contribute to operantly conditioned behavioral changes.
Keywords: conduction velocity; H-Reflex; motoneuron; plasticity; Spinal Cord

Operant conditioning of rat H-reflex: effects on mean latency and duration. - Jonathan Wolpaw; Xiang Yang Chen (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2001)
We are currently studying the mechanisms of operantly conditioned changes in the H-reflex in the rat. Primate data suggest that H-reflex decrease is due to a positive shift in motoneuron firing threshold and a small decrease in the monosynaptic excitatory postsynaptic potential (EPSP), and that increase might be due to change in group-I oligosynaptic (especially disynaptic) input. To further evaluate the possibility of conditioned change in oligosynaptic input, we compared the mean latency (i.e., the average latency of the entire H-reflex) and the duration of control (i.e., pre-conditioning) H-reflexes with those of H-reflexes after up-conditioning or down-conditioning. Up-conditioning was associated with small, statistically significant increases in H-reflex mean latency [+0.11+/-0.05 (+/-SE) ms] and duration (+0.32+/-0.16 ms). The mean latency of the H-reflex increase (i.e., the part added to the H-reflex by up-conditioning) was 0.28+/-0.14 (+/-SE) ms greater than that of the control H-reflex. Down-conditioning had no significant effect on mean latency or duration. While these results indicate that operant conditioning does not greatly change H-reflex mean latency or duration, the effects detected with up-conditioning are consistent with the hypothesis that decreased inhibition, or increased excitation, by homonymous and heteronymous group-I oligosynaptic input contributes to the H-reflex increase produced by up-conditioning. Several other mechanisms might also account for these small effects.
Keywords: conditioning; H-Reflex; Memory; plasticity; Spinal Cord

Short-Term and medium-term effects of spinal cord tract transections on soleus H-reflex in freely moving rats. - Xiang Yang Chen; Feng-Chen, K. C.; Lu Chen; Stark, D. M.; Jonathan Wolpaw (Journal of neurotrauma, 2001)
Spinal cord function is normally influenced by descending activity from supraspinal structures. When injury removes or distorts this influence, function changes and spasticity and other disabling problems eventually appear. Understanding how descending activity affects spinal cord function could lead to new means for inducing, guiding, and assessing recovery after injury. In this study, we investigated the short-term and medium-term effects of spinal cord bilateral dorsal column (DC), unilateral (ipsilateral) lateral column (LC), bilateral dorsal column ascending tract (DA), or bilateral dorsal column corticospinal tract (CST) transection at vertebral level T8-T9 on the soleus H-reflex in freely moving rats. Data were collected continuously for 10-20 days before and for 20-155 days after bilateral DC (13 rats), DA (10 rats), CST (eight rats), or ipsilateral LC (seven rats) transection. Histological examination showed that transections were 98(+/- 3 SD)% complete for DC rats, 80(+/- 20)% complete for LC rats, 91(+/- 13 SD)% complete for DA rats, and 95(+/-13)% complete for CST rats. LC, CST, and DA transections produced an immediate (i.e., first-day) increase in H-reflex amplitude. LC transection also produced a small decrease in background activity in the first few posttransection days. Other than this small decrease, none of the transections produced evidence for the phenomenon of spinal shock. For all transections, all measures returned to or neared pretransection values within 2 weeks. DA and LC transections were associated with modest increase in H-reflex amplitude 1-3 months after transection. These medium-term effects must be taken into account when assessing transection effects on operant conditioning of the H-reflex. At the same time, the results are consistent with other evidence that, while H-reflex rate dependence and H-reflex operant conditioning are sensitive measures of spinal cord injury, the H-reflex itself is not.
Keywords: corticospinal tract; dorsal column; dorsal column ascending tract; lateral column; rat; soleus activity; spinal cord injury

Taking sides: corticospinal tract plasticity during development. - Jonathan Wolpaw; Kaas, J. H. (Neurology, 2001)
Keywords: Pyramidal Tracts

Time course of H-reflex conditioning in the rat. - Xiang Yang Chen; Lu Chen; Jonathan Wolpaw (Neuroscience letters, 2001)
This study sought to define the course of operantly conditioned change in the rat soleus H-reflex and to determine whether, like H-reflex conditioning and spinal stretch reflex conditioning in the monkey, it develops in distinct phases. Data from 33 rats in which the right soleus H-reflex was trained up (i.e. HRup mode) and 38 in which it was trained down (i.e. HRdown mode) were averaged to define the courses of H-reflex increase and decrease. In HRup rats, the H-reflex showed a large phase I increase within the first 2 days followed by gradual phase II increase that continued for weeks. In HRdown rats, the H-reflex appeared to show a small phase I decrease and then showed a gradual phase II decrease over weeks. In combination with other recent work, the data suggest that H-reflex conditioning begins with a rapid mode-appropriate alteration in corticospinal tract influence over the spinal arc of the H-reflex, which causes phase I change, and that the continuation of this altered influence induces gradual spinal cord plasticity that is responsible for phase II change. The results further establish the similarity of H-reflex conditioning in primates and rats. Thus, they encourage efforts to produce a single coherent model of the phenomenon based on data from the two species and indicate the potential clinical relevance of the rat data.
Keywords: conditioning; Learning; Memory; plasticity; rat; Reflex; Spinal Cord

Transillumination and optical properties of cardiac tissue. - Baxter, Bill (Optical Mapping of Cardiac Excitation and Arrhythmias, 2001)

Video mapping of spiral waves in the heart. - Baxter, Bill; Davidenko, J M (Optical Mapping of Cardiac Excitation and Arrhythmias, 2001)

Visualizing excitation waves inside cardiac muscle using transillumination. - Baxter, Bill; Mironov, S F; Zaitsev, A V; Jalife, J; Pertsov, A V (Biophys J, 2001)
Voltage-sensitive fluorescent dyes have become powerful tools for the visualization of excitation propagation in the heart. However, until recently they were used exclusively for surface recordings. Here we demonstrate the possibility of visualizing the electrical activity from inside cardiac muscle via fluorescence measurements in the transillumination mode (in which the light source and photodetector are on opposite sides of the preparation). This mode enables the detection of light escaping from layers deep within the tissue. Experiments were conducted in perfused (8 mm thick) slabs of sheep right ventricular wall stained with the voltage-sensitive dye di-4-ANEPPS. Although the amplitude and signal-to-noise ratio recorded in the transillumination mode were significantly smaller than those recorded in the epi-illumination mode, they were sufficient to reliably determine the activation sequence. Penetration depths (spatial decay constants) derived from measurements of light attenuation in cardiac muscle were 0.8 mm for excitation (520 +/- 30 nm) and 1.3 mm for emission wavelengths (640 +/- 50 nm). Estimates of emitted fluorescence based on these attenuation values in 8-mm-thick tissue suggest that 90% of the transillumination signal originates from a 4-mm-thick layer near the illuminated surface. A 69% fraction of the recorded signal originates from > or =1 mm below the surface. Transillumination recordings may be combined with endocardial and epicardial surface recordings to obtain information about three-dimensional propagation in the thickness of the myocardial wall. We show an example in which transillumination reveals an intramural reentry, undetectable in surface recordings.
Keywords: Animals; Biophysical Phenomena; Biophysics; Electrophysiology; Endocardium; Fluorescent Dyes; Heart; Models, Cardiovascular; Myocardium; Optics and Photonics; Perfusion; Pericardium; Pyridinium Compounds; Sheep

BCI2000: A Generic Brain-Computer Interface - Gerwin Schalk (2000)
Department of Medical Informatics, Technical University of Graz

Brain-computer interface research at the Wadsworth Center. - Jonathan Wolpaw; Dennis J. McFarland; Theresa M Vaughan (IEEE transactions on rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2000)
Studies at the Wadsworth Center over the past 14 years have shown that people with or without motor disabilities can learn to control the amplitude of mu or beta rhythms in electroencephalographic (EEG) activity recorded from the scalp over sensorimotor cortex and can use that control to move a cursor on a computer screen in one or two dimensions. This EEG-based brain-computer interface (BCI) could provide a new augmentative communication technology for those who are totally paralyzed or have other severe motor impairments. Present research focuses on improving the speed and accuracy of BCI communication.
Keywords: User-Computer Interface

Brain-computer interface technology: a review of the first international meeting. - Jonathan Wolpaw; Niels Birbaumer; Heetderks, W. J.; Dennis J. McFarland; Peckham, P. H.; Gerwin Schalk; Emanuel Donchin; Quatrano, L. A.; Robinson, C. J.; Theresa M Vaughan (IEEE transactions on rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2000)
Over the past decade, many laboratories have begun to explore brain-computer interface (BCI) technology as a radically new communication option for those with neuromuscular impairments that prevent them from using conventional augmentative communication methods. BCI's provide these users with communication channels that do not depend on peripheral nerves and muscles. This article summarizes the first international meeting devoted to BCI research and development. Current BCI's use electroencephalographic (EEG) activity recorded at the scalp or single-unit activity recorded from within cortex to control cursor movement, select letters or icons, or operate a neuroprosthesis. The central element in each BCI is a translation algorithm that converts electrophysiological input from the user into output that controls external devices. BCI operation depends on effective interaction between two adaptive controllers, the user who encodes his or her commands in the electrophysiological input provided to the BCI, and the BCI which recognizes the commands contained in the input and expresses them in device control. Current BCI's have maximum information transfer rates of 5-25 b/min. Achievement of greater speed and accuracy depends on improvements in signal processing, translation algorithms, and user training. These improvements depend on increased interdisciplinary cooperation between neuroscientists, engineers, computer programmers, psychologists, and rehabilitation specialists, and on adoption and widespread application of objective methods for evaluating alternative methods. The practical use of BCI technology depends on the development of appropriate applications, identification of appropriate user groups, and careful attention to the needs and desires of individual users. BCI research and development will also benefit from greater emphasis on peer-reviewed publications, and from adoption of standard venues for presentations and discussion.
Keywords: augmentative communication; Brain-computer interface (BCI); electroencephalography (EEG)

Brain-computer interface technology: a review of the first international meeting. - Jonathan Wolpaw; Niels Birbaumer; Heetderks, W J; Dennis J. McFarland; Peckham, P H; Gerwin Schalk; Emanuel Donchin; Quatrano, L A; Robinson, C J; Theresa M Vaughan (IEEE Trans Rehabil Eng, 2000)
Over the past decade, many laboratories have begun to explore brain-computer interface (BCI) technology as a radically new communication option for those with neuromuscular impairments that prevent them from using conventional augmentative communication methods. BCI's provide these users with communication channels that do not depend on peripheral nerves and muscles. This article summarizes the first international meeting devoted to BCI research and development. Current BCI's use electroencephalographic (EEG) activity recorded at the scalp or single-unit activity recorded from within cortex to control cursor movement, select letters or icons, or operate a neuroprosthesis. The central element in each BCI is a translation algorithm that converts electrophysiological input from the user into output that controls external devices. BCI operation depends on effective interaction between two adaptive controllers, the user who encodes his or her commands in the electrophysiological input provided to the BCI, and the BCI which recognizes the commands contained in the input and expresses them in device control. Current BCI's have maximum information transfer rates of 5-25 b/min. Achievement of greater speed and accuracy depends on improvements in signal processing, translation algorithms, and user training. These improvements depend on increased interdisciplinary cooperation between neuroscientists, engineers, computer programmers, psychologists, and rehabilitation specialists, and on adoption and widespread application of objective methods for evaluating alternative methods. The practical use of BCI technology depends on the development of appropriate applications, identification of appropriate user groups, and careful attention to the needs and desires of individual users. BCI research and development will also benefit from greater emphasis on peer-reviewed publications, and from adoption of standard venues for presentations and discussion.
Keywords: Algorithms; Cerebral Cortex; Communication Aids for Disabled; Disabled Persons; Electroencephalography; Evoked Potentials; Humans; Neuromuscular Diseases; Signal Processing, Computer-Assisted; User-Computer Interface

EEG-based communication: presence of an error potential. - Gerwin Schalk; Jonathan Wolpaw; Dennis J. McFarland; Pfurtscheller, G. (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2000)
EEG-based communication could be a valuable new augmentative communication technology for those with severe motor disabilities. Like all communication methods, it faces the problem of errors in transmission. In the Wadsworth EEG-based brain-computer interface (BCI) system, subjects learn to use mu or beta rhythm amplitude to move a cursor to targets on a computer screen. While cursor movement is highly accurate in trained subjects, it is not perfect.
Keywords: augmentative communication; brain-computer interface; Electroencephalography; error potential; error related negativity; event related potential; mu rhythm; Rehabilitation; sensorimotor cortex

Emerging concepts in the pathophysiology of recovery from neonatal brachial plexus injury. - Noetzel, M. J.; Jonathan Wolpaw (Neurology, 2000)
Keywords: Infant; Newborn

Mu and beta rhythm topographies during motor imagery and actual movements. - Dennis J. McFarland; Miner, L. A.; Theresa M Vaughan; Jonathan Wolpaw (Brain topography, 2000)
People can learn to control the 8-12 Hz mu rhythm and/or the 18-25 Hz beta rhythm in the EEG recorded over sensorimotor cortex and use it to control a cursor on a video screen. Subjects often report using motor imagery to control cursor movement, particularly early in training. We compared in untrained subjects the EEG topographies associated with actual hand movement to those associated with imagined hand movement. Sixty-four EEG channels were recorded while each of 33 adults moved left- or right-hand or imagined doing so. Frequency-specific differences between movement or imagery and rest, and between right- and left-hand movement or imagery, were evaluated by scalp topographies of voltage and r spectra, and principal component analysis. Both movement and imagery were associated with mu and beta rhythm desynchronization. The mu topographies showed bilateral foci of desynchronization over sensorimotor cortices, while the beta topographies showed peak desynchronization over the vertex. Both mu and beta rhythm left/right differences showed bilateral central foci that were stronger on the right side. The independence of mu and beta rhythms was demonstrated by differences for movement and imagery for the subjects as a group and by principal components analysis. The results indicated that the effects of imagery were not simply an attenuated version of the effects of movement. They supply evidence that motor imagery could play an important role in EEG-based communication, and suggest that mu and beta rhythms might provide independent control signals.
Keywords: beta rhythm; EEG; imagery; mu rhythm; sensorimotor cortex

What do reflex and voluntary mean? Modern views on an ancient debate. - Prochazka, A.; Clarac, F.; Loeb, G. E.; Rothwell, J. C.; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2000)
Are the words reflex and voluntary useful scientific concepts, or are they prescientific terms that should be discarded? Physiologists use these words routinely in their publications, in laboratory experiments and, indeed, like most lay people, in their daily lives. The tacit assumption is that we all know, more or less, what they mean. However, the issue has a rich history of philosophical and scientific debate; and, as this article demonstrates, present-day researchers still cannot reach a consensus on the meaning of the words and on whether it is possible to draw a scientific distinction between them. The five authors present five quite different analyses. In broad terms, they split into two camps: those who equate voluntary behaviours with consciousness and suppressibility and those who view all behaviours as sensorimotor interactions, the complexity of which determines whether they are reflexive or voluntary. According to the first view, most movements of daily life are neither purely reflex nor purely voluntary. They fall into the middle ground of automatic motor programs. According to the second view, as neuroscience advances the class of reflex behaviours will grow and the class of voluntary behaviours will shrink.
Keywords: Consciousness; Reflex; voluntary

Intramural optical recordings of cardiac electrical activity via transillumination - Baxter, Bill (1999)
PhD Dissertation, October 1999

Operant conditioning of H-reflex increase in spinal cord–injured rats. - Xiang Yang Chen; Jonathan Wolpaw; Jakeman, L. B.; Stokes, B. T. (Journal of neurotrauma, 1999)
Operant conditioning of the spinal stretch reflex or its electrical analog, the H-reflex, is a new model for exploring the mechanisms of long-term supraspinal control over spinal cord function. Primates and rats can gradually increase (HRup conditioning mode) or decrease (HRdown conditioning mode) the H-reflex when reward is based on H-reflex amplitude. An earlier study indicated that HRdown conditioning of the soleus H-reflex in rats is impaired following contusion injury to thoracic spinal cord. The extent of impairment was correlated with the percent of white matter lost at the injury site. The present study investigated the effects of spinal cord injury on HRup conditioning. Soleus H-reflexes were elicited and recorded with chronically implanted electrodes from 14 rats that had been subjected to calibrated contusion injuries to the spinal cord at T8. At the lesion epicenter, 12-39% of the white matter remained. After control-mode data were collected, each rat was exposed to the HRup conditioning mode for 50 days. Final H-reflex amplitudes after HRup conditioning averaged 112% (+/-22% SD) of control. This value was significantly smaller than that for 13 normal rats exposed to HRup conditioning, in which final amplitude averaged 153% (+/-51%) SD of control. As previously reported for HRdown conditioning after spinal cord injury, success was inversely correlated with the severity of the injury as assessed by white matter preservation and by time to return of bladder function. HRup and HRdown conditioning are similarly sensitive to injury. These results further demonstrate that H-reflex conditioning is a sensitive measure of the long-term effects of injury on supraspinal control over spinal cord functions and could prove a valuable measure of therapeutic efficacy.
Keywords: H-Reflex; operant conditioning; plasticity; rat; soleus muscle; spinal cord injury

Sag during unfused tetanic contractions in rat triceps surae motor units. - Jonathan S. Carp; Herchenroder, P. A.; Xiang Yang Chen; Jonathan Wolpaw (Journal of neurophysiology, 1999)
Contractile properties and conduction velocity were studied in 202 single motor units of intact rat triceps surae muscles activated by intra-axonal (or intra-myelin) current injection in L5 or L6 ventral root to assess the factors that determine the expression of sag (i.e., decline in force after initial increase during unfused tetanic stimulation). Sag was consistently detected in motor units with unpotentiated twitch contraction times <20 ms. However, the range of frequencies at which sag was expressed varied among motor units such that there was no single interstimulus interval (ISI), with or without adjusting for twitch contraction time, at which sag could be detected reliably. Further analysis indicated that using the absence of sag as a criterion for identifying slow-twitch motor units requires testing with tetani at several different ISIs. In motor units with sag, the shape of the force profile varied with tetanic frequency and contractile properties. Simple sag force profiles (single maximum reached late in the tetanus followed by monotonic decay) tended to occur at shorter ISIs and were observed more frequently in fatigue-resistant motor units with long half-relaxation times and small twitch amplitudes. Complex sag profiles reached an initial maximum early in the tetanus, tended to occur at longer ISIs, and were more common in fatigue-sensitive motor units with long half-relaxation times and large twitch amplitudes. The differences in frequency dependence and force maximum location suggested that these phenomena represented discrete entities. Successive stimuli elicited near-linear increments in force during tetani in motor units that never exhibited sag. In motor units with at least one tetanus displaying sag, tetanic stimulation elicited large initial force increments followed by rapidly decreasing force increments. That the latter force envelope pattern occurred in these units even in tetani without sag suggested that the factors responsible for sag were expressed in the absence of overt sag. The time-to-peak force (TTP) of the individual contractions during a tetanus decreased in tetani with sag. Differences in the pattern of TTP change during a tetanus were consistent with the differences in force maximum location between tetani exhibiting simple and complex sag. Tetani from motor units that never exhibited sag did not display a net decrease in TTP during successive contractions. These data were consistent with the initial force decrement of sag resulting from a transient reduction in the duration of the contractile state.
Keywords: Regression Analysis

Answering questions with an electroencephalogram-based brain-computer interface. - Miner, L. A.; Dennis J. McFarland; Jonathan Wolpaw (Archives of physical medicine and rehabilitation, 1998)
OBJECTIVE: To demonstrate that humans can learn to control selected electroencephalographic components and use that control to answer simple questions. METHODS: Four adults (one with amyotrophic lateral sclerosis) learned to use electroencephalogram (EEG) mu rhythm (8 to 12Hz) or beta rhythm (18 to 25Hz) activity over sensorimotor cortex to control vertical cursor movement to targets at the top or bottom edge of a video screen. In subsequent sessions, the targets were replaced with the words YES and NO, and individuals used the cursor to answer spoken YES/NO questions from single- or multiple-topic question sets. They confirmed their answers through the response verification (RV) procedure, in which the word positions were switched and the question was answered again. RESULTS: For 5 consecutive sessions after initial question training, individuals were asked an average of 4.0 to 4.6 questions per minute; 64% to 87% of their answers were confirmed by the RV procedure and 93% to 99% of these answers were correct. Performances for single- and multiple-topic question sets did not differ significantly. CONCLUSIONS: The results indicate that (1) EEG-based cursor control can be used to answer simple questions with a high degree of accuracy, (2) attention to auditory queries and formulation of answers does not interfere with EEG-based cursor control, (3) question complexity (at least as represented by single versus multiple-topic question sets) does not noticeably affect performance, and (4) the RV procedure improves accuracy as expected. Several options for increasing the speed of communication appear promising. An EEG-based brain-computer interface could provide a new communication and control modality for people with severe motor disabilities.
Keywords: User-Computer Interface

EEG-based communication: analysis of concurrent EMG activity. - Theresa M Vaughan; Miner, L. A.; Dennis J. McFarland; Jonathan Wolpaw (Electroencephalography and clinical neurophysiology, 1998)
OBJECTIVE: Recent studies indicate that people can learn to control the amplitude of mu or beta rhythms in the EEG recorded from the scalp over sensorimotor cortex and can use that control to move a cursor to targets on the computer screen. While subjects do not move during performance, it is possible that inapparent or unconscious muscle contractions contribute to the changes in the mu and beta rhythm activity responsible for cursor movement. We evaluated this possibility. METHODS: EMG was recorded from 10 distal limb muscle groups while five trained subjects used mu or beta rhythms to move a cursor to targets at the bottom or top edge of a computer screen. RESULTS: EMG activity was very low during performance, averaging 4.0+/-4.4% (SD) of maximum voluntary contraction. Most important, the correlation, measured as r2, between target position and EMG activity averaged only 0.01+/-0.02, much lower than the correlation between target position and the EEG activity that controlled cursor movement, which averaged 0.39+/-0.18. CONCLUSIONS: These results strongly support the conclusion that EEG-based cursor control does no depend on concurrent muscle activity. EEG-based communication and control might provide a new augmentative communication option for those with severe motor disabilities.
Keywords: augmentative communication; conditioning; Electroencephalography; Electromyography; mu rhythm; Rehabilitation; sensorimotor cortex

EEG-based communication and control: short-term role of feedback. - Dennis J. McFarland; McCane, L. M.; Jonathan Wolpaw (IEEE transactions on rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 1998)
When people learn to control the amplitudes of certain electroencephalogram (EEG) components (e.g., the 8-12 Hz mu-rhythm over sensorimotor cortex) and use them to move a cursor to a target on a video screen, feedback about performance is normally provided by cursor movement and by trial outcome (i.e., success or failure). We assessed the short-term effects of this feedback on EEG control. After subjects received initial training with feedback present, feedback was removed intermittently for periods of several minutes. Subjects still displayed EEG control when feedback was removed. Removal of cursor movement alone appeared to have effects comparable to removal of both cursor movement and trial outcome. These results show that, in the short-term at least, mu-rhythm control is not dependent on the sensory input provided by cursor movement. They also suggest that feedback can have inhibitory as well as facilitory effects on EEG control, and that these effects vary across subjects. This finding has implications for the design of training procedures.
Keywords: Sensitivity and Specificity

EEG-based communication: improved accuracy by response verification. - Jonathan Wolpaw; Ramoser, H.; Dennis J. McFarland; Pfurtscheller, G. (IEEE transactions on rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 1998)
Humans can learn to control the amplitude of electroencephalographic (EEG) activity in specific frequency bands over sensorimotor cortex and use it to move a cursor to a target on a computer screen. EEG-based communication could provide a new augmentative communication channel for individuals with motor disabilities. In the present system, each dimension of cursor movement is controlled by a linear equation. While the intercept in the equation is continually updated, it does not perfectly eliminate the impact of spontaneous variations in EEG amplitude. This imperfection reduces the accuracy of cursor movement. We evaluated a response verification (RV) procedure in which each outcome is determined by two opposite trials (e.g., one top-target trial and one bottom-target trial). Success, or failure, on both is required for a definitive outcome. The RV procedure reduces errors due to imperfection in intercept selection. Accuracy for opposite-trial pairs exceeds that predicted from the accuracies of individual trials, and greatly exceeds that for same-trial pairs. The RV procedure should be particularly valuable when the first trial has >2 possible targets, because the second trial need only confirm or deny the outcome of the first, and it should be applicable to nonlinear as well as to linear algorithms.
Keywords: Computer-Assisted; Signal Processing

Quantification of effects of global ischemia on dynamics of ventricular fibrillation in isolated rabbit heart. - Mandapati, R; Asano, Y; Baxter, Bill; Gray, R A; Davidenko, J M; Jalife, J (Circulation, 1998)
BACKGROUND:  Ventricular fibrillation (VF) leads to global ischemia of the heart. After 1 to 2 minutes of onset, the VF rate decreases and appears more organized. The objectives of this study were to determine the effects of no-flow global ischemia on nonlinear wave dynamics and establish the mechanism of ischemia-induced slowing of the VF rate. METHODS AND RESULTS:  Activation patterns of VF in the Langendorff-perfused rabbit heart were studied with the use of 2 protocols: (1) 15 minutes of no-flow global ischemia followed by reperfusion (n=7) and (2) decreased excitability induced by perfusion with 5 micromol/L of tetrodotoxin (TTX) followed by washout (n=3). Video imaging ( approximately 7500 pixels per frame; 240 frames per second) with a voltage-sensitive dye, ECG, and signal processing (fast Fourier transform) were used for analysis. The dominant frequency of VF decreased from 13.5+/-1.3 during control to 9.3+/-1.4 Hz at 5 minutes of global ischemia (P<0.02). The dominant frequency decreased from 13.9+/-1.1 during control to 7.0+/-0.3 Hz at 2 minutes of TTX infusion (P<0.001). The rotation period of rotors on the epicardial surface (n=27) strongly correlated with the inverse dominant frequency of the corresponding episode of VF (R2=0. 93). The core area, measured for 27 transiently appearing rotors, was 5.3+/-0.7 mm2 during control. A remarkable increase in core area was observed both during global ischemia (13.6+/-1.7 mm2; P<0.001) and TTX perfusion (16.8+/-3.6 mm2; P<0.001). Density of wave fronts decreased during both global ischemia (P<0.002) and TTX perfusion (P<0.002) compared with control. CONCLUSIONS:  This study suggests that rotating spiral waves are most likely the underlying mechanism of VF and contribute to its frequency content. Ischemia-induced decrease in the VF rate results from an increase in the rotation period of spiral waves that occurs secondary to an increase in their core area. Remarkably, similar findings in the TTX protocol suggest that reduced excitability during ischemia is an important underlying mechanism for the changes seen.
Keywords: Animals; Electrocardiography; Linear Models; Myocardial Ischemia; Rabbits; Rotation; Sodium Channel Blockers; Tetrodotoxin; Ventricular Fibrillation; Video Recording

The complex structure of a simple memory. - Jonathan Wolpaw (Trends in neurosciences, 1997)
Operant conditioning of the vertebrate H-reflex, which appears to be closely related to learning that occurs in real life, is accompanied by plasticity at multiple sites. Change occurs in the firing threshold and conduction velocity of the motoneuron, in several different synaptic terminal populations on the motoneuron, and probably in interneurons as well. Change also occurs contralaterally. The corticospinal tract probably has an essential role in producing this plasticity. While certain of these changes, such as that in the firing threshold, are likely to contribute to the rewarded behavior (primary plasticity), others might preserve previously learned behaviors (compensatory plasticity), or are simply activity-driven products of change elsewhere (reactive plasticity). As these data and those from other simple vertebrate and invertebrate models indicate, a complex pattern of plasticity appears to be the necessary and inevitable outcome of even the simplest learning.
Keywords: H-Reflex; Learning; Memory; operant conditioning; plasticity; Spinal Cord; stretch reflex

Dorsal column but not lateral column transection prevents down-conditioning of H reflex in rats. - Xiang Yang Chen; Jonathan Wolpaw (Journal of neurophysiology, 1997)
Operant conditioning of the H reflex, the electrical analogue of the spinal stretch reflex, in freely moving rats is a relatively simple model for studying long-term supraspinal control over spinal cord function. Motivated by food reward, rats can gradually increase or decrease the soleus H reflex. This study is the first effort to determine which spinal cord pathways convey the descending influence from supraspinal structures that changes the H reflex. In anesthetized Sprague-Dawley rats, the entire dorsal column (DC), which includes the main corticospinal tract, or the right lateral column (LC) was transected by electrocautery. Animals recovered quickly and the minimal transient effects of transection on the right soleus H reflex disappeared within 16 days. Beginning at least 18 days after transection, 12 rats were exposed to the HRdown-conditioning mode, in which reward was given when the H reflex of the right soleus muscle was below a criterion value. In seven LC rats exposed to the HRdown mode, the H reflex fell to 71 +/- 8% (mean +/- SE) of its initial value. In six of the seven, conditioning was successful (i.e., decrease to < or = 80%). These results were comparable with those previously obtained from normal rats. In contrast, in five DC rats exposed to the HRdown mode, the H reflex at the end of exposure was 106 +/- 12% of its initial value. In none of these rats was HRdown-conditioning successful. DC rats differed significantly from normal and LC rats in both final H reflex values and number successful. In five DC and three LC rats that continued under control conditions over 30-78 days, the H reflex at the end of the period was 98 +/- 4% and 100 +/- 8%, respectively, of its initial value, indicating that DC or LC transection itself did not lead to gradual increase or decrease in the H reflex. The results indicate that the DC, containing the main corticospinal tract, is essential for HRdown-conditioning, whereas the ipsilateral LC, containing the main rubrospinal, vestibulospinal, and reticulospinal tracts, is not essential. Combined with the known muscular specificity of conditioning, these results suggest that the main corticospinal tract is essential for HRdown-conditioning. The DC ascending tract might also be necessary. The respective roles of the DC descending and ascending tracts, and transection effects on HRup-conditioning and on the maintenance of both HRup- and HRdown-conditioning after they have occurred, remain to be defined.
Keywords: Spinal Cord

EEG-based communication: evaluation of alternative signal prediction methods. - Ramoser, H.; Jonathan Wolpaw; Pfurtscheller, G. (Biomedizinische Technik. Biomedical engineering, 1997)
Individuals can learn to control the amplitude of EEG activity in specific frequency bands over sensorimotor cortex and use it to move a cursor to a target on a computer screen. For one-dimensional (i.e., vertical) cursor movement, a linear equation translates the EEG activity into cursor movement. To translate an individual's EEG control into cursor control as effectively as possible, the intercept in this equation, which determines whether upward or downward movement occurs, should be set so that top and bottom targets are equally accessible. The present study compares alternative methods for using an individual's previous performance to select the intercept for subsequent trials. In offline analyses, five different intercept selection methods were applied to EEG data collected while trained subjects were moving the cursor to targets at the top or bottom edge of the screen. In the first two methods-moving average, and weighted sum-a single intercept was selected for the entire 1-2 sec period of each trial. In the other three methods-blocked moving average, blocked weighted sum, and blocked recursive sum (a variation of the weighted sum)-an intercept was selected for each 200-ms segment of the trial. The results from these methods were compared in regard to their balance between upward and downward movements and their consistency of performance across trials. For all subjects combined, the five methods performed similarly. However, performance across subjects was more consistent for the moving average, blocked moving average, and blocked recursive sum methods than for the weighted sum and blocked weighted sum methods. Due to its consistent performance and its computational simplicity, the moving average method, using the five most recent pairs of top and bottom trials, appears to be the method of choice.
Keywords: Somatosensory Cortex

Optical mapping of drug-induced polymorphic arrhythmias and torsade de pointes in the isolated rabbit heart. - Asano, Y; Davidenko, J M; Baxter, Bill; Gray, R A; Jalife, J (J Am Coll Cardiol, 1997)
OBJECTIVES:  This study sought to 1) test the hypothesis that in the setting of bradycardia and drug-induced action potential prolongation, multiple foci of early afterdepolarizations (EADs) result in beat to beat changes in the origin and direction of the excitation wave front and are responsible for polymorphic arrhythmias; and 2) determine whether EADs may initiate nonstationary reentry, giving rise to the typical torsade de pointes (TDP) pattern. BACKGROUND:  In the past, it has been difficult to associate EADs or reentry with the undulating electrocardiographic (ECG) patterns of TDP. METHODS:  A voltage-sensitive dye was used for high resolution video imaging of electrical waves on the epicardial and endocardial surface of the Langendorff-perfused rabbit heart. ECG and monophasic action potentials from the right septal region were also recorded. Bradycardia was induced by ablation of the atrioventricular node. RESULTS:  Perfusion of low potassium chloride Tyrode solution plus quinidine led to prolongation of the action potential and the QT interval. Eventually, EADs and triggered activity ensued, giving rise to intermittent episodes of polymorphic arrhythmia. In one experiment, triggered activity was followed by a long episode of vortex-like reentry with an ECG pattern characteristic of TDP. However, in most experiments, focal activity of varying origins and propagation patterns was observed. Triggered responses also showed varying degrees of local block. Similar results were obtained with E-4031. Burst pacing both at control conditions and in the presence of quinidine consistently led to vortex-like reentry whose ECG pattern resembled TDP. However, the cycle length of the arrhythmia with quinidine was longer than that for control ([mean +/- SEM] 194 +/- 12 vs. 132 +/- 8 ms, p < 0.03). CONCLUSIONS:  Drug-induced polymorphic ventricular arrhythmias may result from beat to beat changes in wave propagation patterns initiated by EADs or EAD-induced nonstationary reentrant activity. In contrast, burst pacing-induced polymorphic tachycardia in the presence or absence of drugs is the result of nonstationary reentrant activity.
Keywords: Action Potentials; Animals; Anti-Arrhythmia Agents; Arrhythmias, Cardiac; Electrocardiography; Heart; Heart Conduction System; Image Processing, Computer-Assisted; Models, Cardiovascular; Organ Culture Techniques; Perfusion; Piperidines; Pyridines; Quinidine; Rabbits; Torsades de Pointes

Spatial filter selection for EEG-based communication. - Dennis J. McFarland; McCane, L. M.; David, S. V.; Jonathan Wolpaw (Electroencephalography and clinical neurophysiology, 1997)
Individuals can learn to control the amplitude of mu-rhythm activity in the EEG recorded over sensorimotor cortex and use it to move a cursor to a target on a video screen. The speed and accuracy of cursor movement depend on the consistency of the control signal and on the signal-to-noise ratio achieved by the spatial and temporal filtering methods that extract the activity prior to its translation into cursor movement. The present study compared alternative spatial filtering methods. Sixty-four channel EEG data collected while well-trained subjects were moving the cursor to targets at the top or bottom edge of a video screen were analyzed offline by four different spatial filters, namely a standard ear-reference, a common average reference (CAR), a small Laplacian (3 cm to set of surrounding electrodes) and a large Laplacian (6 cm to set of surrounding electrodes). The CAR and large Laplacian methods proved best able to distinguish between top and bottom targets. They were significantly superior to the ear-reference method. The difference in performance between the large Laplacian and small Laplacian methods presumably indicated that the former was better matched to the topographical extent of the EEG control signal. The results as a whole demonstrate the importance of proper spatial filter selection for maximizing the signal-to-noise ratio and thereby improving the speed and accuracy of EEG-based communication.
Keywords: assistive communication; Electroencephalography; mu rhythm; operant conditioning; prosthesis; Rehabilitation; sensorimotor cortex

Technical features of a CCD video camera system to record cardiac fluorescence data. - Baxter, Bill; Davidenko, J M; Loew, L M; Wuskell, J P; Jalife, J (Ann Biomed Eng, 1997)
A charge-coupled device (CCD) camera was used to acquire movies of transmembrane activity from thin slices of sheep ventricular epicardial muscle stained with a voltage-sensitive dye. Compared with photodiodes, CCDs have high spatial resolution, but low temporal resolution. Spatial resolution in our system ranged from 0.04 to 0.14 mm/pixel; the acquisition rate was 60, 120, or 240 frames/sec. Propagating waves were readily visualized after subtraction of a background image. The optical signal had an amplitude of 1 to 6 gray levels, with signal-to-noise ratios between 1.5 and 4.4. Because CCD cameras integrate light over the frame interval, moving objects, including propagating waves, are blurred in the resulting movies. A computer model of such an integrating imaging system was developed to study the effects of blur, noise, filtering, and quantization on the ability to measure conduction velocity and action potential duration (APD). The model indicated that blurring, filtering, and quantization do not affect the ability to localize wave fronts in the optical data (i.e., no systematic error in determining spatial position), but noise does increase the uncertainty of the measurements. The model also showed that the low frame rates of the CCD camera introduced a systematic error in the calculation of APD: for cutoff levels > 50%, the APD was erroneously long. Both noise and quantization increased the uncertainty in the APD measurements. The optical measures of conduction velocity were not significantly different from those measured simultaneously with microelectrodes. Optical APDs, however, were longer than the electrically recorded APDs. This APD error could be reduced by using the 50% cutoff level and the fastest frame rate possible.
Keywords: Action Potentials; Algorithms; Animals; Body Surface Potential Mapping; Calibration; Computer Simulation; Electric Conductivity; Fluorescent Dyes; Image Processing, Computer-Assisted; Models, Cardiovascular; Sheep; Ventricular Function; Video Recording

Timing of EEG-based cursor control. - Jonathan Wolpaw; Flotzinger, D.; Pfurtscheller, G.; Dennis J. McFarland (Journal of clinical neurophysiology : official publication of the American Electroencephalographic Society, 1997)
Recent studies show that humans can learn to control the amplitude of electroencephalography (EEG) activity in specific frequency bands over sensorimotor cortex and use it to move a cursor to a target on a computer screen. EEG-based communication could be a valuable new communication and control option for those with severe motor disabilities. Realization of this potential requires detailed knowledge of the characteristic features of EEG control. This study examined the course of EEG control after presentation of a target. At the beginning of each trial, a target appeared at the top or bottom edge of the subject's video screen and 1 sec later a cursor began to move vertically as a function of EEG amplitude in a specific frequency band. In well-trained subjects, this amplitude was high at the time the target appeared and then either remained high (i.e., for a top target) or fell rapidly (i.e., for a bottom target). Target-specific EEG amplitude control began 0.5 sec after the target appeared and appeared to wax and wane with a period of approximately 1 sec until the cursor reached the target (i.e., a hit) or the opposite edge of the screen (i.e., a miss). Accuracy was 90% or greater for each subject. Top-target errors usually occurred later in the trial because of failure to reach and/or maintain sufficiently high amplitude, whereas bottom-target errors usually occurred immediately because of failure to reduce an initially high amplitude quickly enough. The results suggest modifications that could improve performance. These include lengthening the intertrial period, shortening the delay between target appearance and cursor movement, and including time within the trial as a variable in the equation that translates EEG into cursor movement.
Keywords: assistive communication; Electroencephalography; mu rhythm; operant conditioning; prosthesis; Rehabilitation; sensorimotor cortex

Video imaging of re-entry on the epicardial surface of the isolated rabbit heart. - Baxter, Bill; Gray, R A; Cabo, C; Davidenko, J M; Pertsov, A V; Jalife, J (Computational Biology of the Heart, 1997)

EEG-based communication: prospects and problems. - Theresa M Vaughan; Jonathan Wolpaw; Emanuel Donchin (IEEE transactions on rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 1996)
Current rehabilitation engineering combines new prosthetic methods with recent developments in personal computers to provide alternative communication and control channels to individuals with motor impairments. Despite these advances, all commercially available systems still require some measure of voluntary motor control. Thus, these systems are not useful for individuals who are totally paralyzed. Electroencephalographic (EEG) activity may provide the basis for a system that would completely bypass normal motor output. EEG-based communication technology might provide assistive devices for individuals who have little or no reliable motor function. This paper reviews the prospects for and problems of EEG-based communication. It summarizes current approaches to development of this new technology, describes the major problems that must be resolved, and focuses on issues critical for its use by those with severe motor disabilities.
Keywords: Visual Perception

Operant conditioning of H-reflex changes synaptic terminals on primate motoneurons. - Feng-Chen, K. C.; Jonathan Wolpaw (Proceedings of the National Academy of Sciences of the United States of America, 1996)
Operant conditioning of the primate triceps surae H-reflex, the electrical analog of the spinal stretch reflex, creates a memory trace that includes changes in the spinal cord. To define the morphological correlates of this plasticity, we analyzed the synaptic terminal coverage of triceps surae motoneurons from animals in which the triceps surae H-reflex in one leg had been increased (HRup mode) or decreased (HRdown mode) by conditioning and compared them to each other and to motoneurons from unconditioned animals. Motoneurons were labeled by intramuscular injection of cholera toxin-horseradish peroxidase. A total of 5055 terminals on the cell bodies and proximal dendrites of 114 motoneurons from 14 animals were studied by electron microscopy. Significant differences were found between HRup and HRdown animals and between HRup and naive (i.e., unconditioned) animals. F terminals (i.e., putative inhibitory terminals) were smaller and their active zone coverage on the cell body was lower on motoneurons from the conditioned side of HRup animals than on motoneurons from the conditioned side of HRdown animals. C terminals (i.e., terminals associated with postsynaptic cisterns and rough endoplasmic reticulum) were smaller and the number of C terminals in each C complex (i.e., a group of contiguous C terminals) was larger on motoneurons from the conditioned side of HRup animals than on motoneurons either from the conditioned side of HRdown animals or from naive animals. Because the treatment of HRup and HRdown animals differed only in the reward contingency, the results imply that the two contingencies had different effects on motoneuron synaptic terminals. In combination with other recent data, they show that H-reflex conditioning produces a complex pattern of spinal cord plasticity that includes changes in motoneuron physiological properties as well as in synaptic terminals. Further delineation of this pattern should reveal the contribution of the structural changes described here to the learned change in behavior.
Keywords: Synapses

Operant conditioning of H-reflex in spinal cord-injured rats. - Xiang Yang Chen; Jonathan Wolpaw; Jakeman, L. B.; Stokes, B. T. (Journal of neurotrauma, 1996)
Operant conditioning of the spinal stretch reflex or its electrical analog, the H-reflex, is a new model for exploring the mechanisms of supraspinal control over spinal cord function. Both rats and primates can gradually increase (HRup conditioning mode) or decrease (HRdown conditioning mode) soleus H-reflex magnitude when exposed to an operant conditioning task. This study used H-reflex operant conditioning to assess and modify spinal cord function after injury. Soleus H-reflexes were elicited and recorded with chronically implanted electrodes from rats that had been subjected to calibrated contusion injuries to the spinal cord at T8. From 18 to 140 days after injury, background EMG, M response amplitude, and initial H-reflex amplitude were not significantly different from those of normal rats. HRdown conditioning was successful in some, but not all, spinal cord-injured rats. The H-reflex decrease achieved by conditioning was inversely correlated with the severity of the injury as assessed histologically or by time to return of bladder function. It was not correlated with the length of time between injury and the beginning of conditioning. The results confirm the importance of descending control from supraspinal structures in mediating operantly conditioned change in H-reflex amplitude. In conjunction with recent human studies, they suggest that H-reflex conditioning could provide a sensitive new means for assessing spinal cord function after injury, and might also provide a method for initiating and guiding functional rehabilitation.
Keywords: H-Reflex; operant conditioning; plasticity; rat; soleus muscle; spinal cord injury

Reversal of H-reflex operant conditioning in the rat. - Xiang Yang Chen; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 1996)
In response to an operant conditioning task, rats can gradually increase or decrease soleus H-reflex amplitude without change in background electromyographic activity or M response amplitude. Both increase (under the HRup mode) and decrease (under the HRdown mode) develop over weeks. The present study investigated reversal of conditioned H-reflex change. Following collection of control data, rats were exposed to one mode (HRup or HRdown) for 50 days, and then exposed to the opposite mode for up to 72 days. Rats responded to each mode exposure with gradual, mode-appropriate change in H-reflex amplitude. This finding is consistent with other evidence that H-reflex conditioning depends on spinal cord plasticity. The effects of exposure to the HRup (or HRdown) mode were not affected by whether exposure followed previous exposure to the HRdown (or HRup) mode. In accord with recent studies suggesting that HRup and HRdown conditioning have different spinal mechanisms, these results suggest that reversal of H-reflex change is due primarily to the superimposition of additional plasticity rather than to decay of the plasticity responsible for the initial change.
Keywords: H-Reflex; operant conditioning; plasticity; rat; soleus muscle; Spinal Cord

Therapeutic neural effects of electrical stimulation. - Janis J. Daly; Marsolais, E. B.; Mendell, L. M.; Rymer, W. Z.; Stefanovska, A.; Jonathan Wolpaw; Kantor, C. (IEEE transactions on rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 1996)
The use of a functional neuromuscular stimulation (FNS) device can have therapeutic effects that persist when the device is not in use. Clinicians have reported changes in both voluntary and electrically assisted neuromuscular function and improvements in the condition of soft tissue. Motor recovery has been observed in people with incomplete spinal cord injury, stroke, or traumatic brain injury after the use of motor prostheses. Improvement in voluntary dorsiflexion and overall gait pattern has been reported both in the short term (several hours) and permanently. Electrical stimulation of skin over flexor muscles in the upper limb produced substantial reductions for up to 1 h in the severity of spasticity in brain-injured subjects, as measured by the change in torque generation during ramp-and-hold muscle stretch. There was typically an aggravation of the severity of spasticity when surface stimulation reached intensities sufficient to also excite muscle. Animals were trained to alter the size of the H-reflex to obtain a reward. The plasticity that underlies this operantly conditioned H-reflex change includes changes in the spinal cord itself. Comparable changes appear to occur with acquisition of certain motor skills. Current studies are exploring such changes in humans and animals with spinal cord injuries with the goal of using conditioning methods to assess function after injury and to promote and guide recovery of function. A better understanding of the mechanisms of neural plasticity, achieved through human and animal studies, may help us to design and implement FNS systems that have the potential to produce beneficial changes in the subject's central nervous systems.
Keywords: Treatment Outcome

Vortex shedding as a precursor of turbulent electrical activity in cardiac muscle. - Cabo, C; Pertsov, A V; Davidenko, J M; Baxter, Bill; Gray, R A; Jalife, J (Biophys J, 1996)
In cardiac tissue, during partial blockade of the membrane sodium channels, or at high frequencies of excitation, inexcitable obstacles with sharp edges may destabilize the propagation of electrical excitation waves, causing the formation of self-sustained vortices and turbulent cardiac electrical activity. The formation of such vortices, which visually resembles vortex shedding in hydrodynamic turbulent flows, was observed in sheep epicardial tissue using voltage-sensitive dyes in combination with video-imaging techniques. Vortex shedding is a potential mechanism leading to the spontaneous initiation of uncontrolled high-frequency excitation of the heart.
Keywords: Animals; Biophysical Phenomena; Biophysics; Cell Membrane; Computer Simulation; Electric Stimulation; Electrochemistry; Electrophysiology; Heart; Models, Cardiovascular; Myocardial Contraction; Myocardium; Sheep; Sodium Channels

EEG-based brain computer interface (BCI). Search for optimal electrode positions and frequency components. - Pfurtscheller, G.; Flotzinger, D.; Pregenzer, M.; Jonathan Wolpaw; Dennis J. McFarland (Medical progress through technology, 1995)
Several laboratories around the world have recently started to investigate EEG-based brain computer interface (BCI) systems in order to create a new communication channel for subjects with severe motor impairments. The present paper describes an initial evaluation of 64-channel EEG data recorded while subjects used one EEG channel over the left sensorimotor area to control on-line vertical cursor movement. Targets were given at the top or bottom of a computer screen. Data from 3 subjects in the early stages of training were analyzed by calculating band power time courses and maps for top and bottom targets separately. In addition, the Distinction Sensitive Learning Vector Quantizer (DSLVQ) was applied to single-trial EEG data. It was found that for each subject there exist optimal electrode positions and frequency components for on-line EEG-based cursor control.
Keywords: User-Computer Interface

Effects of pacing on stationary reentrant activity. Theoretical and experimental study. - Davidenko, J M; Salomonsz, R; Pertsov, A V; Baxter, Bill; Jalife, J (Circ Res, 1995)
It is well known that electrical pacing may either terminate or change the rate and/or ECG appearance of reentrant ventricular tachycardia. However, the dynamics of interaction of reentrant waves with waves initiated by external pacing are poorly understood. Prevailing concepts are based on simplistic models in which propagation occurs in one-dimensional rings of cardiac tissue. Since reentrant activation in the ventricles occurs in two or three dimensions, such concepts might be insufficient to explain the mechanisms of pacing-induced effects. We used numerical and biological models of cardiac excitation to explore the phenomena, which may take place as a result of electrical pacing during functionally determined reentry. Computer simulations of a two-dimensional array of electrically coupled FitzHugh-Nagumo cells were used to predict the response patterns expected from thin slices of sheep ventricular epicardial muscle, in which self-sustaining reentrant activity in the form of spiral waves was consistently initiated by premature stimulation and monitored by means of video mapping techniques. The results show that depending on their timing and shape, externally induced waves may collide with the self-sustaining spiral and result in one of three possible outcomes: (1) direct annihilation of the spiral, (2) multiplication of the spiral, or (3) shift of the spiral center (ie, core). Multiplication and shift of the spiral core were attended by changes in rate and morphology of the arrhythmia as seen by "pseudo-ECGs." Furthermore, delayed termination (ie, termination of the activity one to three cycles after the stimulus) occurred after both multiplication and shift of the spiral center. Both numerical predictions and experimental results support the hypothesis that whether a pacing stimulus will terminate a reentrant arrhythmia or modify its ECG appearance depends on whether the interactions between the externally induced wave and the spiral wave result in the de novo formation of one or more "wavebreaks." The final outcome depends on the stimulus parameters (ie, position and size of the electrodes and timing of the stimulus) as well as on the position of the newly formed wavebreak(s) in relation to that of the original wave.
Keywords: Acceleration; Animals; Cardiac Pacing, Artificial; Computer Simulation; Deceleration; Electrocardiography; Models, Cardiovascular; Sheep; Tachycardia, Ventricular

Mechanisms of cardiac fibrillation. - Gray, R A; Jalife, J; Panfilov, A; Baxter, Bill; Cabo, C; Davidenko, J M; Pertsov, A V (Science, 1995)
Keywords: Animals; Computer Simulation; Electrocardiography; Heart Ventricles; Models, Cardiovascular; Rabbits; Ventricular Fibrillation

Motoneuron properties after operantly conditioned increase in primate H-reflex. - Jonathan S. Carp; Jonathan Wolpaw (Journal of neurophysiology, 1995)
1. Monkeys can increase (HRup conditioning mode) or decrease (HRdown conditioning mode) the triceps surae (TS) H-reflex in response to an operant conditioning task. This conditioning modifies the spinal cord. To define this spinal cord plasticity and its role in the behavioral change (H-reflex increase or decrease), we have recorded intracellularly from TS motoneurons in conditioned animals. The present report describes data from HRup animals and compares them with data from previously studied naive (NV; i.e., unconditioned) animals. 2. Thirteen monkeys (Macaca nemestrina, male, 3.8-7.1 kg) were exposed to the HRup conditioning mode, in which reward occurred when H-reflex size in one leg (i.e., the trained leg) was above a criterion value. Conditioning was successful (i.e., increase of > or = 20%) in 12 of the 13 animals. At the end of conditioning, H-reflex size in the trained leg averaged 188% of its initial value, whereas size in the control leg averaged 134% of its initial value. 3. Intracellular recordings were obtained from 136 TS motoneurons on trained (UT + motoneurons) and control (UC + motoneurons) sides of the successful animals. Measurements included axonal conduction velocity, input resistance, time constant, electrotonic length, rheobase, firing threshold to current injection, afterhyperpolarization duration and amplitude, and composite homonymous and heteronymous excitatory postsynaptic potential (EPSP) size and shape. Results were compared with intracellular data from NV animals.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Reward

Nonstationary vortexlike reentrant activity as a mechanism of polymorphic ventricular tachycardia in the isolated rabbit heart. - Gray, R A; Jalife, J; Panfilov, A; Baxter, Bill; Cabo, C; Davidenko, J M; Pertsov, A V (Circulation, 1995)
BACKGROUND:  Ventricular tachycardia may result from vortexlike reentrant excitation of the myocardium. Our general hypothesis is that in the structurally normal heart, these arrhythmias are the result of one or two nonstationary three-dimensional electrical scroll waves activating the heart muscle at very high frequencies. METHODS AND RESULTS:  We used a combination of high-resolution video imaging, electrocardiography, and image processing in the isolated rabbit heart, together with mathematical modeling. We characterized the dynamics of changes in transmembrane potential patterns on the epicardial surface of the ventricles using optical mapping. Image processing techniques were used to identify the surface manifestation of the reentrant organizing centers, and the location of these centers was used to determine the movement of the reentrant pathway. We also used numerical simulations incorporating Fitzhugh-Nagumo kinetics and realistic heart geometry to study how stationary and nonstationary scroll waves are manifest on the epicardial surface and in the simulated ECG. We present epicardial surface manifestations (reentrant spiral waves) and ECG patterns of nonstationary reentrant activity that are consistent with those generated by scroll waves established at the right and left ventricles. We identified the organizing centers of the reentrant circuits on the epicardial surface during polymorphic tachycardia, and these centers moved during the episodes. In addition, the arrhythmias that showed the greatest movement of the reentrant centers displayed the largest changes in QRS morphology. The numerical simulations showed that stationary scroll waves give rise to monomorphic ECG signals, but nonstationary meandering scroll waves give rise to undulating ECGs characteristic of torsade de pointes. CONCLUSIONS:  Polymorphic ventricular tachycardia in the healthy, isolated rabbit heart is the result of either a single or paired ("figure-of-eight") nonstationary scroll waves. The extent of the scroll wave movement corresponds to the degree of polymorphism in the ECG. These results are consistent with our numerical simulations that showed monomorphic ECG patterns of activity for stationary scroll waves but polymorphic patterns for scroll waves that were nonstationary.
Keywords: Animals; Electrocardiography; Heart; Image Processing, Computer-Assisted; Models, Cardiovascular; Perfusion; Rabbits; Tachycardia, Ventricular

Operant conditioning of H-reflex in freely moving rats. - Xiang Yang Chen; Jonathan Wolpaw (Journal of neurophysiology, 1995)
1. Primates can increase or decrease the spinal stretch reflex and its electrical analogue, the H-reflex (HR), in response to an operant conditioning task. This conditioning changes the spinal cord itself and thereby provides an experimental model for defining the processes and substrates of a learned change in behavior. Because the phenomenon has been demonstrated only in primates, its generality and theoretical implications remain unclear, and its experimental use is restricted by the difficulties of primate research. In response to these issues, the present study explored operant conditioning of the H-reflex in the rat. 2. Seventeen Sprague-Dawley rats implanted with chronic electromyographic (EMG) recording electrodes in one soleus muscle and nerve cuff stimulating electrodes on the posterior tibial nerve were rewarded (either with medial forebrain bundle stimulation or food) for increasing (HRup conditioning mode) or decreasing (HRdown conditioning mode) soleus H-reflex amplitude without change in background EMG or M response (direct muscle response) amplitude. 3. H-reflex amplitude changed appropriately over 3-4 wk. Under the HRup mode, it rose to an average of 158 +/- 54% (mean +/- SD) of initial value, whereas under the HRdown mode it fell to an average of 67 +/- 11% of initial value. Background EMG and M response amplitude did not change. 4. Operant conditioning of the H-reflex in the rat appears similar in rate and final magnitude of change to that observed in the monkey.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Spinal Cord

Operantly conditioned motoneuron plasticity: possible role of sodium channels. - Halter, J. A.; Jonathan S. Carp; Jonathan Wolpaw (Journal of neurophysiology, 1995)
1. Learning is traditionally thought to depend on synaptic plasticity. However, recent work shows that operantly conditioned decrease in the primate H reflex is associated with an increase in the depolarization needed to fire the spinal motoneuron (VDEP) and a decrease in its conduction velocity (CV). Furthermore, the increase in VDEP appears to be largely responsible for the H-reflex decrease. The conjunction of these changes in VDEP and CV suggests that an alteration in Na+ channel properties throughout the soma and axon could be responsible. 2. A mathematical model of the mammalian myelinated axon was used to test whether a positive shift in the voltage dependence of Na+ channel activation, a decrease in Na+ channel peak permeability, or changes in other fiber properties could have accounted for the experimental findings. 3. A positive shift of 2.2 mV in Na+ channel activation reproduced the experimentally observed changes in VDEP and CV, whereas a reduction in Na+ channel permeability or changes in other fiber properties did not. 4. These results are consistent with the hypothesis that operantly conditioned decrease in the primate H reflex is largely due to a positive shift in the voltage dependence of Na+ channel activation. Recent studies suggest that change in activation of protein kinase C may mediate this effect.
Keywords: Sodium Channels

Operantly conditioned plasticity and circadian rhythm in rat H-reflex are independent phenomena. - Xiang Yang Chen; Jonathan Wolpaw (Neuroscience letters, 1995)
Recent studies indicate that rats can increase or decrease H-reflex amplitude in response to an operant conditioning paradigm. In addition, rats also display a circadian rhythm in H-reflex amplitude. As part of the development of H-reflex conditioning in the rat as a new model for defining the plasticity underlying a simple form of learning, this study examined the relationship in the rat between operantly conditioned H-reflex change and the H-reflex circadian rhythm. When H-reflex amplitude increased or decreased in response to the operant conditioning program, its circadian rhythm showed no changes in phase and minimal change in amplitude. Furthermore, animals did not alter daily performance schedule so as to use the rhythm to increase reward probability. Thus, in the rat, H-reflex operant conditioning and the H-reflex circadian rhythm appear to be independent phenomena. The circadian rhythm should not be a significant complicating factor in studies of operantly conditioned H-reflex change.
Keywords: circadian rhythm; H-Reflex; Learning; Memory; operant conditioning; Rats

Acquisition and maintenance of the simplest motor skill: investigation of CNS mechanisms. - Jonathan Wolpaw (Medicine and science in sports and exercise, 1994)
The spinal stretch reflex (SSR), or tendon jerk, is the simplest behavior of the vertebrate nervous system. It is mediated primarily by a wholly spinal, two-neuron pathway. Recent studies from several laboratories have shown that primates, human and nonhuman, can gradually increase or decrease the size of the SSR when reward depends on such change. Evidence of this training remains in the spinal cord after all supraspinal influence is removed. Thus, the learning of this simple motor skill changes the spinal cord itself. Comparable spinal plasticity probably plays a role in the acquisition of many complex motor skills. Intracellular physiological and anatomical studies are seeking the location and nature of this spinal cord plasticity. Attention focuses on the most probable sites of change, the group Ia afferent synapse on the alpha motoneuron and the motoneuron itself. Results to date indicate that modifications are present at several places in the spinal cord. Current clinical studies are investigating the use of spinal cord adaptive plasticity as a basis for a new therapeutic approach to spasticity and other forms of abnormal spinal reflex function that result from spinal cord injury, stroke, or other neurological disorders. In the future, understanding of spinal reflex plasticity may lead to development of improved training methods for a variety of motor skills.
Keywords: conditioning; Learning; Memory; Motor control; plasticity; primate; Spinal Cord; training

Circadian rhythm in rat H-reflex. - Xiang Yang Chen; Jonathan Wolpaw (Brain research, 1994)
We measured soleus H-reflex in the Sprague-Dawley rat as a function of time of day. H-reflex amplitude displayed a marked diurnal variation, even though background EMG and M-response amplitude were stable through the day. The H-reflex was largest in the late morning and smallest around midnight. Thus, its rhythm was opposite in phase to the circadian rhythm found in the primate H-reflex. This rhythm is a potentially confounding factor in studies of motor function. Furthermore, its existence implies that the CNS activity underlying a specific motor performance varies with time of day.
Keywords: circadian rhythm; electromyogram; H-Reflex; rat; soleus

The influence of stimulus intensity, contralateral masking and handedness on the temporal N1 and the T complex components of the auditory N1 wave, by John F. Connolly. - Jonathan Wolpaw; Anthony T. Cacace (Electroencephalography and clinical neurophysiology, 1994)
Keywords: Humans

Motoneuron plasticity underlying operantly conditioned decrease in primate H-reflex. - Jonathan S. Carp; Jonathan Wolpaw (Journal of neurophysiology, 1994)
1. Monkeys can gradually increase or decrease the size of the triceps surae H-reflex in response to an operant conditioning task. This conditioning modifies the spinal cord. To determine the location and nature of the spinal cord plasticity and define its role in the behavioral change (i.e., H-reflex increase or decrease) we have recorded intracellularly from triceps surae motoneurons in conditioned animals and compared the results with data from naive (i.e., unconditioned) animals. 2. Eleven monkeys (Macaca nemestrina, male) were exposed to the HRdown conditioning mode, in which reward occurred when H-reflex size in one leg (i.e., the trained leg) was below a criterion value. In six animals (5.1-8.2 kg) H-reflex size in the trained leg fell to 24-58% of its initial value, whereas in the other five animals (4.0-5.5 kg) it remained at 92-114% of its initial value. This outcome, which was in accord with recent data indicating that success in HRdown conditioning is age dependent, allowed comparison of intracellular data from successful HRdown animals with data from unsuccessful animals as well as with data from naive (i.e., unconditioned) animals. 3. Intracellular recordings were obtained from 221 triceps surae motoneurons on trained and control sides of successful and unsuccessful HRdown animals. Measurements included axonal conduction velocity, input resistance, time constant, electrotonic length, rheobase, firing threshold, afterhyperpolarization duration and amplitude, and composite homonymous and heteronymous excitatory postsynaptic potentials to peripheral nerve stimulation. Results were compared with data from 109 triceps surae motoneurons in naive animals. 4. Motoneurons from the trained side of successful HRdown animals had a significantly more positive average firing threshold (-52 vs. -55 mV) and a significantly lower average conduction velocity (67 vs. 71 m/s) than those from naive animals. In contrast, motoneurons from the trained side of unsuccessful HRdown animals were not significantly different from naive motoneurons. 5. These data are consistent with the hypothesis that operantly conditioned decrease in H-reflex size is due to a positive shift in motoneuron firing threshold and a consequent increase in the depolarization needed to reach that threshold. 6. The more positive firing threshold, if present in the axon as well as in the soma, could also account for the decreased conduction velocity observed in motoneurons from the trained side of successful animals.
Keywords: Synaptic Transmission

Multichannel EEG-based brain-computer communication. - Jonathan Wolpaw; Dennis J. McFarland (Electroencephalography and clinical neurophysiology, 1994)
Individuals who are paralyzed or have other severe movement disorders often need alternative means for communicating with and controlling their environments. In this study, human subjects learned to use two channels of bipolar EEG activity to control 2-dimensional movement of a cursor on a computer screen. Amplitudes of 8-12 Hz activity in the EEG recorded from the scalp across right and left central sulci were determined by fast Fourier transform and combined to control vertical and horizontal cursor movements simultaneously. This independent control of two separate EEG channels cannot be attributed to a non-specific change in brain activity and appeared to be specific to the mu rhythm frequency range. With further development, multichannel EEG-based communication may prove of significant value to those with severe motor disabilities.
Keywords: assistive communication; Electroencephalography; mu rhythm; operant conditioning; prosthesis; Rehabilitation; sensorimotor cortex

Operant conditioning of primate H-reflex: phases of development. - Jonathan Wolpaw; Maniccia, D. M.; Elia, T. (Neuroscience letters, 1994)
This study sought to determine whether operantly conditioned change in the primate triceps surae (TS) H-reflex develops in distinct phases. Data from 20 animals in which the TS H-reflex in one leg was trained up (i.e., HRup mode) and 18 in which it was trained down (i.e., HRdown mode) were averaged to define H-reflex behavior in trained and control legs. In HRup animals, the trained-leg H-reflex showed a large phase I increase in the first two days followed by gradual phase II increase that continued for weeks. The control-leg H-reflex appeared to show much smaller phase I and phase II increases. In HRdown animals, the trained-leg H-reflex decreased gradually over weeks, while the control-leg H-reflex appeared to increase within 2 days and did not change from then on. The initial rapid increase in the HRdown control leg suggested that two early events occurred in the HRdown trained leg: a nonspecific increase like that in the control leg and an operantly conditioned mode-specific decrease. These two effects may have obscured each other, so that H-reflex size in the HRdown trained leg did not drop rapidly in the first few days. These results improve understanding of adaptive H-reflex change as an operantly conditioned phenomenon, and provide encouragement and direction for efforts to reproduce and study the phenomenon in reduced or anesthetized preparations.
Keywords: Time Factors

Synaptic terminal coverage of primate triceps surae motoneurons. - Starr, K. A.; Jonathan Wolpaw (The Journal of comparative neurology, 1994)
This study examined the synaptic terminal coverage of primate triceps surae (TS) motoneurons at the electron microscopic level. In three male pigtail macaques, motoneurons were labeled by retrograde transport of cholera toxin-horseradish peroxidase that was injected into TS muscles bilaterally and visualized with tetramethylbenzidine stabilized with diaminobenzidine. Somatic, proximal dendritic, and distal dendritic synaptic terminals were classified by standard criteria and measured. Overall and type-specific synaptic terminal coverages and frequencies were determined. Labeled cells were located in caudal L5 to rostral S1 ventral horn and ranged from 40 to 74 microns in diameter (average, 54 microns). The range and unimodal distribution of diameters, the label used, and the presence of C terminals on almost all cells indicated that the 15 cell bodies and associated proximal dendrites analyzed here probably belonged to alpha-motoneurons. Synaptic terminals covered 39% of the cell body membrane, 60% of the proximal dendritic membrane, and 40% of the distal dendritic membrane. At each of these three sites, F terminals (flattened or pleomorphic vesicles, usually symmetric active zones, average contact length 1.6 microns) were most common, averaging 52%, 56%, and 58% of total coverage and 56%, 57%, and 58% of total number of cell bodies, proximal dendrites, and distal dendrites respectively. S terminals (round vesicles, usually asymmetric active zones, average contact length 1.3 microns) averaged 24%, 29%, and 33% of coverage and 33%, 35%, and 36% of number at these three sites, respectively. Thus, S terminals were slightly more prominent relative to F terminals on distal dendrites than on cell bodies. C terminals (spherical vesicles, subsynaptic cisterns associated with rough endoplasmic reticulum, average contact length 3.5 microns) constituted 24% and 11% of total terminal coverage on cell bodies and proximal dendrites, respectively, and averaged 11% and 6% of terminal number at these two locations. M terminals (spherical vesicles, postsynaptic Taxi bodies, some with presynaptic terminals, average contact length 2.7 microns) were absent on cell bodies and averaged 3% and 7% of total coverage and 2% and 5% of terminals on proximal and distal dendrites, respectively. Except for M terminals, which tended to be smaller distally, terminal contact length was not correlated with location. Total and type-specific coverages and frequencies were not correlated with cell body diameter. Primate TS motoneurons are similar to cat TS motoneurons in synaptic terminal morphology, frequency, and distribution. However, primate terminals appear to be smaller, so that the fraction of membrane covered by them is lower.
Keywords: Spinal Cord

Transmitter and electrical stimulations of [3H]taurine release from rat sympathetic ganglia. - Waniewski, R. A.; Jonathan S. Carp; Martin, D. L. (Advances in experimental medicine and biology, 1994)
Astroglial cells release taurine in response to stimulation with neurotransmitters. This process has been studied most extensively with primary cultures of astrocytes and LRM55 glial cells. These studies have demonstrated that several transmitters can elicit release. The second messenger systems involved in activating release have been characterized (10, 15, 19). An important issue concerning all studies of this type is the applicability of results obtained with glia in culture to glia in vivo. We have chosen the rat superior cervical ganglion as a nervous tissue having the potential for exploring taurine release from glial cells in situ. The major neuronal composition of the ganglion consists of preganglionic nerve terminals providing cholinergic input and principal neurons providing noradrenergic output. The superior cervical ganglion also contains a very small population of dopamine-containing intrinsic neurons known as SIF cells (3). The glial population of the superior cervical ganglion is composed of Schwann cells responsible for myelination and satellite glia, immunoreactive to glial fibrillary acidic protein, that surround the cell bodies of the principal neurons (1, 7). Currently available data suggest that taurine is selectively taken up by the satellite glia. Autoradiographic studies have demonstrated that the ω-amino acids GABA and β-alanine are selectively accumulated by satellite glial cells in the superior cervical ganglion (5, 20), while transport studies have shown that taurine inhibits [3H]GABA uptake and that GABA inhibits [14C]taurine uptake by the superior cervical ganglion (5). The demonstration that potassium-stimulated efflux of [3H]GABA from the superior cervical ganglion is not reduced by preganglionic denervation also supports the glial localization of ω-amino acid transporters in this tissue (4).
Keywords: Tritium

Triceps surae motoneuron morphology in the rat: a quantitative light microscopic study. - Xiang Yang Chen; Jonathan Wolpaw (The Journal of comparative neurology, 1994)
The rat is now the model of choice for many studies of motor function. However, little quantitative information on the structure of rat motoneurons is available. In conjunction with efforts to define the physiologic and anatomic substrates of operantly conditioned plasticity in the spinal cord, 13 physiologically identified triceps surae motoneurons in the rat lumbar spinal cord were labeled intracellularly with horseradish peroxidase and completely reconstructed and measured with a computer-based neuron-tracing system. Somata were all located in the ventral horn of lumbar segments 4-5, had an average diameter of 35 microns, and had 6-12 dendrites. Dendrites ramified throughout the ventral horn and also penetrated the white matter. Their spread was greater in the rostrocaudal and dorsoventral directions (1.53 +/- 0.24 mm and 1.35 +/- 0.23 mm, respectively) than in the mediolateral direction (0.85 +/- 0.14 mm). Regardless of soma location, dendritic fields usually extended throughout the ipsilateral coronal cross-section of the ventral horn. As a result, the ventral or lateral extent of the field was correlated strongly with the soma's distance from the ventral or lateral border, respectively, of the ventral horn. Furthermore, although soma locations in the coronal plane varied widely, the centers of the dendritic fields tended to cluster near the center of the ventral horn. Dendrites constituted 96.2-98.4% (mean +/- SD = 97.3 +/- 0.7%) of the total neuronal surface area. Each of the 104 dendrites studied had an average of 13 branch points and 27 segments. First-order segment diameters ranged from 1.4 to 11.7 microns (mean +/- SD = 5.3 +/- 2.1 microns). Total dendritic length, surface area, volume, number of dendritic segments, and maximum segment order were correlated strongly with diameter of the first-order segment. Proceeding distally between branch points, the mean decrease in dendritic diameter (i.e., tapering) +/- the standard deviation was 22 +/- 8% of the proximal diameter. The average ratio +/- the standard deviation of the sum of the average diameters of each daughter segment raised to the 1.5 power to the average diameter of the parent segment raised to the 1.5 power (i.e., Rall's ratio; Rall, 1959) was 0.87 +/- 0.08. In comparison with cat alpha-motoneurons, rat motoneurons had smaller soma diameters, fewer dendrites, smaller total surface areas, and shorter total dendritic lengths. However, the number of terminations per dendrite was similar in the two species, so that rat motoneurons had more terminations per unit dendritic length.(ABSTRACT TRUNCATED AT 400 WORDS)
Keywords: computer assisted; dendrites; horseradish peroxidase; image processing; Software; Spinal Cord

Wave-front curvature as a cause of slow conduction and block in isolated cardiac muscle. - Cabo, C; Pertsov, A V; Baxter, Bill; Davidenko, J M; Gray, R A; Jalife, J (Circ Res, 1994)
We have investigated the role of wave-front curvature on propagation by following the wave front that was diffracted through a narrow isthmus created in a two-dimensional ionic model (Luo-Rudy) of ventricular muscle and in a thin (0.5-mm) sheet of sheep ventricular epicardial muscle. The electrical activity in the experimental preparations was imaged by using a high-resolution video camera that monitored the changes in fluorescence of the potentiometric dye di-4-ANEPPS on the surface of the tissue. Isthmuses were created both parallel and perpendicular to the fiber orientation. In both numerical and biological experiments, when a planar wave front reached the isthmus, it was diffracted to an elliptical wave front whose pronounced curvature was very similar to that of a wave front initiated by point stimulation. In addition, the velocity of propagation was reduced in relation to that of the original planar wave. Furthermore, as shown by the numerical results, wave-front curvature changed as a function of the distance from the isthmus. Such changes in local curvature were accompanied by corresponding changes in velocity of propagation. In the model, the critical isthmus width was 200 microns for longitudinal propagation and 600 microns for transverse propagation of a single planar wave initiated proximal to the isthmus. In the experiments, propagation depended on the width of the isthmus for a fixed stimulation frequency. Propagation through an isthmus of fixed width was rate dependent both along and across fibers. Thus, the critical isthmus width for propagation was estimated in both directions for different frequencies of stimulation. In the longitudinal direction, for cycle lengths between 200 and 500 milliseconds, the critical width was < 1 mm; for 150 milliseconds, it was estimated to be between 1.3 and 2 mm; and for the maximum frequency of stimulation (117 +/- 15 milliseconds), it was > 2.5 mm. In the transverse direction, critical width was between 1.78 and 2.32 mm for a basic cycle length of 200 milliseconds. It increased to values between 2.46 and 3.53 mm for a basic cycle length of 150 milliseconds. The overall results demonstrate that the curvature of the wave front plays an important role in propagation in two-dimensional cardiac muscle and that changes in curvature may cause slow conduction or block.
Keywords: Animals; Computer Simulation; Electric Conductivity; Heart; Heart Block; Heart Conduction System; Humans; Models, Cardiovascular; Motion Pictures as Topic; Sheep; Staining and Labeling

Adaptive plasticity in spinal cord. - Jonathan Wolpaw; Jonathan S. Carp (Advances in neurology, 1993)
Keywords: Spinal Cord

Ethical and social issues in organ procurement for transplantation. - Rosner, F.; Henry, J. B.; Jonathan Wolpaw; Sordillo, P. P.; Sechzer, P. H.; Rogatz, P.; Risemberg, H. M.; Ona, F. V.; Numann, P. J.; Lowenstein, R. E. (New York state journal of medicine, 1993)
Keywords: Voluntary Programs

Monosynaptic EPSPs in primate lumbar motoneurons. - Jonathan S. Carp (Journal of neurophysiology, 1993)
1. Homonymous and heteronymous monosynaptic composite excitatory postsynaptic potentials (EPSPs) were evaluated by intracellular recordings from 89 motoneurons innervating triceps surae (n = 59) and more distal (n = 30) muscles in 14 pentobarbital-anesthetized monkeys (Macaca nemestrina). 2. Homonymous EPSPs were found in all motoneurons tested. The mean values +/- SD for maximum EPSP amplitude of triceps surae motoneurons were 2.5 +/- 1.3, 1.8 +/- 1.3 and 4.5 +/- 2.0 mV for medial gastrocnemius, lateral gastrocnemius, and soleus motoneurons, respectively. Heteronymous EPSPs were almost always smaller than their corresponding homonymous EPSPs. 3. Triceps surae EPSP amplitude was larger in motoneurons with higher input resistance. However, this relationship was weak, suggesting that factors related to input resistance play a limited role in determining the magnitude of the EPSP. 4. The mean ratio +/- SD of the amplitude of the EPSP elicited by combined stimulation of all triceps surae nerves to the amplitude of the algebraic sum of the three individual EPSPs was 0.95 +/- 0.05. This ratio was greater in motoneurons with lower rheobase. 5. Some patterns of synaptic connectivity in the macaque are consistent with previously reported differences between primates and cat (e.g., heteronymous EPSPs elicited by medial gastrocnemius nerve stimulation in soleus motoneurons are small in macaque and other primates but large in cat). However, no overall pattern emerges from a comparison of the similarities and differences in EPSPs among species in which they have been studied (i.e., macaque, baboon, and cat). That is, there are no two species in which EPSP properties are consistently similar to each other, but different from those of the third species.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Synapses

Operant conditioning of the primate H-reflex: factors affecting the magnitude of change. - Jonathan Wolpaw; Herchenroder, P. A.; Jonathan S. Carp (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 1993)
Primates can gradually increase or decrease H-reflex amplitude in one leg when reward depends on that amplitude. The magnitude of change varies greatly from animal to animal. This study sought to define the factors that control this magnitude. It evaluated the influence of animal age, muscle size (absolute and relative), background electromyographic activity (EMG) level, M response amplitude, initial H-reflex amplitude, performance intensity, and behavior of the contralateral leg. Fifty-four animals (Macaca nemestrina) underwent operant conditioning of the triceps surae H-reflex in one leg (the trained leg). Twenty-eight were rewarded for larger H-reflexes (HRup animals), and 26 were rewarded for smaller H-reflexes (HRdown animals). In the HRup animals, H-reflex amplitude in the trained leg rose to an average final value of 177% of its initial amplitude. Magnitude of increase varied widely across animals. Nine animals rose to 120-140%, 11 to 160-240%, three to 300% or more, and five remained within 20% of initial amplitude. In the HRdown animals, H-reflex amplitude in the trained leg decreased to an average of 69% of initial amplitude. Magnitude of decrease varied widely. Five animals decreased to 20-40%, seven to 40-60%, six to 60-80%, and eight remained within 20% of initial amplitude. Animal age, as assessed by weight, markedly affected HRdown conditioning, but not HRup conditioning. Heavy HRdown animals (> or = 6 kg) were more successful than light HRdown animals (< 6 kg). Thirteen of 14 heavy animals and only five of 12 light animals decreased to less than 80% of initial amplitude.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: H-Reflex; monkey; operant conditioning; plasticity; Spinal Cord

Spiral waves of excitation underlie reentrant activity in isolated cardiac muscle. - Pertsov, A V; Davidenko, J M; Salomonsz, R; Baxter, Bill; Jalife, J (Circ Res, 1993)
The mechanism of reentrant ventricular tachycardia was studied in computer simulations and in thin (approximately 20 x 20 x 0.5-mm) slices of dog and sheep ventricular epicardial muscle. A two-dimensional matrix consisting of 96 x 96 electrically coupled cells modeled by the FitzHugh-Nagumo equations was used to analyze the dynamics of self-sustaining reentrant activity in the form of elliptical spiral waves induced by premature stimulation. In homogeneous anisotropic media, spirals are stationary and may last indefinitely. However, the presence of small parameter gradients may lead to drifting and eventual termination of the spiral at the boundary of the medium. On the other hand, spirals may anchor and rotate around small discontinuities within the matrix. Similar results were obtained experimentally in 10 preparations whose electrical activity was monitored by means of a potentiometric dye and high-resolution optical mapping techniques; premature stimulation triggered reproducible episodes of sustained or nonsustained reentrant tachycardia in the form of spiral waves. As a rule, the spirals were elongated, with the major hemiaxis parallel to the longitudinal axis of the cells. The period of rotation (183 +/- 68 msec [mean +/- SD]) was longer than the refractory period (131 +/- 38 msec) and appeared to be determined by the size of the spiral's core, which was measured using a newly devised "frame-stack" plot. Drifting of spiral waves was also observed experimentally. Drift velocity was 9.8% of the velocity of wave propagation. In some cases, the core became stationary by anchoring to small arteries or other heterogeneities, and the spiral rotated rhythmically for prolonged periods of time. Yet, when drift occurred, spatiotemporal variations in the excitation period were manifested as a result of a Doppler effect, with the excitation period ahead of the core being 20 +/- 6% shorter than the excitation period behind the core. As a result of these coexisting frequencies, a pseudoelectrocardiogram of the activity in the presence of a drifting spiral wave exhibited "QRS complexes" with an undulating axis, which resembled those observed in patients with torsade de pointes. The overall results show that spiral wave activity is a property of cardiac muscle and suggest that such activity may be the common mechanism of a number of monomorphic and polymorphic tachycardias.
Keywords: Animals; Computer Simulation; Disease Models, Animal; Dogs; Electrophysiology; Sheep; Tachycardia, Atrioventricular Nodal Reentry; Torsades de Pointes

The volitional nature of the simplest reflex. - Jonathan Wolpaw; Jonathan S. Carp (Acta neurobiologiae experimentalis, 1993)
Recent studies suggest that none of the behaviors of the vertebrate CNS are fixed responses incapable of change. Even the simplest reflex of all, the two-neuron, monosynaptic spinal stretch reflex (SSR), undergoes adaptive change under appropriate circumstances. Operantly conditioned SSR change occurs gradually over days and weeks and is associated with a complex pattern of CNS plasticity at both spinal and supraspinal sites.
Keywords: behavior; Brain; conditioning; human physiology; Learning; Memory; motoneuron; nature; primate; Reflex; Spinal Cord; spinal site; supra spinal site; vertebrate

Constancy of motor axon conduction time during growth in rats. - Xiang Yang Chen; Jonathan S. Carp; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 1992)
Axon conduction distance, conduction velocity, and conduction time were measured for individual triceps surae motoneurons in Sprague-Dawley rats weighing 230-630 g (i.e., age range 6-16 weeks). Both conduction distance (nerve length) and velocity were closely correlated with weight (r = 0.95 and r = 0.82, respectively). In contrast, conduction time did not change as weight increased nearly threefold. This striking constancy is probably due to a corresponding increase in axon diameter. It could contribute to maintenance of stable motor performance during rapid growth.
Keywords: development; motoneuron; motor axon; nerve conduction; rat

Ethical considerations concerning the HIV-positive physician. - Rosner, F.; Sordillo, P. P.; Jonathan Wolpaw; Farnsworth, P. B.; Bennett, A. J.; Buscaglia, A.; Cassell, E. J.; Halpern, A. L.; Henry, J. B.; Kark, P. R. (New York state journal of medicine, 1992)
Keywords: Voluntary Programs

Physiological properties of primate lumbar motoneurons. - Jonathan S. Carp (Journal of neurophysiology, 1992)
1. Intracellular recordings were obtained from 149 motoneurons innervating triceps surae (n = 109) and more distal muscles (n = 40) in 14 pentobarbital-anesthetized monkeys (Macaca nemestrina). The variables evaluated were resting membrane potential, action potential amplitude, conduction velocity (CV), input resistance (RN), membrane time constant (tau m), electrotonic length (L), whole-cell capacitance (Ctot), long current pulse threshold (rheobase), short current pulse threshold (Ishort), afterhyperpolarization (AHP) maximum amplitude (AHPmax), AHP duration (AHPdur), time to half maximum AHP amplitude (AHP t1/2), depolarization from resting potential to elicit action potential (Vdep), and threshold voltage for action potential discharge (Vthr). 2. Mean values +/- SD for the entire sample of motoneurons are as follows: resting membrane potential -67 +/- 6 mV; action potential amplitude 75 +/- 7 mV; CV 71 +/- 6 m/s; RN 1.0 +/- 0.5 M omega; tau m 4.4 +/- 1.5 ms; L 1.4 +/- 0.2 lambda; Ctot 7.1 +/- 1.8 nF; rheobase 13 +/- 7 nA; Ishort 29 +/- 14 nA; AHPmax 3.5 +/- 1.3 mV; AHPdur 77 +/- 26 ms; AHP t 1/2 21 +/- 7 ms; Vdep 11 +/- 4 mV; and Vthr -56 +/- 5 mV. CV is lower in soleus than in either medial or lateral gastrocnemius motoneurons, and RN is lower and tau m is longer in soleus than in lateral gastrocnemius motoneurons. 3. RN is higher in motoneurons with longer tau m and slower CV. A linear relationship exists between log(CV) and log(1/RN) with a slope of 1.8-2.2 (depending on the action potential amplitude acceptance criteria used), suggesting that membrane resistivity (Rm) does not vary systematically with cell size. 4. Rheobase is higher in motoneurons with lower RN, longer tau m, shorter AHP time course, and higher CV. Ishort and normalized rheobase (i.e., rheobase/Ctot) vary similarly with these motoneuron properties, except that Ishort is independent of tau m and normalized rheobase is independent of CV. 5. Vthr tends to be more depolarized in motoneurons with large Ctot, but the relationship is sufficiently weak so that any systematic variation in Vthr according to cell size probably contributes only minimally to recruitment order. Vthr does not vary systematically with CV, AHP time course, RN, or tau m. 6. Quantitative differences between macaque and cat triceps surae motoneurons are apparent in CV, which is slower in macaque than in cat, and to a lesser extent in tau m and RN, which are lower in macaque than in cat.(ABSTRACT TRUNCATED AT 400 WORDS)
Keywords: Spinal Cord

Spatiotemporal irregularities of spiral wave activity in isolated ventricular muscle. - Davidenko, J M; Pertsov, A V; Salomonsz, R; Baxter, Bill; Jalife, J (J Electrocardiol, 1992)
Voltage-sensitive dyes and high resolution optical mapping were used to analyze the characteristics of spiral waves of excitation in isolated ventricular myocardium. In addition, analytical techniques, which have been previously used in the study of the characteristics of spiral waves in chemical reactions, were applied to determine the voltage structure of the center of the rotating activity (ie, the core). During stable spiral wave activity local activation occurs in a periodic fashion (ie, 1:1 stimulus: response activation ratio) throughout the preparation, except at the core, which is a small elongated area where the activity is of low voltage and the activation ratio is 1:0. The voltage amplitude increases gradually from the center of the core to the periphery. In some cases, however, regular activation patterns at the periphery may coexist with irregular local activation patterns near the core. Such a spatiotemporal irregularity is attended by variations in the core size and shape and results from changes in the core position. The authors conclude that functionally determined reentrant activity in the heart may be the result of spiral waves of propagation and that local spatiotemporal irregularities in the activation pattern are the result of changes in the core position.
Keywords: Animals; Cardiac Pacing, Artificial; Fluorescent Dyes; Heart Conduction System; Membrane Potentials; Optics and Photonics; Pericardium; Signal Processing, Computer-Assisted; Tachycardia; Ventricular Function

Stationary and drifting spiral waves of excitation in isolated cardiac muscle. - Davidenko, J M; Pertsov, A V; Salomonsz, R; Baxter, Bill; Jalife, J (Nature, 1992)
Excitable media can support spiral waves rotating around an organizing centre. Spiral waves have been discovered in different types of autocatalytic chemical reactions and in biological systems. The so-called 're-entrant excitation' of myocardial cells, causing the most dangerous cardiac arrhythmias, including ventricular tachycardia and fibrillation, could be the result of spiral waves. Here we use a potentiometric dye in combination with CCD (charge-coupled device) imaging technology to demonstrate spiral waves in the heart muscle. The spirals were elongated and the rotation period, Ts, was about 180 ms (3-5 times faster than normal heart rate). In most episodes, the spiral was anchored to small arteries or bands of connective tissue, and gave rise to stationary rotations. In some cases, the core drifted away from its site of origin and dissipated at a tissue border. Drift was associated with a Doppler shift in the local excitation period, T, with T ahead of the core being about 20% shorter than T behind the core.
Keywords: Animals; Dogs; Heart; Mathematics; Membrane Potentials; Models, Biological; Myocardial Contraction; Sheep

Alterations in motoneuron properties induced by acute dorsal spinal hemisection in the decerebrate cat. - Jonathan S. Carp; Powers, R. K.; Rymer, W. Z. (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 1991)
Using intracellular recording techniques, we studied the response characteristics of two separate populations of triceps surae motoneurons in unanesthetized decerebrate cats, recorded before and after low thoracic hemisection of the spinal cord. In each preparation, we studied the response properties of one group of motoneurons and the protocol was then repeated for a separate group, immediately following the dorsal hemisection. In each group, we examined both the minimum firing rates of motoneurons during intracellular current injection and a range of cellular properties, including input resistance, rheobase current and afterhyperpolarization time course and magnitude. Although earlier studies from this laboratory have shown substantial reductions in minimum firing rate in reflexively active motoneurons in the hemisected decerebrated preparation, the response of motoneurons to intracellular current injection in the current preparation proved to be quite different. Minimum firing rates were either normal or even somewhat higher in the post-lesion group, while the time course of the afterhyperpolarization was shortened. Moreover, these effects were not evenly distributed across the motoneuron pool. The rate effect was most evident in motoneurons with higher conduction velocity, while the afterhyperpolarization effect occurred predominantly in motoneurons with lower conduction velocity. Neither of these effects could be accounted for by lesion-induced changes in other cellular properties. We conclude that tonically active neurons with descending axons traversing dorsolateral white matter may influence both the discharge characteristics and membrane properties of spinal motoneurons in novel ways, presumably by modifying voltage or calcium activated motoneuronal conductances. The previously described reactions in the firing rate of motoneurons after such lesions appear to be mediated by different means, perhaps by alterations in synaptic input from segmental interneurons.
Keywords: afterhyperpolarization; cat; lesion; motoneuron; repetitive discharge; Spinal Cord

An EEG-based brain-computer interface for cursor control. - Jonathan Wolpaw; Dennis J. McFarland; Neat, G. W.; Forneris, C. A. (Electroencephalography and clinical neurophysiology, 1991)
This study began development of a new communication and control modality for individuals with severe motor deficits. We trained normal subjects to use the 8-12 Hz mu rhythm recorded from the scalp over the central sulcus of one hemisphere to move a cursor from the center of a video screen to a target located at the top or bottom edge. Mu rhythm amplitude was assessed by on-line frequency analysis and translated into cursor movement: larger amplitudes moved the cursor up and smaller amplitudes moved it down. Over several weeks, subjects learned to change mu rhythm amplitude quickly and accurately, so that the cursor typically reached the target in 3 sec. The parameters that translated mu rhythm amplitudes into cursor movements were derived from evaluation of the distributions of amplitudes in response to top and bottom targets. The use of these distributions was a distinctive feature of this study and the key factor in its success. Refinements in training procedures and in the distribution-based method used to translate mu rhythm amplitudes into cursor movements should further improve this 1-dimensional control. Achievement of 2-dimensional control is under study. The mu rhythm may provide a significant new communication and control option for disabled individuals.
Keywords: Communication; computer control; EEG; mu rhythm; operant conditioning; prosthesis; sensorimotor rhythm

Operantly conditioned plasticity in spinal cord. - Jonathan Wolpaw; Lee, C. L.; Jonathan S. Carp (Annals of the New York Academy of Sciences, 1991)
Recent work has shown that the monosynaptic pathway of the SSR can be operantly conditioned, and that a significant part of the plasticity responsible for the behavioral change resides in the spinal cord. The most likely sites of this activity-driven plasticity are the synapse of the Ia afferent neuron on the motoneuron and/or the motoneuron itself. Because the SSR pathway is the simplest and most accessible stimulus-response pathway in the vertebrate CNS, it may provide a valuable experimental model for elucidating activity-driven CNS changes responsible for learning.
Keywords: Spinal Cord

The allocation of scarce medical resources. - Rosner, F.; Sordillo, P. P.; Sechzer, P. H.; Risemberg, H. M.; Ona, F. V.; Numann, P. J.; Loeb, L.; Farnsworth, P. B.; Bennett, A. J.; Jonathan Wolpaw (New York state journal of medicine, 1990)
Keywords: Vulnerable Populations

Human middle-latency auditory evoked potentials: vertex and temporal components. - Anthony T. Cacace; Satya-Murti, S.; Jonathan Wolpaw (Electroencephalography and clinical neurophysiology, 1990)
We recorded middle-latency (20-70 msec) auditory evoked potentials (MLAEPs) to monaural and binaural clicks in 30 normal adults (ages 20-49 years) at 32 scalp locations all referred to a balanced non-cephalic reference. Our goal was to define the MLAEP components that were present at comparable latencies and comparable locations across the subject population. Group and individual data were evaluated both as topographic maps and as MLAEPs at selected electrode locations. Three major components occurred between 20 and 70 msec, two well-known peaks centered at the vertex, and one previously undefined peak focused over the posterior temporal area. Pa is a 29 msec positive peak centered at the vertex and present with both monaural and binaural stimulation. Pb is a 53 msec positive peak also centered at the vertex but seen consistently only with binaural and right ear stimulation. TP41 is a 41 msec positive peak focused over both temporal areas. TP41 has not been identified in previous MLAEP studies that concentrated on central scalp locations and/or used active reference electrode sites such as ears or mastoids. Available topographic, intracranial, pharmacologic, and lesion studies indicate that Pa, Pb and TP41 are of neural origin. Whether Pa and/or Pb are produced in Heschl's gyrus, primary auditory cortex, remains unclear. TP41 is probably produced by auditory cortex on the posterior lateral surface of the temporal lobe. It should prove of considerable value in experimental and clinical evaluation of higher level auditory function in particular and of cortical function in general.
Keywords: (human); middle-latency auditory evoked potential (MLAEP); temporal components; vertex components

Memory traces in spinal cord. - Jonathan Wolpaw; Jonathan S. Carp (Trends in neurosciences, 1990)
The complexity and inaccessibility of the vertebrate CNS impede the localization and description of memory traces and the definition of the processes that create them. Recent work has shown that the spinal stretch reflex (SSR), which is produced by a monosynaptic two-neuron pathway, can be operantly conditioned, and that memory traces responsible for this behavioral change reside in the spinal cord. The probable locations are the terminal of the Ia affernt neuron on the motoneuron and/or the motoneuron itself. Because it modifies a simple well-defined and accessible pathway, SSR conditioning may be a valuable experimental model for studying vertebrate memory.
Keywords: Spinal Cord

Operant conditioning of H-reflex in freely moving monkeys. - Jonathan Wolpaw; Herchenroder, P. A. (Journal of neuroscience methods, 1990)
The H-reflex, the electrical analog of the stretch reflex or tendon jerk, is the simplest behavior of the primate CNS. It is subserved by a wholly spinal two-neuron reflex arc. Recent studies show that this reflex can be increased or decreased by operant conditioning, and that such conditioning causes plastic changes in the spinal cord itself. Thus, H-reflex conditioning provides a powerful new model for investigating primate memory traces. The key feature of this model, the conditioning task, originally required animal restraint. This report describes a new tether-based design that allows H-reflex measurement and conditioning without restraint. This design integrates the conditioning task into the life of the freely moving animal.
Keywords: conditioning; H-Reflex; Memory; plasticity; primate; spinal reflex; stretch reflex

Chronic exposure of primates to 60-Hz electric and magnetic fields: I. Exposure system and measurements of general health and performance. - Jonathan Wolpaw; Seegal, R. F.; Dowman, R. (Bioelectromagnetics, 1989)
We exposed pigtailed macaques (Macaca nemestrina) to electric (E) and magnetic (B) fields at strengths of 3 kV/m and 0.1 G, 10 kV/m and 0.3 G, and 30 kV/m and 0.9 G for three 21 day segments. These three exposure segments were preceded and followed by 21 day sham exposure segments. Additional animals received only sham exposure for five 21 day segments. Detailed description of the exposure chamber and field generation apparatus is given. We evaluated measures of animal well-being, including weight, blood chemistry, blood cell counts, and performance on a simple motor task, and performed postmortem examinations. Reliable and consistent results were obtained throughout data collection. None of the measures evaluated was significantly affected by E- and B-field exposures. Data obtained during actual exposure segments were not distinguishable from those obtained during the initial and final sham exposure segments, nor were they different from data obtained from the sham-exposed animals. Thus, field exposure had no apparent effects on general health or performance.
Keywords: 60-Hz fields; central nervous system; electric field; magnetic field; primate

Chronic exposure of primates to 60-Hz electric and magnetic fields: III. Neurophysiologic effects. - Dowman, R.; Jonathan Wolpaw; Seegal, R. F.; Satya-Murti, S. (Bioelectromagnetics, 1989)
The neurophysiologic effects of combined 60-Hz electric (E) and magnetic (B) fields, of magnitudes comparable to those produced by high-voltage powerlines, were investigated in 10 monkeys (Macaca nemestrina). Six animals (experimental group) were each exposed to three different levels of E and B fields: 3 kV/m and 0.1 G, 10 kV/m and 0.3 G, and 30 kV/m and 0.9 G. Field exposures were preceded and followed by sham exposures, during which factors of field generation were present (e.g., heat, vibration, noise, etc.) without E and B fields. Each of the five segments (i.e., the three exposure segments and the initial and final sham exposure segments) lasted 3 weeks. Animals were exposed for 18 h/day (fields on at 1600 h, off at 1000 h). Four other animals (external control group) were given sham exposure for the entire 15-week period. Auditory, visual, and somatosensory evoked potentials were recorded twice a week, during the daily 6-h field-off period. E- and B-field exposure had no effect on the early or mid-latency evoked potential components, suggesting that exposure at these levels has no effect on peripheral or central sensory afferent pathways. However, there was a statistically significant decrease in the amplitudes of late components of the somatosensory evoked potential during the 10kV/m and 0.3 G, and 30 kV/m and 0.9 G exposure levels. This result is possibly related to the opiate antagonist effect of electromagnetic field exposure reported by others.
Keywords: 60-Hz electromagnetic radiation; auditory; brainstem auditory; evoked potential; primates; somatosensory; visual

Chronic exposure of primates to 60-Hz electric and magnetic fields: II. Neurochemical effects. - Seegal, R. F.; Jonathan Wolpaw; Dowman, R. (Bioelectromagnetics, 1989)
We exposed Macaca nemestrina (pig-tailed macaques) to electric (E) and magnetic (B) fields ranging in intensity from 3 kV/m and 0.1 G to 30 kV/m and 0.9 G for three 21-day (d) periods. Experimental animals were exposed to sham E and B fields for two 21-d periods, one prior to and one following actual exposure to E and B fields, resulting in a total of five 21-d periods. Control animals were exposed to sham E and B fields for the entire 105-d interval. At the end of each 21-d period cerebrospinal fluid (CSF) was obtained by lumbar puncture and analyzed for concentrations of homovanillic acid (HVA) and 5-hydroxyindoleacetic acid (5-HIAA), metabolites of dopamine and serotonin neurotransmitters, respectively, by high-performance liquid chromatography with electrochemical detection (HPLC-ECD). Results are based on an examination of six experimental and four control animals. Exposure to E and B fields at all strengths was associated with a significant decline in CSF concentrations of both HVA and 5-HIAA when statistical comparisons were made against values obtained at the end of the preexposure interval. However, HVA returned to preexposure levels during the postexposure period, while 5-HIAA did not. No significant change in the concentrations of HVA or 5-HIAA was noted in the control animals. These results strongly suggest that exposure of the nonhuman primate to E and B fields can significantly affect specific biochemical estimates of nervous system function. These effects may involve alterations either in neuronal activity or in the activity of enzymes that catabolize the neurotransmitters.
Keywords: Neurotransmitter Agents

Diurnal rhythms in primate spinal reflexes and accompanying cortical somatosensory evoked potentials. - Dowman, R.; Jonathan Wolpaw (Electroencephalography and clinical neurophysiology, 1989)
We recorded spinal reflexes and cortical somatosensory evoked potentials (SEPs), elicited by stretching the biceps or the triceps muscle or by electrically stimulating the posterior tibial nerve, from monkeys throughout the day. Amplitudes of the spinal stretch reflex (SSR) and of its electrically evoked analogue, the H-reflex, varied diurnally: both were greatest midway through the lights-off period and smallest during the lights-on period. Stretch-evoked and electrically evoked SEP amplitudes also varied diurnally, but were out of phase with the spinal reflex rhythms. The H-reflex is elicited by direct stimulation of the nerve and thus, unlike the SSR, bypasses the muscle spindle. The H-reflex diurnal rhythm and the phase difference between the spinal reflex and SEP diurnal rhythms indicate that these rhythms are mediated at least in part by central mechanisms. Furthermore, both the spinal reflex and SEP diurnal rhythms appeared to be entrained by the light-dark cycle, which suggests that they may be coupled to the same oscillator. Besides their theoretical importance, these rhythms have important implications for experimental and clinical studies of spinal reflexes and SEPs. These rhythms are especially pertinent to the interpretation of long-term monitoring studies, as are often carried out in the Intensive Care Unit and during lengthy neurosurgical procedures.
Keywords: Spinal Cord

Horizontal organization of orientation-sensitive cells in primate visual cortex. - Baxter, Bill; Dow, B M (Biol Cybern, 1989)
In the visual cortex of the monkey the horizontal organization of the preferred orientations of orientation-selective cells follows two opposing rules: (1) neighbors tend to have similar orientation preferences, and (2) many different orientations are observed in a local region. We have described a classification for orientation maps based on the types of topological singularities and the spacing of these singularities relative to the cytochrome oxidase blobs. Using the orientation drift rate as a measure we have compared simulated orientation maps to published records of horizontal electrode recordings.
Keywords: Animals; Electron Transport Complex IV; Form Perception; Models, Neurological; Pattern Recognition, Visual; Visual Cortex

Memory traces in primate spinal cord produced by operant conditioning of H-reflex. - Jonathan Wolpaw; Lee, C. L. (Journal of neurophysiology, 1989)
1. Study of memory traces in higher animals requires experimental models possessing well-localized and technically accessible memory traces–plasticity responsible for behavioral change, not dependent on control from elsewhere, and open to detailed investigation. Our purpose has been to develop such a model based on the wholly spinal, largely monosynaptic path of the spinal stretch reflex. Previous studies described operant conditioning of this reflex and of its electrical analog, the H-reflex. In this study, we sought to determine whether conditioning causes changes in the spinal cord that affect the reflex and are not dependent on continued supraspinal influence, and thus qualify as memory traces. 2. Sixteen monkeys underwent chronic conditioning of the triceps surae H-reflex. Eight were rewarded for increasing H-reflex amplitude (HR increases mode), and eight were rewarded for decreasing it (HR decreases mode). In each animal, the other leg was an internal control. Over several months of conditioning, H-reflex amplitude in the conditioned leg rose in HR increases animals and fell in HR decreases animals. H-reflex amplitude in the control leg changed little. 3. After HR increases or HR decreases conditioning, each animal was deeply anesthetized and surgically prepared. The reflex response to supramaximal dorsal root stimulation was measured from the triceps surae nerve as percent of response to supramaximal ventral root stimulation, which was the maximum possible response. Data from both legs were collected before and for up to 3 days after thoracic (T9-10) cord transection. The animal remained deeply anesthetized throughout and was killed by overdose. 4. The reflex asymmetries produced by conditioning were still present several days after transection removed supraspinal influence: reflexes of HR increases animals were significantly larger in HR increases legs than in control legs and reflexes of HR decreases animals were significantly smaller in HR decreases legs than in control legs. 5. Reflex amplitude was much greater in the control legs of anesthetized HR decreases animals than in the control legs of anesthetized HR increases animals. 6. Chronic conditioning had at least two effects on the spinal cord. The first effect, task-appropriate reflex asymmetry, was evident both in the awake behaving animal and in the anesthetized transected animal. The second effect, larger control leg reflexes in HR decreases than in HR increases animals, was evident only in the anesthetized animal. By removing supraspinal control, anesthesia and transection revealed a previously hidden effect of conditioning.(ABSTRACT TRUNCATED AT 400 WORDS)
Keywords: Spinal Cord

Memory traces in spinal cord produced by H-reflex conditioning: effects of post-tetanic potentiation. - Jonathan Wolpaw; Jonathan S. Carp; Lee, C. L. (Neuroscience letters, 1989)
Operant conditioning of the wholly spinal, largely monosynaptic triceps surae H-reflex in monkeys causes changes in lumbosacral spinal cord that persist after removal of supraspinal influence. We evaluated the interaction between post-tetanic potentiation and these memory traces. Animals in which the triceps surae H-reflex in one leg had been increased or decreased by conditioning were deeply anesthetized, and monosynaptic reflexes to L6-S1 dorsal root stimulation were recorded before and after tetanization from both legs for 3 days after thoracic cord transection. Animals remained anesthetized throughout and were sacrificed by overdose. Reflex asymmetries consistent with the effect of H-reflex conditioning were present after transection and persisted through the 3 days of study. Tetanization affected conditioned leg and control leg reflexes similarly. This finding suggests that, while post-tetanic potentiation and probably H-reflex conditioning alter Ia synaptic transmission, the two phenomena have different mechanisms.
Keywords: conditioning; Learning; Memory; motoneuron; potentiation; primate; spinal reflex

Operant conditioning of primate triceps surae H-reflex produces reflex asymmetry. - Jonathan Wolpaw; Lee, C. L.; Calaitges, J. G. (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 1989)
Monkeys are able to increase or decrease triceps surae H-reflex when reward depends on reflex amplitude. Operantly conditioned change occurs over weeks and produces persistent alterations in the lumbosacral spinal cord which should be technically accessible substrates of primate memory. Previous work monitored and conditioned triceps surae H-reflex in one leg. To determine whether H-reflex conditioning in one leg affects the control leg, the present study monitored H-reflexes in both legs while the reflex in one leg underwent HR increases or HR decreases conditioning. Under the HR increases mode, H-reflex increase was much greater in the HR increases leg than in the control leg. Under the HR decreases mode, H-reflex decrease was confined to the HR decreases leg. By showing that conditioning of one leg's H-reflex produces H-reflex asymmetry, the data further define the phenomenon and indicate that the other leg can serve as an internal control for physiologic and anatomic studies exploring the sites and mechanisms of the spinal cord memory substrates.
Keywords: Learning; Memory; monosynaptic reflex; operant conditioning; plasticity; Spinal Cord; spinal reflex

Prevention of phencyclidine-induced depression of the segmental reflex by L-3,4-dihydroxyphenylalanine in the rat spinal cord in vitro. - Jonathan S. Carp; Ohno, Y.; Warnick, J. E. (The Journal of pharmacology and experimental therapeutics, 1989)
The interaction between phencyclidine (PCP) and the catecholamine precursor L-3,4-dihydroxyphenylalanine (DOPA) was studied in the isolated spinal cord from neonatal rats. PCP decreased the magnitude of the dorsal-ventral reflex and enhanced frequency-dependent depression of the reflex in a concentration-dependent manner. Although DOPA and DL-threo-3,4-dihydroxyphenylserine (a direct precursor for norepinephrine) had no effect on the reflex by themselves, DOPA, but not DL-threo-3,4-dihydroxyphenylserine prevented the depression of the reflex response by PCP in a concentration-dependent manner. Inhibition of aromatic-L-amino-acid decarboxylase (EC 4.1.1.2A) by m-hydroxybenzylhydrazine markedly attenuated the action of DOPA in preventing the depression caused by PCP. The dopamine receptor antagonists haloperidol and chlorpromazine blocked the action of DOPA, but the alpha and beta adrenergic receptor antagonists phentolamine and timolol, respectively, did not. In addition, prior treatment of neonatal rats with 6-hydroxydopamine diminished the ability of DOPA to prevent the depressant effect of PCP whereas partially attenuating the depressant effect of PCP alone. These results suggest that DOPA attenuated PCP-induced depression of spinal cord transmission through its conversion to dopamine rather than norepinephrine.
Keywords: Spinal Cord

Jendrassik maneuver facilitates soleus H-reflex without change in average soleus motoneuron pool membrane potential. - Dowman, R.; Jonathan Wolpaw (Experimental neurology, 1988)
Facilitation of spinal reflex amplitude by remote muscle contraction, otherwise known as the Jendrassik maneuver (JM), was first shown over 100 years ago, yet the mechanism by which this facilitation operates remains undetermined. Earlier work has eliminated participation of the muscle spindle in JM-induced spinal reflex facilitation, leaving changes in postsynaptic (e.g., change in average soleus motoneuron membrane potential) and presynaptic (e.g., inhibition of presynaptic inhibition) mechanisms as viable candidates. We recorded background EMG in the soleus muscle during JM-induced soleus H-reflex facilitation in humans. The JM in this experiment consisted of wrist muscle contraction. Soleus background EMG was maintained by the subject at either a zero level (e.g., relaxed) or a specified moderate level prior to and during the JM. The JM increased H-reflex amplitude by comparable amounts in both situations, but had no effect on soleus background EMG. Given the well-known relationship between the average motoneuron pool membrane potential and background EMG, we conclude that JM facilitation of the soleus H-reflex is not caused by an increase in background excitatory input to the soleus motoneuron pool. Remaining candidates for mediation of JM induced H-reflex facilitation include change in stimulus-evoked afferent input at some point proximal to the muscle spindle, such as reduction in presynaptic inhibition, or a change in motoneuron input resistance.
Keywords: Reflex; Stretch

Operant conditioning of primate spinal reflexes: effect on cortical SEPs. - Jonathan Wolpaw; Dowman, R. (Electroencephalography and clinical neurophysiology, 1988)
Previous studies have demonstrated operant conditioning of the primate spinal stretch reflex (SSR) and of its electrical analog, the H-reflex. We studied the evoked potential recorded over primary somatosensory cortex (SEP) which accompanies the H-reflex to determine whether the initial cortical response changes in the course of conditioned H-reflex change. When H-reflex amplitude changed, SEP amplitude also changed, but only half as much as the H-reflex. The results indicate that, while operant conditioning of the H-reflex has its largest effect on the spinal pathway of the reflex, it also has some effect on supraspinal pathways of the initial cortical response.
Keywords: cortical response; H-Reflex; Learning; Memory; operant conditioning; plasticity; somatosensory evoked potential; spinal reflex

Retrograde transport of the lectin Phaseolus vulgaris leucoagglutinin (PHA-L) by rat spinal motoneurons. - Lee, C. L.; Dennis J. McFarland; Jonathan Wolpaw (Neuroscience letters, 1988)
The lectin Phaseolus vulgaris leucoagglutinin (PHA-L) has been used primarily as an anterograde transport tracer in the CNS. We present evidence of PHA-L retrograde transport by rat spinal motoneurons after injection into the triceps brachii. Labelled motoneurons were localized in specific and well-defined neuron pools in the ventral horn. Primary afferent labelling was not seen in the spinal gray matter. Dorsal rhizotomy did not eliminate or decrease motoneuron labelling. The retrograde transport rate was about 8 mm/day. PHA-L can clearly undergo retrograde, as well as anterograde, transport.
Keywords: lectin; phaseolus vulgaris leucoagglutinin (PHA-L); rat; retrograde transport; spinal motoneuron

Spinal stretch reflex and cortical evoked potential amplitudes versus muscle stretch amplitude in the monkey arm. - Jonathan Wolpaw; Dowman, R. (Electroencephalography and clinical neurophysiology, 1988)
While investigating operant conditioning of the primate spinal stretch reflex (SSR), we studied SSR amplitude and cortical somatosensory evoked potential (SEP) amplitude as stretch amplitude changed in the monkey arm. Initial muscle length and background EMG activity remained constant. With change in stretch amplitude (and proportional change in stretch velocity and acceleration), changes in SSR and SEP amplitudes were respectively 0.75 and 0.66 as great. The lesser change in SSR amplitude may reflect saturation of Ia afferents, while that in SEP amplitude may also reflect participation of other peripheral receptors.
Keywords: muscle stretch; primate; Somatosensory Cortex; somatosensory evoked potential; spinal reflex; stretch reflex

T complex hemispheric asymmetries: effects of stimulus intensity. - Anthony T. Cacace; Dowman, R.; Jonathan Wolpaw (Hearing research, 1988)
The T complex component of the human auditory evoked potential (AEP) is thought to be produced in auditory cortex, on the posterior lateral surface of the temporal lobe. Recorded over temporal scalp, it consists of an 80-90 ms positive peak, Ta, and a 120-140 negative peak, Tb. As part of an effort to develop the clinical usefulness of the T complex in assessing auditory cortical function, we studied the effects of change in monaural stimulus intensity (20-80 dB SL) on T complex latency, amplitude, and hemispheric differences in normal adults. Ta and Tb peak latencies decreased as stimulus intensity increased. These latency changes were not dependent on ear or hemisphere. Right hemisphere Ta latency was shorter with contralateral than with ipsilateral stimulation; while left hemisphere Ta latency was not dependent on the ear stimulated. Tb latency was shorter over the left hemisphere, and over the contralateral hemisphere. Ta-b amplitude increased as stimulus intensity increased. This amplitude change was not dependent on ear or hemisphere. Ta-b amplitudes were larger over the right hemisphere and over the contralateral hemisphere. Hemispheric asymmetries were not significantly affected by stimulus intensity.
Keywords: Reaction Time

Motoneuron response to dorsal root stimulation in anesthetized monkeys after spinal cord transection. - Jonathan Wolpaw; Lee, C. L. (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 1987)
In preparation for studying the spinal cord alterations produced by operant conditioning of spinal reflexes, we studied peripheral nerve responses to supramaximal dorsal root stimulation in the lumbosacral cord of deeply anesthetized monkeys before and after thoracic cord transection. Except for variable depression in the first few minutes, reflex responses were not reduced or otherwise significantly affected by transection in the hour immediately following the lesion or for at least 50 h. The results suggest that reduction in muscle spindle sensitivity and/or in polysynaptic motoneuron excitation contributes to stretch reflex depression after cord transection.
Keywords: monosynaptic reflex; primate; Spinal Cord; spinal cord injury; spinal reflex; spinal shock

Operant conditioning of primate spinal reflexes: the H-reflex. - Jonathan Wolpaw (Journal of neurophysiology, 1987)
The study of primate memory substrates, the CNS alterations which preserve conditioned responses, requires an experimental model that fulfills two criteria. First, the essential alterations must be in a technically accessible location. Second, they must persist without input from other CNS regions. The spinal cord is the most technically accessible and readily isolated portion of the primate CNS. Recent work has demonstrated that the spinal stretch reflex (SSR), the initial, wholly segmental response to muscle stretch, can be operantly conditioned and suggests that this conditioning may produce persistent spinal alteration. The present study attempted similar operant conditioning of the H-reflex, the electrical analog of the SSR. The primary goals were to demonstrate that spinal reflex conditioning can occur even if the muscle spindle is removed from the reflex arc and to demonstrate conditioning in the lumbosacral cord, which is far preferable to the cervical cord for future studies of neuronal and synaptic mechanisms. Nine monkeys prepared with chronic fine-wire triceps surae (gastrocnemius and soleus) electromyographic (EMG) electrodes were taught by computer to maintain a given level of background EMG activity. At random times, a voltage pulse just above M response (direct muscle response) threshold was delivered to the posterior tibial nerve via a chronically implanted silicon nerve cuff and elicited the triceps surae H-reflex. Under the control mode, reward always followed. Under the HR increases or HR decreases mode, reward followed only if the absolute value of triceps surae EMG from 12 to 22 ms after the pulse (the H-reflex interval) was above (HR increases) or below (HR decreases) a set value. Monkeys completed 3,000-6,000 trials/day over study periods of 2-3 mo. Background EMG and M response amplitude remained stable throughout data collection. H-reflex amplitude remained stable under the control mode. Under the HR increases mode (5 animals) or HR decreases mode (4 animals), H-reflex amplitude (EMG amplitude in the H-reflex interval minus background EMG amplitude) changed appropriately over at least 6 wk. Change appeared to occur in two phases: an abrupt change within the first day, followed by slower change, which continued indefinitely. Change occurred in all three triceps surae muscles (medial and lateral gastrocnemii and soleus). Under the HR increases mode, H-reflex amplitude rose to an average of 213% of control, whereas under the HR decreases mode it fell to an average of 68% of control. The results demonstrate that the H-reflex can be operantly conditioned.(ABSTRACT TRUNCATED AT 400 WORDS)
Keywords: Spinal Cord

Adaptive plasticity in primate spinal stretch reflex: persistence. - Jonathan Wolpaw; O'Keefe, J. A.; Noonan, P. A.; Sanders, M. G. (Journal of neurophysiology, 1986)
Monkeys can gradually change the amplitude of the wholly segmental, largely monosynaptic, spinal stretch reflex (SSR) when confronted by a task requiring such change (15-19). Change develops over months and may reverse and redevelop at similarly slow rates. We investigated the persistence of SSR amplitude change over nonperformance periods of up to 38 days. Eight animals with chronic EMG electrodes learned to maintain elbow angle and a given level of biceps background EMG against constant extension torque. At random times, a brief additional extension torque pulse elicited the biceps SSR. In the control mode, reward always followed. Under the SSR increase or SSR decrease mode, reward occurred only if the absolute value of biceps EMG in the SSR interval was above or below a set value. Animals completed 3,000-6,000 trials/day over data-collection periods of 2-17 mo. Animals worked first under the control mode for up to 60 days and then under the SSR increase or SSR decrease mode for up to 274 days. Mode was switched once or twice more (SSR increase to SSR decrease or vice versa) over subsequent months. Animals responded to each SSR increase or SSR decrease mode exposure with gradual mode-appropriate change in SSR amplitude. Mode exposures were interrupted by gaps in performance of 10-38 days. Gaps produced transient 10- to 15% decreases in SSR amplitude under the control mode. This nonspecific decrease disappeared over the first week of postgap performance. Under the control mode, gaps had no other effects on SSR amplitude.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Spinal Cord

Enhancement by serotonin of tonic vibration and stretch reflexes in the decerebrate cat. - Jonathan S. Carp; Rymer, W. Z. (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 1986)
The effects of pharmacological manipulation of serotonergic systems on spinal reflexes were determined in the unanesthetized decerebrate cat. The prolonged motor output that continues after cessation of high frequency longitudinal tendon vibration was strongly enhanced by the serotonin reuptake blocker fluoxetine and the serotonin precursor 5-hydroxytryptophan, and was decreased by the serotonin receptor antagonist methysergide. In addition, both dynamic and static stretch reflex stiffness was markedly increased by fluoxetine and 5-hydroxytryptophan, while methysergide produced a decrease in stretch reflex stiffness. These powerful effects on tonic vibration and stretch reflexes could not be explained by drug-induced alterations in muscle spindle primary afferent discharge. In light of other recent results on serotonin-mediated effects on motoneurons, we believe that the effects of these agents result from modification of an intrinsically mediated prolonged depolarization of spinal neurons. However, the possibility that these drugs modify longlasting discharge in associated interneuronal pathways cannot be ruled out.
Keywords: bistable neuronal behavior; serotonin; Spinal Cord; stretch reflex; tonic vibration reflex

Adaptive plasticity in the spinal stretch reflex: an accessible substrate of memory?. - Jonathan Wolpaw (Cellular and molecular neurobiology, 1985)
The study of the substrates of memory in higher vertebrates is one of the major problems of neurobiology. A simple and technically accessible experimental model is needed. Recent studies have demonstrated long-term adaptive plasticity, a form of memory, in the spinal stretch reflex (SSR). The SSR is due largely to a two-neuron monosynaptic arc, the simplest, best-defined, and most accessible pathway in the primate central nervous system (CNS). Monkeys can slowly change SSR amplitude without a change in initial muscle length or alpha motoneuron tone, when reward is made contingent on amplitude. Change occurs over weeks and months and persists for long periods. It is relatively specific to the agonist muscle and affects movement. The salient features of SSR adaptive plasticity, combined with clinical and laboratory evidence indicating spinal cord capacity for intrinsic change, suggest that SSR change eventually involves persistent segmental alteration. If this is the case, SSR plasticity should be a powerful model for studying the neuronal and synaptic substrates of memory in a primate.
Keywords: Learning; Memory; plasticity; primate; spinal reflex; stretch reflex

Reduced day-to-day variation accompanies adaptive plasticity in the primate spinal stretch reflex. - Jonathan Wolpaw; O'Keefe, J. A.; Kieffer, V. A.; Sanders, M. G. (Neuroscience letters, 1985)
Monkeys can change the amplitude of the spinal stretch reflex (SSR), or M1, when reward is made contingent on amplitude. The present study demonstrates that reduced SSR day-to-day variation accompanies such adaptive SSR change. This finding supports the assumption that initial, phase I, SSR change results from contingency-appropriate stabilization of tonic activity in relevant descending spinal cord pathways.
Keywords: Learning; Memory; plasticity; primate; spinal reflex; stretch reflex

Adaptive plasticity and diurnal rhythm in the primate spinal stretch reflex are independent phenomena. - Jonathan Wolpaw; Noonan, P. A.; O'Keefe, J. A. (Brain research, 1984)
Recent studies have revealed two phenomena producing considerable variation in amplitude of the initial, purely segmental, largely monosynaptic, response to sudden muscle stretch, the spinal stretch reflex (SSR), without change in background EMG activity or initial muscle length. The first is small and short-term, a modest diurnal rhythm in SSR amplitude. The second is large and long-term, marked adaptive change in SSR amplitude which occurs gradually over weeks and months when animals are rewarded for such change. This second phenomenon may involve persistent segmental alteration, and, if so, could constitute a technically accessible substrate of memory. The present study compared the two phenomena and sought evidence of interaction between them. The diurnal rhythm persisted, without change in phase and with only minimal change in amplitude, despite the occurrence of marked adaptive change. Animals did not utilize the rhythm to increase reward percentage by altering daily performance schedules. These results suggest that the mechanisms of the diurnal rhythm and of adaptive plasticity in SSR amplitude are separate and independent. The diurnal rhythm's effect on movement was not altered by adaptive change in SSR amplitude. This effect was comparable to adaptive change's effect on movement when both were expressed as change in movement/change in SSR amplitude.
Keywords: adaptive plasticity; diurnal rhythm; Learning; Memory; primate; stretch reflex

Adaptive plasticity in the primate spinal stretch reflex: evidence for a two-phase process. - Jonathan Wolpaw; O'Keefe, J. A. (The Journal of neuroscience : the official journal of the Society for Neuroscience, 1984)
Monkeys can slowly increase or decrease the amplitude of the purely spinal, largely monosynaptic portion of the response to sudden muscle stretch, the spinal stretch reflex (SSR), when confronted by a task requiring such change (Wolpaw, J.R., V.A. Kieffer, R.F. Seegal, D.J. Braitman, and M.G. Sanders (1983) Brain Res. 267: 196-200; Wolpaw, J.R., D.J. Braitman, and R.F. Seegal (1983) J. Neurophysiol. 50: 1296-1311). Change occurs without alteration in initial muscle length or in background activity of agonist, antagonist, or synergist muscles. This study uses composite curves to describe in detail the development of SSR amplitude change. It reveals important, previously unexpected features of this development. SSR increase or decrease appears to occur in two distinct phases. Phase I, a nearly immediate 8% change, occurs within the first 6 hr. Phase II, a 2%/day change, continues for at least 2 months. Although phase II is much slower than phase I, its final magnitude is far greater. Phase I indicates a nearly immediate change in suprasegmental influence of the segmental arc of the SSR. Because stretch onset time is unpredictable and the SSR occurs before any other possible response, this change in descending activity must be tonic; it must be present continually, day after day, for the 5 to 7 hr/day the animal spends at the task. Phase I produces a rapid and significant increase in reward probability. Thus, it may be readily interpreted as an example of operant conditioning, provoked by the reward contingency.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Time Factors

Psychoacoustic and electrophysiologic effects of partial eighth nerve damage. - Anthony T. Cacace; Goldstein, J. C.; Parnes, S. M.; Satya-Murti, S.; Jonathan Wolpaw (American journal of otolaryngology, 1984)
The authors present psychoacoustic and electrophysiologic data concerning a patient with partial damage to the auditory nerve, presumably from a dilated arterial vessel. The lesion was described and documented during neurosurgery for vestibular nerve decompression. Pure tone thresholds, psychoacoustical tuning curves, speech reception ability for spondaic words, maximum word recognition performance for monosyllabic NU-6 word lists, and performance on the synthetic sentence identification test in the ipsilateral and contralateral competing message modalities were normal. Findings consistent with eighth nerve dysfunction, absent contralateral acoustic reflexes, absent or unrecognizable early evoked potentials occurring in the first 10 msec, brainstem auditory evoked potentials (BAEPs), and slight rollover of the performance intensity function for monosyllabic words were obtained on the involved side. In spite of the grossly abnormal BAEPs, two late, presumably cortical, auditory evoked potential components, which occur in the 60 to 250-msec range–vertex potential and T complex–were present and normal. The findings indicate that the perceptual processes needed for speech reception and recognition and for the appearance of later, presumably cortical-evoked potentials can be preserved despite partial damage to the auditory nerve.
Keywords: Vestibulocochlear Nerve Diseases

Adaptive plasticity in primate spinal stretch reflex: behavior of synergist and antagonist muscles. - Jonathan Wolpaw; Seegal, R. F.; O'Keefe, J. A. (Journal of neurophysiology, 1983)
Monkeys can gradually change the amplitude of the biceps spinal stretch reflex (SSR) without change in initial muscle length or biceps background electromyographic activity (EMG) (17). We investigated the concurrent behavior of synergist (brachialis and brachioradialis) and antagonist (triceps) muscles. Synergist background EMG remained stable while marked change occurred in biceps SSR amplitude. Triceps background EMG was minimal under all conditions. Thus biceps SSR amplitude change was not due to change in the background activity of closely related muscles. When biceps SSR amplitude changed, synergist SSR amplitude changed similarly but to a lesser extent. Brachialis change averaged 72% of biceps change, while brachioradialis change averaged 33%. By indicating that SSR amplitude change is relatively specific to the agonist muscle, this finding eliminates a number of nonspecific mechanisms as possible origins of SSR amplitude change. Thus it supports the potential value of the SSR as a system for studying the neuronal and synaptic bases of memory in the primate central nervous system (CNS).
Keywords: Spinal Cord

Adaptive plasticity in primate spinal stretch reflex: initial development. - Jonathan Wolpaw; Braitman, D. J.; Seegal, R. F. (Journal of neurophysiology, 1983)
Description of the neuronal and synaptic bases of memory in the vertebrate central nervous system (CNS) requires a CNS stimulus-response pathway that is defined and accessible, has the capacity for adaptive change, and clearly contains the responsible substrates. This study was an attempt to determine whether the spinal stretch reflex (SSR), the initial, purely spinal, portion of the muscle stretch response, which satisfies the first requirement, also satisfies the second, capacity for adaptive change. Monkeys prepared with chronic fine-wire biceps electromyographic (EMG) electrodes were trained to maintain elbow position and a given level of biceps background EMG activity against constant extension torque. At random times, a brief additional extension torque pulse extended the elbow and elicited the biceps SSR. Under the control mode, reward always followed. Under the SSR increases or SSR decreases mode, reward followed only if the absolute value of biceps EMG from 14 to 24 ms after stretch onset (the SSR interval) was above or below a set value. Animals performed 3,000-6,000 trials/day over data-collection periods of up to 15 mo. Background EMG and the initial 30 ms of pulse-induced extension remained stable throughout data collection. Under the SSR increases or SSR decreases mode, SSR amplitude (EMG amplitude in the SSR interval minus background EMG amplitude) changed appropriately. Change was evident in 5-10 days and progressed over at least 4 wk. The SSR increased (SSR increases) to 140-190% control amplitude or decreased (SSR decreases) to 22-79%. SSR change did not regress over 12-day gaps in task performance. A second pair of biceps electrodes, monitored simultaneously, supplied comparable data, indicating that SSR amplitude change occurred throughout the muscle. Beyond 40 ms after pulse onset, elbow extension was inversely correlated with SSR amplitude. The delay between the SSR and its apparent effect on movement is consistent with expected motor-unit contraction time. The data demonstrate that the SSR is capable of adaptive change. At present the most likely site(s) of the mechanism of SSR amplitude change are the Ia synapse and/or the muscle spindle. Available related evidence suggests persistent segmental change may in fact come to mediate SSR amplitude change. If so, such segmental change would constitute a technically accessible fragment of a memory.
Keywords: Spinal Cord

Adaptive plasticity in the primate spinal stretch reflex: reversal and re-development. - Jonathan Wolpaw (Brain research, 1983)
Monkeys can gradually increase or decrease the amplitude of the segmentally mediated spinal stretch reflex (SSR) without change in initial muscle length or background EMG activity. Both increase (under the SSR increases mode) and decrease (under the SSR decreases mode) occur slowly, progressing steadily over weeks. The present study investigated reversal and re-development of SSR amplitude change. Over a period of months, following collection of control data, monkeys were exposed to one mode, then to the other, and then to the first mode again. Development, reversal, and re-development of change all took place over weeks, following very similar courses. These data are consistent with the hypothesis that persistent segmental alteration underlies SSR amplitude change. Such persistent segmental alteration would constitute a technically accessible substrate of memory.
Keywords: Learning; Memory; plasticity; primate; spinal reflex; stretch reflex

Adaptive plasticity in the spinal stretch reflex. - Jonathan Wolpaw; Kieffer, V. A.; Seegal, R. F.; Braitman, D. J.; Sanders, M. G. (Brain research, 1983)
Monkeys can change the amplitude of the spinal stretch reflex without change in initial alpha motor neuron tone, as measured by EMG, or in initial muscle length. Change is apparent in 5-10 days, continues to develop over weeks, and persists during inactive periods. Spinal stretch reflex change may be a valuable system for studying the neuronal and synaptic bases of an adaptive change in primate CNS function.
Keywords: Learning; Memory; plasticity; primate; spinal reflex; stretch reflex

Electrophysiological and biochemical studies on enhancement of desensitization by phenothiazine neuroleptics. - Jonathan S. Carp; Aronstam, R. S.; Witkop, B.; Albuquerque, E. X. (Proceedings of the National Academy of Sciences of the United States of America, 1983)
The actions of the phenothiazines chlorpromazine, prochlorperazine, and trifluoperazine were studied on the acetylcholine receptor-ionic channel complex of frog and rat skeletal muscle and of Torpedo californica to determine their role in pharmacological desensitization and their interactions with different states of the receptor-ionic channel complex. The phenothiazines depressed the peak amplitude of spontaneous and evoked endplate currents while having negligible effect on the decay time constants. Mean channel lifetime and single channel conductance were not altered by these drugs. They also produced a frequency-dependent depression of the peak amplitude of endplate potentials evoked by repetitive microiontophoresis at the extrajunctional region. In addition, these drugs enhanced the ability of carbamoylcholine to displace 125I-labeled alpha-bungarotoxin from receptor-rich membrane preparations of T. californica when used in concentrations that had no effect on 125I-labeled alpha-bungarotoxin binding alone (10 microM). Similarly, the phenothiazines inhibited the binding of tritiated ionic channel ligands, such as phencyclidine and perhydrohistrionicotoxin, a process also enhanced by the presence of carbamoylcholine. These data suggest that the phenothiazines augment agonist-induced desensitization primarily by interacting with the receptor-ionic channel complex prior to channel opening.
Keywords: Torpedo

Late auditory evoked potentials can occur without brain stem potentials. - Satya-Murti, S.; Jonathan Wolpaw; Anthony T. Cacace; Schaffer, C. A. (Electroencephalography and clinical neurophysiology, 1983)
The sequence of early, middle and late auditory evoked potentials is well known. However, it is unknown whether the late (60-250 msec) potentials can occur independently of the early, brain stem potentials. Therefore, in 6 subjects with markedly abnormal or absent brain stem potentials, we recorded two of the late potentials: the vertex potential and the T-complex. The latter is a putative product of auditory cortex. Both of these potentials were clearly evident in all patients in spite of the absence of or marked abnormalities in brain stem potentials.
Keywords: Humans

Change in short-latency response to limb displacement in primates. - Jonathan Wolpaw (Federation proceedings, 1982)
When a muscle is stretched in an awake, behaving primate the earliest electromyographic (EMG) responses of the muscle consists of several reflex components. The earliest, M1, is mediated entirely at the segmental level and is largely monosynaptic. The next M2, is at least in part the result of an oligosynaptic transcortical loop to control the M1 response remains to be established. If primates can learn to control M1 amplitude, the M1 loop, which is the simplest and most accessible stimulus-response pathway in the primate central nervous system, may serve as a model for the study of mechanisms of memory. Preliminary evidence presented here strongly suggests that primates can control M1 gain without change in prestimulus EMG activity. The mechanisms of such change remain to be determined. Possibilities include change in gamma motor neuron tone, in Ia synaptic function, and in alpha motor neuron recruitment. The usefulness of learned M1 change as a model for memory will depend to a large extent on the nature of the responsible mechanism and on demonstration that the change can eventually become resident at the segmental level, without need for continued descending input.
Keywords: Reflex; Stretch

Diurnal rhythm in the spinal stretch reflex. - Jonathan Wolpaw; Seegal, R. F. (Brain research, 1982)
We studied primate spinal stretch reflex (SSR) amplitude as a function of time of day. SSR amplitude was greatest around midnight and smallest around noon. The diurnal rhythm was not simply a function of number of trials, or of the lighting cycle. This rhythm offers an opportunity to study the neuronal and synaptic mechanisms producing a diurnal change in CNS function. Its existence indicates that the CNS response to a given limb disturbance, and thus the CNS activity underlying a given performance, varies with time of day.
Keywords: circadian rhythm; diurnal rhythm; muscle stretch; primate; spinal reflex; stretch reflex

Dopamine receptor-mediated depression of spinal monosynaptic transmission. - Jonathan S. Carp; Anderson, R. J. (Brain research, 1982)
The effects of the dopamine agonists apomorphine, lisuride and lergotrile were evaluated on cat spinal cord monosynaptic transmission by stimulating the dorsal root and recording the ventral root compound action potential. All 3 agonists decreased the area of the monosynaptic response. This effect was prevented by pretreatment with the dopamine antagonists haloperidol and metoclopramide, but not with the alpha-adrenergic antagonist phentolamine. These results suggest the existence of spinal cord dopamine receptors which can modulate motor output.
Keywords: apomorphine; dopamine agonists; dopamine receptors; lergotrile; lisuride; monosynaptic transmission; Spinal Cord

Scalp distribution of human auditory evoked potentials. I. Evaluation of reference electrode sites. - Jonathan Wolpaw; Wood, C. C. (Electroencephalography and clinical neurophysiology, 1982)
In an attempt to settle the long-standing controversy about the relative activity of nose, sternovertebral (SV), and other commonly used AEP reference sites, we recorded AEPs from a coronal chain of electrodes from the vertex to the tragus, extending down the neck, and from the nose, ear, mastoid process, knee and ankle. All electrodes were referred to a sternovertebral reference balanced to minimize EKG. Voltage gradients and wave forms corresponding to other references were derived by computer. Stimuli were presented at fixed durations after the R wave of the EKG and averages with no stimulus were subtracted from averages with click stimuli to minimize synchronized EKG activity in non-cephalic derivations. Because the activity at a given electrode site cannot be determined in absolute terms, alternative reference sites must be compard by examining the relative location of each site in the total potential field. An indifferent electrode site defined in this manner is one at which the spatial and temporal voltage gradients are minimal over the duration of the activity of interest. AEP voltage gradients in this experiment were steepest in the temporal region, became extremely shallow at locations on the upper neck, and showed no detectable gradients below that point attributable to AEP activity. A gradient of this form was obtained in all subjects, in spite of significant intersubject differences in the magnitude of potentials in nose-SV derivations. Commonly used reference sites on the head such as the nose, ear and mastoid process, were shown to lie in regions of the AEP field characterized by significant voltage gradients over time and spatial location in most subjects. The balanced sternovertebral reference of Stephenson and Gibbs (1951) appears to be the best general choice for AEP recordings.
Keywords: Sternum

Scalp distribution of human auditory evoked potentials. II. Evidence for overlapping sources and involvement of auditory cortex. - Wood, C. C.; Jonathan Wolpaw (Electroencephalography and clinical neurophysiology, 1982)
The scalp distributions of human auditory evoked potentials (AEPs) between 20 and 250 msec were investigated using non-cephalic reference recordings. AEPs to binaural click stimuli were recorded simultaneously from 20 scalp locations over the right hemisphere in 11 subjects. Computer-generated isovoltage topographic maps at high temporal resolution were used to assess the stability of AEP scalp distributions over time and relate them to major peaks in the AEP wave forms. For potentials between 20 and 60 msec, the results demonstrate a stable scalp distribution of dipolar form that is consistent with sources in primary auditory cortex on the superior temporal plant near the temporoparietal junction. For potentials between 60 and 250 msec, the results demonstrate changes in AEP morphology across electrode locations and changes in scalp distribution over time that lead to two major conclusions. First, AEPs in this latency period are generated by multiple sources which partially overlap in time. Second, one or more regions of auditory cortex contribute significantly to AEPs in this period. Additional data are needed to determine the relative contribution of auditory cortex sources on the superior temporal plane and the lateral temporal surface and to identify AEP sources outside the temporal lobe.
Keywords: Temporal Lobe

Modification of spinal cord transmission by an interaction of chlorpromazine and phenytoin. - Jonathan S. Carp; Anderson, R. J. (The Journal of pharmacology and experimental therapeutics, 1981)
Cat spinal cord monosynaptic activity during slow repetitive stimulation (0.2 Hz) and post-tetanic potentiation was used to evaluate the combination effects of phenytoin and chlorpromazine. The drug effects were compared in anesthetized cats with either high spinal transection or intact central nervous systems to determine whether the drugs were acting segmentally or suprasegmentally. When chlorpromazine and phenytoin were given in combination to intact animals, the depressant effect on the monosynaptic response was limited to 50% of control, which was not more than the maximum effect of either drug given alone. In spinal animals, chlorpromazine reversed the phenytoin-induced depression during 0.2 Hz stimulation, whereas only the effects of phenytoin on post-tetanic potentiation were evident after the drug combination. These results show that although phenytoin and chlorpromazine each have a depressant effect on spinal cord transmission, the combined effect is limited to a 50% decrease in intact animals. It is suggested that this occlusive drug effect demonstrates that the drug combination has a limited depressant action in the intact nervous system, an action which permits the expression of the effects of these drugs on the other elements of the reflex arc. Collectively, these actions of the drug combination are consistent with their known efficacy in treating certain cases of spasticity.
Keywords: Synaptic Transmission

Amplitude of responses to perturbation in primate sensorimotor cortex as a function of task. - Jonathan Wolpaw (Journal of neurophysiology, 1980)
1. Monkeys learned to maintain hand position against a range of background forces. Short-latency responses to passive wrist extension or flexion were recorded from units in areas 4, 3, 1, and 2. Response amplitude was studied as a function of background force direction (extension or flexion). 2. For 40% of the precentral and postcentral responses, response amplitude depended on constant force direction. For these dependent responses, amplitude with background force in one direction averaged 2.8 times amplitude with background force in the opposite direction. 3. Units for which background activity varied with constant force direction were designated task related. Dependent responses from area 4 task-related units were usually larger when background activity was greater and when background force direction matched the direction of the passive movement. 4. Dependent responses from area 4 task-related units occurred significantly later than nondependent responses from the same units. 5. Since most area 4 task-related activity was explicable as a result of peripheral input via the same oligosynaptic path mediating area 4 responses to passive movements (32), the present findings imply that area 4-task-related activity may result in large part from centrally mediated change in the access of short-latency peripheral input to area 4 units. 6. The dependence of responses from non-task-related area 4 units and from non-task-related and task-related postcentral units showed no dominant correlation with background activity or with background force direction. Their dependence appeared to require no explanation other than a change in peripheral input with change in background force direction.
Keywords: Wrist

Correlations between task-related activity and responses to perturbation in primate sensorimotor cortex. - Jonathan Wolpaw (Journal of neurophysiology, 1980)
1. Monkeys were trained to maintain hand position against a range of constant forces. Short-latency responses to passive wrist extension or flexion, as well as short-latency responses to stretch of a single wrist muscle, were recorded from units in areas 4, 3, 1, and 2. These responses were compared to unit activity during active holding and during active movement. 2. Units related to active holding and to active movement were most common in areas 4 and 2. Three-quarters of these units displayed a specific correlation between their passive and active behaviors. Thus, a unit excited by passive extension was excited during active holding against extension force and excited during an active flexion movement. This behavior is similar to the expected concurrent behavior of muscle stretch receptors. By demonstrating that a significant number of task-related units give qualitatively similar responses to passive extension and passive flexion, the results appear to explain the disagreement among previous studies (5, 9, 36) in regard to area 4 behavior during active and passive movements. 3. Area 4 units responded similarly to passive wrist extension and electromagnetic stretch of a single flexor muscle occurring in the absence of wrist extension, indicating that muscle stretch was important in determining area 4 unit responses to passive movements. 4. The similarity of area 4 behavior to area 2 behavior in active and passive situations, along with the observation that area 2 responses to passive movements occurred several milliseconds earlier than those of area 4, emphasizes the importance of area 2 in motor performance and is consistent with significant area 2 mediation of area 4 responses. 5. Results support the hypothesis of an oligosynaptic transcortical pathway (22, 32, 34), beginning in large part with muscle stretch receptors. Furthermore, the correlation noted between short-latency responses to passive movement and task-related activity suggests that this transcortical pathway not only mediates responses to passive movement but may be responsible, to a significant degree, for task-related activity during undisturbed performance. Thus, active position maintenance and active movement were probably accomplished, at least in part, by increasing and decreasing the influence of this pathway on specific area 4 neurons and thereby producing the patterns of area 4 activity responsible for task performance.
Keywords: Task Performance and Analysis

Electromagnetic method for in situ stretch of individual muscles. - Colburn, T. R.; Vaughn, W.; Christensen, J. L.; Jonathan Wolpaw (Medical & biological engineering & computing, 1980)
A technique for stretching individual muscles in intact behaving animals via chronic intramuscular implantation of a permeable slug and use of an external electromagnet to apply force to the slug has been developed for use in the study of the role of sensory input due to muscle stretch in the control of skilled motor activity. This paper is an analysis of the force exerted on a permeable slug by a solenoid, and a discussion of practical aspects of design and control. The force exerted on a slug inside a coil is a function of slug length, cross-sectional area, and magnetisation properties and of coil size, geometry, and current. The force inside the coil may be increased by surrounding the coil with a permeable sleeve and thereby increasing the field strength inside the coil.
Keywords: Electromagnetic force; Electromagnetic muscle strength; Motor control; Muscle stimulation; Sensorimotor system; Stimulation with force

The effects of phenytoin on motor function in awake cats. - Jonathan S. Carp; Anderson, R. J. (Archives internationales de pharmacodynamie et de thérapie, 1979)
Adult cats were monitored for their performance of a variety of motor functions before and after acute administration of phenytoin (5, 10 or 20 mg/kg) in a schedule in which each animal received all drug doses. The only significant loss in motor function was balance and coordination. Half the animals could not balance or walk along a narrow-edged beam after 20 mg/kg of phenytoin although their performance was not impaired at lower drug doses or on wider surfaces. There were no effects of phenytoin on the righting reflex, flexor reflex, muscle strength, the hopping response, the blind placing response or visually aided placing. The data suggest that phenytoin has a selective effect on higher order neuronal systems involved with balance and locomotion rather than simple reflex pathways.
Keywords: Reflex

Electromagnetic muscle stretch strongly excites sensorimotor cortex neurons in behaving primates. - Jonathan Wolpaw (Science (New York, N.Y.), 1979)
Responses of single units in primary motor and sensory cortex of behaving primates to electromagnetic stretch of the muscle flexor carpi ulnaris are comparable in latency and intensity to responses to wrist extension. Thus, muscle stretch appears to be a major factor in cortical response to limb displacement during performance and probably has an important role in motor control at the cortical level.
Keywords: Proprioception

Gyral impressions in the skull as a guide to cortical topography in chronic transdural unit recording. - Jonathan Wolpaw (Brain research, 1979)
Keywords: Skull

Sensorimotor deficits produced by phenytoin and chlorpromazine in unanesthetized cats. - Jonathan S. Carp; Anderson, R. J. (Pharmacology, biochemistry, and behavior, 1979)
Unanesthetized adult cats were evaluated for suprasegmental reflex activity and motor skills before and after administration of chlorpromazine (0.0625–0.5 mg/kg) alone and in combination with phenytoin (20 mg/kg). The greatest deficits were seen in the tests of balance and corrdination in which half the animals failed to match their control responses after administration of chlorpromazine and phenytoin. The impairment was most noticeable with the most stringent test (walking a 4 cm wide beam), and the effects of the two drugs were additive. Although there was no effect of either drug on muscle strength, the two drugs in combination depressed the animals' motivational state, making them less willing to work against imposed loads. Neither drug, alone or in combination, altered responses to the flexor reflex, blind placing, the hopping response or visually aided placing. It is concluded that the effects of chlorpromazine and phenytoin on motor control are selective for the CNS loci which control balance and coordination. Although the two drugs produce additive responses, the deficits occur only at doses which are well above those needed for clinical efficacy and thus may not pose a problem in their long term clinical use.
Keywords: Chlorpromazine; Phenytoin; Sensorimotor deficits

Single unit activity vs. amplitude of the epidural evoked potential in primary auditory cortex of awake cats. - Jonathan Wolpaw (Electroencephalography and clinical neurophysiology, 1979)
The study investigated, in primary auditory cortex (AI) of awake cats, the relationship over a range of stimuli between the amplitude and latency of the initial positive deflection (P1) of the primary evoked potential and the intensity of concurrent underlying evoked single unit activity. Epidural evoked potentials and extracellular responses of 155 single units to monaural 100 musec clicks ranging from 45 to 110 dB were recorded. At low stimulus levels, considerable unit response could occur with a very small P1. At middle stimulus levels, unit response was directly proportional to P1 amplitude. At higher stimulus levels, P1 amplitude continued to increase while unit response began to saturate.
Keywords: Reaction Time

Acute and chronic antiepileptic drug effect on the T complex interhemispheric latency difference. - Jonathan Wolpaw; Penry, J. K. (Epilepsia, 1978)
Antiepileptic drugs may significantly affect brain function in the absence of overt toxicity or excessive serum drug levels. A clinically practical monitor of such effects would be of considerable value in clinical research and practice. Auditory evoked responses were recorded from patients before and after initiation of antiepileptic drug therapy and from patients on therapy for at least 1 year. T complexes were isolated (Wolpaw and Penry, 1975), and Ta peak ipsilateral versus contralateral latency differences were determined. In 13 patients beginning phenobarbital, more than half the postdrug determinations were significantly increased over the patients' predrug control values in the first 30 days and thereafter, and grossly abnormal values were frequent. In 10 patients beginning phenytoin, latency differences were similarly increased, although grossly abnormal values were less common. In 2 patients beginning clonazepam, 14 of 15 postdrug determinations were significantly increased, and five were grossly abnormal. In no patients were serum drug levels above the therapeutic ranges. In 40 patients chronically treated with phenobarbital or primidone, phenytoin, or a combination of phenytoin and phenobarbital or primidone, abnormal latency differences were obtained in 33, 36, and 29% of the determinations, respectively. The Ta peak ipsilateral versus contralateral latency difference is an internally controlled correlate of higher level specific sensory function which is sensitive to acute and chronic therapy with phenobarbital, phenytoin, or clonazepam in therapeutic dosages. With further investigation, it may be of clinical use.
Keywords: Antiepileptic drug effects; Auditory evoked response; Hemispheric difference; T complex

Effects of ethanol, caffeine, and placebo on the auditory evoked response. - Jonathan Wolpaw; Penry, J. K. (Electroencephalography and clinical neurophysiology, 1978)
A previous paper (Wolpaw and Penry 1975) described separation of the 75-250 msec portion of the AER into N1P2, a product of large areas of cortex, and the T complex, probably a product of secondary auditory cortex. With monaural stimulation, the T complex is larger and earlier on the side contralateral to stimulation and on the right side. Thirty-one normal adults received 3 oz. of ethanol, 300 mg of caffeine, or placebo. Monaural AERs were recorded before intake in all cases, 1 and 4 h after ethanol and 80 min after caffeine or placebo. Blood levels of ethanol and caffeine were measured. Placebo produced mild (20%) decreases in N1P2 amplitude. Caffeine did not decrease N1P2 amplitude. It did produce a statistically significant 2% decrease in Ta peak latency. Ethanol reduced N1P2 amplitude markedly at 1 h and mildly at 4 h. Placebo did not affect hemispheric differences. Caffeine significantly increased the Ta peak ipsilateral vs. contralateral latency difference in 3 of 7 individuals. Ethanol significantly increased it in 3 of 6 subjects at 1 h and in 7 of 10 at 4 h, primarily by increasing ipsilateral latencies.
Keywords: Placebos

Electromagnetic stretch of individual muscles in behaving primates. - Jonathan Wolpaw; Colburn, T. R. (Brain research, 1978)
Keywords: Wakefulness

Hemispheric differences in the auditory evoked response. - Jonathan Wolpaw; Penry, J. K. (Electroencephalography and clinical neurophysiology, 1977)
The separation of the 80-250 msec portion of the AER to click stimulation into N1P2, produced by large areas of cortex, and the T complex, probably produced by secondary auditory cortex, was recently described (Wolpaw and Penry 1975). The present study investigated the ipsilateral vs. contralateral and right vs. left hemispheric differences in N1P2 and T complex latencies and amplitudes. One msec clicks at 60 dB above threshold were presented at 4.7 sec intervals monaurally to 32 normal adults and binaurally to 13 of the 32. AERs were recorded from vertex and temporal referred to a balanced non-cephalic reference electrode. For monaural stimulation, N1P2 and T complex amplitudes were significantly greater and T complex latency was significantly less over the contralateral and right hemispheres. The ipsilateral vs. contralateral and right vs. left hemispheric amplitude differences were significanlty greater for the T complex than for N1P2. Binaural results, which provided in additional measure of right vs. left hemispheric differences, were in agreement with the monaural findings. The results are consistent with neurophysiologic and behavioral findings in regard to ipsilateral vs. contralateral and right vs. left hemispheric differences and support the hypothesis that the T complex is produced by secondary auditory cortex.
Keywords: Reaction Time

A temporal component of the auditory evoked response. - Jonathan Wolpaw; Penry, J. K. (Electroencephalography and clinical neurophysiology, 1975)
We studied the 75-225 msec portion of the auditory evoked response (AER) in 32 normal adults at vertex (Cz) and temporal (T3 and T4) placements referred to a balanced, noncephalic reference electrode using a monaural 1 msec click stimulus delivered every 4.7 sec at 60 dB above threshold. The tape-recorded EEG was filtered at 1-25 c/sec, and 128 individual responses were summed, sampling every 0.5 msec for 250 msec post-stimulation. The Cz AERs showed the classic vertex response, a negative peak, N1, at 100 msec, followed by a positive peak, P2, at 160-200 msec. The T3 and T4 AERs were similar to the Cz AERs from 0 to 80 msec and from 200 to 250 msec. They differed significantly from the Cz AERs from 80 to 200 msec. The difference is best explained by the hypothesis that the Cz AERs consisted of N1P2, while the T3 and T4 AERs consisted of N1P2 plus an additional superimposed component, which we called the T complex, comprising a positive peak, Ta, at 105-110 msec, and a negative peak, Tb, at 150-160 msec. By computer, the corresponding Cz and T3 or T4 AERs were normalized to equalize their amplitudes, and the former was subtracted from the latter, thus isolating the T complex. The Ta peak was found to occur 1.5 +/- 1.6 msec earlier at the electrode contralateral to stimulation, and 2.2 +/- 4.0 msec earlier at the T4 (right) electrode. Both differences were statistically significant. The T complex amplitude was greater at the electrode contralateral to stimulation and at the T4 electrode. These findings appear to resolve current controversies concerning the form of the temporal AER. While N1P2 is apparently a product of widespread areas of cortex, we conclude that the T complex is probably a product of secondary auditory cortex.
Keywords: Time Factors

Tongue necrosis attributed to ergotamine in temporal arteritis. - Jonathan Wolpaw; Brottem, J. L.; Martin, H. L. (JAMA : the journal of the American Medical Association, 1973)
On two occasions, a woman with temporal arteritis developed tongue cyanosis and numbness shortly after the administration of ergotamine tartrate. Partial necrosis of the tongue resulted. Presumably, the lingual artery compromise, frequently present in temporal arteritis, was made symptomatic by the vasoconstrictive action of ergotamine tartrate.
Keywords: Tongue Diseases

The aetiology of retrograde amnesia. - Jonathan Wolpaw (Lancet, 1971)
To date, hypotheses of the ætiology of retrograde amnesia have focused on anatomical effects of traumatic lesions and on the presumed existence of short-term memory. The invariable association of retrograde amnesia with post-traumatic amnesia has been ignored as a clue to the origin of retrograde amnesia. It is suggested here that post-traumatic amnesia, by depriving preceding memories of a large proportion of their associated memories, leads to retrograde amnesia. The hypothesis accounts for the occurrence of retrograde amnesia in so many different situations and allows for the existence of very long retrograde amnesia.
Keywords: Wounds and Injuries

Aetiology of retrograde amnesia. - Jonathan Wolpaw (Lancet, 1971)
Keywords: Wounds and Injuries

Advances in Epileptic Seizure Onset Prediction in the EEG with ICA and Phase Synchronization - Disha Gupta (Biomedical Signal Processing Group, Institute of Sound and Vibration Research)
Seizure onset prediction in epilepsy is a challenge which is under investigation using many and varied signal processing techniques, across the world. This research thesis contributes to the advancement of digital signal analysis of neurophysiological signals of epileptic patients. It has been studied especially in the context of epileptic seizure onset prediction, with a motivation to help epileptic patients by advancing the knowledge on the possibilities of seizure prediction and inching towards a clinically viable seizure predictor. In this work, a synchrony based multi-stage system is analyzed that brings to bear the advantages of many techniques in each substage. The 1st stage of the system unmixes and de-noises continuous long-term (2-4 days) multichannel scalp Electroencephalograms using spatially constrained Independent Component Analysis. The 2d stage estimates the long term significant phase synchrony dynamics of narrowband (2-8 Hz and 8-14 Hz) seizure components. The synchrony dynamics are assessed with a novel statistic, the PLV-d, analyzing the joint synchrony in two frequency bands of interest. The 3rd stage creates multidimensional features of these synchrony dynamics for two classes (‘seizure free’ and ‘seizure predictive’) which are then projected onto a 2-dimensional map using a supervised Neuroscale, a topographic projection scheme based on a Radial Basis Neural Network. The 4th stage evaluates the probability of occurrence of predictive events using Gaussian Mixture Models used in supervised and semi-supervised forms. Preliminary analysis is performed on shorter data segments and the final system is based on nine patient’s long term (2-4 days each) continuous data. The training and testing for feature extraction analysis is performed on five patient datasets. The features extracted and the parameters ascertained with this analysis are then applied on the remaining four long-term datasets as a test of performance. The analysis is tested against random predictors as well. We show the possibility of seizure onset prediction (performing better than a random predictor) within a prediction window of 35-65 minutes with a sensitivity of 65-100% and specificity of 60-100% across the epileptic patients.